Causes of Treatment Failure in Children With Inflammatory Bowel Disease Treated With Infliximab: A Pharmacokinetic Study. - Naviglio, Samuele; Lacorte, Doriana; Lucafò, Marianna; Cifù, Adriana; Favretto, Diego; Cuzzoni, Eva; Silvestri, Tania; Pozzi Mucelli, Martina; Radillo, Oriano; Decorti, Giuliana; Fabris, Martina; Bramuzzo, Matteo; et al. (J Pediatr Gastroenterol Nutr, 2019)
OBJECTIVES: Anti-tumor necrosis factor antibodies have led to a revolution in the treatment of inflammatory bowel diseases (IBD); however, a sizable proportion of patients does not respond to therapy. There is increasing evidence suggesting that treatment failure may be classified as mechanistic (pharmacodynamic), pharmacokinetic, or immune-mediated. Data regarding the contribution of these factors in children with IBD treated with infliximab (IFX) are still incomplete. The aim was to assess the causes of treatment failure in a prospective cohort of pediatric patients treated with IFX. METHODS: This observational study considered 49 pediatric (median age 14.4) IBD patients (34 Crohn disease, 15 ulcerative colitis) treated with IFX. Serum samples were collected at 6, 14, 22 and 54 weeks, before IFX infusions. IFX and anti-infliximab antibodies (AIA) were measured using enzyme linked immunosorbent assays. Disease activity was determined by Pediatric Crohn's Disease Activity Index or Pediatric Ulcerative Colitis Activity Index. RESULTS: Clinical remission, defined as a clinical score <10, was obtained by 76.3% of patients at week 14 and by 73.9% at week 54. Median trough IFX concentration was higher at all time points in patients achieving sustained clinical remission. IFX levels during maintenance correlated also with C-reactive protein, albumin, and fecal calprotectin. After multivariate analysis, IFX concentration at week 14 >3.11 μg/mL emerged as the strongest predictor of sustained clinical remission. AIA concentrations were correlated inversely with IFX concentrations and directly with adverse reactions. CONCLUSIONS: Most cases of therapeutic failure were associated with low serum drug levels. IFX trough levels at the end of induction are associated with sustained long-term response.

Changing Epidemiology of Liver Involvement in Children With Celiac Disease. - Benelli, Elisa; Naviglio, Samuele; De Leo, Luigina; Stera, Giacomo; Giangreco, Manuela; Ronfani, Luca; Villanacci, Vincenzo; Martelossi, Stefano; Ventura, Alessandro; Not, Tarcisio (J Pediatr Gastroenterol Nutr, 2019)
OBJECTIVES: Available data indicate that liver involvement is present in a significant proportion of children with celiac disease (CD) at the diagnosis (elevated transaminases 15%-57%, autoimmune liver disease 1%-2%). We sought to evaluate prevalence, clinical course, and risk factors for liver involvement in a large cohort of children with CD. METHODS: Children (age 0-18 years) diagnosed with CD from March 2010 to April 2016 were enrolled. Liver involvement was considered to be present when alanine transaminase (ALT) levels were >40 U/L (hypertransaminasemia [HTS]). Patients with HTS were re-evaluated after at least 12 months of a gluten-free diet. RESULTS: CD was diagnosed in 806 patients during the study period; of these, ALT levels were available for 700 patients (86.9%), and were elevated in 27 (3.9%, HTS group); median ALT and aspartate transaminase levels in the HTS group were 57 U/L (interquartile range 49-80 U/L) and 67 U/L (interquartile range 53-85 U/L), respectively. Younger age, malabsorption symptoms, and low hemoglobin or ferritin were significantly more common in the HTS group at univariate analysis. At multivariate analysis, only age ≤4.27 years correlated with risk of liver involvement (odds ratio 3.73; 95% confidence interval: 1.61-8.66). When retested on a gluten-free diet, all but 3 patients normalized ALT levels; of these, 1 was diagnosed with sclerosing cholangitis. CONCLUSIONS: Liver involvement in celiac children is now less frequent than previously reported, possibly due to changing CD epidemiology. Younger age is the only risk factor. Associated autoimmune liver disease is rare.

Four-miRNA Signature to Identify Asbestos-Related Lung Malignancies. - Santarelli, Lory; Gaetani, Simona; Monaco, Federica; Bracci, Massimo; Valentino, Matteo; Amati, Monica; Rubini, Corrado; Sabbatini, Armando; Pasquini, Ernesto; Zanotta, Nunzia; Comar, Manola; Neuzil, Jiri; et al. (Cancer Epidemiol Biomarkers Prev, 2019)
BACKGROUND: Altered miRNA expression is an early event upon exposure to occupational/environmental carcinogens; thus, identification of a novel asbestos-related profile of miRNAs able to distinguish asbestos-induced cancer from cancer with different etiology can be useful for diagnosis. We therefore performed a study to identify miRNAs associated with asbestos-induced malignancies. METHODS: Four groups of patients were included in the study, including patients with asbestos-related (NSCLC) and asbestos-unrelated non-small cell lung cancer (NSCLC) or with malignant pleural mesothelioma (MPM), and disease-free subjects (CTRL). The selected miRNAs were evaluated in asbestos-exposed population. RESULTS: Four serum miRNAs, that is miR-126, miR-205, miR-222, and miR-520g, were found to be implicated in asbestos-related malignant diseases. Notably, increased expression of miR-126 and miR-222 were found in asbestos-exposed subjects, and both miRNAs are involved in major pathways linked to cancer development. Epigenetic changes and cancer-stroma cross-talk could induce repression of miR-126 to facilitate tumor formation, angiogenesis, and invasion. CONCLUSIONS: This study indicates that miRNAs are potentially involved in asbestos-related malignancies, and their expression outlines mechanism(s) whereby miRNAs may be involved in an asbestos-induced pathogenesis. IMPACT: The discovery of a miRNA panel for asbestos-related malignancies would impact on occupational compensation and may be utilized for screening asbestos-exposed populations.

Gadolinium tissue deposition in the periodontal ligament of mice with reduced renal function exposed to Gd-based contrast agents. - Delfino, Riccarda; Biasotto, Matteo; Candido, Riccardo; Altissimo, Matteo; Stebel, Marco; Salomè, Murielle; van Elteren, Johannes T; Vogel Mikuš, Katarina; Zennaro, Cristina; Šala, Martin; Addobbati, Riccardo; Tromba, Giuliana; et al. (Toxicol Lett, 2019)
Gadolinium deposition in tissue is linked to nephrogenic systemic fibrosis (NSF): a rare disorder occurring in patients with severe chronic kidney disease and associated with administration of Gd-based contrast agents (GBCAs) for Magnetic Resonance Imaging (MRI). It is suggested that the GBCAs prolonged permanence in blood in these patients may result in a Gd precipitation in peripheral or central organs, where it initiates a fibrotic process. In this study we investigated new sites of retention/precipitation of Gd in a mouse model of renal disease (5/6 nephrectomy) receiving two doses (closely after each other) of a linear GBCA. Two commercial GBCAs (Omniscan® and Magnevist®) were administered at doses slightly higher than those used in clinical practice (0.7 mmol/kg body weight, each). The animals were sacrificed one month after the last administration and the explanted organs (kidney, liver, femur, dorsal skin, teeth) were analysed by X-ray fluorescence (XRF) at two synchrotron facilities. The XRF analysis with a millimetre-sized beam at the SYRMEP beamline (Elettra, Italy) produced no detectable levels of Gd in the examined tissues, with the notable exception of the incisors of the nephrectomised mice. The XRF analyses at sub-micron resolution performed at ID21 (ESRF, France) allowed to clearly localize Gd in the periodontal ligaments of teeth both from Omniscan® and Magnevist® treated nephrectomised mice. The latter results were further confirmed by laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). The study prompts that prolonged permanence of GBCAs in blood may result in Gd retention in this particular muscular tissue, opening possibilities for diagnostic applications at this level when investigating Gd-related toxicities.
Keywords: Animals; Contrast Media; Disease Models, Animal; Dose-Response Relationship, Drug; Female; Gadolinium; Gadolinium DTPA; Magnetic Resonance Imaging; Mice; Nephrogenic Fibrosing Dermopathy; Periodontal Ligament; Renal Insufficiency; Tissue Distribution

Idiopathic neutropenia of infancy: Data from the Italian Neutropenia Registry. - Farruggia, Piero; Fioredda, Francesca; Puccio, Giuseppe; Onofrillo, Daniela; Russo, Giovanna; Barone, Angelica; Bonanomi, Sonia; Boscarol, Gianluca; Finocchi, Andrea; Ghilardi, Roberta; Giordano, Paola; Ladogana, Saverio; et al. (Am J Hematol, 2019)
Autoimmune neutropenia of infancy (AIN) is characterized by low risk of severe infection, tendency to spontaneously resolve and typically onset at ≤4-5 years of age; it is due to auto-antibodies whose detection is often difficult. In case of negativity of 4 antineutrophils autoantibody tests, after having excluded ethnic, postinfection, drug induced, or congenital neutropenia, according to the Italian guidelines the patients will be defined as affected by "idiopathic neutropenia" (IN). We describe the characteristics of 85 IN patients enrolled in the Italian neutropenia registry: they were compared with 336 children affected by AIN. The 2 groups were clinically very similar and the main differences were detection age (later in IN), length of disease (longer in IN) and, among recovered patients, age of spontaneous recovery: the median age at resolution was 2.13 years in AINs and 3.03 years in INs (P = .00002). At bivariate analysis among AIN patients earlier detection age (P = .00013), male sex (P = .000748), absence of leucopenia (P = .0045), and absence of monocytosis (P = .0419) were significantly associated with earlier recovery; in the IN group only detection age (P = .013) and absence of monocytosis (P = .0333) were significant. At multivariate analysis detection age and absence of monocytosis were independently significant (P = 6.7e-05 and 4.4e-03, respectively) in the AIN group, whereas in the IN group only detection age stayed significant (P = .013).

Management of endometrial, ovarian and cervical cancer in the elderly: current approach to a challenging condition. - Vitale, Salvatore Giovanni; Capriglione, Stella; Zito, Gabriella; Lopez, Salvatore; Gulino, Ferdinando Antonio; Di Guardo, Federica; Vitagliano, Amerigo; Noventa, Marco; La Rosa, Valentina Lucia; Sapia, Fabrizio; Valenti, Gaetano; Rapisarda, Agnese Maria Chiara; et al. (Arch Gynecol Obstet, 2019)
PURPOSE: Gynaecological cancer management in older people represents a current challenge. Therefore, in the present paper, we aimed to gather all the evidence reported in the literature concerning gynecological cancers in the elderly, illustrating the state of art and the future perspectives. METHODS: We searched MEDLINE (PubMed), EMBASE, Cochrane Central Register of Controlled Trials, IBECS, BIOSIS, Web of Science, SCOPUS and Grey literature (Google Scholar; British Library) from January 1952 to May 2017, using the terms "ovarian cancer", "endometrial cancer", "cervical cancer", "gynecological cancers" combined with 'elderly', 'cancer', 'clinical trial' and 'geriatric assessment'. RESULTS: The search identified 81 citations, of which 65 were potentially relevant after initial evaluation and met the criteria for inclusion and were analyzed. We divided all included studies into three different issue: "Endometrial cancer", "Ovarian cancer" and "Cervical cancer". CONCLUSIONS: The present literature review shows that, in spite of the higher burden of comorbidities, elderly patients can also benefit from standard treatment to manage their gynecological cancers. It is important to overcome the common habit of undertreating the elderly patients because they are more fragile and with a lower life expectancy than their younger counterpart. Further trials with elderly women are warranted.

Next-generation sequencing identified SPATC1L as a possible candidate gene for both early-onset and age-related hearing loss. - Morgan, Anna; Vuckovic, Dragana; Krishnamoorthy, Navaneethakrishnan; Rubinato, Elisa; Ambrosetti, Umberto; Castorina, Pierangela; Franzè, Annamaria; Vozzi, Diego; La Bianca, Martina; Cappellani, Stefania; Di Stazio, Mariateresa; Gasparini, Paolo; et al. (Eur J Hum Genet, 2019)
Hereditary hearing loss (HHL) and age-related hearing loss (ARHL) are two major sensory diseases affecting millions of people worldwide. Despite many efforts, additional HHL-genes and ARHL genetic risk factors still need to be identified. To fill this gap a large genomic screening based on next-generation sequencing technologies was performed. Whole exome sequencing in a 3-generation Italian HHL family and targeted re-sequencing in 464 ARHL patients were performed. We detected three variants in SPATC1L: a nonsense allele in an HHL family and a frameshift insertion and a missense variation in two unrelated ARHL patients. In silico molecular modelling of all variants suggested a significant impact on the structural stability of the protein itself, likely leading to deleterious effects and resulting in truncated isoforms. After demonstrating Spatc1l expression in mice inner ear, in vitro functional experiments were performed confirming the results of the molecular modelling studies. Finally, a candidate-gene population-based statistical study in cohorts from Caucasus and Central Asia revealed a statistically significant association of SPATC1L with normal hearing function at low and medium hearing frequencies. Overall, the amount of different genetic data presented here (variants with early-onset and late-onset hearing loss in addition to genetic association with normal hearing function), together with relevant functional evidence, likely suggest a role of SPATC1L in hearing function and loss.

Retrospective study showed that palpitations with tachycardia on admission to a paediatric emergency department were related to cardiac arrhythmias. - Bobbo, Marco; Amoroso, Stefano; Tamaro, Gianluca; Gesuete, Valentina; D'agata Mottolese, Biancamaria; Barbi, Egidio; Ventura, Alessandro (Acta Paediatr, 2019)
AIM: This retrospective study reviewed the prevalence and long-term prognosis of children aged 0-18 with palpitations who were admitted to the emergency department (ED) of an Italian paediatric hospital. METHODS: We examined all admissions to the ED of the IRCCS Burlo Garofolo between January 2009 and December 2015 by selecting triage diagnoses of palpitations. The hospital discharge cards were reviewed to assess vital parameters, physical examinations, diagnostic tests, cardiology consultations and final diagnoses. RESULTS: Of the 142 803 patients who attended our ED for any reason, 96 (0.07%) complained of palpitations. Despite this low prevalence, it was noteworthy that 13.5% had a real underlying arrhythmic cause and needed medical assistance. Over half (52.1%) were women and the mean age was 12.7 years. At the long-term follow-up, at a mean of 47 ± 23 months, 53.8% of patients with a cardiac arrhythmia had received medical therapy and 46.1% had undergone trans-catheter ablation for supraventricular tachycardia. A heart rate above 146 beats per minute or palpitations for more than an hour was statistically related to a cardiac arrhythmia. CONCLUSION: Palpitations were an infrequent cause of admission to our ED, but 13.5% who displayed them had an underlying cardiac arrhythmia.

Afebrile seizures in infants: Never forget magnesium! - Minute, Marta; Ventura, Giovanna; Giorgi, Rita; Faletra, Flavio; Costa, Paola; Cozzi, Giorgio (J Paediatr Child Health, 2018)

Antibody response to polyomavirus primary infection: high seroprevalence of Merkel cell polyomavirus and lymphoid tissue involvement. - Cason, Carolina; Monasta, Lorenzo; Zanotta, Nunzia; Campisciano, Giuseppina; Maestri, Iva; Tommasino, Massimo; Pawlita, Michael; Villani, Sonia; Comar, Manola; Delbue, Serena (J Neurovirol, 2018)
Human polyomaviruses (HPyVs) asymptomatically infect the human population establishing latency in the host, and their seroprevalence can reach 90% in healthy adults. Few studies have focused on the pediatric population, and there are no reports regarding the seroprevalence of all the newly isolated HPyVs among Italian children. Therefore, we investigated the frequency of serum antibodies against 12 PyVs in 182 immunocompetent children from Northeast Italy, by means of a multiplex antibody detection system. Additionally, secondary lymphoid tissues were collected to analyze the presence of HPyV DNA sequences using a specific real-time PCRs or PCRs. Almost 100% of subjects were seropositive for at least one PyV. Seropositivity ranged from 3% for antibodies against simian virus 40 (SV40) in children from 0 to 3 years, to 91% for antibodies against WU polyomavirus (WUPyV) and HPyV10 in children from 8 to 17 years. The mean number of PyV for which children were seropositive increased with the increasing of age: 4 standard deviations (SD) 1.8 in the 0-3-year group, 5 (SD 1.9) in the 4-7-year group, and 6 (SD 2.2) in the 8-17-year group. JC polyomavirus (JCPyV) DNA was detected in 1% of the adenoids, WUPyV in 12% of the tonsils, and 28% of the adenoids, and Merkel cell polyomavirus (MCPyV) was present in 6 and 2% of the tonsils and adenoids, respectively. Our study gives new insights on the serological evidence of exposure to PyVs during childhood, and on their possible respiratory route of transmission.

Anti-transglutaminase 6 Antibody Development in Children With Celiac Disease Correlates With Duration of Gluten Exposure. - De Leo, Luigina; Aeschlimann, Daniel; Hadjivassiliou, Marios; Aeschlimann, Pascale; Salce, Nicola; Vatta, Serena; Ziberna, Fabiana; Cozzi, Giorgio; Martelossi, Stefano; Ventura, Alessandro; Not, Tarcisio (J Pediatr Gastroenterol Nutr, 2018)
OBJECTIVES: Antibodies against transglutaminase 6 (anti-TG6) have been implicated in neurological manifestations in adult patients with genetic gluten intolerance, and it is unclear whether autoimmunity to TG6 develops following prolonged gluten exposure. We measured the anti-TG6 in children with celiac disease (CD) at the diagnosis time to establish a correlation between these autoantibodies and the duration of gluten exposure. We investigated a correlation between anti-TG6 and the presence of neurological disorders. METHODS: Anti-TG6 (IgA/IgG) were measured by ELISA in sera of children with biopsy-proven CD and of children experiencing gastrointestinal disorders. CD patients positive for anti-TG6 were retested after 2 years of gluten-free diet (GFD). RESULTS: We analyzed the sera of 274 CD children and of 121 controls. Anti-TG6 were detected in 68/274 (25%) CD patients and in 19/121 (16%) controls, with significant difference between the 2 groups (P = 0.04). None of the CD patients and of the controls testing positive for anti-TG6 were experiencing neurological disorders. Eleven of 18 (61%) CD patients with other autoimmune diseases were positive for anti-TG6. In CD patients, a significant correlation between the gluten exposure before the CD diagnosis and anti-TG6 concentration was found (P = 0.006 for IgA; P < 0.0001 for IgG). After GFD anti-TG6 concentrations were significantly reduced (P < 0.001). No significant correlation was observed between anti-TG6 and anti-TG2 serum concentrations. CONCLUSIONS: Anti-TG6 are more prevalent in children with untreated CD in the absence of overt neurological disorders. The synthesis of the anti-TG6 is related to a longer exposure to gluten before the CD diagnosis, and the autoimmunity against TG6 is gluten dependent and disappeared during GFD.

Are aortic coarctation and rheumatoid arthritis different models of aortic stiffness? Data from an echocardiographic study. - Faganello, Giorgio; Cioffi, Giovanni; Rossini, Maurizio; Ognibeni, Federica; Giollo, Alessandro; Fisicaro, Maurizio; Russo, Giulia; Di Nora, Concetta; Doimo, Sara; Tarantini, Luigi; Mazzone, Carmine; Cherubini, Antonella; et al. (Cardiovasc Ultrasound, 2018)
BACKGROUND: Patients who underwent a successful repair of the aortic coarctation (CoA) show high risk for cardiovascular (CV) events. Mechanical and structural abnormalities in the ascending aorta (Ao) might have a role in the prognosis of CoA patients. We analyzed the elastic properties of Ao measured as aortic stiffness index (AoSI) in CoA patients in the long-term period and we compared AoSI with a cohort of 38 patients with rheumatoid arthritis (RA) and 38 non-RA matched controls. METHODS: Data from 19 CoA patients were analyzed 28 ± 13 years after surgery. Abnormally high AoSI was diagnosed if AoSI > 6.07% (95th percentile of the AoSI detected in our reference healthy population). AoSI was assessed at the level of the aortic root by two-dimensional guided M-mode evaluation. RESULTS: CoA patients showed more than two-fold higher AoSI compared to RA and controls (9.8 ± 12.6 vs 4.8 ± 2.5% and 3.1 ± 2.0%, respectively; all p < 0.05 and in 5 of 19 patients with CoA (26%) AoSI was exceptionally high. The 5 patients with abnormally high AoSI were older with higher BP, LV mass and prevalence of LV diastolic dysfunction. Multiple linear regression analysis revealed that AoSI was independently related to the presence of LV hypertrophy and higher LV relative wall thickness. CONCLUSIONS: CoA patients have higher AoSI levels than RA patients and non-RA matched controls. AoSI levels are abnormally high in a small sub-group of CoA patients who show a very high-risk clinical profile for adverse CV events.
Keywords: Aorta; Aortic Coarctation; Arthritis, Rheumatoid; Humans; Prognosis; Vascular Stiffness

Cell-autonomous and cell non-autonomous downregulation of tumor suppressor DAB2IP by microRNA-149-3p promotes aggressiveness of cancer cells. - Bellazzo, Arianna; Di Minin, Giulio; Valentino, Elena; Sicari, Daria; Torre, Denis; Marchionni, Luigi; Serpi, Federica; Stadler, Michael B; Taverna, Daniela; Zuccolotto, Gaia; Montagner, Isabella Monia; Rosato, Antonio; et al. (Cell Death Differ, 2018)
The tumor suppressor DAB2IP contributes to modulate the network of information established between cancer cells and tumor microenvironment. Epigenetic and post-transcriptional inactivation of this protein is commonly observed in multiple human malignancies, and can potentially favor progression of tumors driven by a variety of genetic mutations. Performing a high-throughput screening of a large collection of human microRNA mimics, we identified miR-149-3p as a negative post-transcriptional modulator of DAB2IP. By efficiently downregulating DAB2IP, this miRNA enhances cancer cell motility and invasiveness, facilitating activation of NF-kB signaling and promoting expression of pro-inflammatory and pro-angiogenic factors. In addition, we found that miR-149-3p secreted by prostate cancer cells induces DAB2IP downregulation in recipient vascular endothelial cells, stimulating their proliferation and motility, thus potentially remodeling the tumor microenvironment. Finally, we found that inhibition of endogenous miR-149-3p restores DAB2IP activity and efficiently reduces tumor growth and dissemination of malignant cells. These observations suggest that miR-149-3p can promote cancer progression via coordinated inhibition of DAB2IP in tumor cells and in stromal cells.

Cooking influence in tolerance acquisition in egg-induced acute food protein enterocolitis syndrome. - Miceli Sopo, S; Romano, A; Bersani, G; Fantacci, C; Badina, L; Longo, G; Monti, G; Viola, S; Tripodi, S; Barilaro, G; Iacono, I D; Caffarelli, C; et al. (Allergol Immunopathol (Madr), 2018)
BACKGROUND: Few studies on the age of resolution of Food Protein Induced Enterocolitis Syndrome (FPIES) induced by solid foods are available. In particular, for FPIES induced by egg, the mean age of tolerance acquisition reported in the literature ranges from 42 to 63 months. OBJECTIVE: We have assessed whether the age of tolerance acquisition in acute egg FPIES varies depending on whether the egg is cooked or raw. METHODS: We conducted a retrospective and multicentric study of children with diagnosis of acute egg FPIES seen in 10 Italian allergy units between July 2003 and October 2017. The collected data regarded sex, presence of other allergic diseases, age of onset of symptoms, kind and severity of symptoms, cooking technique of the ingested egg, outcome of the allergy test, age of tolerance acquisition. RESULTS: Sixty-one children with acute egg FPIES were enrolled, 34 (56%) males and 27 (44%) females. Tolerance to cooked egg has been demonstrated by 47/61 (77%) children at a mean age of 30.2 months. For 32 of them, tolerance to raw egg has been demonstrated at a mean age of 43.9 months. No episodes of severe adverse reaction after baked egg ingestion have been recorded. CONCLUSIONS: It is possible to perform an OFC with baked egg, to verify the possible acquisition of tolerance, at about 30 months of life in children with acute egg FPIES.

Cx26 partial loss causes accelerated presbycusis by redox imbalance and dysregulation of Nfr2 pathway. - Fetoni, Anna Rita; Zorzi, Veronica; Paciello, Fabiola; Ziraldo, Gaia; Peres, Chiara; Raspa, Marcello; Scavizzi, Ferdinando; Salvatore, Anna Maria; Crispino, Giulia; Tognola, Gabriella; Gentile, Giulia; Spampinato, Antonio Gianmaria; et al. (Redox Biol, 2018)
Mutations in GJB2, the gene that encodes connexin 26 (Cx26), are the most common cause of sensorineural hearing impairment. The truncating variant 35delG, which determines a complete loss of Cx26 protein function, is the prevalent GJB2 mutation in several populations. Here, we generated and analyzed Gjb2 mice as a model of heterozygous human carriers of 35delG. Compared to control mice, auditory brainstem responses (ABRs) and distortion product otoacoustic emissions (DPOAEs) worsened over time more rapidly in Gjb2 mice, indicating they were affected by accelerated age-related hearing loss (ARHL), or presbycusis. We linked causally the auditory phenotype of Gjb2 mice to apoptosis and oxidative damage in the cochlear duct, reduced release of glutathione from connexin hemichannels, decreased nutrient delivery to the sensory epithelium via cochlear gap junctions and deregulated expression of genes that are under transcriptional control of the nuclear factor erythroid 2-related factor 2 (Nrf2), a pivotal regulator of tolerance to redox stress. Moreover, a statistically significant genome-wide association with two genes (PRKCE and TGFB1) related to the Nrf2 pathway (p-value < 4 × 10) was detected in a very large cohort of 4091 individuals, originating from Europe, Caucasus and Central Asia, with hearing phenotype (including 1076 presbycusis patients and 1290 healthy matched controls). We conclude that (i) elements of the Nrf2 pathway are essential for hearing maintenance and (ii) their dysfunction may play an important role in the etiopathogenesis of human presbycusis.
Keywords: Animals; Apoptosis; Connexin 26; Female; Gene Deletion; Male; Mice; Mice, Inbred C57BL; NF-E2-Related Factor 2; Oxidation-Reduction; Presbycusis; Signal Transduction

Cytokine profiles of women with vulvodynia: Identification of a panel of pro-inflammatory molecular targets. - Zanotta, Nunzia; Campisciano, Giuseppina; Scrimin, Federica; Blendi, Ura; Marcuzzi, Annalisa; Vincenti, Ezio; Crovella, Sergio; Comar, Manola (Eur J Obstet Gynecol Reprod Biol, 2018)
OBJECTIVE: The vulvar pain syndrome (VPS) is a multifactorial disease severely influencing the lifestyle of affected women. Among possible etiological factors, local injury, peripheral and/or central sensitization of the nervous system, and a chronic inflammatory status have been positively associated with the development of VPS. The identification of a constitutive altered local inflammatory profile in VPS women may represent an important point in the characterization of patients' phenotype as a useful marker influencing the vulvar micro-environment. The aim of this study was to investigative the possible role of the local cytokines production in women with VPS in comparison to healthy women. STUDY DESIGN: In this study were collected vaginal swabs from 57 healthy women (HC) who never suffered from VPS and from 30 patients diagnosed with vulvodynia (VPS) by at least 3 years and currently symptomatic. All patients included in this study showed the absence of Sexually Transmitted (STD) diseases and Reproductive Tract Infection. Real-time PCR was performed to assess the genomic sequences of ST pathogens. The Luminex Bio-Plex platform was used for the analysis of a panel of 48 immune factors. RESULTS: Eleven molecules, specifically involved in the pro-inflammatory pathway were significantly modulated in VPS patients in comparison to healthy women, suggesting a persistent inflammatory process. CONCLUSIONS: Therefore, these inflammatory factors could be possible biological markers involved in this disease. Nevertheless, other studies are needed to consider this specific immune profile as a valid marker of the vulvodynia.
Keywords: Adult; Aged; Cytokines; Female; Humans; Inflammation; Middle Aged; Vaginal Smears; Vulva; Vulvodynia; Women's Health

De novo unbalanced translocations have a complex history/aetiology. - Bonaglia, Maria Clara; Kurtas, Nehir Edibe; Errichiello, Edoardo; Bertuzzo, Sara; Beri, Silvana; Mehrjouy, Mana M; Provenzano, Aldesia; Vergani, Debora; Pecile, Vanna; Novara, Francesca; Reho, Paolo; Di Giacomo, Marilena Carmela; et al. (Hum Genet, 2018)
We investigated 52 cases of de novo unbalanced translocations, consisting in a terminally deleted or inverted-duplicated deleted (inv-dup del) 46th chromosome to which the distal portion of another chromosome or its opposite end was transposed. Array CGH, whole-genome sequencing, qPCR, FISH, and trio genotyping were applied. A biparental origin of the deletion and duplication was detected in 6 cases, whereas in 46, both imbalances have the same parental origin. Moreover, the duplicated region was of maternal origin in more than half of the cases, with 25% of them showing two maternal and one paternal haplotype. In all these cases, maternal age was increased. These findings indicate that the primary driver for the occurrence of the de novo unbalanced translocations is a maternal meiotic non-disjunction, followed by partial trisomy rescue of the supernumerary chromosome present in the trisomic zygote. In contrast, asymmetric breakage of a dicentric chromosome, originated either at the meiosis or postzygotically, in which the two resulting chromosomes, one being deleted and the other one inv-dup del, are repaired by telomere capture, appears at the basis of all inv-dup del translocations. Notably, this mechanism also fits with the origin of some simple translocations in which the duplicated region was of paternal origin. In all cases, the signature at the translocation junctions was that of non-homologous end joining (NHEJ) rather than non-allelic homologous recombination (NAHR). Our data imply that there is no risk of recurrence in the following pregnancies for any of the de novo unbalanced translocations we discuss here.
Keywords: DNA End-Joining Repair; Female; Humans; Male; Meiosis; Recombinational DNA Repair; Translocation, Genetic

Exome-chip meta-analysis identifies novel loci associated with cardiac conduction, including ADAMTS6. - Prins, Bram P; Mead, Timothy J; Brody, Jennifer A; Sveinbjornsson, Gardar; Ntalla, Ioanna; Bihlmeyer, Nathan A; van den Berg, Marten; Bork-Jensen, Jette; Cappellani, Stefania; Van Duijvenboden, Stefan; Klena, Nikolai T; Gabriel, George C; et al. (Genome Biol, 2018)
BACKGROUND: Genome-wide association studies conducted on QRS duration, an electrocardiographic measurement associated with heart failure and sudden cardiac death, have led to novel biological insights into cardiac function. However, the variants identified fall predominantly in non-coding regions and their underlying mechanisms remain unclear. RESULTS: Here, we identify putative functional coding variation associated with changes in the QRS interval duration by combining Illumina HumanExome BeadChip genotype data from 77,898 participants of European ancestry and 7695 of African descent in our discovery cohort, followed by replication in 111,874 individuals of European ancestry from the UK Biobank and deCODE cohorts. We identify ten novel loci, seven within coding regions, including ADAMTS6, significantly associated with QRS duration in gene-based analyses. ADAMTS6 encodes a secreted metalloprotease of currently unknown function. In vitro validation analysis shows that the QRS-associated variants lead to impaired ADAMTS6 secretion and loss-of function analysis in mice demonstrates a previously unappreciated role for ADAMTS6 in connexin 43 gap junction expression, which is essential for myocardial conduction. CONCLUSIONS: Our approach identifies novel coding and non-coding variants underlying ventricular depolarization and provides a possible mechanism for the ADAMTS6-associated conduction changes.
Keywords: ADAMTS Proteins; African Continental Ancestry Group; Animals; Connexin 43; Electrocardiography; European Continental Ancestry Group; Exome; Female; Gene Expression; Gene Expression Profiling; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Humans; Male; Mice; Middle Aged; Myocardium; Open Reading Frames; Polymorphism, Single Nucleotide; Whole Exome Sequencing

Fecal Calprotectin to Detect Inflammatory Bowel Disease in Juvenile Idiopathic Arthritis. - Ferrara, Giovanna; Pastore, Serena; Sancin, Lara; Torelli, Lucio; Radillo, Oriano; Bramuzzo, Matteo; Bibalo, Chiara; Tommasini, Alberto; Ventura, Alessandro; Taddio, Andrea (J Rheumatol, 2018)
OBJECTIVE: This study aimed to test fecal calprotectin (FC) as a screening tool to identify inflammatory bowel disease (IBD) among patients with juvenile idiopathic arthritis (JIA). METHODS: FC level < 100 g/kg was considered normal. Patients with 2 consecutive FC dosage ≥ 100 g/kg underwent endoscopic evaluation. RESULTS: There were 113 patients with JIA enrolled. FC was raised in 7 patients out of 113. All patients had IBD. In 3/7 patients, high FC levels were the only sign consistent with IBD. CONCLUSION: FC is a useful, economical, and noninvasive diagnostic tool to identify JIA patients with underlying IBD.

Gene discovery and polygenic prediction from a genome-wide association study of educational attainment in 1.1 million individuals. - Lee, James J; Wedow, Robbee; Okbay, Aysu; Kong, Edward; Maghzian, Omeed; Zacher, Meghan; Nguyen-Viet, Tuan Anh; Bowers, Peter; Sidorenko, Julia; Karlsson Linnér, Richard; Fontana, Mark Alan; Kundu, Tushar; et al. (Nat Genet, 2018)
Here we conducted a large-scale genetic association analysis of educational attainment in a sample of approximately 1.1 million individuals and identify 1,271 independent genome-wide-significant SNPs. For the SNPs taken together, we found evidence of heterogeneous effects across environments. The SNPs implicate genes involved in brain-development processes and neuron-to-neuron communication. In a separate analysis of the X chromosome, we identify 10 independent genome-wide-significant SNPs and estimate a SNP heritability of around 0.3% in both men and women, consistent with partial dosage compensation. A joint (multi-phenotype) analysis of educational attainment and three related cognitive phenotypes generates polygenic scores that explain 11-13% of the variance in educational attainment and 7-10% of the variance in cognitive performance. This prediction accuracy substantially increases the utility of polygenic scores as tools in research.

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.

Genetic profile of patients with early onset inflammatory bowel disease. - Girardelli, Martina; Basaldella, Federica; Paolera, Sara Della; Vuch, Josef; Tommasini, Alberto; Martelossi, Stefano; Crovella, Sergio; Bianco, Anna Monica (Gene, 2018)
Inflammatory Bowel disease (IBD) is a widespread pathological condition with clinical heterogeneity and with different levels of severity. Although IBD usually occurs in young adults, onset in childhood and infancy are described in patients within the 10th and second year of age. By genome-wide association studies and meta-analysis, several genetic loci have been identified associated with an increased risk of developing IBD in Western populations with variants that may alter the normal mucosal immunity in the gastrointestinal tract. The clinical complexity and the heterogeneity of the IBD phenotype probably reflect the presence of genetic heterogeneity where different genes or combinations of them may be involved, together with environmental factors. We hypothesized that patients with early onset IBD could have either more severe genetic variants in genes associated with IBD or multiple variants in different genes. Under the multifactorial diseases is crucial to consider the small contribution of a single variant in all not only to other small variations in the same gene but also in different genes belonging to the same pathway. We performed direct gene sequencing looking for 94 variations in NOD2, ATG16L1, IL23R, IL10R, IL10 and XIAP genes previously shown as correlated with IBD both in multifactorial and in Mendelian models. All variants identified are known in literature as being associated with IBD except for three variants in the genes NOD2, IL10 and IL10RB that even though present in online databases have never been involved in association studies on IBD patients. Moreover, we coupled genetic variants identification with an accurate "in silico" analysis to verify their predictive impact on the protein structure and function. The in-silico prediction of these variants results as benign therefore even if they exhibit a very low frequency in control population being benign, they cannot be considered pathogenic as monogenic disease but fall within the multifactorial range. The variants identified in our study partially reflect the association data described in the literature but there are no significant differences with the onset of disease (VEO vs EO-IBD).
Keywords: Age of Onset; Autophagy-Related Proteins; Child; Child, Preschool; Computer Simulation; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Infant; Inflammatory Bowel Diseases; Interleukin-10; Male; Nod2 Signaling Adaptor Protein; Polymorphism, Single Nucleotide; Receptors, Interleukin; Receptors, Interleukin-10; Sequence Analysis, DNA; X-Linked Inhibitor of Apoptosis Protein

A genetic variant of NLRP1 gene is associated with asbestos body burden in patients with malignant pleural mesothelioma. - Crovella, S; Moura, R R; Cappellani, S; Celsi, F; Trevisan, E; Schneider, M; Brollo, A; Nicastro, E M; Vita, F; Finotto, L; Zabucchi, G; Borelli, V (J Toxicol Environ Health A, 2018)
The presence of asbestos bodies (ABs) in lung parenchyma is considered a histopathologic hallmark of past exposure to asbestos fibers, of which there was a population of longer fibers. The mechanisms underlying AB formation are complex, involving inflammatory responses and iron (Fe) metabolism. Thus, the responsiveness to AB formation is variable, with some individuals appearing to be poor AB formers. The aim of this study was to disclose the possible role of genetic variants of genes encoding inflammasome and iron metabolism proteins in the ability to form ABs in a population of 81 individuals from North East Italy, who died after having developed malignant pleural mesothelioma (MPM). This study included 86 genetic variants distributed in 10 genes involved in Fe metabolism and 7 genetic variants in two genes encoding for inflammasome molecules. Genotypes/haplotypes were compared according to the number of lung ABs. Data showed that the NLRP1 rs12150220 missense variant (H155L) was significantly correlated with numbers of ABs in MPM patients. Specifically, a low number of ABs was detected in individuals carrying the NLRP1 rs12150220 A/T genotype. Our findings suggest that the NLRP1 inflammasome might contribute in the development of lung ABs. It is postulated that the NLRP1 missense variant may be considered as one of the possible host genetic factors contributing to individual variability in coating efficiency, which needs to be taken when assessing occupational exposure to asbestos.

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.

Genome-wide association meta-analysis highlights light-induced signaling as a driver for refractive error. - Tedja, Milly S; Wojciechowski, Robert; Hysi, Pirro G; Eriksson, Nicholas; Furlotte, Nicholas A; Verhoeven, Virginie J M; Iglesias, Adriana I; Meester-Smoor, Magda A; Tompson, Stuart W; Fan, Qiao; Khawaja, Anthony P; Cheng, Ching-Yu; et al. (Nat Genet, 2018)
Refractive errors, including myopia, are the most frequent eye disorders worldwide and an increasingly common cause of blindness. This genome-wide association meta-analysis in 160,420 participants and replication in 95,505 participants increased the number of established independent signals from 37 to 161 and showed high genetic correlation between Europeans and Asians (>0.78). Expression experiments and comprehensive in silico analyses identified retinal cell physiology and light processing as prominent mechanisms, and also identified functional contributions to refractive-error development in all cell types of the neurosensory retina, retinal pigment epithelium, vascular endothelium and extracellular matrix. Newly identified genes implicate novel mechanisms such as rod-and-cone bipolar synaptic neurotransmission, anterior-segment morphology and angiogenesis. Thirty-one loci resided in or near regions transcribing small RNAs, thus suggesting a role for post-transcriptional regulation. Our results support the notion that refractive errors are caused by a light-dependent retina-to-sclera signaling cascade and delineate potential pathobiological molecular drivers.

Genome-wide association meta-analysis of individuals of European ancestry identifies new loci explaining a substantial fraction of hair color variation and heritability. - Hysi, Pirro G; Valdes, Ana M; Liu, Fan; Furlotte, Nicholas A; Evans, David M; Bataille, Veronique; Visconti, Alessia; Hemani, Gibran; McMahon, George; Ring, Susan M; Smith, George Davey; Duffy, David L; et al. (Nat Genet, 2018)
Hair color is one of the most recognizable visual traits in European populations and is under strong genetic control. Here we report the results of a genome-wide association study meta-analysis of almost 300,000 participants of European descent. We identified 123 autosomal and one X-chromosome loci significantly associated with hair color; all but 13 are novel. Collectively, single-nucleotide polymorphisms associated with hair color within these loci explain 34.6% of red hair, 24.8% of blond hair, and 26.1% of black hair heritability in the study populations. These results confirm the polygenic nature of complex phenotypes and improve our understanding of melanin pigment metabolism in humans.

A genome-wide association study of corneal astigmatism: The CREAM Consortium. - Shah, Rupal L; Li, Qing; Zhao, Wanting; Tedja, Milly S; Tideman, J Willem L; Khawaja, Anthony P; Fan, Qiao; Yazar, Seyhan; Williams, Katie M; Verhoeven, Virginie J M; Xie, Jing; Wang, Ya Xing; et al. (Mol Vis, 2018)
Purpose: To identify genes and genetic markers associated with corneal astigmatism. Methods: A meta-analysis of genome-wide association studies (GWASs) of corneal astigmatism undertaken for 14 European ancestry (n=22,250) and 8 Asian ancestry (n=9,120) cohorts was performed by the Consortium for Refractive Error and Myopia. Cases were defined as having >0.75 diopters of corneal astigmatism. Subsequent gene-based and gene-set analyses of the meta-analyzed results of European ancestry cohorts were performed using VEGAS2 and MAGMA software. Additionally, estimates of single nucleotide polymorphism (SNP)-based heritability for corneal and refractive astigmatism and the spherical equivalent were calculated for Europeans using LD score regression. Results: The meta-analysis of all cohorts identified a genome-wide significant locus near the platelet-derived growth factor receptor alpha () gene: top SNP: rs7673984, odds ratio=1.12 (95% CI:1.08-1.16), p=5.55×10. No other genome-wide significant loci were identified in the combined analysis or European/Asian ancestry-specific analyses. Gene-based analysis identified three novel candidate genes for corneal astigmatism in Europeans-claudin-7 (), acid phosphatase 2, lysosomal (), and TNF alpha-induced protein 8 like 3 (). Conclusions: In addition to replicating a previously identified genome-wide significant locus for corneal astigmatism near the gene, gene-based analysis identified three novel candidate genes, , , and , that warrant further investigation to understand their role in the pathogenesis of corneal astigmatism. The much lower number of genetic variants and genes demonstrating an association with corneal astigmatism compared to published spherical equivalent GWAS analyses suggest a greater influence of rare genetic variants, non-additive genetic effects, or environmental factors in the development of astigmatism.
Keywords: Acid Phosphatase; Asian Continental Ancestry Group; Astigmatism; Claudins; Cohort Studies; Cornea; Corneal Diseases; European Continental Ancestry Group; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Intracellular Signaling Peptides and Proteins; Odds Ratio; Polymorphism, Single Nucleotide; Receptor, Platelet-Derived Growth Factor alpha; Software

High-Throughput Sequencing of microRNAs in Glucocorticoid Sensitive Paediatric Inflammatory Bowel Disease Patients. - De Iudicibus, Sara; Lucafò, Marianna; Vitulo, Nicola; Martelossi, Stefano; Zimbello, Rosanna; De Pascale, Fabio; Forcato, Claudio; Naviglio, Samuele; Di Silvestre, Alessia; Gerdol, Marco; Stocco, Gabriele; Valle, Giorgio; et al. (Int J Mol Sci, 2018)
The aim of this research was the identification of novel pharmacogenomic biomarkers for better understanding the complex gene regulation mechanisms underpinning glucocorticoid (GC) action in paediatric inflammatory bowel disease (IBD). This goal was achieved by evaluating high-throughput microRNA (miRNA) profiles during GC treatment, integrated with the assessment of expression changes in GC receptor (GR) heterocomplex genes. Furthermore, we tested the hypothesis that differentially expressed miRNAs could be directly regulated by GCs through investigating the presence of GC responsive elements (GREs) in their gene promoters. Ten IBD paediatric patients responding to GCs were enrolled. Peripheral blood was obtained at diagnosis (T0) and after four weeks of steroid treatment (T4). MicroRNA profiles were analyzed using next generation sequencing, and selected significantly differentially expressed miRNAs were validated by quantitative reverse transcription-polymerase chain reaction. In detail, 18 miRNAs were differentially expressed from T0 to T4, 16 of which were upregulated and 2 of which were downregulated. Out of these, three miRNAs (miR-144, miR-142, and miR-96) could putatively recognize the 3’UTR of the GR gene and three miRNAs (miR-363, miR-96, miR-142) contained GREs sequences, thereby potentially enabling direct regulation by the GR. In conclusion, we identified miRNAs differently expressed during GC treatment and miRNAs which could be directly regulated by GCs in blood cells of young IBD patients. These results could represent a first step towards their translation as pharmacogenomic biomarkers.
Keywords: Adolescent; Biomarkers; Child; Female; Gene Expression Regulation; Glucocorticoids; High-Throughput Nucleotide Sequencing; Humans; Inflammatory Bowel Diseases; Male; MicroRNAs; Receptors, Glucocorticoid; Transcriptome

How to predict response to anti-tumour necrosis factor agents in inflammatory bowel disease. - Naviglio, Samuele; Giuffrida, Paolo; Stocco, Gabriele; Lenti, Marco Vincenzo; Ventura, Alessandro; Corazza, Gino Roberto; Di Sabatino, Antonio (Expert Rev Gastroenterol Hepatol, 2018)
INTRODUCTION: Anti-tumor necrosis factor (TNF) agents have changed the therapeutic approach to inflammatory bowel disease (IBD). However, a considerable proportion of patients either do not primarily respond or lose response to treatment. Despite the long-standing experience in the use of these drugs, still there is the need of identifying the possible predictors of efficacy. Areas covered: We critically review the current knowledge on predictors of response to anti-TNF therapy - both those available in clinical practice and those still under investigation. Multiple factors are involved in treatment success, including disease phenotype and severity, adherence to medications, and pharmacogenomic, pharmacokinetic, and immunologic factors. Literature search was conducted in PubMed using keywords 'inflammatory bowel disease,' 'Crohn's disease,' and 'ulcerative colitis,' matched with 'antitumor necrosis factor,' 'biologic therapy,' 'clinical response,' 'predictors,' and 'efficacy,' Relevant articles were selected for review. Expert commentary: While the role of several factors in clinical practice is clearly established, other investigational markers have been proposed, mostly in small studies, yet for many of them little external validation exists. Therapeutic drug monitoring is emerging as a pivotal strategy to guide decisions in clinical practice. In the near future, novel markers could improve our ability to direct treatment and personalize therapy.
Keywords: Antibodies, Monoclonal; Biological Therapy; Gastrointestinal Agents; Humans; Inflammatory Bowel Diseases; Patient Selection; Prognosis; Treatment Outcome; Tumor Necrosis Factor-alpha

Immunohistologic analysis of the duodenal bulb: a new method for celiac disease diagnosis in children. - De Leo, Luigina; Villanacci, Vincenzo; Ziberna, Fabiana; Vatta, Serena; Martelossi, Stefano; Di Leo, Grazia; Zanchi, Chiara; Bramuzzo, Matteo; Giudici, Fabiola; Ventura, Alessandro; Not, Tarcisio (Gastrointest Endosc, 2018)
BACKGROUND AND AIMS: Anti-tissue transglutaminase antibodies (anti-tTG) have simplified celiac disease (CD) diagnosis. However, in atypical forms of CD, intestinal biopsy sampling is still required. This prospective study investigates whether histologic analysis of the duodenal bulb combined with intestinal IgA anti-tTG deposit immunoassay makes CD diagnosis possible in at-risk children with low concentrations of serum anti-tTG. METHODS: Histologic and intestinal IgA anti-tTG deposit immunoassays were used. RESULTS: Two hundred forty-five symptomatic children positive for serum anti-tTG (>7 U/mL) were enrolled and divided into 3 groups: extensive duodenal atrophy (n = 209), with IgA anti-tTG deposits throughout the duodenum and high serum anti-tTG concentrations (157 ± 178 U/mL); bulb duodenal atrophy (n = 22), with widespread IgA anti-tTG deposits in 9 and in the bulb alone in 13 and low serum anti-tTG concentrations (13.9 ± 8.7 U/mL); and normal duodenum (n = 14), with widespread IgA anti-tTG deposits in 8 and in the bulb alone in 6 and low serum anti-tTG concentrations (10.6 ± 6.2 U/mL). All patients in the first 2 groups were diagnosed with CD and 8 from the third group. All improved after 1 year of gluten-free diet. Bulb duodenal analysis led to a 12% (30/245) increase in CD diagnosis. No CD-related lesions were observed in the 30 control subjects. CONCLUSIONS: In children at risk for CD, bulb duodenum biopsy sampling is essential to identify villous atrophy and detect IgA anti-tTG deposits even in absence of intestinal lesions. These mucosal autoantibodies could well represent a new standard for diagnosing CD.
Keywords: Adolescent; Autoantibodies; Celiac Disease; Child; Child, Preschool; Duodenum; Female; Humans; Immunoglobulin A; Immunohistochemistry; Infant; Male; Prospective Studies; Transglutaminases

A Klinefelter boy with congenital adrenal hyperplasia: too much or too little androgens? - Zanella, Giada; Tornese, Gianluca; Mascheroni, Elisabetta; Faleschini, Elena; Ventura, Alessandro; Barbi, Egidio (Ital J Pediatr, 2018)
BACKGROUND: The simultaneous occurrence of Klinefelter Syndrome (KS) and Congenital Adrenal Hyperplasia (CAH) is an exceptional event: there are just three case reports (two children and a 51 years old man) describing males affected by both KS and 21OHD (21-hydroxylase deficiency) CAH, the first causing androgen deficiency, the latter leading to androgen excess. CASE REPORT: We report the 4th case of association of KS and CAH in a young man with CAH with good androgen control and with normal secondary sex characteristics, whose Klinefelter syndrome was diagnosed because of reduced testicular volume. He was the first reported case of association of KS and CAH who started androgen replacement therapy in the pubertal age and whose pubertal development was described and followed up step by step. CONCLUSION: In a boy with CAH and small testicular volume, it's important to consider that hypogonadism may be masked by the adrenal androgens excess and a karyotype should be performed once testicular adrenal rests have been ruled out.
Keywords: Adolescent; Adrenal Hyperplasia, Congenital; Androgens; Follow-Up Studies; Hormone Replacement Therapy; Humans; Klinefelter Syndrome; Male; Rare Diseases; Risk Assessment; Testis

A Large-Scale Multi-ancestry Genome-wide Study Accounting for Smoking Behavior Identifies Multiple Significant Loci for Blood Pressure. - Sung, Yun J; Winkler, Thomas W; de Las Fuentes, Lisa; Bentley, Amy R; Brown, Michael R; Kraja, Aldi T; Schwander, Karen; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Lu, Yingchang; Cheng, Ching-Yu; et al. (Am J Hum Genet, 2018)
Genome-wide association analysis advanced understanding of blood pressure (BP), a major risk factor for vascular conditions such as coronary heart disease and stroke. Accounting for smoking behavior may help identify BP loci and extend our knowledge of its genetic architecture. We performed genome-wide association meta-analyses of systolic and diastolic BP incorporating gene-smoking interactions in 610,091 individuals. Stage 1 analysis examined ∼18.8 million SNPs and small insertion/deletion variants in 129,913 individuals from four ancestries (European, African, Asian, and Hispanic) with follow-up analysis of promising variants in 480,178 additional individuals from five ancestries. We identified 15 loci that were genome-wide significant (p < 5 × 10) in stage 1 and formally replicated in stage 2. A combined stage 1 and 2 meta-analysis identified 66 additional genome-wide significant loci (13, 35, and 18 loci in European, African, and trans-ancestry, respectively). A total of 56 known BP loci were also identified by our results (p < 5 × 10). Of the newly identified loci, ten showed significant interaction with smoking status, but none of them were replicated in stage 2. Several loci were identified in African ancestry, highlighting the importance of genetic studies in diverse populations. The identified loci show strong evidence for regulatory features and support shared pathophysiology with cardiometabolic and addiction traits. They also highlight a role in BP regulation for biological candidates such as modulators of vascular structure and function (CDKN1B, BCAR1-CFDP1, PXDN, EEA1), ciliopathies (SDCCAG8, RPGRIP1L), telomere maintenance (TNKS, PINX1, AKTIP), and central dopaminergic signaling (MSRA, EBF2).
Keywords: Blood Pressure; Cohort Studies; Continental Population Groups; Diastole; Epistasis, Genetic; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Smoking; Systole

Light element distribution in fresh and frozen-thawed human ovarian tissues: a preliminary study. - Pascolo, Lorella; Venturin, Irene; Gianoncelli, Alessandra; Bortul, Roberta; Zito, Gabriella; Giolo, Elena; Salomè, Murielle; Bedolla, Diana E; Altissimo, Matteo; Zweyer, Marina; Ricci, Giuseppe (Reprod Biomed Online, 2018)
RESEARCH QUESTION: Does synchrotron X-ray fluorescence (XRF) provide novel chemical information for the evaluation of human ovarian tissue cryopreservation protocols? DESIGN: Tissues from five patients undergoing laparoscopic surgery for benign gynaecological conditions were fixed for microscopic analysis either immediately or after cryopreservation. After fixation, fresh and slowly frozen samples were selected by light microscopy and transmission electron microscopy, and subsequently analysed with synchrotron XRF microscopy at different incident energies. RESULTS: The distributions of elements detected at 7.3 keV (S, P, K, Cl, Fe, and Os) and 1.5 keV (Na and Mg) were related to the changes revealed by light microscopy and transmission electron microscopy analyses. The light elements showed highly informative findings. The S distribution was found to be an indicator of extracellular component changes in the stromal tissues of the freeze-stored samples, further revealed by the transmission electron microscopy analyses. Low-quality follicles, frequent in the freeze-thawed tissues, showed a high Na level in the ooplasm. On the contrary, good-quality follicles were detected by a homogeneous Cl distribution. The occurrence of vacuolated follicles increased after cryopreservation, and the XRF analyses showed that the vacuolar structures contained mainly Cl and Na. CONCLUSIONS: The study demonstrates that elemental imaging techniques, particularly revealing the distribution of light elements, could be useful in establishing new cryopreservation protocols.
Keywords: Cryopreservation; Female; Humans; Microscopy, Electron, Transmission; Organ Preservation; Ovarian Follicle; Ovary

Low-dose sirolimus in two cousins with autoimmune lymphoproliferative syndrome-associated infection. - Nocerino, Agostino; Valencic, Erica; Loganes, Claudia; Pelos, Giorgio; Tommasini, Alberto (Pediatr Int, 2018)
Keywords: Anti-Bacterial Agents; Autoimmune Lymphoproliferative Syndrome; Child; Child, Preschool; Dose-Response Relationship, Drug; Female; Humans; Immunosuppressive Agents; Infant; Male; Otitis Media; Pneumonia, Bacterial; Sirolimus

Multicenter randomized, double-blind controlled trial to evaluate the efficacy of laser therapy for the treatment of severe oral mucositis induced by chemotherapy in children: laMPO RCT. - Gobbo, Margherita; Verzegnassi, Federico; Ronfani, Luca; Zanon, Davide; Melchionda, Fraia; Bagattoni, Simone; Majorana, Alessandra; Bardellini, Elena; Mura, Rosamaria; Piras, Alessandra; Petris, Maria Grazia; Mariuzzi, Maria Livia; et al. (Pediatr Blood Cancer, 2018)
OBJECTIVES: To demonstrate the efficacy of laser photobiomodulation (PBM) compared to that of placebo on severe oral mucositis (OM) in pediatric oncology patients. The primary objective was the reduction of OM grade (World Health Organization [WHO] scale) 7 days after starting PBM. Secondary objectives were reduction of pain, analgesic consumption, and incidence of side effects. METHODS: One hundred and one children with WHO grade > 2 chemotherapy-induced OM were enrolled in eight Italian hospitals. Patients were randomized to either PBM or sham treatment for four consecutive days (days +1 to +4). On days +4, +7, and +11, OM grade, pain (following a 0-10 numeric pain rating scale, NRS) and need for analgesics were evaluated by an operator blinded to treatment. RESULTS: Fifty-one patients were allocated to the PBM group, and 50 were allocated to the sham group. In total, 93.7% of PBM patients and 72% of sham patients had OM grade < 3 WHO on day +7 (P = 0.01). A significant reduction of pain was registered on day +7 in the PBM versus sham group (NRS 1 [0-3] vs. 2.5 [1-5], P < 0.006). Reduced use of analgesics was reported in the PBM group, although it was not statistically significant. No significant adverse events attributable to treatment were recorded. CONCLUSIONS: PBM is a safe, feasible, and effective treatment for children affected by chemotherapy-induced OM, as it accelerates mucosal recovery and reduces pain.

Multiple successful pregnancies in a woman with biliary atresia and native liver. - Matarazzo, Lorenza; Assandro, Paola; Martelossi, Stefano; Maggiore, Giuseppe; Ventura, Alessandro (Eur J Obstet Gynecol Reprod Biol, 2018)

Needle-related pain and distress management during needle-related procedures in children with and without intellectual disability. - Pascolo, Paola; Peri, Francesca; Montico, Marcella; Funaro, Mishelle; Parrino, Roberta; Vanadia, Francesca; Rusalen, Francesca; Vecchiato, Luca; Benini, Franca; Congedi, Sabrina; Barbi, Egidio; Cozzi, Giorgio (Eur J Pediatr, 2018)
Children with intellectual disability frequently undergo needle-related procedures for diagnosis or treatment. Nevertheless, only a few studies deal with pain and distress management during the procedure in this population of children. This study aimed to investigate the number of anxiety and pain management techniques performed during needle procedure in children with intellectual disability (cases) compared to a population of children without intellectual disability (controls). This multicenter cohort study was performed from July 2016 to January 2018 in the pediatric ward of four urban hospitals in Italy. Eligible subjects were children with and without intellectual disability, from 4 to 17 years old, who needed venipuncture or intravenous cannulation for diagnosis or treatment. Use of topical anesthesia, distraction techniques, and physical or verbal comfort during procedures were recorded. Pain and anxiety scores were also recorded. Forty-seven cases and 94 controls were recruited. Three pain- and anxiety-relieving techniques were performed during the procedure in 12 (25%) cases and in 10 controls (11%); two techniques were performed in 23 (50%) cases and in 26 (28%) controls; 12 (25%) cases and 52 (55%) controls received only one.Conclusion: In this series, children with intellectual disability received significantly more relieving techniques, but experienced more pain and anxiety when compared to children without intellectual disability. What is Known: • Children with intellectual disability experience more episodes of pain than cognitively healthy ones, and almost 10% of these episodes are due to medical procedures. What is New: • Children with intellectual disability despite receiving more relieving techniques during a needle-related procedure experienced more pain and anxiety when compared to healthy children.
Keywords: Adolescent; Anxiety; Child; Child, Preschool; Cohort Studies; Female; Humans; Intellectual Disability; Italy; Male; Pain Management; Pain Measurement; Pain, Procedural; Phlebotomy

Neuronal Dysfunction Associated with Cholesterol Deregulation. - Marcuzzi, Annalisa; Loganes, Claudia; Valencic, Erica; Piscianz, Elisa; Monasta, Lorenzo; Bilel, Sabrine; Bortul, Roberta; Celeghini, Claudio; Zweyer, Marina; Tommasini, Alberto (Int J Mol Sci, 2018)
Cholesterol metabolism is crucial for cells and, in particular, its biosynthesis in the central nervous system occurs in situ, and its deregulation involves morphological changes that cause functional variations and trigger programmed cell death. The pathogenesis of rare diseases, such as Mevalonate Kinase Deficiency or Smith⁻Lemli⁻Opitz Syndrome, arises due to enzymatic defects in the cholesterol metabolic pathways, resulting in a shortage of downstream products. The most severe clinical manifestations of these diseases appear as neurological defects. Expanding the knowledge of this biological mechanism will be useful for identifying potential targets and preventing neuronal damage. Several studies have demonstrated that deregulation of the cholesterol pathway induces mitochondrial dysfunction as the result of respiratory chain damage. We set out to determine whether mitochondrial damage may be prevented by using protective mitochondria-targeted compounds, such as MitoQ, in a neuronal cell line treated with a statin to induce a biochemical block of the cholesterol pathway. Evidence from the literature suggests that mitochondria play a crucial role in the apoptotic mechanism secondary to blocking the cholesterol pathway. Our study shows that MitoQ, administered as a preventive agent, could counteract the cell damage induced by statins in the early stages, but its protective role fades over time.
Keywords: Anticholesteremic Agents; Cell Line, Tumor; Cholesterol; Electron Transport; Humans; Lovastatin; Mitochondria; Neurons; Neuroprotective Agents; Organophosphorus Compounds; Ubiquinone

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alcohol Drinking; Blood Pressure; Cohort Studies; Continental Population Groups; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Young Adult

Ocular Manifestations of Paediatric Inflammatory Bowel Disease: A Systematic Review and Meta-analysis. - Ottaviano, Giorgio; Salvatore, Silvia; Salvatoni, Alessandro; Martelossi, Stefano; Ventura, Alessandro; Naviglio, Samuele (J Crohns Colitis, 2018)
Background and Aims: Ocular extraintestinal manifestations [O-EIMs] are known complications of Crohn's disease [CD], ulcerative colitis [UC], and inflammatory bowel disease unclassified [IBD-U]. However, data on their prevalence in children are scarce and there are no clear recommendations on what follow-up should be offered. We aimed to review available data on O-EIMs in children. Methods: In January 2018, we performed a systematic review of published English literature using PubMed and EMBASE databases and disease-specific queries. Results: Fifteen studies [7467 patients] reported data on O-EIMs prevalence in children. Overall prevalence of O-EIMs was 0.62-1.82%. Uveitis was the most common O-EIM. Meta-analysis showed that children with CD are at increased risk of O-EIMs as compared with children with UC and IBD-U (odds ratio [OR] 2.70, 95% confidence interval [CI] 1.51-4.83). Five studies [357 patients] reported data on ophthalmological screening in asymptomatic children: mild asymptomatic uveitis was identified in a variable proportion of patients [1.06-23.1%], more frequently in male patients with CD and colonic involvement. No evidence of ocular complications from untreated uveitis was detected. A total of 23 case reports [24 patients] were identified. Conclusions: Data on O-EIMs in children are scarce. Prevalence of O-EIMs is lower than in adults but may be underestimated because of the possibility of asymptomatic uveitis; however, the long-term significance of this condition is unknown. Children with CD may be at increased risk of O-EIMs. No recommendations on routine ophthalmological examination can be made, but a low threshold for ophthalmological referral should be maintained. Larger studies in paediatric IBD populations are needed.
Keywords: Adolescent; Cataract; Child; Child, Preschool; Colitis, Ulcerative; Crohn Disease; Eye Diseases; Humans; Prevalence; Uveitis

Orthopaedic challenges for mucopolysaccharidoses. - Borgo, Andrea; Cossio, Andrea; Gallone, Denise; Vittoria, Francesca; Carbone, Marco (Ital J Pediatr, 2018)
Mucopolysaccharidoses (MPS) are a group of diseases characterized by abnormal accumulation of glycosaminoglycans (GAGs). Although there are differences among the various disease types, the osteoarticular system is always involved. The aim of the present study was to establish a framework for MPS-related orthopaedic manifestations and for their treatment. The authors, affiliated to three different Italian Orthopaedic Centres, report data taken from the literature reviewed in light of their accumulated professional experience. Bone alterations make up what is known as dysostosis multiplex, involving the trunk and limbs and with typical radiological findings. Joints are affected by pathological tissue infiltrations. The cervical spinal cord is involved, with stenosis and cervical and occipitocervical instability. In MPS there is a much higher incidence of scoliosis compared with healthy subjects without any particular distinctive feature. Kyphosis of the spine is more frequent and also more severe because of its possible neurological complications, and it is localized at the thoracolumbar level with a malformed vertebra at the top of the deformity. Evolving forms, and those associated with neurological damage, require anteroposterior spine fusion. The hip is invariably involved, with dysplasia affecting the femoral neck (coxa valga), the femoral epiphysis (loss of sphericity, osteonecrosis), and the femoral acetabulum which is flared. All these features explain the tendency to progressive hip migration. Genu valgum is often found (a deviation of the physiological axis with an obtuse angle opening laterally). This deformity is often localized at the proximal tibial metaphysis; it causes functional limitations and leads to an irregular erosion of the articular cartilage. In young patients who still have the growth plate, it is possible to execute a medial hemiepiphysiodesis, a temporary inhibition of cartilage growth, with progressive axis correction. In this paper, the characterisation of clinical features and the review of treatments are divided into separate sections based on the part of the body involved. The conclusions of each section are presented as a summary. One section discusses the high risk of anaesthesia-related complications requiring the collaboration of specifically trained personnel.
Keywords: Bone Diseases; Humans; Mucopolysaccharidoses; Orthopedic Procedures

Paediatric Home Artificial Nutrition in Italy: Report from 2016 Survey on Behalf of Artificial Nutrition Network of Italian Society for Gastroenterology, Hepatology and Nutrition (SIGENP). - Lezo, Antonella; Capriati, Teresa; Spagnuolo, Maria Immacolata; Lacitignola, Laura; Goreva, Irina; Di Leo, Grazia; Cecchi, Nicola; Gandullia, Paolo; Amarri, Sergio; Forchielli, Maria Luisa; Dipasquale, Valeria; Parma, Barbara; et al. (Nutrients, 2018)
Home Artificial Nutrition (HAN) is a safe and efficacious technique that insures children's reintegration into the family, society and school. Epidemiological data on paediatric HAN in Italy are not available. AIM: to detect the prevalence and incidence of Home Parenteral Nutrition (HPN) and Home Enteral Nutrition (HEN), either via tube or mouth, in Italy in 2016. MATERIALS AND METHODS: a specific form was sent to all registered SIGENP members and investigators of local HAN centres, inviting them to provide the requested centre's data and demographics, underlying diseases and HAN characteristics of the patients. RESULTS: we recorded 3403 Italian patients on HAN aged 0 to 19 years from 22 centres: 2277 HEN, 950 Oral Nutritional Supplements (ONS) and 179 HPN programs. The prevalence of HEN (205 pts/million inhabitants) and HPN (16 pts/million inhabitants) has dramatically increased in Italy in the last 9 years. Neurodisabling conditions were the first indication for HEN by tube or mouth while HPN is mainly requested in digestive disorders. CONCLUSIONS: HAN is a widespread and rapidly growing treatment in Italy, as well as in other European countries. Awareness of its extent and characteristics helps improving HAN service and patients' quality of life.
Keywords: Adolescent; Age Factors; Child; Child Nutritional Physiological Phenomena; Child, Preschool; Enteral Nutrition; Female; Health Care Surveys; Home Care Services; Humans; Infant; Infant, Newborn; Italy; Male; Nutritional Status; Parenteral Nutrition, Home; Pediatrics; Time Factors; Young Adult

Potential use of MCR-ALS for the identification of coeliac-related biochemical changes in hyperspectral Raman maps from pediatric intestinal biopsies. - Fornasaro, Stefano; Vicario, Annalisa; De Leo, Luigina; Bonifacio, Alois; Not, Tarcisio; Sergo, Valter (Integr Biol (Camb), 2018)
Raman hyperspectral imaging is an emerging practice in biological and biomedical research for label free analysis of tissues and cells. Using this method, both spatial distribution and spectral information of analyzed samples can be obtained. The current study reports the first Raman microspectroscopic characterisation of colon tissues from patients with Coeliac Disease (CD). The aim was to assess if Raman imaging coupled with hyperspectral multivariate image analysis is capable of detecting the alterations in the biochemical composition of intestinal tissues associated with CD. The analytical approach was based on a multi-step methodology: duodenal biopsies from healthy and coeliac patients were measured and processed with Multivariate Curve Resolution Alternating Least Squares (MCR-ALS). Based on the distribution maps and the pure spectra of the image constituents obtained from MCR-ALS, interesting biochemical differences between healthy and coeliac patients has been derived. Noticeably, a reduced distribution of complex lipids in the pericryptic space, and a different distribution and abundance of proteins rich in beta-sheet structures was found in CD patients. The output of the MCR-ALS analysis was then used as a starting point for two clustering algorithms (k-means clustering and hierarchical clustering methods). Both methods converged with similar results providing precise segmentation over multiple Raman images of studied tissues.

PR interval genome-wide association meta-analysis identifies 50 loci associated with atrial and atrioventricular electrical activity. - van Setten, Jessica; Brody, Jennifer A; Jamshidi, Yalda; Swenson, Brenton R; Butler, Anne M; Campbell, Harry; Del Greco, Fabiola M; Evans, Daniel S; Gibson, Quince; Gudbjartsson, Daniel F; Kerr, Kathleen F; Krijthe, Bouwe P; et al. (Nat Commun, 2018)
Electrocardiographic PR interval measures atrio-ventricular depolarization and conduction, and abnormal PR interval is a risk factor for atrial fibrillation and heart block. Our genome-wide association study of over 92,000 European-descent individuals identifies 44 PR interval loci (34 novel). Examination of these loci reveals known and previously not-yet-reported biological processes involved in cardiac atrial electrical activity. Genes in these loci are over-represented in cardiac disease processes including heart block and atrial fibrillation. Variants in over half of the 44 loci were associated with atrial or blood transcript expression levels, or were in high linkage disequilibrium with missense variants. Six additional loci were identified either by meta-analysis of ~105,000 African and European-descent individuals and/or by pleiotropic analyses combining PR interval with heart rate, QRS interval, and atrial fibrillation. These findings implicate developmental pathways, and identify transcription factors, ion-channel genes, and cell-junction/cell-signaling proteins in atrio-ventricular conduction, identifying potential targets for drug development.
Keywords: Atrial Function; Atrioventricular Node; Electrocardiography; Electrophysiological Phenomena; Female; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Mutation, Missense; Risk Factors

Predictive value of the number of adverse reaction episodes for the IgE-mediated food allergy diagnosis. - Miceli Sopo, S; Gurnari, G; Monaco, S; Romano, A; Liotti, L; Cuomo, B; Dello Iacono, I; Badina, L; Longo, G; Calvani, M; Giannone, A; Calabrò, C; et al. (Allergol Immunopathol (Madr), 2018)
INTRODUCTION AND OBJECTIVES: The reproducibility of the adverse reaction increases the suggestiveness of a history of food allergy. However, the positive predictive value (PPV) of multiple adverse reaction episodes for the diagnosis of IgE-mediated food allergy is not known. This evaluation was the objective of our study. PATIENTS AND METHODS: We retrospectively studied 180 children with a history of non-anaphylactic adverse reactions after the ingestion of a food. All children had the prick test positive for the offending food and performed the oral food challenge (OFC) within 12 months after the last adverse reaction episode (ARE). We have evaluated whether increasing the number of ARE increased the probability that the OFC would be positive (failed). RESULTS: 93 patients (52%) presented one ARE, 49 (27%) presented two ARE, 24 (13%) presented three ARE, 14 (8%) patients presented≥four ARE. The OFC was positive in 94/180 (52%). The outcome of the OFC was found to be positively correlated with the number of ARE (OR=1.56; 95% CI=1.16-2.09; p=0.003). A PPV=100% was observed with a number of ARE≥five. CONCLUSIONS: The number of ARE is an important predictor of the diagnosis of food allergy, although less than we would have imagined. The number of ARE could be used to increase the predictability of the diagnostic tests currently in use, to define clinical prediction rules alternative to OFC and easy to use in clinical practice.

Pre-eclampsia affects procalcitonin production in placental tissue. - Agostinis, Chiara; Rami, Damiano; Zacchi, Paola; Bossi, Fleur; Stampalija, Tamara; Mangogna, Alessandro; Amadio, Leonardo; Vidergar, Romana; Vecchi Brumatti, Liza; Ricci, Giuseppe; Celeghini, Claudio; Radillo, Oriano; et al. (Am J Reprod Immunol, 2018)
PROBLEM: Procalcitonin (PCT) is the prohormone of calcitonin which is usually released from neuroendocrine cells of the thyroid gland (parafollicular) and the lungs (K cells). PCT is synthesized by almost all cell types and tissues, including monocytes and parenchymal tissue, upon LPS stimulation. To date, there is no evidence for PCT expression in the placenta both in physiological and pathological conditions. METHOD: Circulating and placental PCT levels were analysed in pre-eclamptic (PE) and control patients. Placental cells and macrophages (PBDM), stimulated with PE sera, were analysed for PCT expression. The effect of anti-TNF-α antibody was analysed. RESULTS: Higher PCT levels were detected in PE sera and in PE placentae compared to healthy women. PE trophoblasts showed increased PCT expression compared to those isolated from healthy placentae. PE sera induced an upregulation of PCT production in macrophages and placental cells. The treatment of PBDM with PE sera in the presence of anti-TNF-α completely abrogated the effect induced by pathologic sera. CONCLUSION: Trophoblast cells are the main producer of PCT in PE placentae. TNF-α, in association with other circulating factors present in PE sera, upregulates PCT production in macrophages and normal placental cells, thus contributing to the observed increased in circulating PCT in PE sera.
Keywords: Adult; Calcitonin; Cohort Studies; Female; Humans; Macrophages; Placenta; Pre-Eclampsia; Pregnancy; Trophoblasts; Tumor Necrosis Factor-alpha; Up-Regulation; Young Adult

Report on an international workshop on kangaroo mother care: lessons learned and a vision for the future. - Cattaneo, Adriano; Amani, Adidja; Charpak, Nathalie; De Leon-Mendoza, Socorro; Moxon, Sarah; Nimbalkar, Somashekhar; Tamburlini, Giorgio; Villegas, Julieta; Bergh, Anne-Marie (BMC Pregnancy Childbirth, 2018)
BACKGROUND: Globally, complications of prematurity are the leading cause of death in children under five. Preterm infants who survive their first month of life are at greater risk for various diseases and impairments in infancy, childhood and later life, representing a heavy social and economic burden for families, communities and health and social systems. Kangaroo mother care (KMC) is recommended as a beneficial and effective intervention for improving short- and long-term preterm birth outcomes in low- and high-income settings. Nevertheless, KMC is not as widely used as it should be. The International Network on KMC runs biennial workshops and congresses to help improve the coverage and quality of KMC worldwide. This paper reports the results of the two-day workshop held in November 2016, where 92 participants from 33 countries shared experiences in a series of round tables, group work sessions and plenaries. FINDINGS: Barriers to and enablers of KMC are discussed with regard to parents, health workers and the health system. Key factors for effective implementation and uptake relate to appropriate training for health staff, adherence to protocols and the creation of a welcoming environment for families. Recommendations for planning for national programmes are made according to a six-stage change model. Resources and the cost of making progress are discussed in terms of investment, maintenance, and acceleration and scaling-up costs. KMC training requirements are presented according to three levels of care. To ensure quality KMC, key requisites are proposed for the different KMC components and for sensitive communication with caregivers. The group attending to the monitoring and evaluation of KMC at a national and subnational level highlight the lack of standard indicator definitions. Key priorities for investment include health services research, harmonisation of indicators, development of a costing tool, programming and scaling up, and the follow-up of preterm infants. CONCLUSION: It is hoped that this report will help to further scale-up and sustain KMC through a systematic approach that includes raising commitment, identifying key strategies to address the main barriers and using existing facilitators, ensuring training and quality, agreeing on indicators for monitoring and evaluation, and advancing implementation research.
Keywords: Education; Education, Nonprofessional; Female; Government Programs; Health Plan Implementation; Humans; Infant; Infant Mortality; Infant, Newborn; Infant, Premature; Infant, Premature, Diseases; International Cooperation; Kangaroo-Mother Care Method; Male

The Role of Oxidative Stress and Membrane Transport Systems during Endometriosis: A Fresh Look at a Busy Corner. - Vitale, Salvatore Giovanni; Capriglione, Stella; Peterlunger, Isabel; La Rosa, Valentina Lucia; Vitagliano, Amerigo; Noventa, Marco; Valenti, Gaetano; Sapia, Fabrizio; Angioli, Roberto; Lopez, Salvatore; Sarpietro, Giuseppe; Rossetti, Diego; et al. (Oxid Med Cell Longev, 2018)
Endometriosis is a condition characterized by the presence of endometrial tissue outside the uterine cavity, leading to a chronic inflammatory reaction. It is one of the most widespread gynecological diseases with a 10-15% prevalence in the general female population, rising up to 30-45% in patients with infertility. Although it was first described in 1860, its etiology and pathogenesis are still unclear. It is now accepted that inflammation plays a central role in the development and progression of endometriosis. In particular, it is marked by an inflammatory process associated with the overproduction of an array of inflammatory mediators such as prostaglandins, metalloproteinases, cytokines, and chemokines. In addition, the growth and adhesion of endometrial cells in the peritoneal cavity due to reactive oxygen species (ROS) and free radicals lead to disease onset, its ensuing symptoms-among which pain and infertility. The aim of our review is to evaluate the role of oxidative stress and ROS in the pathogenesis of endometriosis and the efficacy of antioxidant therapy in the treatment and mitigation of its symptoms.
Keywords: Endometriosis; Female; Humans; Oxidative Stress

Role of the Long Non-Coding RNA Growth Arrest-Specific 5 in Glucocorticoid Response in Children with Inflammatory Bowel Disease. - Lucafò, Marianna; Di Silvestre, Alessia; Romano, Maurizio; Avian, Alice; Antonelli, Roberta; Martelossi, Stefano; Naviglio, Samuele; Tommasini, Alberto; Stocco, Gabriele; Ventura, Alessandro; Decorti, Giuliana; De Iudicibus, Sara (Basic Clin Pharmacol Toxicol, 2018)
Glucocorticoids (GCs) are widely employed in inflammatory, autoimmune and neoplastic diseases, and, despite the introduction of novel therapies, remain the first-line treatment for inducing remission in inflammatory bowel disease (IBD). Given the high incidence of suboptimal response, associated with a significant number of side-effects, that are particularly severe in paediatric patients, the identification of subjects that are most likely to respond poorly to GCs is extremely important. Recent evidence suggests that the long non-coding RNA (lncRNA) GAS5 could be a potential marker of GC resistance. To address this issue, we evaluated the association between the lncRNA GAS5 and the efficacy of steroids, in terms of inhibition of proliferation, in two cell lines derived from colon and ovarian cancers, to confirm the sensitivity and specificity of these lncRNAs. These cells showed a different sensitivity to GCs and revealed differential expression of GAS5 after treatment. GAS5 was up-regulated in GC-resistant cells and accumulated more in the cytoplasm compared to the nucleus in response to the drug. The functions of GAS5 were assessed by silencing, and we found that GAS5 knock-down reduced the proliferation during GC treatment. Furthermore, for the first time, we measured GAS5 levels in 19 paediatric IBD patients at diagnosis and after the first cycle of GCs, and we demonstrated an up-regulation of the lncRNA in patients with unfavourable steroid response. Our preliminary results indicate that GAS5 could be considered a novel pharmacogenomic marker useful for the personalization of GC therapy.
Keywords: Biomarkers; Cell Line, Tumor; Cell Proliferation; Child; Drug Resistance; Female; Gene Knockdown Techniques; Glucocorticoids; Humans; Inflammatory Bowel Diseases; Male; Patient Selection; Pharmacogenomic Testing; Precision Medicine; RNA, Long Noncoding; RNA, Small Interfering; Treatment Outcome; Up-Regulation

Teaching pain recognition through art: the Ramsay-Caravaggio sedation scale. - Poropat, Federico; Cozzi, Giorgio; Magnolato, Andrea; Monasta, Lorenzo; Borrometi, Fabio; Krauss, Baruch; Ventura, Alessandro; Barbi, Egidio (Ital J Pediatr, 2018)
BACKGROUND: Clinical observation is a key component of medical ability, enabling immediate evaluation of the patient's emotional state and contributing to a clinical clue that leads to final decision making. In medical schools, the art of learning to look can be taught using medical humanities and especially visual arts. By presenting a Ramsay sedation score (RSS) integrated with Caravaggio's paintings during a procedural sedation conference for pediatric residents, we want to test the effectiveness of this approach to improve the quality of learning. METHODS: In this preliminary study, we presented videos showing sedated pediatric patients in the setting of a procedural sedation lesson to two randomized groups of residents, one attending a lesson on RSS explained through the masterpieces of Caravaggio, the other without artistic support. A week later we tested their learning with ten multi-choice questions focused on theoretical questions about sedation monitoring and ten more questions focused on recognizing the appropriate RSS viewing the videos. The primary outcome was the comparison of the total number of RSS layers properly recognized in both groups. We also evaluated the appreciation of the residents of the use of works of art integrated with the lesson. RESULTS: Eleven students were randomized to each group. Two residents in the standard lesson did not attend the test. The percentage of correct answers on the theoretical part was similar, 82% in the art group and 89% in the other (p > 0.05). No difference was found in the video recognition part of the RSS recognition test. Residents exposed to paintings shown great appreciation for the integration of the lesson with the Caravaggio's masterpieces. CONCLUSIONS: Adding artwork to a standard medical conference does not improve the performance of student tests, although this approach has been greatly appreciated by residents.
Keywords: Clinical Competence; Conscious Sedation; Deep Sedation; Education, Medical, Graduate; Female; Hospitals, University; Humans; Internship and Residency; Italy; Male; Medicine in the Arts; Monitoring, Physiologic; Pain Measurement; Paintings; Pediatrics; Video Recording

Theophylline as a precision therapy in a young girl with PIK3R1 immunodeficiency. - Valencic, Erica; Grasso, Antonio Giacomo; Conversano, Ester; Lucafò, Marianna; Piscianz, Elisa; Gregori, Massimo; Conti, Francesca; Cancrini, Caterina; Tommasini, Alberto (J Allergy Clin Immunol Pract, 2018)

An unusual unilateral breast enlargement in a prepubertal girl. - Pavan, Matteo; Faleschini, Elena; Tornese, Gianluca; Zandonà, Lorenzo; Ventura, Alessandro (Arch Dis Child, 2018)

1000 Genomes-based meta-analysis identifies 10 novel loci for kidney function. - Gorski, Mathias; van der Most, Peter J; Teumer, Alexander; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Nolte, Ilja M; Cocca, Massimiliano; Taliun, Daniel; Gomez, Felicia; Li, Yong; Tayo, Bamidele; et al. (Sci Rep, 2017)
HapMap imputed genome-wide association studies (GWAS) have revealed >50 loci at which common variants with minor allele frequency >5% are associated with kidney function. GWAS using more complete reference sets for imputation, such as those from The 1000 Genomes project, promise to identify novel loci that have been missed by previous efforts. To investigate the value of such a more complete variant catalog, we conducted a GWAS meta-analysis of kidney function based on the estimated glomerular filtration rate (eGFR) in 110,517 European ancestry participants using 1000 Genomes imputed data. We identified 10 novel loci with p-value < 5 × 10 previously missed by HapMap-based GWAS. Six of these loci (HOXD8, ARL15, PIK3R1, EYA4, ASTN2, and EPB41L3) are tagged by common SNPs unique to the 1000 Genomes reference panel. Using pathway analysis, we identified 39 significant (FDR < 0.05) genes and 127 significantly (FDR < 0.05) enriched gene sets, which were missed by our previous analyses. Among those, the 10 identified novel genes are part of pathways of kidney development, carbohydrate metabolism, cardiac septum development and glucose metabolism. These results highlight the utility of re-imputing from denser reference panels, until whole-genome sequencing becomes feasible in large samples.
Keywords: Computational Biology; Gene Frequency; Genetic Loci; Genome, Human; Genome-Wide Association Study; Genotyping Techniques; Humans; Kidney; Polymorphism, Single Nucleotide

ADA2 deficiency (DADA2) as an unrecognised cause of early onset polyarteritis nodosa and stroke: a multicentre national study. - Caorsi, Roberta; Penco, Federica; Grossi, Alice; Insalaco, Antonella; Omenetti, Alessia; Alessio, Maria; Conti, Giovanni; Marchetti, Federico; Picco, Paolo; Tommasini, Alberto; Martino, Silvana; Malattia, Clara; et al. (Ann Rheum Dis, 2017)
OBJECTIVES: To analyse the prevalence of mutations in patients diagnosed with early onset livedo reticularis and/or haemorrhagic/ischaemic strokes in the context of inflammation or polyarteritis nodosa (PAN). Forty-eight patients from 43 families were included in the study. METHODS: Direct sequencing of was performed by Sanger analysis. Adenosine deaminase 2 (ADA2) enzymatic activity was analysed in monocyte isolated from patients and healthy controls incubated with adenosine and with or without an ADA1 inhibitor. RESULTS: Biallelic homozygous or compound heterozygous mutations were detected in 15/48 patients. A heterozygous disease-associated mutation (p.G47V) was observed in two affected brothers. The mean age of onset of the genetically positive patients was 24 months (6 months to 7 years). Ten patients displayed one or more cerebral strokes during their disease course. Low immunoglobulin levels were detected in six patients. Thalidomide and anti-TNF (tumour necrosis factor) blockers were the most effective drugs. Patients without mutations had a later age at disease onset, a lower prevalence of neurological and skin manifestations; one of these patients displayed all the clinical features of adenosine deaminase 2deficiency (DADA2) and a defective enzymatic activity suggesting the presence of a missed mutation or a synthesis defect. CONCLUSIONS: DADA2 accounts for paediatric patients diagnosed with PAN-like disease and strokes and might explain an unrecognised condition in patients followed by adult rheumatologist. Timely diagnosis and treatment with anti-TNF agents are crucial for the prevention of severe complications of the disease. Functional assay to measure ADA2 activity should complement genetic testing in patients with non-confirming genotypes.
Keywords: Adenosine Deaminase; Adolescent; Age of Onset; Case-Control Studies; Child; Child, Preschool; DNA Mutational Analysis; Female; Heterozygote; Homozygote; Humans; Immunoglobulins; Immunosuppressive Agents; Infant; Intercellular Signaling Peptides and Proteins; Italy; Livedo Reticularis; Male; Pedigree; Polyarteritis Nodosa; Stroke; Thalidomide; Tumor Necrosis Factor-alpha; Young Adult

ANCA-associated vasculitis in childhood: recent advances. - Calatroni, Marta; Oliva, Elena; Gianfreda, Davide; Gregorini, Gina; Allinovi, Marco; Ramirez, Giuseppe A; Bozzolo, Enrica P; Monti, Sara; Bracaglia, Claudia; Marucci, Giulia; Bodria, Monica; Sinico, Renato A; et al. (Ital J Pediatr, 2017)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitides are rare systemic diseases that usually occur in adulthood. They comprise granulomatosis with polyangiitis (GPA, Wegener's), microscopic polyangiitis (MPA) and eosinophilic granulomatosis with polyangiitis (EGPA, Churg-Strauss syndrome). Their clinical presentation is often heterogeneous, with frequent involvement of the respiratory tract, the kidney, the skin and the joints. ANCA-associated vasculitis is rare in childhood but North-American and European cohort studies performed during the last decade have clarified their phenotype, patterns of renal involvement and their prognostic implications, and outcome. Herein, we review the main clinical and therapeutic aspects of childhood-onset ANCA-associated vasculitis, and provide preliminary data on demographic characteristics and organ manifestations of an Italian multicentre cohort.
Keywords: Age Distribution; Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis; Antibodies, Antineutrophil Cytoplasmic; Child; Child, Preschool; Churg-Strauss Syndrome; Female; Granulomatosis with Polyangiitis; Humans; Incidence; Male; Microscopic Polyangiitis; Rare Diseases; Risk Assessment; Severity of Illness Index; Sex Distribution; Survival Rate

and Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function. - Li, Man; Li, Yong; Weeks, Olivia; Mijatovic, Vladan; Teumer, Alexander; Huffman, Jennifer E; Tromp, Gerard; Fuchsberger, Christian; Gorski, Mathias; Lyytikäinen, Leo-Pekka; Nutile, Teresa; Sedaghat, Sanaz; et al. (J Am Soc Nephrol, 2017)
Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (: 111,666; : 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated with eGFRcrea (, , and ; <3.7×10), of which most were common and annotated as nonsynonymous variants. Gene-based analysis identified associations of functional rare variants in three genes with eGFRcrea, including a novel association with the SOS Ras/Rho guanine nucleotide exchange factor 2 gene, (=5.4×10 by sequence kernel association test). Experimental follow-up in zebrafish embryos revealed changes in glomerular gene expression and renal tubule morphology in the embryonic kidney of and -knockdowns. These developmental abnormalities associated with altered blood clearance rate and heightened prevalence of edema. This study expands the number of loci associated with kidney function and identifies novel genes with potential roles in kidney formation.
Keywords: Animals; Exome; Genetic Loci; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Protein Tyrosine Phosphatases; Proto-Oncogene Proteins; Son of Sevenless Proteins; Zebrafish

Autoimmune neutropenia of childhood secondary to other autoimmune disorders: Data from the Italian neutropenia registry. - Farruggia, Piero; Puccio, Giuseppe; Fioredda, Francesca; Lanza, Tiziana; Porretti, Laura; Ramenghi, Ugo; Barone, Angelica; Bonanomi, Sonia; Finocchi, Andrea; Ghilardi, Roberta; Ladogana, Saverio; Marra, Nicoletta; et al. (Am J Hematol, 2017)
Keywords: Autoimmune Diseases; Child; Disease Susceptibility; Female; Humans; Immunoglobulins, Intravenous; Immunosuppressive Agents; Infant, Newborn; Infant, Premature; Infant, Premature, Diseases; Italy; Male; Neutropenia; Prevalence; Registries

Bilateral Finger Swelling in an Adolescent. - Naviglio, Samuele; Mazzolai, Michele; Ventura, Alessandro (J Pediatr, 2017)

CCR5Δ32 and the genetic susceptibility to rheumatoid arthritis in admixed populations: a multicentre study. - Toson, Bruno; Dos Santos, Eduardo José; Adelino, José Eduardo; Sandrin-Garcia, Paula; Crovella, Sergio; Louzada-Júnior, Paulo; Oliveira, Renê Donizete Ribeiro; Pedroza, Larysse Santa Rosa Aquino; de Fátima Lobato Cunha Sauma, Maria; de Lima, Clayton Pereira Silva; Barbosa, Fabiola Brasil; Brenol, Claiton Viegas; et al. (Rheumatology (Oxford), 2017)
Keywords: Arthritis, Rheumatoid; Brazil; Case-Control Studies; Consanguinity; Gene Frequency; Genetic Predisposition to Disease; Humans; Polymorphism, Single Nucleotide; Receptors, CCR5

Child and Adolescent Health From 1990 to 2015: Findings From the Global Burden of Diseases, Injuries, and Risk Factors 2015 Study. - Kassebaum, Nicholas; Kyu, Hmwe Hmwe; Zoeckler, Leo; Olsen, Helen Elizabeth; Thomas, Katie; Pinho, Christine; Bhutta, Zulfiqar A; Dandona, Lalit; Ferrari, Alize; Ghiwot, Tsegaye Tewelde; Hay, Simon I; Kinfu, Yohannes; et al. (JAMA Pediatr, 2017)
Importance: Comprehensive and timely monitoring of disease burden in all age groups, including children and adolescents, is essential for improving population health. Objective: To quantify and describe levels and trends of mortality and nonfatal health outcomes among children and adolescents from 1990 to 2015 to provide a framework for policy discussion. Evidence Review: Cause-specific mortality and nonfatal health outcomes were analyzed for 195 countries and territories by age group, sex, and year from 1990 to 2015 using standardized approaches for data processing and statistical modeling, with subsequent analysis of the findings to describe levels and trends across geography and time among children and adolescents 19 years or younger. A composite indicator of income, education, and fertility was developed (Socio-demographic Index [SDI]) for each geographic unit and year, which evaluates the historical association between SDI and health loss. Findings: Global child and adolescent mortality decreased from 14.18 million (95% uncertainty interval [UI], 14.09 million to 14.28 million) deaths in 1990 to 7.26 million (95% UI, 7.14 million to 7.39 million) deaths in 2015, but progress has been unevenly distributed. Countries with a lower SDI had a larger proportion of mortality burden (75%) in 2015 than was the case in 1990 (61%). Most deaths in 2015 occurred in South Asia and sub-Saharan Africa. Global trends were driven by reductions in mortality owing to infectious, nutritional, and neonatal disorders, which in the aggregate led to a relative increase in the importance of noncommunicable diseases and injuries in explaining global disease burden. The absolute burden of disability in children and adolescents increased 4.3% (95% UI, 3.1%-5.6%) from 1990 to 2015, with much of the increase owing to population growth and improved survival for children and adolescents to older ages. Other than infectious conditions, many top causes of disability are associated with long-term sequelae of conditions present at birth (eg, neonatal disorders, congenital birth defects, and hemoglobinopathies) and complications of a variety of infections and nutritional deficiencies. Anemia, developmental intellectual disability, hearing loss, epilepsy, and vision loss are important contributors to childhood disability that can arise from multiple causes. Maternal and reproductive health remains a key cause of disease burden in adolescent females, especially in lower-SDI countries. In low-SDI countries, mortality is the primary driver of health loss for children and adolescents, whereas disability predominates in higher-SDI locations; the specific pattern of epidemiological transition varies across diseases and injuries. Conclusions and Relevance: Consistent international attention and investment have led to sustained improvements in causes of health loss among children and adolescents in many countries, although progress has been uneven. The persistence of infectious diseases in some countries, coupled with ongoing epidemiologic transition to injuries and noncommunicable diseases, require all countries to carefully evaluate and implement appropriate strategies to maximize the health of their children and adolescents and for the international community to carefully consider which elements of child and adolescent health should be monitored.
Keywords: Adolescent; Adolescent Health; Age Factors; Cause of Death; Child; Child Health; Child Mortality; Disabled Children; Female; Global Burden of Disease; Global Health; Humans; Male; Pregnancy; Pregnancy Complications; Risk Factors; Sex Factors; Wounds and Injuries

Children with cancer: a survey on the experience of Italian primary care pediatricians. - Minute, Marta; Cozzi, Giorgio; Plotti, Chiara; Montanari, Giuseppe; Pecile, Paolo; Zanazzo, Giulio Andrea; Ventura, Alessandro; Barbi, Egidio (Ital J Pediatr, 2017)
BACKGROUND: Cancer is the second cause of death in children and its diagnosis can be difficult, due to the presence of vague and non-specific symptoms. The primary care pediatrician is often involved in the diagnostic process, but no longer in child care once the treatment started. Care models involving both primary care pediatricians and oncologic referral centre highlighted a higher family satisfaction when they worked together. We conducted a survey on primary care pediatricians involved in childhood cancer in order to describe the actual situation. METHODS: We conducted a retrospective survey enrolling primary care pediatricians from a north-eastern area of Italy. They received a questionnaire that consisted in two parts: the first one aimed to assess the physician's seniority and experience and the second one pertained to each case of cancer and explored the relationship between the pediatrician, the family and the referral centre, and pediatricians degree of satisfaction and emotional impact. RESULTS: We obtained data from 79 pediatricians who described 150 cancer cases. In 99 cases the primary care pediatrician had visited the child at the onset of symptoms and had referred him to the hospital. In 89 cases, he understood the severity of the disease. In 53.3% of cases the pediatrician was informed by the referral centre. The relationship between the pediatrician and child's family improved in 38% of cases and this was related with their participation to the multidisciplinary meetings on child health. CONCLUSIONS: Primary pediatricians' sharing in the management of their patients with cancer was not satisfactory. Development of specific protocols targeted to an integrated care is needed to increase primary pediatricians' involvement and families' satisfactions.
Keywords: Child; Child, Preschool; Cross-Sectional Studies; Disease-Free Survival; Female; Humans; Italy; Male; Needs Assessment; Neoplasms; Outcome Assessment (Health Care); Pediatricians; Practice Patterns, Physicians'; Prevalence; Primary Health Care; Retrospective Studies; Risk Assessment; Survival Analysis

Common variants in CLDN14 are associated with differential excretion of magnesium over calcium in urine. - Corre, Tanguy; Olinger, Eric; Harris, Sarah E; Traglia, Michela; Ulivi, Sheila; Lenarduzzi, Stefania; Belge, Hendrica; Youhanna, Sonia; Tokonami, Natsuko; Bonny, Olivier; Houillier, Pascal; Polasek, Ozren; et al. (Pflugers Arch, 2017)
The nature and importance of genetic factors regulating the differential handling of Ca and Mg by the renal tubule in the general population are poorly defined. We conducted a genome-wide meta-analysis of urinary magnesium-to-calcium ratio to identify associated common genetic variants. We included 9320 adults of European descent from four genetic isolates and three urban cohorts. Urinary magnesium and calcium concentrations were measured centrally in spot urine, and each study conducted linear regression analysis of urinary magnesium-to-calcium ratio on ~2.5 million single-nucleotide polymorphisms (SNPs) using an additive model. We investigated, in mouse, the renal expression profile of the top candidate gene and its variation upon changes in dietary magnesium. The genome-wide analysis evidenced a top locus (rs172639, p = 1.7 × 10), encompassing CLDN14, the gene coding for claudin-14, that was genome-wide significant when using urinary magnesium-to-calcium ratio, but not either one taken separately. In mouse, claudin-14 is expressed in the distal nephron segments specifically handling magnesium, and its expression is regulated by chronic changes in dietary magnesium content. A genome-wide approach identified common variants in the CLDN14 gene exerting a robust influence on the differential excretion of Mg over Ca in urine. These data highlight the power of urinary electrolyte ratios to unravel genetic determinants of renal tubular function. Coupled with mouse experiments, these results support a major role for claudin-14, a gene associated with kidney stones, in the differential paracellular handling of divalent cations by the renal tubule.
Keywords: Animals; Calcium; Claudins; Humans; Kidney Tubules; Magnesium; Polymorphism, Single Nucleotide; Urine

Complement Protein C1q Binds to Hyaluronic Acid in the Malignant Pleural Mesothelioma Microenvironment and Promotes Tumor Growth. - Agostinis, Chiara; Vidergar, Romana; Belmonte, Beatrice; Mangogna, Alessandro; Amadio, Leonardo; Geri, Pietro; Borelli, Violetta; Zanconati, Fabrizio; Tedesco, Francesco; Confalonieri, Marco; Tripodo, Claudio; Kishore, Uday; et al. (Front Immunol, 2017)
C1q is the first recognition subcomponent of the complement classical pathway, which acts toward the clearance of pathogens and apoptotic cells. C1q is also known to modulate a range of functions of immune and non-immune cells, and has been shown to be involved in placental development and sensorial synaptic pruning. We have recently shown that C1q can promote tumor by encouraging their adhesion, migration, and proliferation in addition to angiogenesis and metastasis. In this study, we have examined the role of human C1q in the microenvironment of malignant pleural mesothelioma (MPM), a rare form of cancer commonly associated with exposure to asbestos. We found that C1q was highly expressed in all MPM histotypes, particularly in epithelioid rather than in sarcomatoid histotype. C1q avidly bound high and low molecular weight hyaluronic acid (HA) its globular domain. C1q bound to HA was able to induce adhesion and proliferation of mesothelioma cells (MES) enhancement of ERK1/2, SAPK/JNK, and p38 phosphorylation; however, it did not activate the complement cascade. Consistent with the modular organization of the globular domain, we demonstrated that C1q may bind to HA through ghA module, whereas it may interact with human MES through the ghC. In conclusion, C1q highly expressed in MPM binds to HA and enhances the tumor growth promoting cell adhesion and proliferation. These data can help develop novel diagnostic markers and molecular targets for MPM.

A complete duplication of X chromosome resulting in a tricentric isochromosome originated by centromere repositioning. - Villa, N; Conconi, D; Benussi, D Gambel; Tornese, G; Crosti, F; Sala, E; Dalprà, L; Pecile, V (Mol Cytogenet, 2017)
BACKGROUND: Neocentromeres are rare and considered chromosomal aberrations, because a non-centromeric region evolves in an active centromere by mutation. The literature reported several structural anomalies of X chromosome and they influence the female reproductive capacity or are associated to Turner syndrome in the presence of monosomy X cell line. CASE PRESENTATION: We report a case of chromosome X complex rearrangement found in a prenatal diagnosis. The fetal karyotype showed a mosaicism with a 45,X cell line and a 46 chromosomes second line with a big marker, instead of a sex chromosome. The marker morphology and fluorescence in situ hybridization (FISH) characterization allowed us to identify a tricentric X chromosome constituted by two complete X chromosome fused at the p arms telomere and an active neocentromere in the middle, at the union of the two Xp arms, where usually are the telomeric regions. FISH also showed the presence of a paracentric inversion of both Xp arms. Furthermore, fragility figures were found in 56% of metaphases from peripheral blood lymphocytes culture at birth: a shorter marker chromosome and an apparently acentric fragment frequently lost. CONCLUSIONS: At our knowledge, this is the first isochromosome of an entire non-acrocentric chromosome. The neocentromere is constituted by canonical sequences but localized in an unusual position and the original centromeres are inactivated. We speculated that marker chromosome was the result of a double rearrangement: firstly, a paracentric inversion which involved the Xp arm, shifting a part of the centromere at the p end and subsequently a duplication of the entire X chromosome, which gave rise to an isochromosome. It is possible to suppose that the first event could be a result of a non-allelic homologous recombination mediated by inverted low-copy repeats. As expected, our case shows a Turner phenotype with mild facial features and no major skeletal deformity, normal psychomotor development and a spontaneous development of puberty and menarche, although with irregular menses since the last follow-up.

A congenital purplish tumour. - Matarazzo, L; Delise, A; Zennaro, F; Bussani, R; Demarini, S; Berti, I; Ventura, A (Arch Dis Child Educ Pract Ed, 2017)
Keywords: Congenital Abnormalities; Humans; India; Infant; Infant, Newborn; Knee; Male; Neonatology; Neoplasms; Treatment Outcome

Curcumin Anti-Apoptotic Action in a Model of Intestinal Epithelial Inflammatory Damage. - Loganes, Claudia; Lega, Sara; Bramuzzo, Matteo; Vecchi Brumatti, Liza; Piscianz, Elisa; Valencic, Erica; Tommasini, Alberto; Marcuzzi, Annalisa (Nutrients, 2017)
The purpose of this study is to determine if a preventive treatment with curcumin can protect intestinal epithelial cells from inflammatory damage induced by IFNγ. To achieve this goal we have used a human intestinal epithelial cell line (HT29) treated with IFNγ to undergo apoptotic changes that can reproduce the damage of intestinal epithelia exposed to inflammatory cytokines. In this model, we measured the effect of curcumin (curcuminoid from ) added as a pre-treatment at different time intervals before stimulation with IFNγ. Curcumin administration to HT29 culture before the inflammatory stimulus IFNγ reduced the cell apoptosis rate. This effect gradually declined with the reduction of the curcumin pre-incubation time. This anti-apoptotic action by curcumin pre-treatment was paralleled by a reduction of secreted IL7 in the HT29 culture media, while there was no relevant change in the other cytokine levels. Even though curcumin pre-administration did not impact the activation of the NF-κB pathway, a slight effect on the phosphorylation of proteins in this inflammatory signaling pathway was observed. In conclusion, curcumin pre-treatment can protect intestinal cells from inflammatory damage. These results can be the basis for studying the preventive role of curcumin in inflammatory bowel diseases.
Keywords: Anti-Inflammatory Agents, Non-Steroidal; Apoptosis; Cell Survival; Curcuma; Curcumin; Cytokines; Epithelial Cells; HT29 Cells; Humans; Inflammation; Interferon-gamma; Interleukin-7; Intestinal Mucosa; NF-kappa B; Phosphorylation; Signal Transduction

CYP3A genes and the association between prenatal methylmercury exposure and neurodevelopment. - Llop, Sabrina; Tran, Van; Ballester, Ferran; Barbone, Fabio; Sofianou-Katsoulis, Aikaterini; Sunyer, Jordi; Engström, Karin; Alhamdow, Ayman; Love, Tanzy M; Watson, Gene E; Bustamante, Mariona; Murcia, Mario; et al. (Environ Int, 2017)
BACKGROUND: Results on the association between prenatal exposure to methylmercury (MeHg) and child neuropsychological development are heterogeneous. Underlying genetic differences across study populations could contribute to this varied response to MeHg. Studies in Drosophila have identified the cytochrome p450 3A (CYP3A) family as candidate MeHg susceptibility genes. OBJECTIVES: We evaluated whether genetic variation in CYP3A genes influences the association between prenatal exposure to MeHg and child neuropsychological development. METHODS: The study population included 2639 children from three birth cohort studies: two subcohorts in Seychelles (SCDS) (n=1160, 20 and 30months of age, studied during the years 2001-2012), two subcohorts from Spain (INMA) (n=625, 14months of age, 2003-2009), and two subcohorts from Italy and Greece (PHIME) (n=854, 18months of age, 2006-2011). Total mercury, as a surrogate of MeHg, was analyzed in maternal hair and/or cord blood samples. Neuropsychological development was evaluated using Bayley Scales of Infant Development (BSID). Three functional polymorphisms in the CYP3A family were analyzed: rs2257401 (CYP3A7), rs776746 (CYP3A5), and rs2740574 (CYP3A4). RESULTS: There was no association between CYP3A polymorphisms and cord mercury concentrations. The scores for the BSID mental scale improved with increasing cord blood mercury concentrations for carriers of the most active alleles (β[95% CI]:=2.9[1.53,4.27] for CYP3A7 rs2257401 GG+GC, 2.51[1.04,3.98] for CYP3A5 rs776746 AA+AG and 2.31[0.12,4.50] for CYP3A4 rs2740574 GG+AG). This association was near the null for CYP3A7 CC, CYP3A5 GG and CYP3A4 AA genotypes. The interaction between the CYP3A genes and total mercury was significant (p<0.05) in European cohorts only. CONCLUSIONS: Our results suggest that the polymorphisms in CYP3A genes may modify the response to dietary MeHg exposure during early life development.
Keywords: Adult; Child Development; Child, Preschool; Cohort Studies; Cytochrome P-450 CYP3A; Female; Fetal Blood; Genotype; Greece; Humans; Infant; Italy; Male; Mercury; Methylmercury Compounds; Neurodevelopmental Disorders; Neuropsychological Tests; Polymorphism, Genetic; Pregnancy; Prenatal Exposure Delayed Effects; Seychelles; Spain

Describing Kawasaki shock syndrome: results from a retrospective study and literature review. - Taddio, Andrea; Rossi, Eleonora Dei; Monasta, Lorenzo; Pastore, Serena; Tommasini, Alberto; Lepore, Loredana; Bronzetti, Gabriele; Marrani, Edoardo; Mottolese, Biancamaria D'Agata; Simonini, Gabriele; Cimaz, Rolando; Ventura, Alessandro (Clin Rheumatol, 2017)
Kawasaki shock syndrome (KSS) is a rare manifestation of Kawasaki disease (KD) characterized by systolic hypotension or clinical signs of poor perfusion. The objectives of the study are to describe the main clinical presentation, echocardiographic, and laboratory findings, as well as the treatment options and clinical outcomes of KSS patients when compared with KD patients. This is a retrospective study. All children referred to two pediatric rheumatology units from January 1, 2012, to December 31, 2014, were enrolled. Patients were divided into patients with or without KSS. We compared the two groups according to the following variables: sex, age, type of KD (classic, with less frequent manifestations, or incomplete), clinical manifestations, cardiac involvement, laboratory findings, therapy administered, response to treatment, and outcome. Eighty-four patients with KD were enrolled. Of these, five (6 %) met the criteria for KSS. Patients with KSS had higher values of C-reactive protein (p = 0.005), lower hemoglobin levels (p = 0.003); more frequent hyponatremia (p = 0.004), hypoalbuminemia (p = 0.004), and coagulopathy (p = 0.003); and increase in cardiac troponins (p = 0.000). Among the KSS patients, three had a coronary artery involvement, but none developed a permanent aneurysm. Intravenous immunoglobulin resistance was more frequent in the KSS group, although not significantly so (3/5, 60 % vs. 23/79, 30 %, P = NS). None of the five cases was fatal, and all recovered without sequelae. KSS patients are more likely to have higher rates of cardiac involvement. However, most cardiovascular abnormalities resolved promptly with therapy.
Keywords: C-Reactive Protein; Child; Child, Preschool; Echocardiography; Female; Heart Failure; Hemoglobins; Humans; Immunoglobulins, Intravenous; Male; Mucocutaneous Lymph Node Syndrome; Retrospective Studies; Shock; Syndrome

Diagnosis and management of newly diagnosed childhood autoimmune haemolytic anaemia. Recommendations from the Red Cell Study Group of the Paediatric Haemato-Oncology Italian Association. - Ladogana, Saverio; Maruzzi, Matteo; Samperi, Piera; Perrotta, Silverio; Del Vecchio, Giovanni C; Notarangelo, Lucia D; Farruggia, Piero; Verzegnassi, Federico; Masera, Nicoletta; Saracco, Paola; Fasoli, Silvia; Miano, Maurizio; et al. (Blood Transfus, 2017)
Autoimmune haemolytic anaemia is an uncommon disorder to which paediatric haematology centres take a variety of diagnostic and therapeutic approaches. The Red Cell Working Group of the Italian Association of Paediatric Onco-haematology (Associazione Italiana di Ematologia ed Oncologia Pediatrica, AIEOP) developed this document in order to collate expert opinions on the management of newly diagnosed childhood autoimmune haemolytic anaemia.The diagnostic process includes the direct and indirect antiglobulin tests; recommendations are given regarding further diagnostic tests, specifically in the cases that the direct and indirect antiglobulin tests are negative. Clear-cut definitions of clinical response are stated. Specific recommendations for treatment include: dosage of steroid therapy and tapering modality for warm autoimmune haemolytic anaemia; the choice of rituximab as first-line therapy for the rare primary transfusion-dependent cold autoimmune haemolytic anaemia; the indications for supportive therapy; the need for switching to second-line therapy. Each statement is provided with a score expressing the level of appropriateness and the agreement among participants.
Keywords: Anemia, Hemolytic, Autoimmune; Blood Transfusion; Child; Coombs Test; Disease Management; Hematology; Humans; Immunoglobulin M; Italy; Pediatrics; Societies, Medical; Steroids

Dynamic quadripolar radiofrequency treatment of vaginal laxity/menopausal vulvo-vaginal atrophy: 12-month efficacy and safety. - Vicariotto, Franco; De Seta, Francesco; Faoro, Valentina; Raichi, Mauro (Minerva Ginecol, 2017)
BACKGROUND: Twelve-month extension of a previous spontaneous exploratory study investigating safety and efficacy of a new low-energy dynamic quadripolar radiofrequency (DQRF) device in: A) premenopausal women with symptoms of vaginal laxity, with special reference to dysuria, urinary incontinence and unsatisfactory sexual life (vaginal laxity arm of the study); B) postmenopausal women with vulvovaginal atrophy/genitourinary syndrome of menopause (VVA/GSM) and VVA/GSM-related symptoms (VVA/GSM arm of the study). DQRF treatment schedule in both study arms: 4 to 6 procedures of 15 to 20 min every 14 days (vaginal laxity, range 12-17 days; VVA/GSM, range 13-16). Operative temperatures in vaginal target tissues during procedure: vaginal laxity, 42 °C (range 40-43 °C); VVA/GSM, 40 °C (range 40-42 °C). METHODS: In the vaginal laxity arm of the study, 25 women with subjective sensation of vaginal introital laxity (very to slightly loose). Assessment of urinary incontinence, satisfaction with sexual relationship and contribution of pelvic organ prolapse: Vaginal Laxity Questionnaire (VLQ, Italian certified translation) and short form of the Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire (PISQ-12, Italian certified translation). Further evaluation of sexual gratification: Sexual Satisfaction Questionnaire (SSQ). In the VVA/GSM arm of the study, 32 women with objective evidence of VVA and vaginal dryness and/or dyspareunia as most bothersome symptoms. Assessment of VVA/GSM symptoms and overall satisfaction with sexual life: specifically designed 10-cm visual analogue scales. RESULTS: All 4 to 6 planned DQRF sessions were well tolerated in both the vaginal laxity and VVA/GSM arms of the study, with no troubling pain, thermal injury or other immediate adverse effects during all the procedures. All screened women completed the planned DQRF treatment sessions in both arms of the extension study. There was no participant attrition with only a few occasionally missing visits over the 12-month follow-up period. Improvements were rapid in self-perception of introital looseness and related symptoms like dysuria/urinary incontinence and unrewarding sexual relationship (vaginal laxity patients) and atrophy-related symptoms including painful and unsatisfactory sexual activity (VVA/GSM patients). Participating women consistently reported wide-spectrum strong clinical improvements by the end of the planned DQRF sessions. Clinical improvements remained steady for the whole follow-up period in postmenopausal women; a statistically non-significant tendency to slight deterioration in VLQ, PISQ-12 and SSQ mean scores was detected after 6 to 9 months of follow-up in the vaginal laxity arm of the study. CONCLUSIONS: Safety was excellent during all DQRF procedures and over the 12 months following the end of the treatment sessions. VLQ, PISQ-12 and SSQ scores (women with vaginal laxity), VAS self-evaluation of VVA/GSM symptoms and overall satisfaction with sexual life (women with VVA/GSM symptoms) improved rapidly, reaching almost normal levels by the last DQRF session and suggesting rapid, but also persistent, vaginal rejuvenation in both indications. A late tendency to some slight deterioration in women treated for vaginal laxity suggests such women might benefit from new DQRF treatments 6 to 9 months after the previous cycle.
Keywords: Adult; Atrophy; Dyspareunia; Electric Stimulation Therapy; Female; Follow-Up Studies; Humans; Italy; Middle Aged; Orgasm; Patient Satisfaction; Pelvic Organ Prolapse; Postmenopause; Premenopause; Sexual Behavior; Surveys and Questionnaires; Time Factors; Treatment Outcome; Urinary Incontinence; Vagina; Vaginal Diseases; Vulva

Fetal monitoring indications for delivery and 2-year outcome in 310 infants with fetal growth restriction delivered before 32 weeks' gestation in the TRUFFLE study. - Visser, G H A; Bilardo, C M; Derks, J B; Ferrazzi, E; Fratelli, N; Frusca, T; Ganzevoort, W; Lees, C C; Napolitano, R; Todros, T; Wolf, H; Hecher, K (Ultrasound Obstet Gynecol, 2017)
OBJECTIVE: In the TRUFFLE (Trial of Randomized Umbilical and Fetal Flow in Europe) study on the outcome of early fetal growth restriction, women were allocated to one of three groups of indication for delivery according to the following monitoring strategies: (1) reduced fetal heart rate (FHR) short-term variation (STV) on cardiotocography (CTG); (2) early changes in fetal ductus venosus (DV) waveform (DV-p95); and (3) late changes in fetal DV waveform (DV-no-A). However, many infants per monitoring protocol were delivered because of safety-net criteria, for maternal or other fetal indications, or after 32 weeks of gestation when the protocol was no longer applied. The objective of the present posthoc subanalysis was to investigate the indications for delivery in relation to 2-year outcome in infants delivered before 32 weeks to further refine management proposals. METHODS: We included all 310 cases of the TRUFFLE study with known outcome at 2 years' corrected age and seven fetal deaths, excluding seven cases with inevitable perinatal death. Data were analyzed according to the allocated fetal monitoring strategy in combination with the indication for delivery. RESULTS: Overall, only 32% of liveborn infants were delivered according to the specified monitoring parameter for indication for delivery; 38% were delivered because of safety-net criteria, 15% for other fetal reasons and 15% for maternal reasons. In the CTG-STV group, 51% of infants were delivered because of reduced STV. In the DV-p95 group, 34% of infants were delivered because of abnormal DV and, in the DV-no-A group, only 10% of infants were delivered accordingly. The majority of infants in the DV groups were delivered for the safety-net criterion of spontaneous decelerations in FHR. Two-year intact survival was highest in the DV groups combined compared with the CTG-STV group (P = 0.05 for live births only, P = 0.21 including fetal death), with no difference between DV groups. A poorer outcome in the CTG-STV group was restricted to infants delivered because of FHR decelerations in the safety-net subgroup. Infants delivered because of maternal reasons had the highest birth weight and a non-significantly higher intact survival. CONCLUSIONS: In this subanalysis of infants delivered before 32 weeks, the majority were delivered for reasons other than the allocated monitoring strategy indication. Since, in the DV group, CTG-STV criteria were used as a safety net but in the CTG-STV group, no DV safety-net criteria were applied, we speculate that the slightly poorer outcome in the CTG-STV group might be explained by the absence of DV data. The optimal timing of delivery of fetuses with early intrauterine growth restriction may therefore be best determined by monitoring them longitudinally, with both DV and CTG monitoring. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Cardiotocography; Delivery, Obstetric; Female; Fetal Growth Retardation; Fetal Monitoring; Fetus; Gestational Age; Humans; Infant, Newborn; Male; Netherlands; Pregnancy; Pregnancy Outcome; Pulsatile Flow; Survival Analysis; Ultrasonography, Prenatal; Umbilical Arteries

Genome-wide association analysis identifies novel blood pressure loci and offers biological insights into cardiovascular risk. - Warren, Helen R; Evangelou, Evangelos; Cabrera, Claudia P; Gao, He; Ren, Meixia; Mifsud, Borbala; Ntalla, Ioanna; Surendran, Praveen; Liu, Chunyu; Cook, James P; Kraja, Aldi T; Drenos, Fotios; et al. (Nat Genet, 2017)
Elevated blood pressure is the leading heritable risk factor for cardiovascular disease worldwide. We report genetic association of blood pressure (systolic, diastolic, pulse pressure) among UK Biobank participants of European ancestry with independent replication in other cohorts, and robust validation of 107 independent loci. We also identify new independent variants at 11 previously reported blood pressure loci. In combination with results from a range of in silico functional analyses and wet bench experiments, our findings highlight new biological pathways for blood pressure regulation enriched for genes expressed in vascular tissues and identify potential therapeutic targets for hypertension. Results from genetic risk score models raise the possibility of a precision medicine approach through early lifestyle intervention to offset the impact of blood pressure-raising genetic variants on future cardiovascular disease risk.
Keywords: Adult; Blood Pressure; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Genomic analyses identify hundreds of variants associated with age at menarche and support a role for puberty timing in cancer risk. - Day, Felix R; Thompson, Deborah J; Helgason, Hannes; Chasman, Daniel I; Finucane, Hilary; Sulem, Patrick; Ruth, Katherine S; Whalen, Sean; Sarkar, Abhishek K; Albrecht, Eva; Altmaier, Elisabeth; Amini, Marzyeh; et al. (Nat Genet, 2017)
The timing of puberty is a highly polygenic childhood trait that is epidemiologically associated with various adult diseases. Using 1000 Genomes Project-imputed genotype data in up to ∼370,000 women, we identify 389 independent signals (P < 5 × 10) for age at menarche, a milestone in female pubertal development. In Icelandic data, these signals explain ∼7.4% of the population variance in age at menarche, corresponding to ∼25% of the estimated heritability. We implicate ∼250 genes via coding variation or associated expression, demonstrating significant enrichment in neural tissues. Rare variants near the imprinted genes MKRN3 and DLK1 were identified, exhibiting large effects when paternally inherited. Mendelian randomization analyses suggest causal inverse associations, independent of body mass index (BMI), between puberty timing and risks for breast and endometrial cancers in women and prostate cancer in men. In aggregate, our findings highlight the complexity of the genetic regulation of puberty timing and support causal links with cancer susceptibility.
Keywords: Adolescent; Age Factors; Body Mass Index; Databases, Genetic; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomic Imprinting; Humans; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Neoplasms; Polymorphism, Single Nucleotide; Puberty; Quantitative Trait Loci; Ribonucleoproteins; Risk Factors

Guidelines of the Italian Society of Videosurgery in Infancy for the minimally invasive treatment of the esophageal atresia. - Chiarenza, Salvatore Fabio; Conighi, Maria Luisa; Conforti, Andrea; Esposito, Ciro; Escolino, Maria; Beretta, Fabio; Cheli, Maurizio; Di Benedetto, Vincenzo; Scuderi, Maria Grazia; Casadio, Giovanni; Marzaro, Maurizio; Fascetti, Leon Francesco; et al. (Pediatr Med Chir, 2017)
Not available.
Keywords: Esophageal Atresia; Humans; Infant; Minimally Invasive Surgical Procedures; Video-Assisted Surgery

Guidelines of the Italian Society of Videosurgery in Infancy for the minimally invasive treatment of the ureteropelvic-junction obstruction. - Chiarenza, Salvatore Fabio; Bleve, Cosimo; Esposito, Ciro; Escolino, Maria; Beretta, Fabio; Cheli, Maurizio; Di Benedetto, Vincenzo; Scuderi, Maria Grazia; Casadio, Giovanni; Marzaro, Maurizio; Fascetti, Leon Francesco; Bagolan, Pietro; et al. (Pediatr Med Chir, 2017)
Not available.
Keywords: Humans; Infant; Kidney Pelvis; Minimally Invasive Surgical Procedures; Ureteral Obstruction; Video-Assisted Surgery

How to monitor pregnancies complicated by fetal growth restriction and delivery before 32 weeks: post-hoc analysis of TRUFFLE study. - Ganzevoort, W; Mensing Van Charante, N; Thilaganathan, B; Prefumo, F; Arabin, B; Bilardo, C M; Brezinka, C; Derks, J B; Diemert, A; Duvekot, J J; Ferrazzi, E; Frusca, T; et al. (Ultrasound Obstet Gynecol, 2017)
OBJECTIVES: In the recent TRUFFLE study, it appeared that, in pregnancies complicated by fetal growth restriction (FGR) between 26 and 32 weeks' gestation, monitoring of the fetal ductus venosus (DV) waveform combined with computed cardiotocography (CTG) to determine timing of delivery increased the chance of infant survival without neurological impairment. However, concerns with the interpretation were raised, as DV monitoring appeared to be associated with a non-significant increase in fetal death, and some infants were delivered after 32 weeks, at which time the study protocol no longer applied. This secondary sensitivity analysis of the TRUFFLE study focuses on women who delivered before 32 completed weeks' gestation and analyzes in detail the cases of fetal death. METHODS: Monitoring data of 317 pregnancies with FGR that delivered before 32 weeks were analyzed, excluding those with absent outcome data or inevitable perinatal death. Women were allocated randomly to one of three groups of indication for delivery according to the following monitoring strategies: (1) reduced fetal heart rate short-term variation (STV) on CTG; (2) early changes in fetal DV waveform; and (3) late changes in fetal DV waveform. Primary outcome was 2-year survival without neurological impairment. The association of the last monitoring data before delivery and infant outcome was assessed by multivariable analysis. RESULTS: Two-year survival without neurological impairment occurred more often in the two DV groups (both 83%) than in the CTG-STV group (77%), however, the difference was not statistically significant (P = 0.21). Among the surviving infants in the DV groups, 93% were free of neurological impairment vs 85% of surviving infants in the CTG-STV group (P = 0.049). All fetal deaths (n = 7) occurred in the groups with DV monitoring. Of the monitoring parameters obtained shortly before fetal death in these seven cases, an abnormal CTG was observed in only one case. Multivariable regression analysis of factors at study entry demonstrated that a later gestational age, higher estimated fetal weight-to-50 percentile ratio and lower umbilical artery pulsatility index (PI)/fetal middle cerebral artery-PI ratio were significantly associated with normal outcome. Allocation to DV monitoring had a smaller effect on outcome, but remained in the model (P < 0.1). Abnormal fetal arterial Doppler before delivery was significantly associated with adverse outcome in the CTG-STV group. In contrast, abnormal DV flow was the only monitoring parameter associated with adverse outcome in the DV groups, while fetal arterial Doppler, STV below the cut-off used in the CTG-STV group and recurrent decelerations in fetal heart rate were not. CONCLUSIONS: In accordance with the findings of the TRUFFLE study on monitoring and intervention management of very preterm FGR, we found that the proportion of infants surviving without neuroimpairment was not significantly different when the decision for delivery was based on changes in DV waveform vs reduced STV on CTG. The uneven distribution of fetal deaths towards the DV groups was probably a chance effect, and neurological outcome was better among surviving children in these groups. Before 32 weeks, delaying delivery until abnormalities in DV-PI or STV and/or recurrent decelerations in fetal heat rate occur, as defined by the study protocol, is likely to be safe and possibly benefits long-term outcome. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Adult; Cardiotocography; Central Nervous System Diseases; Child, Preschool; Female; Fetal Growth Retardation; Fetal Membranes, Premature Rupture; Gestational Age; Heart Rate, Fetal; Humans; Infant; Infant, Extremely Premature; Male; Middle Cerebral Artery; Pregnancy; Pulsatile Flow; Survival Analysis; Treatment Outcome; Ultrasonography, Prenatal; Uterine Artery

Impaired fasting glucose and impaired glucose tolerance in children and adolescents with overweight/obesity. - Di Bonito, P; Pacifico, L; Chiesa, C; Valerio, G; Miraglia Del Giudice, E; Maffeis, C; Morandi, A; Invitti, C; Licenziati, M R; Loche, S; Tornese, G; Franco, F; et al. (J Endocrinol Invest, 2017)
OBJECTIVE: To investigate in a large sample of overweight/obese (OW/OB) children and adolescents the prevalence of prediabetic phenotypes such as impaired fasting glucose (IFG) and impaired glucose tolerance (IGT), and to assess their association with cardiometabolic risk (CMR) factors including hepatic steatosis (HS). METHODS: Population data were obtained from the CARdiometabolic risk factors in children and adolescents in ITALY study. Between 2003 and 2013, 3088 youths (972 children and 2116 adolescents) received oral glucose tolerance test (OGTT) and were included in the study. In 798 individuals, abdominal ultrasound for identification of HS was available. RESULTS: The prevalence of IFG (3.2 vs. 3.3%) and IGT (4.6 vs. 5.0%) was similar between children and adolescents. Children with isolated IGT had a 2-11 fold increased risk of high LDL-C, non-HDL-C, Tg/HDL-C ratio, and low insulin sensitivity, when compared to those with normal glucose tolerance (NGT). No significant association of IFG with any CMR factor was found in children. Among adolescents, IGT subjects, and to a lesser extent those with IFG, showed a worse CMR profile compared to NGT subgroup. In the overall sample, IGT phenotype showed a twofold increased risk of HS compared to NGT subgroup. CONCLUSIONS: Our study shows an unexpected similar prevalence of IFG and IGT between children and adolescents with overweight/obesity. The IGT phenotype was associated with a worse CMR profile in both children and adolescents. Phenotyping prediabetes conditions by OGTT should be done as part of prediction and prevention of cardiometabolic diseases in OW/OB youth since early childhood.
Keywords: Adolescent; Blood Glucose; Case-Control Studies; Child; Fasting; Female; Glucose Intolerance; Glucose Tolerance Test; Humans; Insulin; Insulin Resistance; Italy; Male; Obesity; Overweight; Prediabetic State; Prevalence

Imported arboviral infections in Italy, July 2014-October 2015: a National Reference Laboratory report. - Fortuna, Claudia; Remoli, Maria Elena; Rizzo, Caterina; Benedetti, Eleonora; Fiorentini, Cristiano; Bella, Antonino; Argentini, Claudio; Farchi, Francesca; Castilletti, Concetta; Capobianchi, Maria Rosaria; Zammarchi, Lorenzo; Bartoloni, Alessandro; et al. (BMC Infect Dis, 2017)
BACKGROUND: Imported cases of infections due to Dengue (DENV) and Chikungunya (CHIKV) viruses and, more recently, Zika virus (ZIKV) are commonly reported among travelers returning from endemic regions. In areas where potentially competent vectors are present, the risk of autochthonous transmission of these vector-borne pathogens is relatively high. Laboratory surveillance is crucial to rapidly detect imported cases in order to reduce the risk of transmission. This study describes the laboratory activity performed by the National Reference Laboratory for Arboviruses (NRLA) at the Italian National Institute of Health in the period from July 2014 to October 2015. METHODS: Samples from 180 patients visited/hospitalized with a suspected DENV/CHIKV/ZIKV infection were sent to the NRLA from several Italian Hospitals and from Regional Reference Laboratories for Arboviruses, in agreement with the National Plan on human surveillance of vector-borne diseases. Both serological (ELISA IgM test and Plaque Reduction Neutralization Test-PRNT) and molecular assays (Real Time PCR tests, RT-PCR plus nested PCR and sequencing of positive samples) were performed. RESULTS: DENV infection was the most frequently diagnosed (80 confirmed/probable cases), and all four genotypes were detected. However, an increase in imported CHIKV cases (41 confirmed/probable cases) was observed, along with the detection of the first ZIKV cases (4 confirmed cases), as a consequence of the recent spread of both CHIKV and ZIKV in the Americas. CONCLUSIONS: Main diagnostic issues highlighted in our study are sensitivity limitations of molecular tests, and the importance of PRNT to confirm serological results for differential diagnosis of Arboviruses. The continuous evaluation of diagnostic strategy, and the implementation of laboratories networks involved in surveillance activities is essential to ensure correct diagnosis, and to improve the preparedness for a rapid and proper identification of viral threats.
Keywords: Chikungunya Fever; Chikungunya virus; Dengue; Dengue Virus; Disease Outbreaks; Female; Genotype; Humans; Italy; Male; Molecular Diagnostic Techniques; Population Surveillance; Public Health; Travel; Young Adult; Zika Virus; Zika Virus Infection

Influence of vaginal lactoferrin administration on amniotic fluid cytokines and its role against inflammatory complications of pregnancy. - Maritati, Martina; Comar, Manola; Zanotta, Nunzia; Seraceni, Silva; Trentini, Alessandro; Corazza, Fabrizio; Vesce, Fortunato; Contini, Carlo (J Inflamm (Lond), 2017)
BACKGROUND: An altered amniotic cytokine profile has been reported in inflammatory pregnancy complications with a leading role for IL-6, a marker of the foetal systemic inflammatory response. Up to this date there is no exhaustive information neither on the foetal cytokine balance nor on the best method for its modulation. We aimed to evaluate the influence of vaginal lactoferrin administration on amniotic fluid concentration of 47 cytokines, chemokines and growth factors. METHODS: Sixty women undergoing genetic amniocentesis were enrolled in an open-label clinical trial. 300 mg of vaginal lactoferrin (Florence, Italy) were randomly administered to obtain 3 groups: A, 20 untreated patients; B and C (20 patients in each) respectively treated 4 and 12 h before amniocentesis. Cytokines, chemokines and growth factors concentrations were quantified by a magnetic bead Luminex multiplex immunoassays panel technology. Data analysis was performed with the software Stata (v. 13.1) and GraphPad Prism (v. 5). Group comparisons were performed using Kruskal-Wallis followed by Mann-Whitney U tests, with Bonferroni correction for multiple comparisons. A  < 0.05 was considered significant. RESULTS: Among the 47 tested mediators, 24 (51.06%) were influenced by lactoferrin. 11 (23.4%), showed a highly significant difference (p <0.001); among these IL-9, IL-15, IFN-γ, IP-10, TNF-α, IL-1α and MCP-3 underwent a down-regulation, while IL-17 and FGF-basic, G-CSF, GM-CSF an up-regulation. Difference between group C and both B and A was small for IL-15, IP-10, IL-1α, MCP-3, while it was negligible for IL-9, IFN-γ and TNF-α. IL-17 and the 3 growth factors were strongly enhanced in B and C groups. IL-17, FGF-basic and GM-CSF showed increasing concentrations in both B and C groups, while G-CSF resulted up-regulated only in group C. Significance was intermediate ( < 0.01) for the down regulated IL-2RA, IL-12p40 and IFNα2 (6.38%) while it was small for 10 mediators (21.27%) 7 of which (IL-2, IL-4, eotaxin, PDGF-BB, RANTES, IL-18 and MIF) down-regulated and 3 (MCP-1, IL-3, and SDF-1α) up-regulated. CONCLUSION: Lactoferrin down-regulates 17 pro-inflammatory amniotic mediators while up-regulating 7 anti-inflammatory amniotic mediators, 5 of which definitively belonging to an anti-inflammatory profile. These findings open to clinical investigation on its use against inflammatory complications of pregnancy.

Intra-articular corticosteroids versus intra-articular corticosteroids plus methotrexate in oligoarticular juvenile idiopathic arthritis: a multicentre, prospective, randomised, open-label trial. - Ravelli, Angelo; Davì, Sergio; Bracciolini, Giulia; Pistorio, Angela; Consolaro, Alessandro; van Dijkhuizen, Evert Hendrik Pieter; Lattanzi, Bianca; Filocamo, Giovanni; Verazza, Sara; Gerloni, Valeria; Gattinara, Maurizio; Pontikaki, Irene; et al. (Lancet, 2017)
BACKGROUND: Little evidence-based information is available to guide the treatment of oligoarticular juvenile idiopathic arthritis. We aimed to investigate whether oral methotrexate increases the efficacy of intra-articular corticosteroid therapy. METHODS: We did this prospective, open-label, randomised trial at ten hospitals in Italy. Using a concealed computer-generated list, children younger than 18 years with oligoarticular-onset disease were randomly assigned (1:1) to intra-articular corticosteroids alone or in combination with oral methotrexate (15 mg/m; maximum 20 mg). Corticosteroids used were triamcinolone hexacetonide (shoulder, elbow, wrist, knee, and tibiotalar joints) or methylprednisolone acetate (ie, subtalar and tarsal joints). We did not mask patients or investigators to treatment assignments. Our primary outcome was the proportion of patients in the intention-to-treat population who had remission of arthritis in all injected joints at 12 months. This trial is registered with European Union Clinical Trials Register, EudraCT number 2008-006741-70. FINDINGS: Between July 7, 2009, and March 31, 2013, we screened 226 participants and randomly assigned 102 to intra-articular corticosteroids alone and 105 to intra-articular corticosteroids plus methotrexate. 33 (32%) patients assigned to intra-articular corticosteroids alone and 39 (37%) assigned to intra-articular corticosteroids and methotrexate therapy had remission of arthritis in all injected joints (p=0·48). Adverse events were recorded for 20 (17%) patients who received methotrexate, which led to permanent treatment discontinuation in two patients (one due to increased liver transaminases and one due to gastrointestinal discomfort). No patient had a serious adverse event. INTERPRETATION: Concomitant administration of methotrexate did not augment the effectiveness of intra-articular corticosteroid therapy. Future studies are needed to define the optimal therapeutic strategies for oligoarticular juvenile idiopathic arthritis. FUNDING: Italian Agency of Drug Evaluation.
Keywords: Adrenal Cortex Hormones; Arthritis, Juvenile; Humans; Injections, Intra-Articular; Italy; Methotrexate; Prospective Studies; Treatment Outcome

Longitudinal study of computerized cardiotocography in early fetal growth restriction. - Wolf, H; Arabin, B; Lees, C C; Oepkes, D; Prefumo, F; Thilaganathan, B; Todros, T; Visser, G H A; Bilardo, C M; Derks, J B; Diemert, A; Duvekot, J J; et al. (Ultrasound Obstet Gynecol, 2017)
OBJECTIVES: To explore whether, in early fetal growth restriction (FGR), the longitudinal pattern of fetal heart rate (FHR) short-term variation (STV) can be used to identify imminent fetal distress and whether abnormalities of FHR recordings are associated with 2-year infant outcome. METHODS: The original TRUFFLE study assessed whether, in early FGR, delivery based on ductus venosus (DV) Doppler pulsatility index (PI), in combination with safety-net criteria of very low STV on cardiotocography (CTG) and/or recurrent FHR decelerations, could improve 2-year infant survival without neurological impairment in comparison with delivery based on CTG monitoring only. This was a secondary analysis of women who delivered before 32 weeks and had consecutive STV data recorded > 3 days before delivery and known infant outcome at 2 years of age. Women who received corticosteroids within 3 days of delivery were excluded. Individual regression line algorithms of all STV values, except the last one before delivery, were calculated. Life tables and Cox regression analysis were used to calculate the daily risk for low STV or very low STV and/or FHR decelerations (below DV group safety-net criteria) and to assess which parameters were associated with this risk. Furthermore, it was assessed whether STV pattern, last STV value or recurrent FHR decelerations were associated with 2-year infant outcome. RESULTS: One hundred and forty-nine women from the original TRUFFLE study met the inclusion criteria. Using the individual STV regression lines, prediction of a last STV below the cut-off used by the CTG monitoring group had sensitivity of 42% and specificity of 91%. For each day after study inclusion, the median risk for low STV (CTG group cut-off) was 4% (interquartile range (IQR), 2-7%) and for very low STV and/or recurrent FHR decelerations (below DV group safety-net criteria) was 5% (IQR, 4-7%). Measures of STV pattern, fetal Doppler (arterial or venous), birth-weight multiples of the median and gestational age did not usefully improve daily risk prediction. There was no association of STV regression coefficients, a low last STV and/or recurrent FHR decelerations with short- or long-term infant outcomes. CONCLUSION: The TRUFFLE study showed that a strategy of DV monitoring with safety-net criteria of very low STV and/or recurrent FHR decelerations for delivery indication could increase 2-year infant survival without neurological impairment. This post-hoc analysis demonstrates that, in early FGR, the daily risk of abnormal CTG, as defined by the DV group safety-net criteria, is 5%, and that prediction is not possible. This supports the rationale for CTG monitoring more often than daily in these high-risk fetuses. Low STV and/or recurrent FHR decelerations were not associated with adverse infant outcome and it appears safe to delay intervention until such abnormalities occur, as long as DV-PI is within normal range. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Adult; Cardiotocography; Child, Preschool; Female; Fetal Growth Retardation; Fetal Heart; Heart Rate, Fetal; Humans; Infant; Infant, Newborn; Longitudinal Studies; Middle Cerebral Artery; Pregnancy; Pregnancy Outcome; Pulsatile Flow; Survival Analysis; Ultrasonography, Prenatal

Long-Term Survival After Hematopoietic Stem Cell Transplantation for Complete STAT1 Deficiency. - Naviglio, Samuele; Soncini, Elena; Vairo, Donatella; Lanfranchi, Arnalda; Badolato, Raffaele; Porta, Fulvio (J Clin Immunol, 2017)
PURPOSE: Complete signal transducer and activator of transcription 1 (STAT1) deficiency is a rare autosomal recessive condition characterized by impairment of intracellular signaling from both type I and type II interferons (IFN). Affected patients are prone to early severe mycobacterial and viral infections, which usually result in death before 18 months of age. We previously reported a patient affected by complete STAT1 deficiency who underwent hematopoietic stem cell transplantation (HSCT). Here, we describe the transplantation procedures and long-term outcomes. METHODS: The patient, who had suffered multiple life-threatening mycobacterial and viral infections in the first years of life, underwent HSCT at 4 years of age from a partially matched (HLA compatibility 8/10) unrelated donor after a myeloablative conditioning regimen consisting of busulfan, cyclophosphamide, and anti-thymocyte globulin. RESULTS: Hematological reconstitution was detected at d+15, with full donor engraftment demonstrated by molecular analysis of leukocytes. Several complications occurred in the post-transplantation phase, including acute graft versus host disease, posterior reversible encephalopathy, thrombotic thrombocytopenic purpura, bilateral keratoconjunctivitis with complete loss of vision, and chronic lower limb lymphedema. Analysis of STAT1 in CD3 cells at 90 and 120 days after HSCT by flow cytometry showed normal STAT1 phosphorylation levels in response to IFN-α. CONCLUSIONS: Notably, no severe infections occurred after discharge (day + 90) during a 9-year follow-up, suggesting that normal response to IFNs in hematopoietic cells is sufficient to provide protection in humans.
Keywords: Child, Preschool; Hematopoietic Stem Cell Transplantation; Humans; Immunologic Deficiency Syndromes; Male; STAT1 Transcription Factor; Treatment Outcome

Mental Health Problems in Children and Adolescents in the Emergency Department: "The Times They Are A-Changin'". - Cozzi, Giorgio; Minute, Marta; Ventura, Giovanna; Barbi, Egidio (Pediatr Emerg Care, 2017)
Keywords: Adolescent; Child; Emergency Service, Hospital; Humans; Mental Disorders; Mental Health Services; Patient Admission

Metastatic neuroblastoma in infants: are survival rates excellent only within the stringent framework of clinical trials? - Di Cataldo, A; Agodi, A; Balaguer, J; Garaventa, A; Barchitta, M; Segura, V; Bianchi, M; Castel, V; Castellano, A; Cesaro, S; Couselo, J M; Cruz, O; et al. (Clin Transl Oncol, 2017)
INTRODUCTION: SIOPEN INES protocol yielded excellent 5-year survival rates for MYCN-non-amplified metastatic neuroblastoma. Patients deemed ineligible due to lack or delay of MYCN status or late registration were treated, but not included in the study. Our goal was to analyse survival at 10 years among the whole population. MATERIALS AND METHODS: Italian and Spanish metastatic INES patients' data are reported. SPSS 20.0 was used for statistical analysis. RESULTS: Among 98 infants, 27 had events and 19 died, while 79 were disease free. Five- and 10-year event-free survival (EFS) were 73 and 70 %, and overall survival (OS) was 81 and 74 %, respectively. MYCN status was significant for EFS, but not for OS in multivariate analysis. CONCLUSIONS: The survival rates of patients who complied with all the inclusion criteria for INES trials are higher compared to those that included also not registered patients. Five-year EFS and OS for INES 99.2 were 87.8 and 95.7 %, while our stage 4s population obtained 78 and 87 %. Concerning 99.3, 5-year EFS and OS were 86.7 and 95.6 %, while for stage 4 we registered 61 and 68 %. MYCN amplification had a strong impact on prognosis and therefore we consider it unacceptable that many patients were not studied for MYCN and probably inadequately treated. Ten-year survival rates were shown to decrease: EFS from 73 to 70 % and OS from 81 to 74 %, indicating a risk of late events, particularly in stage 4s. Population-based registries like European ENCCA WP 11-task 11 will possibly clarify these data.
Keywords: Biomarkers, Tumor; Child; Child, Preschool; Clinical Trials as Topic; Combined Modality Therapy; Female; Follow-Up Studies; Gene Amplification; Humans; Infant; Infant, Newborn; Male; N-Myc Proto-Oncogene Protein; Neoplasm Staging; Neuroblastoma; Prognosis; Survival Rate

Multicentric Case-Control Study on Azathioprine Dose and Pharmacokinetics in Early-onset Pediatric Inflammatory Bowel Disease. - Stocco, Gabriele; Martelossi, Stefano; Arrigo, Serena; Barabino, Arrigo; Aloi, Marina; Martinelli, Massimo; Miele, Erasmo; Knafelz, Daniela; Romano, Claudio; Naviglio, Samuele; Favretto, Diego; Cuzzoni, Eva; et al. (Inflamm Bowel Dis, 2017)
BACKGROUND: Early-onset inflammatory bowel disease (IBD) is generally aggressive, with a high probability of complications and need of surgery. Despite the introduction of highly effective biological drugs, treatment with azathioprine continues to be important even for early-onset IBD; however, in these patients azathioprine response seems to be reduced. This study evaluated azathioprine doses, metabolite concentrations, and their associations with patients' age in children with IBD treated at 6 tertiary pediatric referral centers. METHODS: Azathioprine doses, metabolites, and clinical effects were assessed after at least 3 months of therapy in 17 early-onset (age < 6 yr, cases) and 51 nonearly-onset (aged > 12 and <18 yrs, controls) patients with IBD. Azathioprine dose was titrated on therapeutic efficacy (response and adverse effects). Azathioprine metabolites and thiopurine methyltransferase activity were determined by high-performance liquid chromatography with ultra violet-vis detection (HPLC-UV) methods. RESULTS: Frequency of patients in remission was similar among early-onset and control groups, respectively (82% and 84%, P value = 0.72). Early-onset patients required higher doses of azathioprine (median 2.7 versus 2.0 mg·kg·d, P value = 1.1 × 10). Different doses resulted in comparable azathioprine active thioguanine nucleotide metabolite concentrations (median 263 versus 366 pmol/8 × 10 erythrocytes, P value = 0.41) and methylmercaptopurine nucleotide concentrations (median 1455 versus 1532 pmol/8 × 10 erythrocytes, P value = 0.60). Lower ratios between thioguanine nucleotide metabolites and azathioprine doses were found in early-onset patients (median 98 versus 184 pmol/8 × 10 erythrocytes·mg·kg·d, P value = 0.017). Interestingly, early-onset patients presented also higher thiopurine methyltransferase activity (median 476 versus 350 nmol methylmercaptopurine/mg hemoglobin/h, P-value = 0.046). CONCLUSIONS: This study demonstrated that patients with early-onset IBD present increased inactivating azathioprine metabolism, likely because of elevated activity of the enzyme thiopurine methyltransferase.
Keywords: Adolescent; Age of Onset; Antimetabolites; Azathioprine; Case-Control Studies; Child; Child, Preschool; Chromatography, High Pressure Liquid; Dose-Response Relationship, Drug; Erythrocytes; Female; Guanine Nucleotides; Humans; Inflammatory Bowel Diseases; Male; Mercaptopurine; Methyltransferases; Thioguanine

Novel Blood Pressure Locus and Gene Discovery Using Genome-Wide Association Study and Expression Data Sets From Blood and the Kidney. - Wain, Louise V; Vaez, Ahmad; Jansen, Rick; Joehanes, Roby; van der Most, Peter J; Erzurumluoglu, A Mesut; O'Reilly, Paul F; Cabrera, Claudia P; Warren, Helen R; Rose, Lynda M; Verwoert, Germaine C; Hottenga, Jouke-Jan; et al. (Hypertension, 2017)
Elevated blood pressure is a major risk factor for cardiovascular disease and has a substantial genetic contribution. Genetic variation influencing blood pressure has the potential to identify new pharmacological targets for the treatment of hypertension. To discover additional novel blood pressure loci, we used 1000 Genomes Project-based imputation in 150 134 European ancestry individuals and sought significant evidence for independent replication in a further 228 245 individuals. We report 6 new signals of association in or near , , , , , and , and provide new replication evidence for a further 2 signals in and Combining large whole-blood gene expression resources totaling 12 607 individuals, we investigated all novel and previously reported signals and identified 48 genes with evidence for involvement in blood pressure regulation that are significant in multiple resources. Three novel kidney-specific signals were also detected. These robustly implicated genes may provide new leads for therapeutic innovation.

Ocular Involvement in Children with Inflammatory Bowel Disease. - Naviglio, Samuele; Parentin, Fulvio; Nider, Silvia; Rassu, Nicolò; Martelossi, Stefano; Ventura, Alessandro (Inflamm Bowel Dis, 2017)
BACKGROUND: Data on ocular manifestations of inflammatory bowel disease (IBD) in children are limited. Some authors have reported a high prevalence of asymptomatic uveitis, yet the significance of these observations is unknown and there are no recommendations on which ophthalmologic follow-up should be offered. METHODS: Children with IBD seen at a single referral center for pediatric gastroenterology were offered ophthalmologic evaluation as part of routine care for their disease. Ophthalmologic evaluation included review of ocular history as well as slit-lamp and fundoscopic examination. Medical records were also reviewed for previous ophthalmologic diagnoses or complaints. RESULTS: Data from 94 children were included (52 boys; median age 13.4 yr). Forty-six patients had a diagnosis of Crohn's disease, 46 ulcerative colitis, and 2 IBD unclassified. Intestinal disease was in clinical remission in 70% of the patients; fecal calprotectin was elevated in 64%. One patient with Crohn's disease had a previous diagnosis of clinically manifest uveitis (overall uveitis prevalence: 1.06%; incidence rate: 0.3 per 100 patient-years). This patient was also the only one who was found to have asymptomatic uveitis at slit-lamp examination. A second patient had posterior subcapsular cataract associated with corticosteroid treatment. No signs of intraocular complications from previous unrecognized uveitis were observed in any patient. CONCLUSIONS: Children with IBD may have asymptomatic uveitis, yet its prevalence seems lower than previously reported, and it was not found in children without a previous diagnosis of clinically manifest uveitis. No ocular complications from prior unrecognized uveitis were observed.
Keywords: Adolescent; Child; Child, Preschool; Feces; Female; Humans; Inflammatory Bowel Diseases; Italy; Leukocyte L1 Antigen Complex; Male; Remission Induction; Uveitis

Outcome of childhood-onset full-house nephropathy. - Ruggiero, Barbara; Vivarelli, Marina; Gianviti, Alessandra; Pecoraro, Carmine; Peruzzi, Licia; Benetti, Elisa; Ventura, Giovanna; Pennesi, Marco; Murer, Luisa; Coppo, Rosanna; Emma, Francesco (Nephrol Dial Transplant, 2017)
Background: Patients with full-house nephropathy (FHN) present renal lesions that are indistinguishable from those of lupus nephritis (LN) but lack the systemic features necessary to meet diagnostic criteria for systemic lupus erithematosus (SLE). Some have been reported to develop a delayed SLE with time. The clinical outcome of children having FHN without SLE has never been reported. Methods: Children with biopsy-proven FHN were selected after excluding SLE cases by the absence of America College of Rheumatology criteria. The proportion of patients with complete (proteinuria <0.5 g/day) or partial remission (proteinuria ≤50% from baseline), relapse (estimated glomerular filtration rate <25% and/or proteinuria ≥50% from baseline) and progression to Stage III chronic kidney disease (CKD) was described according to age and gender groups with the Kaplan-Meier curve and compared with the Log-rank test. Entity of treatment was summarized by a score at induction (0-6 months) and maintenance (6-18 months). Cox-regression model was performed to test predictors of remission, relapse and progression to CKD. Results: Among 42 patients (28 pre-pubertal) who met the inclusion criteria, 39 (92.9%) achieved partial and 32 (76.2%) complete remission of nephropathy over 2.78 and 7.51 months of follow-up. At 10 years, the probability of progressing to CKD was 4.8%. Of those achieving remission, 18% had a renal flare mainly within 4 years after remission. Pre-pubertal males achieved complete remission more frequently than other patients but often relapsed; pre-pubertal females were treated more aggressively. Cox-regression analysis did not find independent predictors of remission or relapse. Conclusions: The outcome of the patients with FHN we investigated was encouraging. Recurrences are limited to the first 4 years following diagnosis, allowing progressive withdrawal of immunosuppression in patients achieving remission. Evaluation of risk factors for adverse outcome is necessary especially in pre-pubertal children.
Keywords: Adolescent; Age of Onset; Child; Disease Progression; Female; Glomerular Filtration Rate; Glomerulonephritis; Humans; Kidney Diseases; Lupus Erythematosus, Systemic; Lupus Nephritis; Male; Proteinuria; Recurrence; Remission Induction; Retrospective Studies; Risk Factors; Survival Rate

Pediatric Ovarian Torsion and its Recurrence: A Multicenter Study. - Bertozzi, Mirko; Esposito, Ciro; Vella, Claudio; Briganti, Vito; Zampieri, Nicola; Codrich, Daniela; Ubertazzi, Michele; Trucchi, Alessandro; Magrini, Elisa; Battaglia, Sonia; Bini, Vittorio; Conighi, Maria Luisa; et al. (J Pediatr Adolesc Gynecol, 2017)
STUDY OBJECTIVE: To report results of a retrospective multicentric Italian survey concerning the management of pediatric ovarian torsion (OT) and its recurrence. DESIGN: Multicenter retrospective cohort study. SETTING: Italian Units of Pediatric Surgery. PARTICIPANTS: Participants were female aged 1-14 years of age with surgically diagnosed OT between 2004 and 2014. INTERVENTIONS: Adnexal detorsion, adnexectomy, mass excision using laparoscopy or laparotomy. Different kinds of oophoropexy (OPY) for OT or recurrence, respectively. MAIN OUTCOME MEASURES: A total of 124 questionnaires were returned and analyzed to understand the current management of pediatric OT and its recurrence. The questionnaires concerned patient age, presence of menarche, OT site, presence and type of mass, performed procedure, OPY technique adopted, intra- and postoperative complications, recurrence and site, procedure performed for recurrence, OPY technique for recurrence, and 1 year follow-up of detorsed ovaries. RESULTS: Mean age at surgery was 9.79 ± 3.54 years. Performed procedures were open adnexectomy (52 of 125; 41.6%), laparoscopic adnexectomy (25 of 125; 20%), open detorsion (10 of 125; 8%), and laparoscopic detorsion (38 of 125; 30.4%). Recurrence occurred in 15 of 125 cases (12%) and resulted as significant (P = .012) if associated with a normal ovary at the first episode of torsion. Recurrence occurred only in 1 of 19 cases after OPY (5.2%). Ultrasonographic results of detorsed ovaries were not significant whether an OPY was performed or not (P = 1.00). CONCLUSION: Unfortunately, oophorectomy and open technique are still widely adopted even if not advised. Recurrence is not rare and the risk is greater in patients without ovarian masses. OPY does not adversely affect ultrasonographic results at 1 year. When possible OPY should be performed at the first episode of OT.
Keywords: Adolescent; Child; Child, Preschool; Cohort Studies; Female; Humans; Infant; Italy; Laparoscopy; Laparotomy; Menarche; Ovarian Diseases; Ovariectomy; Postoperative Complications; Recurrence; Retrospective Studies; Surveys and Questionnaires; Torsion Abnormality

Polymorphisms in key bone modulator cytokines genes influence bisphosphonates therapy in postmenopausal women. - Lima, C A D; Javorski, N R; Souza, A P O; Barbosa, A D; Valença, A P M C; Crovella, S; Souza, P R E; de Azevêdo Silva, J; Sandrin-Garcia, P (Inflammopharmacology, 2017)
Osteoporosis is a multifactorial and debilitating disease resulting from decreased bone mineral density (BMD) and loss of tissue microarchitecture. Ineffective therapies may lead to bone fractures and subsequent death. Single nucleotide polymorphisms (SNPs) in key immune regulator genes have been associated with therapeutic response to bisphosphonates, which are the first therapeutic line of choice for osteoporosis. However, cytokine pathways and their relation with therapeutic adhesion remain to be fully elucidated. Aimed at better understanding these processes, we investigated the response to bisphosphonate therapy in postmenopausal women and four SNPs in key proinflammatory cytokines genes: IL23R +2284 (C>A) (rs10889677), IL17A +672 (G>A) (rs7747909), IL12B +1188 (T>G) (rs3212227) and INF-γ -1616 (G>A) (rs2069705). A total of 69 patients treated with bisphosphonate were followed for a period of 1 up to 4 years, genotyped and compared according to their changes in bone mineral density (BMD) and level of biochemical markers during their treatment. The INF-γ -1616 G/G associated with increased BMD values in femoral neck (GG/AA, p = 0.016) and decreased BMD values in total hip (GG/GA, p = 0.019; GG/AA, p = 0.011). In relation to biochemical markers, INF-γ -1616 SNP associated with increased alkaline phosphatase (GG/AA; p < 0.0001) and parathyroid hormone levels (AA/GA; p = 0.017). Vitamin D values changes were related to IL17A +672 (GG/GA, p = 0.034) and to IL12B +1188 (TT/TG, p = 0.046) SNPs. Besides, significant differences in changes of calcium levels correlated with IL23R +2284 (CC/CA, p = 0.016) genotypes. Altogether, we suggest that these polymorphisms may play an important role for therapeutic decisions in osteoporosis treatment.
Keywords: Aged; Bone Density; Bone Remodeling; Cytokines; Diphosphonates; Female; Humans; Middle Aged; Osteoporosis, Postmenopausal; Polymorphism, Single Nucleotide; Postmenopause

Pregnant with HIV before age 25: data from a large national study in Italy, 2001-2016. - Floridia, M; Masuelli, G; Tamburrini, E; Cetin, I; Liuzzi, G; Martinelli, P; Guaraldi, G; Spinillo, A; Vimercati, A; Maso, G; Pinnetti, C; Frisina, V; et al. (Epidemiol Infect, 2017)
Young pregnant women with HIV may be at significant risk of unplanned pregnancy, lower treatment coverage, and other adverse pregnancy outcomes. In a large cohort of pregnant women with HIV in Italy, among 2979 pregnancies followed in 2001-2016, 9·0% were in women <25 years, with a significant increase over time (2001-2005: 7·0%; 2006-2010: 9·1%; 2011-2016: 12·2%, P < 0·001). Younger women had a lower rate of planned pregnancy (23·2% vs. 37·7%, odds ratio (OR) 0·50, 95% confidence interval (CI) 0·36-0·69), were more frequently diagnosed with HIV in pregnancy (46·5% vs. 20·9%, OR 3·29, 95% CI 2·54-4·25), and, if already diagnosed with HIV before pregnancy, were less frequently on antiretroviral treatment at conception (<25 years: 56·3%; ⩾25 years: 69·0%, OR 0·58, 95% CI 0·41-0·81). During pregnancy, treatment coverage was almost universal in both age groups (98·5% vs. 99·3%), with no differences in rate of HIV viral suppression at third trimester and adverse pregnancy outcomes. The data show that young women represent a growing proportion of pregnant women with HIV, and are significantly more likely to have unplanned pregnancy, undiagnosed HIV infection, and lower treatment coverage at conception. During pregnancy, antiretroviral treatment, HIV suppression, and pregnancy outcomes are similar compared with older women. Earlier intervention strategies may provide additional benefits in the quality of care for women with HIV.
Keywords: Adolescent; Cohort Studies; Female; HIV Infections; Humans; Italy; Odds Ratio; Pregnancy; Young Adult

A premenarcheal girl with urogenital bleeding. - Lora, Angela; Scrimin, Federica; Taddio, Andrea; Ventura, Alessandro; Barbi, Egidio (Arch Dis Child, 2017)

Presentation of acute suppurative parotitis in a newborn with incessant crying. - Velkoski, Angelika; Amoroso, Stefano; Brovedani, Pierpaolo; Cont, Gabriele; Trappan, Antonella; Travan, Laura (Arch Dis Child Fetal Neonatal Ed, 2017)
Keywords: Acute Disease; Anti-Bacterial Agents; Crying; Female; Humans; Infant, Newborn; Parotitis; Staphylococcal Infections; Staphylococcus aureus

Rare and low-frequency coding variants alter human adult height. - Marouli, Eirini; Graff, Mariaelisa; Medina-Gomez, Carolina; Lo, Ken Sin; Wood, Andrew R; Kjaer, Troels R; Fine, Rebecca S; Lu, Yingchang; Schurmann, Claudia; Highland, Heather M; Rüeger, Sina; Thorleifsson, Gudmar; et al. (Nature, 2017)
Height is a highly heritable, classic polygenic trait with approximately 700 common associated variants identified through genome-wide association studies so far. Here, we report 83 height-associated coding variants with lower minor-allele frequencies (in the range of 0.1-4.8%) and effects of up to 2 centimetres per allele (such as those in IHH, STC2, AR and CRISPLD2), greater than ten times the average effect of common variants. In functional follow-up studies, rare height-increasing alleles of STC2 (giving an increase of 1-2 centimetres per allele) compromised proteolytic inhibition of PAPP-A and increased cleavage of IGFBP-4 in vitro, resulting in higher bioavailability of insulin-like growth factors. These 83 height-associated variants overlap genes that are mutated in monogenic growth disorders and highlight new biological candidates (such as ADAMTS3, IL11RA and NOX4) and pathways (such as proteoglycan and glycosaminoglycan synthesis) involved in growth. Our results demonstrate that sufficiently large sample sizes can uncover rare and low-frequency variants of moderate-to-large effect associated with polygenic human phenotypes, and that these variants implicate relevant genes and pathways.
Keywords: ADAMTS Proteins; Adult; Alleles; Body Height; Cell Adhesion Molecules; Female; Gene Frequency; Genetic Variation; Genome, Human; Glycoproteins; Glycosaminoglycans; Hedgehog Proteins; Humans; Intercellular Signaling Peptides and Proteins; Interferon Regulatory Factors; Interleukin-11 Receptor alpha Subunit; Male; Multifactorial Inheritance; NADPH Oxidase 4; NADPH Oxidases; Phenotype; Pregnancy-Associated Plasma Protein-A; Procollagen N-Endopeptidase; Proteoglycans; Proteolysis; Receptors, Androgen; Somatomedins

Rate, correlates and outcomes of repeat pregnancy in HIV-infected women. - Floridia, M; Tamburrini, E; Masuelli, G; Martinelli, P; Spinillo, A; Liuzzi, G; Vimercati, A; Alberico, S; Maccabruni, A; Pinnetti, C; Frisina, V; Dalzero, S; et al. (HIV Med, 2017)
OBJECTIVES: The aim of the study was to assess the rate, determinants, and outcomes of repeat pregnancies in women with HIV infection. METHODS: Data from a national study of pregnant women with HIV infection were used. Main outcomes were preterm delivery, low birth weight, CD4 cell count and HIV plasma viral load. RESULTS: The rate of repeat pregnancy among 3007 women was 16.2%. Women with a repeat pregnancy were on average younger than those with a single pregnancy (median age 30 vs. 33 years, respectively), more recently diagnosed with HIV infection (median time since diagnosis 25 vs. 51 months, respectively), and more frequently of foreign origin [odds ratio (OR) 1.36; 95% confidence interval (CI) 1.10-1.68], diagnosed with HIV infection in the current pregnancy (OR: 1.69; 95% CI: 1.35-2.11), and at their first pregnancy (OR: 1.33; 95% CI: 1.06-1.66). In women with sequential pregnancies, compared with the first pregnancy, several outcomes showed a significant improvement in the second pregnancy, with a higher rate of antiretroviral treatment at conception (39.0 vs. 65.4%, respectively), better median maternal weight at the start of pregnancy (60 vs. 61 kg, respectively), a higher rate of end-of-pregnancy undetectable HIV RNA (60.7 vs. 71.6%, respectively), a higher median birth weight (2815 vs. 2885 g, respectively), lower rates of preterm delivery (23.0 vs. 17.7%, respectively) and of low birth weight (23.4 vs. 15.4%, respectively), and a higher median CD4 cell count (+47 cells/μL), with almost no clinical progression to Centers for Disease Control and Prevention stage C (CDC-C) HIV disease (0.3%). The second pregnancy was significantly more likely to end in voluntary termination than the first pregnancy (11.4 vs. 6.1%, respectively). CONCLUSIONS: Younger and foreign women were more likely to have a repeat pregnancy; in women with sequential pregnancies, the second pregnancy was characterized by a significant improvement in several outcomes, suggesting that women with HIV infection who desire multiple children may proceed safely and confidently with subsequent pregnancies.
Keywords: Adult; Anti-HIV Agents; CD4 Lymphocyte Count; Emigrants and Immigrants; Female; HIV Infections; HIV-1; Humans; Infant, Low Birth Weight; Pregnancy; Premature Birth; Viral Load

Safety and effectiveness of oral propranolol for infantile hemangiomas started before 5 weeks and after 5 months of age: an Italian multicenter experience. - El Hachem, Maya; Gesualdo, Francesco; Diociaiuti, Andrea; Berti, Irene; Vercellino, Nadia; Boccaletti, Valeria; Neri, Iria; Porcedda, Giulio; Greco, Antonella; Carnevale, Claudia; Oranges, Teresa; Cutrone, Mario; et al. (Ital J Pediatr, 2017)
BACKGROUND: Despite not being licensed for the treatment of infantile hemangiomas (IH) in infants younger than 5 weeks or older than 5 months, propranolol is often used in these age groups to prevent or to treat potentially severe complications. The objective of the present study was to review the experience of 8 Italian pediatric and dermatologic centers regarding propranolol treatment for IH started before 5 weeks or after 5 months of age. METHODS: We retrospectively reviewed the records of patients followed up for IH, on propranolol treatment started before 5 weeks or after 5 months of age, and collected information on sociodemographic data, treatment indications, IH involution, IH relapse, and treatment side effects. RESULTS: A total of 343 patients were enrolled; 15 were started on propranolol before 5 weeks (group 1), 328 were started after 5 months of age (group 2). The most frequent indications were permanent aesthetical disfigurement (91.8%) and function threatening complications (42.6%). In most cases, the treatment was effective. The involution was partial in 67.7% of patients. In 11.8% of cases a relapse was observed. No relapse was observed in group 1. Treatment complications were reported in 15.8% of children, most frequently sleep disorders (6.6%), followed by irritability (5.1%) and diarrhea (2.2%). Only a case of mild constipation was observed in group 1. CONCLUSION: The safety and effectiveness profile of propranolol in infants younger than 5 weeks or older than 5 months may be acceptable. Taking in account propranolol's potential in preventing severe complications, further studies should assess the acceptability of propranolol treatment, especially in the <5-week age group .
Keywords: Administration, Oral; Age Factors; Cohort Studies; Dose-Response Relationship, Drug; Drug Administration Schedule; Female; Hemangioma; Humans; Infant; Infant, Newborn; Italy; Male; Patient Safety; Propranolol; Retrospective Studies; Skin Neoplasms; Treatment Outcome

Somatic symptom disorder was common in children and adolescents attending an emergency department complaining of pain. - Cozzi, Giorgio; Minute, Marta; Skabar, Aldo; Pirrone, Angela; Jaber, Mohamad; Neri, Elena; Montico, Marcella; Ventura, Alessandro; Barbi, Egidio (Acta Paediatr, 2017)
AIM: The aim of this study was to quantify the prevalence of somatic pain in a paediatric emergency department (ED). METHODS: We conducted a prospective observational study using patients admitted to the ED of an Italian children's hospital between December 2014 and February 2015. We enrolled children aged 7-17 who turned up at the ED complaining of pain. Patients and parents were asked to fill in a questionnaire to allow the analysis of the patients' medical history and provide contact details for follow-up. We divided the enrolled patients into four groups: post-traumatic pain, organic pain, functional pain and somatic pain. The questionnaire was used to define pain characteristics and to generate an impairment score. RESULTS: Of the 713 patients who met inclusion criteria, 306 (42.9%) were enrolled in the study. Of these, 135 (44.0%) suffered from post-traumatic pain, 104 (34.0%) from organic pain, 41 (13.4%) from functional pain and 26 (8.6%) from somatic pain. Somatic pain patients had endured pain longer, had missed more school days and had suffered severe functional impairment. CONCLUSION: This study highlighted that somatic pain was a significant contributor to paediatric emergency room visits and should be suspected and diagnosed in children reporting pain.
Keywords: Adolescent; Child; Emergency Service, Hospital; Female; Humans; Italy; Male; Medically Unexplained Symptoms; Pain; Prospective Studies

SV40 Infection of Mesenchymal Stromal Cells From Wharton's Jelly Drives the Production of Inflammatory and Tumoral Mediators. - Cason, Carolina; Campisciano, Giuseppina; Zanotta, Nunzia; Valencic, Erica; Delbue, Serena; Bella, Ramona; Comar, Manola (J Cell Physiol, 2017)
The Mesenchymal Stromal Cells from umbilical cord Wharton's jelly (WJSCs) are a source of cells with high potentiality for the treatment of human immunological disorders. Footprints of the oncogenic viruses Simian Virus 40 (SV40) and JC Virus (JCPyV) have been recently detected in human WJSCs specimens. The aim of this study is to evaluate if WJSCs can be efficiently infected by these Polyomaviruses and if they can potentially exert tumoral activity. Cell culture experiments indicated that WJSCs could sustain both SV40 and JCPyV infections. A transient and lytic replication was observed for JCPyV, while SV40 persistently infected WJSCs over a long period of time, releasing a viral progeny at low titer without evident cytopathic effect (CPE). Considering the association between SV40 and human tumors and the reported ability of the oncogenic viruses to drive the host innate immune response to cell transformation, the expression profile of a large panel of immune mediators was evaluated in supernatants by the Bioplex platform. RANTES, IL-3, MIG, and IL-12p40, involved in chronic inflammation, cells differentiation, and transformation, were constantly measured at high concentration comparing to control. These findings represent a new aspect of SV40 biological activity in the humans, highlighting its interaction with specific host cellular pathways. In view of these results, it seems to be increasingly urgent to consider Polyomaviruses in the management of WJSCs for their safely use as promising therapeutic source. J. Cell. Physiol. 232: 3060-3066, 2017. © 2016 Wiley Periodicals, Inc.
Keywords: Cell Line, Transformed; Cell Separation; Cell Transformation, Viral; Chemokine CCL5; Chemokine CXCL9; Cytopathogenic Effect, Viral; DNA, Viral; Host-Pathogen Interactions; Humans; Inflammation Mediators; Interleukin-12 Subunit p40; Interleukin-3; JC Virus; Mesenchymal Stem Cells; Real-Time Polymerase Chain Reaction; Simian virus 40; Time Factors; Up-Regulation; Viral Load; Virus Replication; Wharton Jelly

Targeted sequencing identifies novel variants involved in autosomal recessive hereditary hearing loss in Qatari families. - Alkowari, Moza K; Vozzi, Diego; Bhagat, Shruti; Krishnamoorthy, Navaneethakrishnan; Morgan, Anna; Hayder, Yousra; Logendra, Barathy; Najjar, Nehal; Gandin, Ilaria; Gasparini, Paolo; Badii, Ramin; Girotto, Giorgia; et al. (Mutat Res, 2017)
Hereditary hearing loss is characterized by a very high genetic heterogeneity. In the Qatari population the role of GJB2, the worldwide HHL major player, seems to be quite limited compared to Caucasian populations. In this study we analysed 18 Qatari families affected by non-syndromic hearing loss using a targeted sequencing approach that allowed us to analyse 81 genes simultaneously. Thanks to this approach, 50% of these families (9 out of 18) resulted positive for the presence of likely causative alleles in 6 different genes: CDH23, MYO6, GJB6, OTOF, TMC1 and OTOA. In particular, 4 novel alleles were detected while the remaining ones were already described to be associated to HHL in other ethnic groups. Molecular modelling has been used to further investigate the role of novel alleles identified in CDH23 and TMC1 genes demonstrating their crucial role in Ca2+ binding and therefore possible functional role in proteins. Present study showed that an accurate molecular diagnosis based on next generation sequencing technologies might largely improve molecular diagnostics outcome leading to benefits for both genetic counseling and definition of recurrence risk.
Keywords: Adolescent; Alleles; Cadherins; Child; Child, Preschool; Connexins; Female; GPI-Linked Proteins; Hearing Loss, Sensorineural; Humans; Infant; Male; Membrane Proteins; Models, Molecular; Mutation; Myosin Heavy Chains; Pedigree; Protein Conformation; Qatar; Sequence Analysis, DNA

A Teenager with Sudden Unilateral Breast Enlargement. - Pellegrin, Maria Chiara; Naviglio, Samuele; Cattaruzzi, Elisabetta; Barbi, Egidio; Ventura, Alessandro (J Pediatr, 2017)
Keywords: Bullying; Child; Gynecomastia; Hematoma; Humans; Male; Wounds, Nonpenetrating

Whole-body MRI reveals high incidence of osteonecrosis in children treated for Hodgkin lymphoma. - Littooij, Annemieke S; Kwee, Thomas C; Enríquez, Goya; Verbeke, Jonathan I M L; Granata, Claudio; Beishuizen, Auke; de Lange, Charlotte; Zennaro, Floriana; Bruin, Marrie C A; Nievelstein, Rutger A J (Br J Haematol, 2017)
Osteonecrosis is a well-recognized complication in patients treated with corticosteroids. The incidence of osteonecrosis in children treated for Hodgkin lymphoma is unknown because prospective whole-body magnetic resonance imaging (MRI) studies are lacking in this patient population. Paediatric patients with newly diagnosed Hodgkin lymphoma who were treated according to a uniform paediatric Hodgkin protocol were eligible for inclusion in this prospective study. Whole-body MRI was performed in all 24 included patients (mean age 15·1 years, 12 girls) both before treatment and after 2 cycles of chemotherapy, and in 16 patients after completion of chemotherapy. Osteonecrosis was identified in 10 patients (41·7%, 95% confidence interval: 22·0-61·4%), with a total of 56 osteonecrotic sites. Osteonecrosis was detected in 8 patients after 2 cycles of OEPA (vincristine, etoposide, prednisone, doxorubicin), and in 2 additional patients after completion of chemotherapy. Epiphyseal involvement of long bones was seen in 4 of 10 children. None of the patients with osteonecrosis had any signs of bone collapse at the times of scanning. Whole-body MRI demonstrates osteonecrosis to be a common finding occurring during therapy response assessment of paediatric Hodgkin lymphoma. Detection of early epiphyseal osteonecrosis could allow for treatment before bone collapse and joint damage may occur.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Child; Doxorubicin; Epiphyses; Etoposide; Female; Hodgkin Disease; Humans; Incidence; Magnetic Resonance Imaging; Male; Osteonecrosis; Prednisone; Prospective Studies; Vincristine

Whole-Genome Sequencing Coupled to Imputation Discovers Genetic Signals for Anthropometric Traits. - Tachmazidou, Ioanna; Süveges, Dániel; Min, Josine L; Ritchie, Graham R S; Steinberg, Julia; Walter, Klaudia; Iotchkova, Valentina; Schwartzentruber, Jeremy; Huang, Jie; Memari, Yasin; McCarthy, Shane; Crawford, Andrew A; et al. (Am J Hum Genet, 2017)
Deep sequence-based imputation can enhance the discovery power of genome-wide association studies by assessing previously unexplored variation across the common- and low-frequency spectra. We applied a hybrid whole-genome sequencing (WGS) and deep imputation approach to examine the broader allelic architecture of 12 anthropometric traits associated with height, body mass, and fat distribution in up to 267,616 individuals. We report 106 genome-wide significant signals that have not been previously identified, including 9 low-frequency variants pointing to functional candidates. Of the 106 signals, 6 are in genomic regions that have not been implicated with related traits before, 28 are independent signals at previously reported regions, and 72 represent previously reported signals for a different anthropometric trait. 71% of signals reside within genes and fine mapping resolves 23 signals to one or two likely causal variants. We confirm genetic overlap between human monogenic and polygenic anthropometric traits and find signal enrichment in cis expression QTLs in relevant tissues. Our results highlight the potential of WGS strategies to enhance biologically relevant discoveries across the frequency spectrum.
Keywords: Anthropometry; Body Height; Cohort Studies; Databases, Genetic; DNA Methylation; Female; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Lipodystrophy; Male; Meta-Analysis as Topic; Obesity; Physical Chromosome Mapping; Quantitative Trait Loci; Sequence Analysis, DNA; Sex Characteristics; Syndrome; United Kingdom

Withdrawal Assessment Tool-1 Monitoring in PICU: A Multicenter Study on Iatrogenic Withdrawal Syndrome. - Amigoni, Angela; Mondardini, Maria Cristina; Vittadello, Ilaria; Zaglia, Federico; Rossetti, Emanuele; Vitale, Francesca; Ferrario, Stefania; Savron, Fabio; Coffaro, Giancarlo; Brugnaro, Luca; Amato, Roberta; Wolfler, Andrea; et al. (Pediatr Crit Care Med, 2017)
OBJECTIVES: Withdrawal syndrome is an adverse reaction of analgesic and sedative therapy, with a reported occurrence rate between 17% and 57% in critically ill children. Although some factors related to the development of withdrawal syndrome have been identified, there is weak evidence for the effectiveness of preventive and therapeutic strategies. The main aim of this study was to evaluate the frequency of withdrawal syndrome in Italian PICUs, using a validated instrument. We also analyzed differences in patient characteristics, analgesic and sedative treatment, and patients' outcome between patients with and without withdrawal syndrome. DESIGN: Observational multicenter prospective study. SETTING: Eight Italian PICUs belonging to the national PICU network Italian PICU network. PATIENTS: One hundred thirteen patients, less than 18 years old, mechanically ventilated and treated with analgesic and sedative therapy for five or more days. They were admitted in PICU from November 2012 to May 2014. INTERVENTIONS: Symptoms of withdrawal syndrome were monitored with Withdrawal Assessment Tool-1 scale. MEASUREMENTS AND MAIN RESULTS: The occurrence rate of withdrawal syndrome was 64.6%. The following variables were significantly different between the patients who developed withdrawal syndrome and those who did not: type, duration, and cumulative dose of analgesic therapy; duration and cumulative dose of sedative therapy; clinical team judgment about analgesia and sedation's difficulty; and duration of analgesic weaning, mechanical ventilation, and PICU stay. Multivariate logistic regression analysis revealed that patients receiving morphine as their primary analgesic were 83% less likely to develop withdrawal syndrome than those receiving fentanyl or remifentanil. CONCLUSIONS: Withdrawal syndrome was frequent in PICU patients, and patients with withdrawal syndrome had prolonged hospital treatment. We suggest adopting the lowest effective dose of analgesic and sedative drugs and frequent reevaluation of the need for continued use. Further studies are necessary to define common preventive and therapeutic strategies.
Keywords: Adolescent; Analgesics; Child; Child, Preschool; Critical Care; Female; Humans; Hypnotics and Sedatives; Iatrogenic Disease; Infant; Infant, Newborn; Intensive Care Units, Pediatric; Italy; Logistic Models; Male; Prospective Studies; Respiration, Artificial; Substance Withdrawal Syndrome

A young goalkeeper with buttock pain and fever. - Moressa, Valentina; Pastore, Serena; Naviglio, Samuele; Ventura, Alessandro (BMJ, 2017)
Keywords: Adolescent; Buttocks; Fever; Humans; Male; Musculoskeletal Pain; Pyomyositis

Action of methotrexate and tofacitinib on directly stimulated and bystander-activated lymphocytes. - Piscianz, Elisa; Candilera, Vanessa; Valencic, Erica; Loganes, Claudia; Paron, Greta; De Iudicibus, Sara; Decorti, Giuliana; Tommasini, Alberto (Mol Med Rep, 2016)
Chronic inflammation associated with autoimmune activation is characteristic of rheumatic diseases from childhood to adulthood. In recent decades, significant improvements in the treatment of these types of disease have been achieved using disease modifying anti-rheumatic drugs (DMARDs), such as methotrexate (MTX) and, more recently, using biologic inhibitors. The recent introduction of kinase inhibitors (for example, tofacitinib; Tofa) further increases the available ARDs. However, there are patients that do not respond to any treatment strategies, for whom combination therapies are proposed. The data regarding the combined action of different drugs is lacking and the knowledge of the mechanisms of ARDs and their actions upon pathogenic lymphocytes, which are hypothesized to sustain disease, is poor. An in vitro model of inflammation was developed in the current study, in which stimulated and unstimulated lymphocytes were cultured together, but tracked separately, to investigate the action of MTX and Tofa on the two populations. By analysing lymphocyte proliferation and activation, and cytokine secretion in the culture supernatants, it was established that, due to the presence of activated cells, unstimulated cells underwent a bystander activation that was modulated by the ARDs. Additionally, varying administration schedules were demonstrated to affect lymphocytes differently in vitro, either directly or via bystander activation. Furthermore, MTX and Tofa exerted different effects; while MTX showed an antiproliferative effect, Tofa marginally effected activation, although only a slight antiproliferative action, which could be potentiated by sequential treatment with MTX. Thus, it was hypothesized that these differences may be exploited in sequential therapeutic strategies, to maximize the anti‑rheumatic effect. These findings are notable and must be accounted for, as bystander‑activated cells in vivo could contribute to the spread of autoimmune activation and disease progression.

Acute myelitis as presenting symptom of HIV-HTLV-1 co-infection. - Cucca, A; Stragapede, L; Antonutti, L; Catalan, M; Caracciolo, I; Valentinotti, Romina; Granato, A; D'Agaro, P; Manganotti, P (J Neurovirol, 2016)
A 21-year-old woman presented with acute-onset spastic paraparesis. The MRI spinal scan revealed a contrast-enhanced T2 hyperintensity between C5-T2. The most common neurotropic pathogens were excluded by first level tests. Under suspicion of an acute immune-mediated myelitis, a corticosteroid therapy was administered. However, a seropositivity for both human immunodeficiency virus (HIV) type 1 and human T-lymphotropic virus (HTLV) subsequently emerged. An antiretroviral therapy was started while steroids discontinued. Patient's clinical conditions remained unchanged. HIV-HTLV-1 co-infection should be included in the differential diagnosis of any acute myelitis, even in patients with a preserved immune status and no risk factors.

Anti-ApoA-1 IgG serum levels predict worse poststroke outcomes. - Carbone, Federico; Satta, Nathalie; Montecucco, Fabrizio; Virzi, Julien; Burger, Fabienne; Roth, Aline; Roversi, Gloria; Tamborino, Carmine; Casetta, Ilaria; Seraceni, Silva; Trentini, Alessandro; Padroni, Marina; et al. (Eur J Clin Invest, 2016)
BACKGROUND: Autoantibodies to apolipoprotein A-1 (anti-ApoA-1 IgG) were shown to predict major adverse cardiovascular events and promote atherogenesis. However, their potential relationship with clinical disability and ischaemic lesion volume after acute ischaemic stroke (AIS) remains unexplored. MATERIALS AND METHODS: We included n = 76 patients admitted for AIS and we investigated whether baseline serum anti-ApoA-1 IgG levels could predict (i) AIS-induced clinical disability [assessed by the modified Rankin Scale (mRS)], and (ii) AIS-related ischaemic lesion volume [assessed by Computed Tomography (CT)]. We also evaluated the possible pro-apoptotic and pro-necrotic effects of anti-ApoA-1 IgG on human astrocytoma cell line (U251) using flow cytometry. RESULTS: High levels of anti-ApoA-1 IgG were retrieved in 15·8% (12/76) of patients. Increased baseline levels of anti-ApoA-1 IgG were independently correlated with worse mRS [β = 0·364; P = 0·002; adjusted odds ratio (OR): 1·05 (95% CI 1·01-1·09); P = 0·017] and CT-assessed ischaemic lesion volume [β = 0·333; P < 0·001; adjusted OR: 1·06 (95% CI 1·01-1·12); P = 0·048] at 3 months. No difference in baseline clinical, biochemical and radiological characteristics was observed between patients with high vs. low levels of anti-ApoA-1 IgG. Incubating human astrocytoma cells with anti-ApoA-1 IgG dose dependently induced necrosis and apoptosis of U251 cells in vitro. CONCLUSION: Anti-ApoA-1 IgG serum levels at AIS onset are associated with poorer clinical recovery and worse brain lesion volume 3 months after AIS. These observations could be partly explained by the deleterious effect of anti-ApoA-1 IgG on human brain cell survival in vitro and may have clinical implication in the prediction of poor outcome in AIS.

Carbamazepine-induced thrombocytopenic purpura in a child: Insights from a genomic analysis. - Abate, Maria Valentina; Stocco, Gabriele; Devescovi, Raffaella; Carrozzi, Marco; Pierobon, Chiara; Valencic, Erica; Lucafò, Marianna; Di Silvestre, Alessia; d'Adamo, Pio; Tommasini, Alberto; Decorti, Giuliana; Ventura, Alessandro (Blood Cells Mol Dis, 2016)

A Child with Severe Developmental Delay and Growth Retardation. - Rossetto, Elena; Matarazzo, Lorenza; Maschio, Massimo; Taddio, Andrea; Costa, Paola; Ventura, Alessandro (J Pediatr, 2016)

CNV analysis in 169 patients with bladder exstrophy-epispadias complex. - von Lowtzow, Catharina; Hofmann, Andrea; Zhang, Rong; Marsch, Florian; Ebert, Anne-Karoline; Rösch, Wolfgang; Stein, Raimund; Boemers, Thomas M; Hirsch, Karin; Marcelis, Carlo; Feitz, Wouter F J; Brusco, Alfredo; et al. (BMC Med Genet, 2016)
BACKGROUND: The bladder exstrophy-epispadias complex (BEEC) represents the severe end of the congenital uro-rectal malformation spectrum. Initial studies have implicated rare copy number variations (CNVs), including recurrent duplications of chromosomal region 22q11.21, in BEEC etiology. METHODS: To detect further CNVs, array analysis was performed in 169 BEEC patients. Prior to inclusion, 22q11.21 duplications were excluded using multiplex ligation-dependent probe amplification. RESULTS: Following the application of stringent filter criteria, seven rare CNVs were identified: n = 4, not present in 1307 in-house controls; n = 3, frequency of <0.002 in controls. These CNVs ranged from 1 to 6.08 Mb in size. To identify smaller CNVs, relaxed filter criteria used in the detection of previously reported BEEC associated chromosomal regions were applied. This resulted in the identification of six additional rare CNVs: n = 4, not present in 1307 in-house controls; n = 2, frequency <0.0008 in controls. These CNVs ranged from 0.03-0.08 Mb in size. For 10 of these 13 CNVs, confirmation and segregation analyses were performed (5 of maternal origin; 5 of paternal origin). Interestingly, one female with classic bladder extrophy carried a 1.18 Mb duplication of 22q11.1, a chromosomal region that is associated with cat eye syndrome. CONCLUSIONS: A number of rare CNVs were identified in BEEC patients, and these represent candidates for further evaluation. Rare inherited CNVs may constitute modifiers of, or contributors to, multifactorial BEEC phenotypes.

Cross-sectional study of coeliac autoimmunity in a population of Vietnamese children. - Zanella, Sara; De Leo, Luigina; Nguyen-Ngoc-Quynh, Le; Nguyen-Duy, Bo; Not, Tarcisio; Tran-Thi-Chi, Mai; Phung-Duc, Son; Le-Thanh, Hai; Malaventura, Cristina; Vatta, Serena; Ziberna, Fabiana; Mazzocco, Martina; et al. (BMJ Open, 2016)
OBJECTIVE: The prevalence of coeliac disease (CD) in Vietnam is unknown. To fill this void, we assessed the prevalence of serological markers of CD autoimmunity in a population of children in Hanoi. SETTING: The outpatient blood drawing laboratory of the largest paediatric hospital in North Vietnam was used for the study, which was part of an international project of collaboration between Italy and Vietnam. PARTICIPANTS: Children having blood drawn for any reason were included. Exclusion criteria were age younger than 2 years, acquired or congenital immune deficiency and inadequate sample. A total of 1961 children (96%) were enrolled (838 females, 1123 males, median age 5.3 years). OUTCOMES: Primary outcome was the prevalence of positive autoimmunity to both IgA antitransglutaminase antibodies (anti-tTG) assessed with an ELISA test and antiendomysial antibodies (EMA). Secondary outcome was the prevalence of CD predisposing human leucocyte antigens (HLA) (HLA DQ2/8) in the positive children and in a random group of samples negative for IgA anti-tTG. RESULTS: The IgA anti-tTG test was positive in 21/1961 (1%; 95% CI 0.61% to 1.53%); however, EMA antibodies were negative in all. HLA DQ2/8 was present in 7/21 (33%; 95% CI 14.5% to 56.9%) of the anti-tTG-positive children and in 72/275 (26%; 95% CI 21% to 32%) of those who were negative. CONCLUSIONS: Coeliac autoimmunity is rare in Vietnam, although prevalence of HLA DQ2/8 is similar to that of other countries. We hypothesise that the scarce exposure to gluten could be responsible for these findings.

Decline in Lung Function in Childhood Asthma. - Bibalo, Cristina; Longo, Giorgio; Ventura, Alessandro (N Engl J Med, 2016)
Keywords: Anti-Inflammatory Agents; Asthma; Female; Humans; Lung; Male

Differential expression of GAS5 in rapamycin-induced reversion of glucocorticoid resistance. - Lucafò, Marianna; Bravin, Vanessa; Tommasini, Alberto; Martelossi, Stefano; Rabach, Ingrid; Ventura, Alessandro; Decorti, Giuliana; De Iudicibus, Sara (Clin Exp Pharmacol Physiol, 2016)
This study evaluates the association between the long noncoding RNA GAS5 levels and the anti-proliferative effect of the glucocorticoid (GC) methylprednisolone (MP) alone and in combination with rapamycin in peripheral blood mononuclear cells (PBMCs) obtained from healthy donors. The effect of MP, rapamycin, and MP plus rapamycin was determined in 17 healthy donors by labelling metabolically active cells with [methyl-3H] thymidine and the expression levels of GAS5 gene were evaluated by real-time RT-PCR TaqMan analysis. We confirmed a role for GAS5 in modulating GC response: poor responders presented higher levels of GAS5 in comparison with good responders. Interestingly, when PBMCs were treated with the combination of rapamycin plus MP, the high levels of GAS5 observed for each drug in the MP poor responders group decreased in comparison with rapamycin (P value = 0.0134) or MP alone (P value = 0.0193). GAS5 is involved in GC resistance and co-treatment of rapamycin with GCs restores GC effectiveness in poor responders through the downregulation of the long noncoding RNA. GAS5 could be considered a biomarker to personalize therapy and a novel therapeutic target useful for the development of new pharmacological approaches to restore GC sensitivity.

Early diagnosis and Early Start Denver Model intervention in autism spectrum disorders delivered in an Italian Public Health System service. - Devescovi, Raffaella; Monasta, Lorenzo; Mancini, Alice; Bin, Maura; Vellante, Valerio; Carrozzi, Marco; Colombi, Costanza (Neuropsychiatr Dis Treat, 2016)
BACKGROUND: Early diagnosis combined with an early intervention program, such as the Early Start Denver Model (ESDM), can positively influence the early natural history of autism spectrum disorders. This study evaluated the effectiveness of an early ESDM-inspired intervention, in a small group of toddlers, delivered at low intensity by the Italian Public Health System. METHODS: Twenty-one toddlers at risk for autism spectrum disorders, aged 20-36 months, received 3 hours/wk of one-to-one ESDM-inspired intervention by trained therapists, combined with parents' and teachers' active engagement in ecological implementation of treatment. The mean duration of treatment was 15 months. Cognitive and communication skills, as well as severity of autism symptoms, were assessed by using standardized measures at pre-intervention (Time 0 [T0]; mean age =27 months) and post-intervention (Time 1 [T1]; mean age =42 months). RESULTS: Children made statistically significant improvements in the language and cognitive domains, as demonstrated by a series of nonparametric Wilcoxon tests for paired data. Regarding severity of autism symptoms, younger age at diagnosis was positively associated with greater improvement at post-assessment. CONCLUSION: Our results are consistent with the literature that underlines the importance of early diagnosis and early intervention, since prompt diagnosis can reduce the severity of autism symptoms and improve cognitive and language skills in younger children. Particularly in toddlers, it seems that an intervention model based on the ESDM principles, involving the active engagement of parents and nursery school teachers, may be effective even when the individual treatment is delivered at low intensity. Furthermore, our study supports the adaptation and the positive impact of the ESDM entirely sustained by the Italian Public Health System.

Effect of Early Versus Late Azathioprine Therapy in Pediatric Ulcerative Colitis. - Aloi, Marina; DʼArcangelo, Giulia; Bramuzzo, Matteo; Gasparetto, Marco; Martinelli, Massimo; Alvisi, Patrizia; Illiceto, Maria Teresa; Valenti, Simona; Distante, Manuela; Pellegrino, Salvatore; Gatti, Simona; Arrigo, Serena; et al. (Inflamm Bowel Dis, 2016)
BACKGROUND: We aimed at describing the efficacy of azathioprine (AZA) in pediatric ulcerative colitis, comparing the outcomes of early (0-6 months) versus late (6-24 months) initiation of therapy. METHODS: Children with ulcerative colitis treated with AZA within 24 months of diagnosis were included. Corticosteroid (CS)-free remission and mucosal healing (MH), assessed by endoscopy or fecal calprotectin, at 12 months were the primary outcomes. Patients were also compared for CS-free remission and MH, need for treatment escalation or surgery, number of hospitalizations, and adverse events during a 24-month follow-up. RESULTS: A total of 121 children entered the study (median age 10.5 ± 4.0 years, 59% girls). Seventy-six (63%) started AZA between 0 and 6 months (early group) and 45 (37%) started between 6 and 24 months (late group). Seventy-five percent and 53% of patients in the early and late group, respectively, received CS at the diagnosis (P = 0.01). CS-free remission at 1 year was achieved by 30 (50%) of the early and 23 (57%) of the late patients (P = 0.54). MH occurred in 37 (37%) patients at 1 year, with no difference between the 2 groups (33% early, 42% late; P = 0.56). No difference was found for the other outcomes. CONCLUSIONS: Introduction of AZA within 6 months of diagnosis seems not more effective than later treatment to achieve CS-free remission in pediatric ulcerative colitis. MH does not depend on the timing of AZA initiation; however, because of the incomplete comparability of the 2 groups at the diagnosis and the use of fecal calprotectin as a surrogate marker of MH, our results should be further confirmed by prospective studies.

Efficacy of ketamine in refractory convulsive status epilepticus in children: a protocol for a sequential design, multicentre, randomised, controlled, open-label, non-profit trial (KETASER01). - Rosati, Anna; Ilvento, Lucrezia; L'Erario, Manuela; De Masi, Salvatore; Biggeri, Annibale; Fabbro, Giancarlo; Bianchi, Roberto; Stoppa, Francesca; Fusco, Lucia; Pulitanò, Silvia; Battaglia, Domenica; Pettenazzo, Andrea; et al. (BMJ Open, 2016)
INTRODUCTION: Status epilepticus (SE) is a life-threatening neurological emergency. SE lasting longer than 120 min and not responding to first-line and second-line antiepileptic drugs is defined as 'refractory' (RCSE) and requires intensive care unit treatment. There is currently neither evidence nor consensus to guide either the optimal choice of therapy or treatment goals for RCSE, which is generally treated with coma induction using conventional anaesthetics (high dose midazolam, thiopental and/or propofol). Increasing evidence indicates that ketamine (KE), a strong N-methyl-d-aspartate glutamate receptor antagonist, may be effective in treating RCSE. We hypothesised that intravenous KE is more efficacious and safer than conventional anaesthetics in treating RCSE. METHODS AND ANALYSIS: A multicentre, randomised, controlled, open-label, non-profit, sequentially designed study will be conducted to assess the efficacy of KE compared with conventional anaesthetics in the treatment of RCSE in children. 10 Italian centres/hospitals are involved in enrolling 57 patients aged 1 month to 18 years with RCSE. Primary outcome is the resolution of SE up to 24 hours after withdrawal of therapy and is updated for each patient treated according to the sequential method. ETHICS AND DISSEMINATION: The study received ethical approval from the Tuscan Paediatric Ethics Committee (12/2015). The results of this study will be published in peer-reviewed journals and presented at international conferences. TRIAL REGISTRATION NUMBER: NCT02431663; Pre-results.

Evidence for three genetic loci involved in both anorexia nervosa risk and variation of body mass index. - Hinney, A; Kesselmeier, M; Jall, S; Volckmar, A-L; Föcker, M; Antel, J; Heid, I M; Winkler, T W; Grant, S F A; Guo, Y; Bergen, A W; Kaye, W; et al. (Mol Psychiatry, 2016)
The maintenance of normal body weight is disrupted in patients with anorexia nervosa (AN) for prolonged periods of time. Prior to the onset of AN, premorbid body mass index (BMI) spans the entire range from underweight to obese. After recovery, patients have reduced rates of overweight and obesity. As such, loci involved in body weight regulation may also be relevant for AN and vice versa. Our primary analysis comprised a cross-trait analysis of the 1000 single-nucleotide polymorphisms (SNPs) with the lowest P-values in a genome-wide association meta-analysis (GWAMA) of AN (GCAN) for evidence of association in the largest published GWAMA for BMI (GIANT). Subsequently we performed sex-stratified analyses for these 1000 SNPs. Functional ex vivo studies on four genes ensued. Lastly, a look-up of GWAMA-derived BMI-related loci was performed in the AN GWAMA. We detected significant associations (P-values <5 × 10(-5), Bonferroni-corrected P<0.05) for nine SNP alleles at three independent loci. Interestingly, all AN susceptibility alleles were consistently associated with increased BMI. None of the genes (chr. 10: CTBP2, chr. 19: CCNE1, chr. 2: CARF and NBEAL1; the latter is a region with high linkage disequilibrium) nearest to these SNPs has previously been associated with AN or obesity. Sex-stratified analyses revealed that the strongest BMI signal originated predominantly from females (chr. 10 rs1561589; Poverall: 2.47 × 10(-06)/Pfemales: 3.45 × 10(-07)/Pmales: 0.043). Functional ex vivo studies in mice revealed reduced hypothalamic expression of Ctbp2 and Nbeal1 after fasting. Hypothalamic expression of Ctbp2 was increased in diet-induced obese (DIO) mice as compared with age-matched lean controls. We observed no evidence for associations for the look-up of BMI-related loci in the AN GWAMA. A cross-trait analysis of AN and BMI loci revealed variants at three chromosomal loci with potential joint impact. The chromosome 10 locus is particularly promising given that the association with obesity was primarily driven by females. In addition, the detected altered hypothalamic expression patterns of Ctbp2 and Nbeal1 as a result of fasting and DIO implicate these genes in weight regulation.Molecular Psychiatry advance online publication, 17 May 2016; doi:10.1038/mp.2016.71.

Fecal Calprotectin: Diagnostic Accuracy of the Immunochromatographic CalFast Assay in a Pediatric Population. - Radillo, Oriano; Pascolo, Lorella; Martelossi, Stefano; Dal Bo, Sara; Ventura, Alessandro (J Clin Lab Anal, 2016)
BACKGROUND: Fecal calprotectin is a noninvasive marker for bowel diseases and it is high valuable to follow disease activity in Crohn's disease (CD) and ulcerative colitis (UC). In this study, we evaluated the diagnostic performance of the recently introduced immunochromatographic assay CalFast in comparison to the well-known ELISA tests for calprotectin assay to obtain a rapid diagnosis of bowel inflammation in pediatric patients. METHODS: CalFast was tested in parallel to the classic ELISA tests CalPrest and PhiCal (gold standards for the calprotectin determination) on 148 fecal samples from pediatric subjects including 104 healthy subjects, 29 with CD, and 15 with UC. RESULTS: In this study, the sensitivity and specificity of CalFast, CalPrest, and PhiCal were 86.4%, 88.6%, and 93.2% and 86.6%, 74%, and 64.4%, respectively. The area under the curve, obtained from receiver operating characteristic analysis, indicated the lack of significant difference among all the kits used. CONCLUSION: The immunochromatographic assay demonstrated good diagnostic predictive values, comparable to those of the ELISA methods, and may represent a valid alternative in order to save operators' time. The test, in fact, has a short turnaround time and does not need a specific ELISA instrumentation.

Genetic associations at 53 loci highlight cell types and biological pathways relevant for kidney function. - Pattaro, Cristian; Teumer, Alexander; Gorski, Mathias; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Garnaas, Maija; Tin, Adrienne; Sorice, Rossella; Li, Yong; Taliun, Daniel; Olden, Matthias; et al. (Nat Commun, 2016)
Reduced glomerular filtration rate defines chronic kidney disease and is associated with cardiovascular and all-cause mortality. We conducted a meta-analysis of genome-wide association studies for estimated glomerular filtration rate (eGFR), combining data across 133,413 individuals with replication in up to 42,166 individuals. We identify 24 new and confirm 29 previously identified loci. Of these 53 loci, 19 associate with eGFR among individuals with diabetes. Using bioinformatics, we show that identified genes at eGFR loci are enriched for expression in kidney tissues and in pathways relevant for kidney development and transmembrane transporter activity, kidney structure, and regulation of glucose metabolism. Chromatin state mapping and DNase I hypersensitivity analyses across adult tissues demonstrate preferential mapping of associated variants to regulatory regions in kidney but not extra-renal tissues. These findings suggest that genetic determinants of eGFR are mediated largely through direct effects within the kidney and highlight important cell types and biological pathways.
Keywords: Gene Expression Regulation; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Renal Insufficiency, Chronic

Genome-wide association study identifies 74 loci associated with educational attainment. - Okbay, Aysu; Beauchamp, Jonathan P; Fontana, Mark Alan; Lee, James J; Pers, Tune H; Rietveld, Cornelius A; Turley, Patrick; Chen, Guo-Bo; Emilsson, Valur; Meddens, S Fleur W; Oskarsson, Sven; Pickrell, Joseph K; et al. (Nature, 2016)
Educational attainment is strongly influenced by social and other environmental factors, but genetic factors are estimated to account for at least 20% of the variation across individuals. Here we report the results of a genome-wide association study (GWAS) for educational attainment that extends our earlier discovery sample of 101,069 individuals to 293,723 individuals, and a replication study in an independent sample of 111,349 individuals from the UK Biobank. We identify 74 genome-wide significant loci associated with the number of years of schooling completed. Single-nucleotide polymorphisms associated with educational attainment are disproportionately found in genomic regions regulating gene expression in the fetal brain. Candidate genes are preferentially expressed in neural tissue, especially during the prenatal period, and enriched for biological pathways involved in neural development. Our findings demonstrate that, even for a behavioural phenotype that is mostly environmentally determined, a well-powered GWAS identifies replicable associated genetic variants that suggest biologically relevant pathways. Because educational attainment is measured in large numbers of individuals, it will continue to be useful as a proxy phenotype in efforts to characterize the genetic influences of related phenotypes, including cognition and neuropsychiatric diseases.
Keywords: Alzheimer Disease; Bipolar Disorder; Brain; Cognition; Computational Biology; Educational Status; Fetus; Gene Expression Regulation; Gene-Environment Interaction; Genome-Wide Association Study; Great Britain; Humans; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Schizophrenia

A Genome-Wide Association Study in isolated populations reveals new genes associated to common food likings. - Pirastu, Nicola; Kooyman, Maarten; Traglia, Michela; Robino, Antonietta; Willems, Sara M; Pistis, Giorgio; Amin, Najaf; Sala, Cinzia; Karssen, Lennart C; van Duijn, Cornelia; Toniolo, Daniela; Gasparini, Paolo (Rev Endocr Metab Disord, 2016)
Food preferences are the first factor driving food choice and thus nutrition. They involve numerous different senses such as taste and olfaction as well as various other factors such as personal experiences and hedonistic aspects. Although it is clear that several of these have a genetic basis, up to now studies have focused mostly on the effects of polymorphisms of taste receptor genes. Therefore, we have carried out one of the first large scale (4611 individuals) GWAS on food likings assessed for 20 specific food likings belonging to 4 different categories (vegetables, fatty, dairy and bitter). A two-step meta-analysis using three different isolated populations from Italy for the discovery step and two populations from The Netherlands and Central Asia for replication, revealed 15 independent genome-wide significant loci (p < 5 × 10(-8)) for 12 different foods. None of the identified genes coded for either taste or olfactory receptors suggesting that genetics impacts in determining food likings in a much broader way than simple differences in taste perception. These results represent a further step in uncovering the genes that underlie liking of common foods that in the end will greatly help understanding the genetics of human nutrition in general.

The Importance of Mortality Risk Assessment: Validation of the Pediatric Index of Mortality 3 Score. - Wolfler, Andrea; Osello, Raffaella; Gualino, Jenny; Calderini, Edoardo; Vigna, Gianluca; Santuz, Pierantonio; Amigoni, Angela; Savron, Fabio; Caramelli, Fabio; Rossetti, Emanuele; Cecchetti, Corrado; Corbari, Maurizio; et al. (Pediatr Crit Care Med, 2016)
OBJECTIVE: To evaluate the performance of the newest version of the Pediatric Index of Mortality 3 score and compare it with the Pediatric Index of Mortality 2 in a multicenter national cohort of children admitted to PICU. DESIGN: Retrospective, prospective cohort study. SETTING: Seventeen Italian PICUs. PATIENTS: All children 0 to 15 years old admitted in PICU from January 2010 to October 2014. INTERVENTIONS: None. MEASUREMENT AND MAIN RESULTS: Eleven thousand one hundred nine children were enrolled in the study. The mean Pediatric Index of Mortality 2 and 3 values of 4.9 and 3.9, respectively, differed significantly (p < 0.05). Overall mortality rate was 3.9%, and the standardized mortality ratio was 0.80 for Pediatric Index of Mortality 2 and 0.98 for Pediatric Index of Mortality 3 (p < 0.05). The area under the curve of the receiver operating characteristic curves was similar for Pediatric Index of Mortality 2 and Pediatric Index of Mortality 3. The Hosmer-Lemeshow test was not significant for Pediatric Index of Mortality 3 (p = 0.21) but was highly significant for Pediatric Index of Mortality 2 (p < 0.001), which overestimated death mainly in high-risk categories. CONCLUSIONS: Mortality indices require validation in each country where it is used. The new Pediatric Index of Mortality 3 score performed well in an Italian population. Both calibration and discrimination were appropriate, and the score more accurately predicted the mortality risk than Pediatric Index of Mortality 2.

Improving regional universal newborn hearing screening programmes in Italy. - Molini, E; Cristi, M C; Lapenna, R; Calzolaro, L; Muzzi, E; Ciciriello, E; Della Volpe, A; Orzan, E; Ricci, G (Acta Otorhinolaryngol Ital, 2016)
The Universal Newborn Hearing Screening (UNHS) programme aims at achieving early detection of hearing impairment. Subsequent diagnosis and intervention should follow promptly. Within the framework of the Ministry of Health project CCM 2013 "Preventing Communication Disorders: a Regional Program for early Identification, Intervention and Care of Hearing Impaired Children", the limitations and strengths of current UNHS programs in Italy have been analysed by a group of professionals working in tertiary centres involved in regional UNHS programmes, using SWOT analysis and a subsequent TOWS matrix. Coverage and lost-to-follow up rates are issues related to UNHS programmes. Recommendations to improve the effectiveness of the UNHS programme have been identified. The need for homogeneous policies, high-quality information and dissemination of knowledge for operators and families of hearing-impaired children emerged from the discussion.

The incidence rate and prevalence of pediatric type 1 diabetes mellitus (age 0-18) in the Italian region Friuli Venezia Giulia: population-based estimates through the analysis of health administrative databases. - Valent, Francesca; Candido, Riccardo; Faleschini, Elena; Tonutti, Laura; Tortul, Carla; Zanatta, Manuela; Zanette, Giorgio; Zanier, Loris (Acta Diabetol, 2016)
AIMS: The main objective of this study was to estimate the incidence rate and prevalence of pediatric type 1 diabetes mellitus (T1DM; population 0-18 years of age) in the northeastern Italian region Friuli Venezia Giulia and to characterize the subjects affected by the disease. METHODS: This was a retrospective population-based study conducted through the individual-level linkage of several health administrative databases of the Friuli Venezia Giulia region. The incidence rate and prevalence were calculated in the population 0-18 years of age. Using the Mid-p exact method, 95 % confidence intervals for rates were calculated. RESULTS: The incidence rate of pediatric T1DM in the years 2010-2013 was 15.8 new cases/100,000 person-years, peaking in the age class 10-14 years. The rate has increased substantially as compared with the previous regional estimate that dated back to 1993. We observed a seasonal pattern both in the date of birth of the incident cases and in the date of onset of the disease. In the region in 2013, there were 294 prevalent cases (15.1/10,000 inhabitants). Most of them had at least one glycated hemoglobin test in the year. More than 15 % had co-existing autoimmune comorbidities. CONCLUSIONS: The incidence rate of pediatric T1DM in Friuli Venezia Giulia has increased in the last years, and the disease is a relevant public health issue in the region.

Innate and adaptive immunity in self-reported nonceliac gluten sensitivity versus celiac disease. - Di Sabatino, Antonio; Giuffrida, Paolo; Fornasa, Giulia; Salvatore, Chiara; Vanoli, Alessandro; Naviglio, Samuele; De Leo, Luigina; Pasini, Alessandra; De Amici, Mara; Alvisi, Costanza; Not, Tarcisio; Rescigno, Maria; et al. (Dig Liver Dis, 2016)
BACKGROUND: Immune mechanisms have been implicated in nonceliac gluten sensitivity (NCGS), a condition characterized by intestinal and/or extraintestinal symptoms caused by the ingestion of gluten in non-celiac/non-wheat allergic individuals. AIMS: We investigated innate and adaptive immunity in self-reported NCGS versus celiac disease (CD). METHODS: In the supernatants of ex vivo-cultured duodenal biopsies from 14 self-reported NCGS patients, 9 untreated and 10 treated CD patients, and 12 controls we detected innate cytokines - interleukin (IL)-15, tumor necrosis factor-α, IL-1β, IL-6, IL-12p70, IL-23, IL-27, IL-32α, thymic stromal lymphopoietin (TSLP), IFN-α-, adaptive cytokines - interferon (IFN)-γ, IL-17A, IL-4, IL-5, IL-10, IL-13-, chemokines - IL-8, CCL1, CCL2, CCL3, CCL4, CCL5, CXCL1, CXCL10-, granulocyte colony stimulating factor (G-CSF) and granulocyte-macrophage colony stimulating factor (GM-CSF). RESULTS: Mucosal innate and adaptive cytokines, chemokines and growth factors did not differ between self-reported NCGS, treated CD and controls. On the contrary, IL-6, IL-15, IL-27, IFN-α, IFN-γ, IL-17A, IL-23, G-CSF, GM-CSF, IL-8, CCL1 and CCL4 were significantly higher in untreated CD than in self-reported NCGS, treated CD and controls, while TSLP was significantly lower in untreated CD than in self-reported NCGS, treated CD and controls. CONCLUSION: In our hands, patients with self-reported NCGS showed no abnormalities of the mucosal immune response.

Iron signature in asbestos-induced malignant pleural mesothelioma: A population-based autopsy study. - Crovella, Sergio; Bianco, Anna Monica; Vuch, Joseph; Zupin, Luisa; Moura, Ronald Rodrigues; Trevisan, Elisa; Schneider, Manuela; Brollo, Alessandro; Nicastro, Enza Maria; Cosenzi, Alessandro; Zabucchi, Giuliano; Borelli, Violetta (J Toxicol Environ Health A, 2016)
Malignant pleural mesothelioma (MPM) is an aggressive cancer with poor prognosis. The development of MPM is frequently linked to inhalation of asbestos fibers. A genetic component of susceptibility to this disease is suggested by the observation that some individuals develop MPM following lower doses of asbestos exposure, whereas others exposed to higher quantities do not seem to be affected. This hypothesis is supported also by frequent reports of MPM familial clustering. Despite the widely recognized role of iron (Fe) in cellular asbestos-induced pulmonary toxicity, the role of the related gene polymorphisms in the etiology of MPM has apparently not been evaluated. Eighty-six single-nucleotide polymorphisms (SNPs) of 10 Fe-metabolism genes were examined by exploiting formalin-fixed paraffin-embedded postmortem samples from 77 patients who died due to MPM (designated AEM) and compared with 48 who were exposed to asbestos but from died in old age of cause other than asbestos (designated AENM). All subjects showed objective signs of asbestos exposure. Three SNPs, localized in the ferritin heavy polypeptide, transferrin, and hephaestin genes, whose frequencies were distributed differently in AEM and AENM populations, were identified. For ferritin and transferrin the C/C and the G/G genotypes, respectively, representing intronic polymorphisms, were significantly associated with protection against MPM and need to be considered as possible genetic markers of protection. Similarly, the C/C hephaestin SNP, a missense variation of this multicopper ferroxidase encoding gene, may be related, also functionally, with protection against MPM. In conclusion, it is proposed that three Fe metabolism-associated genes, significantly associated with protection against development of MPM, may serve as protective markers for this aggressive tumor.
Keywords: Adult; Aged; Asbestos; Autopsy; Case-Control Studies; Female; Ferritins; Gene Frequency; Genetic Markers; Humans; Iron; Lung Neoplasms; Male; Membrane Proteins; Mesothelioma; Middle Aged; Mutation, Missense; Polymorphism, Single Nucleotide; Transferrin; Young Adult

Isolation of the left innominate artery: a question of connection. - Gesuete, Valentina; Sanabor, Daniela; Benettoni, Alessandra; Bobbo, Marco; Ventura, Alessandro (J Cardiovasc Med (Hagerstown), 2016)

Lack of Evidence of Rotavirus-Dependent Molecular Mimicry as a Trigger of Celiac Disease. - Ziberna, Fabiana; De Lorenzo, Giuditta; Schiavon, Valentina; Arnoldi, Francesca; Quaglia, Sara; De Leo, Luigina; Vatta, Serena; Martelossi, Stefano; Burrone, Oscar R; Ventura, Alessandro; Not, Tarcisio (Clin Exp Immunol, 2016)
New data suggest the involvement of Rotavirus (RV) in triggering autoimmunity in celiac disease (CD) by molecular mimicry between the human-transglutaminase protein and the dodecapeptide (260-271 aa) of the RV protein VP7 (pVP7). To assess the role of RV in the onset of CD, we measured the anti-pVP7 antibodies in the sera of children with CD and of control groups. We analysed serum samples of 118 biopsy proven CD patients and 46 patients with potential-CD; 32 children with other gastrointestinal diseases; 107 no-CD children and 107 blood donors. By ELISA assay, we measured IgA-IgG antibodies against the synthetic peptides pVP7, the human transglutaminase-derived peptide (476-487 aa) which shows an homology with VP7 protein and a control peptide. The triple-layered RV particles (TLPs), containing the VP7 protein, and the double-layered RV-particles (DLPs), lacking the VP7 protein were also used as antigens in ELISA assay. Antibody reactivity to the RV-TLPs was positive in 22/118 (18%) CD patients and in both paediatric (17/107, 16%) and adult (29/107, 27%) control groups, without showing a statistically significant difference among them (p=0.6, p=0.1). Biopsy-proven CD patients as well as the adult control group demonstrated a high positive antibody reactivity against both pVP7 (34/118, 29% CD patients; 66/107, 62% adult controls) and control synthetic peptides (35/118, 30% CD patients; 56/107, 52% adult controls) suggesting a non-specific response against RV pVP7. We show that children with CD do not have higher immune reactivity to RV, thus questioning the molecular mimicry mechanism as a triggering factor of CD. This article is protected by copyright. All rights reserved.

Macrocephaly and palmoplantar pitting. - Rabach, Ingrid; Salis, Simona; Bruno, Irene; Ventura, Alessandro (Arch Dis Child, 2016)

Non-additive genome-wide association scan reveals a new gene associated with habitual coffee consumption. - Pirastu, Nicola; Kooyman, Maarten; Robino, Antonietta; van der Spek, Ashley; Navarini, Luciano; Amin, Najaf; Karssen, Lennart C; van Duijn, Cornelia M; Gasparini, Paolo (Sci Rep, 2016)
Coffee is one of the most consumed beverages world-wide and one of the primary sources of caffeine intake. Given its important health and economic impact, the underlying genetics of its consumption has been widely studied. Despite these efforts, much has still to be uncovered. In particular, the use of non-additive genetic models may uncover new information about the genetic variants driving coffee consumption. We have conducted a genome-wide association study in two Italian populations using additive, recessive and dominant models for analysis. This has uncovered a significant association in the PDSS2 gene under the recessive model that has been replicated in an independent cohort from the Netherlands (ERF). The identified gene has been shown to negatively regulate the expression of the caffeine metabolism genes and can thus be linked to coffee consumption. Further bioinformatics analysis of eQTL and histone marks from Roadmap data has evidenced a possible role of the identified SNPs in regulating PDSS2 gene expression through enhancers present in its intron. Our results highlight a novel gene which regulates coffee consumption by regulating the expression of the genes linked to caffeine metabolism. Further studies will be needed to clarify the biological mechanism which links PDSS2 and coffee consumption.

Nonmuscle Myosin Heavy Chain IIA Mutation Predicts Severity and Progression of Sensorineural Hearing Loss in Patients With MYH9-Related Disease. - Verver, Eva J J; Topsakal, Vedat; Kunst, Henricus P M; Huygen, Patrick L M; Heller, Paula G; Pujol-Moix, Núria; Savoia, Anna; Benazzo, Marco; Fierro, Tiziana; Grolman, Wilko; Gresele, Paolo; Pecci, Alessandro (Ear Hear, 2016)
OBJECTIVES: MYH9-related disease (MYH9-RD) is an autosomal- dominant disorder deriving from mutations in MYH9, the gene for the nonmuscle myosin heavy chain (NMMHC)-IIA. MYH9-RD has a complex phenotype including congenital features, such as thrombocytopenia, and noncongenital manifestations, namely sensorineural hearing loss (SNHL), nephropathy, cataract, and liver abnormalities. The disease is caused by a limited number of mutations affecting different regions of the NMMHC-IIA protein. SNHL is the most frequent noncongenital manifestation of MYH9-RD. However, only scarce and anecdotal information is currently available about the clinical and audiometric features of SNHL of MYH9-RD subjects. The objective of this study was to investigate the severity and propensity for progression of SNHL in a large series of MYH9-RD patients in relation to the causative NMMHC-IIA mutations. DESIGN: This study included the consecutive patients diagnosed with MYH9-RD between July 2007 and March 2012 at four participating institutions. A total of 115 audiograms were analyzed from 63 patients belonging to 45 unrelated families with different NMMHC-IIA mutations. Cross-sectional analyses of audiograms were performed. Regression analysis was performed, and age-related typical audiograms (ARTAs) were derived to characterize the type of SNHL associated with different mutations. RESULTS: Severity of SNHL appeared to depend on the specific NMMHC-IIA mutation. Patients carrying substitutions at the residue R702 located in the short functional SH1 helix had the most severe degree of SNHL, whereas patients with the p.E1841K substitution in the coiled-coil region or mutations at the nonhelical tailpiece presented a mild degree of SNHL even at advanced age. The authors also disclosed the effects of different amino acid changes at the same residue: for instance, individuals with the p.R702C mutation had more severe SNHL than those with the p.R702H mutation, and the p.R1165L substitution was associated with a higher degree of hearing loss than the p.R1165C. In general, mild SNHL was associated with a fairly flat audiogram configuration, whereas severe SNHL correlated with downsloping configurations. ARTA plots showed that the most progressive type of SNHL was associated with the p.R702C, the p.R702H, and the p.R1165L substitutions, whereas the p.R1165C mutation correlated with a milder, nonprogressive type of SNHL than the p.R1165L. ARTA for the p.E1841K mutation demonstrated a mild degree of SNHL with only mild progression, whereas the ARTA for the mutations at the nonhelical tailpiece did not show any substantial progression. CONCLUSIONS: These data provide useful tools to predict the progression and the expected degree of severity of SNHL in individual MYH9-RD patients, which is especially relevant in young patients. Consequences in clinical practice are important not only for appropriate patient counseling but also for development of customized, genotype-driven clinical management. The authors recently reported that cochlear implantation has a good outcome in MYH9-RD patients; thus, stricter follow-up and earlier intervention are recommended for patients with unfavorable genotypes.

Pitfalls and promises in FTIR spectromicroscopy analyses to monitor iron-mediated DNA damage in sperm. - Pascolo, Lorella; Bedolla, Diana E; Vaccari, Lisa; Venturin, Irene; Cammisuli, Francesca; Gianoncelli, Alessandra; Mitri, Elisa; Giolo, Elena; Luppi, Stefania; Martinelli, Monica; Zweyer, Marina; Ricci, Giuseppe (Reprod Toxicol, 2016)
Many drugs, chemicals, and environmental factors can impair sperm functionality by inducing DNA damage, one of the important causes of reduced fertility potential. The use of vibrational spectromicroscopy represents a promising approach for monitoring DNA integrity in sperm, although some limitations exist, depending from the experimental conditions. Here, we report that when using FTIR spectromicroscopy to reveal oxidative stress mediated by Fenton's reaction on hydrated sperm samples, DNA damage interpretation is partially compromised by unexpected cell surface precipitates. The precipitates give a broad band in the 1150-1000cm(-1) infrared region, which partially covers one of the signatures of DNA (phosphate stretching bands), and are detected as iron and oxygen containing material when using XRF spectroscopy. On the other hand, the analyses further support the potential of FTIR spectromicroscopy to reveal cellular oxidative damage events such as lipid peroxidation, protein misfolding and aggregations, as well as DNA strain breaks.

Putative modifier genes in mevalonate kinase deficiency. - Marcuzzi, Annalisa; Vozzi, Diego; Girardelli, Martina; Tricarico, Paola Maura; Knowles, Alessandra; Crovella, Sergio; Vuch, Josef; Tommasini, Alberto; Piscianz, Elisa; Bianco, Anna Monica (Mol Med Rep, 2016)
Mevalonate kinase deficiency (MKD) is an autosomal recessive auto‑inflammatory disease, caused by impairment of the mevalonate pathway. Although the molecular mechanism remains to be elucidated, there is clinical evidence suggesting that other regulatory genes may be involved in determining the phenotype. The identification of novel target genes may explain non‑homogeneous genotype‑phenotype correlations, and provide evidence in support of the hypothesis that novel regulatory genes predispose or amplify deregulation of the mevalonate pathway in this orphan disease. In the present study, DNA samples were obtained from five patients with MKD, which were then analyzed using whole exome sequencing. A missense variation in the PEX11γ gene was observed in homozygosis in P2, possibly correlating with visual blurring. The UNG rare gene variant was detected in homozygosis in P5, without correlating with a specific clinical phenotype. A number of other variants were found in the five analyzed DNA samples from the MKD patients, however no correlation with the phenotype was established. The results of the presents study suggested that further analysis, using next generation sequencing approaches, is required on a larger sample size of patients with MKD, who share the same MVK mutations and exhibit 'extreme' clinical phenotypes. As MVK mutations may be associated with MKD, the identification of specific modifier genes may assist in providing an earlier diagnosis.

A reference panel of 64,976 haplotypes for genotype imputation. - McCarthy, Shane; Das, Sayantan; Kretzschmar, Warren; Delaneau, Olivier; Wood, Andrew R; Teumer, Alexander; Kang, Hyun Min; Fuchsberger, Christian; Danecek, Petr; Sharp, Kevin; Luo, Yang; Sidore, Carlo; et al. (Nat Genet, 2016)
We describe a reference panel of 64,976 human haplotypes at 39,235,157 SNPs constructed using whole-genome sequence data from 20 studies of predominantly European ancestry. Using this resource leads to accurate genotype imputation at minor allele frequencies as low as 0.1% and a large increase in the number of SNPs tested in association studies, and it can help to discover and refine causal loci. We describe remote server resources that allow researchers to carry out imputation and phasing consistently and efficiently.

Somatic, hematologic phenotype, long-term outcome, and effect of hematopoietic stem cell transplantation. An analysis of 97 Fanconi anemia patients from the Italian national database on behalf of the Marrow Failure Study Group of the AIEOP (Italian Associ - Svahn, Johanna; Bagnasco, Francesca; Cappelli, Enrico; Onofrillo, Daniela; Caruso, Silvia; Corsolini, Fabio; De Rocco, Daniela; Savoia, Anna; Longoni, Daniela; Pillon, Marta; Marra, Nicoletta; Ramenghi, Ugo; et al. (Am J Hematol, 2016)
We analyzed 97 Fanconi anemia patients from a clinic/biological database for genotype, somatic, and hematologic phenotype, adverse hematological events, solid tumors, and treatment. Seventy-two patients belonged to complementation group A. Eighty percent of patients presented with mild/moderate somatic phenotype and most with cytopenia. No correlation was seen between somatic/hematologic phenotype and number of missense mutations of FANCA alleles. Over follow-up, 33% of patients improved or maintained mild/moderate cytopenia or normal blood count, whereas remaining worsened cytopenia. Eleven patients developed a hematological adverse event (MDS, AML, pathological cytogenetics) and three developed solid tumors. 10 years cumulative risk of death of the whole cohort was 25.6% with median follow-up 5.8 years. In patients eligible to hematopoietic stem cell transplantation because of moderate cytopenia, mortality was significantly higher in subjects transplanted from matched unrelated donor over nontransplanted subjects, whereas there was no significant difference between matched sibling donor transplants and nontransplanted patients. In patients eligible to transplant because of severe cytopenia and clonal disease, mortality risk was not significantly different in transplanted from matched unrelated versus matched sibling donor versus nontransplanted subjects. The decision to transplant should rely on various elements including, type of donor, HLA matching, patient comorbidities, impairment, and clonal evolution of hematopoiesis. Am. J. Hematol. 91:666-671, 2016. © 2016 Wiley Periodicals, Inc.

A Spotted Bone. - Perin, Silvia; Rabach, Ingrid; Pascolo, Paola; Dibello, Daniela; Ventura, Alessandro (J Pediatr, 2016)

Thalidomide for inflammatory bowel disease: Systematic review. - Bramuzzo, Matteo; Ventura, Alessandro; Martelossi, Stefano; Lazzerini, Marzia (Medicine (Baltimore), 2016)
BACKGROUND: Thalidomide is an immunomodulatory drug used in the experimental treatment of refractory Crohn disease and ulcerative colitis. We aimed to review the existing evidence on the efficacy and safety of thalidomide in the treatment of inflammatory bowel diseases. METHODS: CENTRAL, MEDLINE, LILACS, POPLINE, CINHAL, and Web of Science were searched in March 2016. Manual search included conference and reference lists. All types of studies, except single case reports, were included. Outcomes evaluated were: induction of remission; maintenance of remission; steroid reduction; effect on penetrating Crohn disease; endoscopic remission; adverse events. RESULTS: The research strategies retrieved 722 papers. Two randomized controlled trials and 29 uncontrolled studies for a total of 489 patients matched the inclusion criteria. Thalidomide induced a clinical response in 296/427 (69.3%) patients. Clinical remission was achieved in 220/427 (51.5%) cases. Maintenance of remission was reported in 128/160 (80.0%) patients at 6 months and in 96/133 (72.2%) at 12 months. Reduction in steroid dosage was reported in 109/152 (71.7%) patients. Fistulas improved in 49/81 (60.5%) cases and closed in 28/81 (34.6%). Endoscopic improvement was observed in 46/66 (69.7%) and complete mucosal healing in 35/66 (53.0%) patients. Cumulative incidence of total adverse events and of those leading to drug suspension was 75.6 and 19.7/1000 patient-months, respectively. Neurological disturbances accounted for 341/530 (64.3%) adverse events and were the most frequent cause of drug withdrawal. CONCLUSION: Existing evidence suggests that thalidomide may be a valid treatment option for patients with inflammatory bowel diseases refractory to other first- and second-line treatments.

Thiopurine Biotransformation and Pharmacological Effects: Contribution of Oxidative Stress. - Pelin, Marco; De Iudicibus, Sara; Londero, Margherita; Spizzo, Riccardo; Dei Rossi, Sveva; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana; Stocco, Gabriele (Curr Drug Metab, 2016)
BACKGROUND: Thiopurine antimetabolites are important agents for the treatment of severe diseases, such as acute lymphoblastic leukemia and inflammatory bowel disease. Their pharmacological actions depend on biotransformation into active thioguanine-nucleotides; intracellular metabolism is mediated by enzymes of the salvage pathway of nucleotide synthesis and relies on polymorphic enzymes involved in thiopurines' catabolism such as thiopurine-S-methyl transferase. Given the enzymes involved in thiopurines' metabolism, it is reasonable to hypothesize that these drugs are able to induce significant oxidative stress conditions, possibly altering their pharmacological activity. METHODS: A systemic search of peer-reviewed scientific literature in bibliographic databases has been carried out. Both clinical and preclinical studies as well as mechanistic studies have been included to shed light on the role of oxidative stress in thiopurines' pharmacological effects. RESULTS: Sixty-nine papers were included in our review, allowing us to review the contribution of oxidative stress in the pharmacological action of thiopurines. Thiopurines are catabolized in the liver by xanthine oxidase, with potential production of reactive oxidative species and azathioprine is converted into mercaptopurine by a reaction with reduced glutathione, that, in some tissues, may be facilitated by glutathione- S-transferase (GST). A clear role of GSTM1 in modulating azathioprine cytotoxicity, with a close dependency on superoxide anion production, has been recently demonstrated. Interestingly, recent genome-wide association studies have shown that, for both azathioprine in inflammatory bowel disease and mercaptopurine in acute lymphoblastic leukemia, treatment effects on patients' white blood cells are related to variants of a gene, NUDT15, involved in biotransformation of oxidated nucleotides. CONCLUSIONS: Basing on previous evidences published in literature, oxidative stress may contribute to thiopurine effects in significant ways that, however, are still not completely elucidated.

Thromboprophilaxis in neurological conditions in pregnancy. A clinical dilemma or a methods dilemma? - Parco, Sergio; Vascotto, Fulvia; Simeone, Roberto (Minerva Ginecol, 2016)

Time to optimise and enforce training in interpretation of intrapartum cardiotocograph. - Ugwumadu, A; Steer, P; Parer, B; Carbone, B; Vayssiere, C; Maso, G; Arulkumaran, S (BJOG, 2016)

Tracking of the origin of recurrent mutations of the BRCA1 and BRCA2 genes in the North-East of Italy and improved mutation analysis strategy. - Cini, Giulia; Mezzavilla, Massimo; Della Puppa, Lara; Cupelli, Elisa; Fornasin, Alessio; D'Elia, Angela Valentina; Dolcetti, Riccardo; Damante, Giuseppe; Bertok, Sara; Miolo, Gianmaria; Maestro, Roberta; de Paoli, Paolo; et al. (BMC Med Genet, 2016)
BACKGROUND: About 20 % of hereditary breast cancers are caused by mutations in BRCA1 and BRCA2 genes. Since BRCA1 and BRCA2 mutations may be spread throughout the gene, genetic testing is usually performed by direct sequencing of entire coding regions. In some populations, especially if relatively isolated, a few number of recurrent mutations is reported, sometimes caused by founder effect. METHODS: BRCA1 and BRCA2 screening for mutations was carried out on 1114 breast and/or ovarian cancer patients complying with the eligibility criteria for BRCA testing. Haplotype analysis was performed on the probands carrying recurrent mutations and their relatives, using two sets of microsatellite markers covering the BRCA1 (D17S588, D17S806, D17S902, D17S1325, D17S855, D17S1328, D17S800, and D17S250) and BRCA2 (D13S220, D13S267, D13S171, D13S1701, D13S1698, D13S260, D13S290, D13S1246) loci. The DMLE + 2.2 software was used to estimate the age of BRCA1 c.676delT and BRCA2 c.7806-2A > G. A multiplex PCR and two different primer extension assays were optimized and used for genotyping the recurrent mutations of the two genes. RESULTS: In the time frame of almost 20 years of genetic testing, we have found that five BRCA1 and three BRCA2 mutations are recurrent in a substantial subset of carriers from North-East Italy and neighboring Istria, where they represent more than 50 % of all mutations. Microsatellite analyses identified a common haplotype of different length for each mutation. Age estimation of BRCA1 c.676delT and BRCA2 c.7806-2A > G mutations revealed that they arose in the Friuli Venezia Giulia area about 86 and 94 generations ago, respectively. Suggestion of an association between BRCA2 c.7806-2A > G and risk of breast cancer in males has emerged. Finally, we developed a simple and efficient pre-screening test, performing an in-house primer extension SNaPshot® assay for the rapid identification of the eight recurrent mutations. CONCLUSIONS: Proofs of common ancestry has been obtained for the eight recurrent mutations. The observed genotype-phenotype correlation and the proposed rapid mutation detection strategy could improve the clinical management of breast and ovarian patients in North-East of Italy and neighboring geographic areas.
Keywords: Adult; Aged; Alleles; BRCA1 Protein; BRCA2 Protein; Breast Neoplasms; Case-Control Studies; DNA Mutational Analysis; Female; Founder Effect; Genetic Testing; Genome-Wide Association Study; Genotyping Techniques; Haplotypes; Humans; Italy; Male; Microsatellite Repeats; Middle Aged; Mutation; Ovarian Neoplasms; Young Adult

5-Aminoimidazole-4-carboxamide ribonucleotide-transformylase and inosine-triphosphate-pyrophosphatase genes variants predict remission rate during methotrexate therapy in patients with juvenile idiopathic arthritis. - Pastore, Serena; Stocco, Gabriele; Moressa, Valentina; Zandonà, Luigi; Favretto, Diego; Malusà, Noelia; Decorti, Giuliana; Lepore, Loredana; Ventura, Alessandro (Rheumatol Int, 2015)
For children with juvenile idiopathic arthritis (JIA) who fail to respond to methotrexate, the delay in identifying the optimal treatment at an early stage of disease can lead to long-term joint damage. Recent studies indicate that relevant variants to predict methotrexate response in JIA are those in 5-aminoimidazole-4-carboxamide ribonucleotide-transformylase (ATIC), inosine-triphosphate-pyrophosphatase (ITPA) and solute-liquid-carrier-19A1 genes. The purpose of the study was, therefore, to explore the role of these candidate genetic factors on methotrexate response in an Italian cohort of children with JIA. Clinical response to methotrexate was evaluated as clinical remission stable for a 6-month period, as ACRPed score and as change in Juvenile Arthritis Disease score. The most relevant SNPs for each gene considered were assayed on patients' DNA. ITPA activity was measured in patients' erythrocytes. Sixty-nine patients with JIA were analyzed: 52.2 % responded to therapy (ACRPed70 score), while 37.7 % reached clinical remission stable for 6 months. ATIC rs2372536 GG genotype was associated with improved clinical remission (adjusted p value = 0.0090). For ITPA, rs1127354 A variant was associated with reduced clinical remission: (adjusted p value = 0.028); this association was present even for patients with wild-type ITPA and low ITPA activity. These preliminary results indicate that genotyping of ATIC rs2372536 and ITPA rs1127354 variants or measuring ITPA activity could be useful to predict methotrexate response in children with JIA after validation by further prospective studies on a larger patient cohort.

Acute pseudotumoral hemicerebellitis in a child: a rare and distinct entity? - Alberini, Elena; Vellante, Valerio; Zennaro, Floriana; Calligaris, Lorenzo; Barbi, Egidio; Carrozzi, Marco; Devescovi, Raffaella (J Child Neurol, 2015)
A pseudotumoral presentation of acute hemicerebellitis is rare in pediatric age. The authors report a new single case study of a 7-year-old child with pseudotumoral unilateral cerebellitis mimicking an intracranial tumor, which clinically presented itself with signs of intracranial hypertension and mild contralateral hemiparesis, completely recovered after anti-inflammatory therapy. Brain magnetic resonance imaging (MRI) was essential for the differential diagnosis between inflammatory and neoplastic processes. The literature highlighting specific clues about pseudotumoral hemicerebellitis as a distinct clinical and radiological entity is reviewed.
Keywords: Brain; Cerebellar Diseases; Child; Diagnosis, Differential; Encephalitis; Humans; Magnetic Resonance Imaging; Male

An adolescent with an altered state of mind. - Naviglio, Samuele; Papanti, Duccio; Moressa, Valentina; Ventura, Alessandro (BMJ, 2015)
Keywords: Adolescent; Cannabinoids; Designer Drugs; Hallucinations; Humans; Male; Substance-Related Disorders

Alendronate, a double-edged sword acting in the mevalonate pathway. - Tricarico, Paola Maura; Girardelli, Martina; Kleiner, Giulio; Knowles, Alessandra; Valencic, Erica; Crovella, Sergio; Marcuzzi, Annalisa (Mol Med Rep, 2015)
Aminobisphosphonate aledronate is a compound commonly used clinically for the treatment of osteoporosis and other bone diseases, as a result of it preventing bone resorption. However, in previous years it has also been used to obtain cellular and animal models of a rare genetic disorder termed Mevalonate Kinase Deficiency (MKD). MKD is caused by mutations affecting the mevalonate kinase enzyme, in the cholesterol pathway and alendronate can be used to biochemically mimic the genetic defect as it inhibits farnesyl pyrophosphate synthase in the same pathway. Despite evidence in favor of the inhibition exerted on the mevalonate pathway, there is at least one clinical case of MKD in which alendronate improved not only skeletal and bone fractures, as expected, but also MKD clinical features. Based on this finding, the present study assessed the anti‑inflammatory properties of this aminobisphosphonate in vitro. No anti‑inflammatory effects of alendronate were observed in the in vitro experiments. Since MKD lacks specific treatments, these results may assist scientists and physicians in making the decision as to the most suitable choice of therapeutic compounds for this neglected disease.

Altered germinal center reaction and abnormal B cell peripheral maturation in PI3KR1-mutated patients presenting with HIGM-like phenotype. - Lougaris, Vassilios; Faletra, Flavio; Lanzi, Gaetana; Vozzi, Diego; Marcuzzi, Annalisa; Valencic, Erica; Piscianz, Elisa; Bianco, AnnaMonica; Girardelli, Martina; Baronio, Manuela; Loganes, Claudia; Fasth, Anders; et al. (Clin Immunol, 2015)
Keywords: B-Lymphocytes; Child, Preschool; Female; Germinal Center; Humans; Hyper-IgM Immunodeficiency Syndrome; Infant; Male; Mutation; Phenotype; Phosphatidylinositol 3-Kinases; RNA Splice Sites; Sequence Analysis, DNA

Applications of nanoparticles in cancer medicine and beyond: optical and multimodal in vivo imaging, tissue targeting and drug delivery. - Biffi, Stefania; Voltan, Rebecca; Rampazzo, Enrico; Prodi, Luca; Zauli, Giorgio; Secchiero, Paola (Expert Opin Drug Deliv, 2015)
INTRODUCTION: Nanotechnology has opened up the way to the engineering of new organized materials endowed with improved performances. In the past decade, engineered nanoparticles (NPs) have been progressively implemented by exploiting synthetic strategies that yield complex materials capable of performing functions with applications also in medicine. Indeed, in the field of 'nanomedicine' it has been explored the possibility to design multifunctional nanosystems, characterized by high analytical performances and stability, low toxicity and specificity towards a given cell target. Area covered: In this review article, we summarize the advances in the engineering of NPs for biomedical applications, from optical imaging (OI) to multimodal OI and targeted drug delivery. For this purpose, we will provide some examples of how investigations in nanomedicine can support preclinical and clinical research generating innovative diagnostic and therapeutic strategies in oncology. Expert opinion: The progressive breakthroughs in nanomedicine have supported the development of multifunctional and multimodal NPs. In particular, NPs are significantly impacting the diagnostic and therapeutic strategies since they allow the development of: NP-based OI probes containing more than one modality-specific contrast agent; surface functionalized NPs for specific 'molecular recognition'. Therefore, the design and characterization of innovative NP-based systems/devices have great applicative potential into the medical field.

Bedside diagnosis of two major clinical phenotypes of hypertensive disorders of pregnancy. - Ferrazzi, E; Zullino, S; Stampalija, T; Vener, C; Cavoretto, P; Gervasi, M T; Vergani, P; Mecacci, F; Marozio, L; Oggè, G; Algeri, P; Ruffatti, A; et al. (Ultrasound Obstet Gynecol, 2015)
OBJECTIVE: We hypothesized that fetal abdominal circumference (AC) and Uterine Doppler Pulsatility Index (UtA-PI) could select two homogenous subgroups of women affected by hypertensive disorders of pregnancy (HDP), characterized by the coexistence of maternal hypertension with and without IUGR. METHODS: This is a multicentre study that studied cases affected by HDP in whom fetal AC and UtA-PI had been measured at admission to feto Maternal Medicine Units. Maternal characteristics, pregnancy complications and outcome were recorded. These data allowed us to model the characteristics of fetal growth in cases affected by HDP, and to design a composite index for risk factors of maternal metabolic syndrome (rfMMS) and composite index of severity for maternal organ and/or function damage (OFD). RESULTS: Measurements of fetal AC and UtA-PI allowed us to define a group of HDP with AGA fetuses (HDP-AGAf) diagnosed by normal fetal AC and a UtA-PI (#205), and a group of HDP with IUGR fetuses (HDP-IUGR) diagnosed by fetal AC <5(th) centile and UtA-PI >95(th) centile (#124). Curves fitted to birth-weight of the two groups were significantly different, and gestational age at admission for HDP, <34 or ≥34, had no effect on their models. When birth-weight was expressed as standard deviation score (SDS) of local reference charts, the average SDS (±standard error) corresponded to the 6(th) and 48(th) centile respectively. The risk of developing HDP-AGAf was significantly associated with risk factors for maternal metabolic syndrome (OR= 2.79;CI 1.57-4.97), independently of gestational age. The same risk factors yielded a non significant ORs of developing late onset HDP. Women with HDP-IUGR proved to be associated with the worst clinical outcomes. CONCLUSIONS: This study adds genuine new data based on simple prenatal bedside examinations, that might help to differentiate HDP with IUGR, from HDP with AGA fetuses, associated with different fetal growth patterns and different risk factors, not affected by gestational age at onset of the disease.

"Blaschkoid dyspigmentation" in a child: don't forget fibroblast chromosomal analysis. - Gortani, Giulia; Faletra, Flavio; Bruno, Irene; Berti, Irene; Ventura, Alessandro (J Pediatr, 2015)
Keywords: Abnormalities, Multiple; Child, Preschool; Chromosomes; DNA; Female; Fibroblasts; Humans; Phenotype; Pigmentation Disorders

A brain and heart connection: X-linked periventricular heterotopia. - Naviglio, Samuele; Bruno, Irene; Zanus, Caterina; Faletra, Flavio; Ventura, Alessandro (J Pediatr, 2015)
Keywords: Adolescent; Brain; Diagnosis, Differential; DNA Mutational Analysis; Epilepsy; Female; Filamins; Humans; Magnetic Resonance Imaging; Mutation; Periventricular Nodular Heterotopia

A case of Rubinstein-Taybi syndrome associated with growth hormone deficiency in childhood. - Tornese, Gianluca; Marzuillo, Pierluigi; Pellegrin, Maria Chiara; Germani, Claudio; Faleschini, Elena; Zennaro, Floriana; Grandone, Anna; Miraglia Del Giudice, Emanuele; Perrone, Laura; Ventura, Alessandro (Clin Endocrinol (Oxf), 2015)

Coeliac disease in the ERA of the new ESPGHAN and BSPGHAN guidelines: a prospective cohort study. - Benelli, Elisa; Carrato, Valentina; Martelossi, Stefano; Ronfani, Luca; Not, Tarcisio; Ventura, Alessandro (Arch Dis Child, 2015)
OBJECTIVE: To evaluate the consequences of the last European Society of Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) and British Society of Paediatric Gastroenterology, Hepatology and Nutrition (BSPGHAN) guidelines for the diagnosis of coeliac disease (CD) by means of a prospective study. DESIGN: Prospective cohort study. SETTING: Institute for Maternal and Child Health IRCCS Burlo Garofolo (Trieste, Italy). PATIENTS: Children diagnosed with CD without a duodenal biopsy (group 1), following the last ESPGHAN and BSPGHAN guidelines, and children diagnosed with a duodenal biopsy, matched for sex, age and year of diagnosis (group 2), were prospectively enrolled over a 3-year period. All patients were put on a gluten-free diet (GFD) and were followed up for clinical conditions and laboratory testing at 6 months every year since diagnosis (median follow up: 1.9 years). OUTCOME MEASURES: Resolution of symptoms, body mass index, laboratory testing (haemoglobin, anti-transglutaminase IgA), adherence to a GFD, quality of life, and supplementary post-diagnosis medical consultations. RESULTS: 51 out of 468 (11%) patients were diagnosed without a duodenal biopsy (group 1; median age 2.1 years) and matched to 92 patients diagnosed with a biopsy (group 2; median age 2.4 years). At the end of follow-up the two groups were statistically comparable in terms of clinical and nutritional status, anti-transglutaminase IgA antibody titres, quality of life, adherence to a GFD, and number of supplementary medical consultations. CONCLUSIONS: On the basis of this prospective study, diagnosis of CD can be reliably performed without a duodenal biopsy in approximately 11% of cases. At least during a medium-term follow-up, this approach has no negative consequences relating to clinical remission, adherence to diet, and quality of life of children with CD.

Combined circulating epigenetic markers to improve mesothelin performance in the diagnosis of malignant mesothelioma. - Santarelli, Lory; Staffolani, Sara; Strafella, Elisabetta; Nocchi, Linda; Manzella, Nicola; Grossi, Paola; Bracci, Massimo; Pignotti, Elettra; Alleva, Renata; Borghi, Battista; Pompili, Cecilia; Sabbatini, Armando; et al. (Lung Cancer, 2015)
OBJECTIVES: Malignant mesothelioma (MM) is a highly aggressive tumor with poor prognosis. A major challenge is the development and application of early and highly reliable diagnostic marker(s). Serum biomarkers, such as 'soluble mesothelin-related proteins' (SMRPs), is the most studied and frequently used in MM. However, the low sensitivity of SMRPs for early MM limits its value; therefore, additional biomarkers are required. In this study, two epigenetically regulated markers in MM (microRNA-126, miR-126, and methylated thrombomodulin promoter, Met-TM) were combined with SMRPs and evaluated as a potential strategy to detect MM at an early stage. MATERIALS AND METHODS: A total of 188 subjects, including 45 MM patients, 99 asbestos-exposed subjects, and 44 healthy controls were prospectively enrolled, serum samples collected, and serum levels of SMRPs, miR-126 and Met-TM evaluated. Logistic regression analysis was performed to evaluate the diagnostic value of the three biomarkers. Using this approach, the performance of the '3-biomarker classifier' was tested by calculating the overall probability score of the MM and control samples, respectively, and the ROC curve was generated. RESULTS AND CONCLUSION: The combination of the three biomarkers was the best predictor to differentiate MM patients from asbestos-exposed subjects and healthy controls. The accuracy and cancer specificity was confirmed in a second validation cohort and lung cancer population. We propose that the combination of the two epigenetic biomarkers with SMRPs as a diagnosis for early MM overcomes the limitations of using SMRPs alone.

Connexin 26 variant carriers have a better gastrointestinal health: is this the heterozygote advantage? - Vuckovic, Dragana; Dallapiccola, Bruno; Franzè, Annamaria; Mauri, Lucia; Perrone, Maria Dolores; Gasparini, Paolo (Eur J Hum Genet, 2015)

Design, Synthesis, and Biological Characterization of Novel Mitochondria Targeted Dichloroacetate-Loaded Compounds with Antileukemic Activity. - Trapella, Claudio; Voltan, Rebecca; Melloni, Elisabetta; Tisato, Veronica; Celeghini, Claudio; Bianco, Sara; Fantinati, Anna; Salvadori, Severo; Guerrini, Remo; Secchiero, Paola; Zauli, Giorgio (J Med Chem, 2015)
The mitochondrial kinase inhibitor dichloroacetate (DCA) has recently received attention in oncology due to its ability to target glycolysis. However, DCA molecule exhibits poor bioavailability and cellular uptake with limited ability to reach its target mitochondria. To overcome these biases, we have synthesized novel DCA-loaded compounds. The selection of the most promising therapeutic molecule was evaluated by combining in vitro assays, to test the antitumoral potential on leukemic cells, and a preliminary characterization of the molecule stability in vivo, in mice. Among the newly synthesized compounds, we have selected the multiple DCA-loaded compound 10, characterized by a tertiary amine scaffold, because it exhibited enhanced (>30-fold) in vitro antitumor activity with respect to DCA and increased in vivo stability. On the basis of these results, we believe that compound 10 should be considered for further preclinical evaluations for the treatment of cancers and/or other diseases characterized by altered metabolic origin.

Diagnostic criteria currently proposed for "ictal epileptic headache": Perspectives on strengths, weaknesses and pitfalls. - Parisi, Pasquale; Verrotti, Alberto; Costa, Paola; Striano, Pasquale; Zanus, Caterina; Carrozzi, Marco; Raucci, Umberto; Villa, Maria Pia; Belcastro, Vincenzo (Seizure, 2015)
PURPOSE: When we published the diagnostic criteria for "ictal epileptic headache" in 2012, we deliberately and consciously chose to adopt restrictive criteria that probably underestimate the phenomenon, rather than spread panic among patients and physicians who are reluctant to accept this entity. METHODS: Here we discuss four intriguing clinical cases to highlight why we believe, to this day, that it is necessary to follow these restrictive diagnostic criteria. CONCLUSIONS: EEG is not recommended as a routine examination for children diagnosed with headache, but it is mandatory and must be carried out promptly in cases of prolonged headache that does not respond to antimigraine drugs, if epilepsy is suspected or has been diagnosed previously. This is not a marginal or irrelevant question because possible isolated, non-motor, ictal manifestations should be taken into account before declaring that an epileptic patient is "seizure free" so as to ensure that any decision taken to suspend anticonvulsant therapy is safe.

Different presentations of mevalonate kinase deficiency: a case series. - De Pieri, Carlo; Taddio, Andrea; Insalaco, Antonella; Barbi, Egidio; Lepore, Loredana; Ventura, Alessandro; Tommasini, Alberto (Clin Exp Rheumatol, 2015)
OBJECTIVES: We aimed to raise awareness among paediatricians and physicians about this often misunderstood condition. METHODS: We discussed the clinical profiles associated with late or wrong diagnosis of mevalonate kinase deficency (MKD) in a single centre case series. RESULTS: We analysed the most common challenges and pitfalls that a clinician might face during the diagnostic process. Five main clinical profiles were characterised. CONCLUSIONS: We propose a new perspective on MKD, suggesting that the presentation of this disease can vary from patient to patient.
Keywords: Age Factors; Bacterial Infections; Child; Child, Preschool; Diagnosis, Differential; Diagnostic Errors; Female; Genetic Predisposition to Disease; Humans; Infant; Inflammatory Bowel Diseases; Male; Mevalonate Kinase Deficiency; Phenotype; Predictive Value of Tests; Recurrence; Risk Factors; Sepsis; Vasculitis; Young Adult

Differential protein folding and chemical changes in lung tissues exposed to asbestos or particulates. - Pascolo, Lorella; Borelli, Violetta; Canzonieri, Vincenzo; Gianoncelli, Alessandra; Birarda, Giovanni; Bedolla, Diana E; Salomè, Murielle; Vaccari, Lisa; Calligaro, Carla; Cotte, Marine; Hesse, Bernhard; Luisi, Fernando; et al. (Sci Rep, 2015)
Environmental and occupational inhalants may induce a large number of pulmonary diseases, with asbestos exposure being the most risky. The mechanisms are clearly related to chemical composition and physical and surface properties of materials. A combination of X-ray fluorescence (μXRF) and Fourier Transform InfraRed (μFTIR) microscopy was used to chemically characterize and compare asbestos bodies versus environmental particulates (anthracosis) in lung tissues from asbestos exposed and control patients. μXRF analyses revealed heterogeneously aggregated particles in the anthracotic structures, containing mainly Si, K, Al and Fe. Both asbestos and particulates alter lung iron homeostasis, with a more marked effect in asbestos exposure. μFTIR analyses revealed abundant proteins on asbestos bodies but not on anthracotic particles. Most importantly, the analyses demonstrated that the asbestos coating proteins contain high levels of β-sheet structures. The occurrence of conformational changes in the proteic component of the asbestos coating provides new insights into long-term asbestos effects.

Directional dominance on stature and cognition in diverse human populations. - Joshi, Peter K; Esko, Tõnu; Mattsson, Hannele; Eklund, Niina; Gandin, Ilaria; Nutile, Teresa; Jackson, Anne U; Schurmann, Claudia; Smith, Albert V; Zhang, Weihua; Okada, Yukinori; Stančáková, Alena; et al. (Nature, 2015)
Homozygosity has long been associated with rare, often devastating, Mendelian disorders, and Darwin was one of the first to recognize that inbreeding reduces evolutionary fitness. However, the effect of the more distant parental relatedness that is common in modern human populations is less well understood. Genomic data now allow us to investigate the effects of homozygosity on traits of public health importance by observing contiguous homozygous segments (runs of homozygosity), which are inferred to be homozygous along their complete length. Given the low levels of genome-wide homozygosity prevalent in most human populations, information is required on very large numbers of people to provide sufficient power. Here we use runs of homozygosity to study 16 health-related quantitative traits in 354,224 individuals from 102 cohorts, and find statistically significant associations between summed runs of homozygosity and four complex traits: height, forced expiratory lung volume in one second, general cognitive ability and educational attainment (P < 1 × 10(-300), 2.1 × 10(-6), 2.5 × 10(-10) and 1.8 × 10(-10), respectively). In each case, increased homozygosity was associated with decreased trait value, equivalent to the offspring of first cousins being 1.2 cm shorter and having 10 months' less education. Similar effect sizes were found across four continental groups and populations with different degrees of genome-wide homozygosity, providing evidence that homozygosity, rather than confounding, directly contributes to phenotypic variance. Contrary to earlier reports in substantially smaller samples, no evidence was seen of an influence of genome-wide homozygosity on blood pressure and low density lipoprotein cholesterol, or ten other cardio-metabolic traits. Since directional dominance is predicted for traits under directional evolutionary selection, this study provides evidence that increased stature and cognitive function have been positively selected in human evolution, whereas many important risk factors for late-onset complex diseases may not have been.
Keywords: Biological Evolution; Blood Pressure; Body Height; Cholesterol, LDL; Cognition; Cohort Studies; Educational Status; Female; Forced Expiratory Volume; Genome, Human; Homozygote; Humans; Lung Volume Measurements; Male; Phenotype

Dysplastic bone marrow changes during maintenance therapy for acute leukemia. - Chinello, Matteo; Naviglio, Samuele; Shardlow, Alison; Severino, Alessandro; Ventura, Alessandro; Locasciulli, Anna (J Pediatr Hematol Oncol, 2015)
We describe the case of an 8-year-old girl with common precursor B-cell acute lymphoblastic leukemia who presented with severe pancytopenia during maintenance therapy with methotrexate and 6-mercaptopurine. The bone marrow smear showed moderate hypocellularity and trilinear dysplastic changes consistent with a diagnosis of drug toxicity, with no evidence of lymphoblasts. Flow cytometric immunophenotyping was negative for leukemic cells. Blood cell counts normalized after treatment with folinic acid. Maintenance therapy was gradually restarted and she remained well at follow-up visits. Myelotoxicity from methotrexate and 6-mercaptopurine may represent an unpredictable incident during an otherwise uneventful maintenance therapy, and may occur independently of other organ toxicities.
Keywords: 6-Mercaptopurine; Antineoplastic Combined Chemotherapy Protocols; Bone Marrow Diseases; Child; Disease Management; Female; Follow-Up Studies; Humans; Methotrexate; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; Prognosis

Early onset bilateral anterior uveitis preceding a late manifestation of juvenile idiopathic arthritis: a case report. - Parentin, Fulvio; Matarazzo, Lorenza; Lepore, Loredana; Pensiero, Stefano; Ventura, Alessandro (Ocul Immunol Inflamm, 2015)
Keywords: Adolescent; Arthritis, Juvenile; Female; Humans; Time Factors; Tomography, Optical Coherence; Uveitis, Anterior

Effect of Thalidomide on Clinical Remission in Children and Adolescents with Ulcerative Colitis Refractory to Other Immunosuppressives: Pilot Randomized Clinical Trial. - Lazzerini, Marzia; Martelossi, Stefano; Magazzù, Giuseppe; Pellegrino, Salvatore; Lucanto, Maria Cristina; Barabino, Arrigo; Calvi, Angela; Arrigo, Serena; Lionetti, Paolo; Lorusso, Monica; Mangiantini, Francesca; Fontana, Massimo; et al. (Inflamm Bowel Dis, 2015)
BACKGROUND: In a randomized controlled trial, thalidomide has shown to be effective in refractory Crohn's disease in children. This pilot study aimed at evaluating thalidomide in refractory pediatric ulcerative colitis (UC). METHODS: Double-blind, placebo-controlled randomized clinical trial on thalidomide 1.5 to 2.5 mg/kg/day in children with active UC despite multiple immunosuppressive treatments. In an open-label extension, nonresponders to placebo received thalidomide for an additional 8 weeks; all responders were followed up for a minimum of 52 weeks. RESULTS: Twenty-six children with refractory UC were randomized to thalidomide or placebo. Clinical remission at week 8 was achieved by significantly more children treated with thalidomide {10/12 (83.3%) versus 2/11 (18.8%); risk ratio, 4.5 (95% confidence interval [CI], 1.2-16.4); P = 0.005; number needed to treat, 1.5}. Of the nonresponders to placebo who were switched to thalidomide, 8 of 11 (72.7%) subsequently reached remission at week 8 (risk ratio, 4.0 [95% CI, 1.1-14.7]; number needed to treat, 2.45; P = 0.01). Clinical remission in the thalidomide group was 135.0 weeks (95% CI, 32-238), compared with 8.0 weeks (95% CI, 2.4-13.6) in the placebo group (P < 0.0001). Cumulative incidence of severe adverse events was 3.1 per 1000 patient-weeks. Peripheral neuropathy and amenorrhea were the most frequent adverse events. CONCLUSIONS: In this pilot randomized controlled trial on cases of UC refractory to immunosuppressive therapy, thalidomide compared with placebo resulted in improved clinical remission at 8 weeks of treatment and in longer term maintenance of remission. These findings require replication in larger clinical studies evaluating both thalidomide efficacy and safety.

Efficacy of intravenous immunoglobulin therapy in giant cell hepatitis with autoimmune hemolytic anemia: A multicenter study. - Marsalli, Giulia; Nastasio, Silvia; Sciveres, Marco; Calvo, Pier Luigi; Ramenghi, Ugo; Gatti, Simona; Albano, Veronica; Lega, Sara; Ventura, Alessandro; Maggiore, Giuseppe (Clin Res Hepatol Gastroenterol, 2015)
BACKGROUND AND OBJECTIVE: Giant cell hepatitis with autoimmune hemolytic anemia (GCH-AHA) is a rare disease of infancy, of possible autoimmune mechanism with poor prognosis due to its scarce response to immunosuppressive drugs. The aim of this retrospective multicenter study was to evaluate the efficacy and safety of intravenous immunoglobulin (IVIg) treatment in inducing and maintaining remission of the liver disease, in patients with GCH-AHA. METHODS: Seven children with GCH-AHA, four newly diagnosed, and three in relapse, being treated with different therapies, received one to three IVIg infusions (0.5 to 2g/kg) in association with other immunosuppressive drugs. Subsequently five of them received monthly sequential IVIg infusions (mean 13.4, range 7-24). RESULTS: IVIg infusions as first-line therapy associated with prednisone and other immunosuppressive drugs significantly (P=0.04) reduced the aminotransferase activity in all patients and normalized prothombin activity in the only patient with severe liver dysfunction. Sequential monthly IVIg infusions determined a steroid-sparing effect and allowed a complete or partial remission in all patients, although with temporary efficacy, since relapse of the hemolytic anemia and/or of liver disease occurred in all patients. IVIg infusions were associated with mild side effects in two patients. CONCLUSIONS: IVIg infusion can be safely and effectively administered in patients with severe GCH-AHA at diagnosis, or in case of relapse, in association with other immunosuppressive drugs. Repeated IVIg infusions may help maintain remission, however, due to their temporary efficacy, they should not be routinely employed.

Extremely large air distension of the bowel. - Pavan, Matteo; Ventura, Giovanna; Maschio, Massimo; Ventura, Alessandro (Lancet, 2015)
Keywords: Adolescent; Air; Biopsy; Female; Hirschsprung Disease; Humans; Intestine, Large; Rectum

Failure of interferon-γ pre-treated mesenchymal stem cell treatment in a patient with Crohn's disease. - Taddio, Andrea; Tommasini, Alberto; Valencic, Erica; Biagi, Ettore; Decorti, Giuliana; De Iudicibus, Sara; Cuzzoni, Eva; Gaipa, Giuseppe; Badolato, Raffaela; Prandini, Alberto; Biondi, Andrea; Ventura, Alessandro (World J Gastroenterol, 2015)
Mesenchymal stem cells (MSC) are cells of stromal origin which exhibit unlimited self-renewal capacity and pluripotency in vitro. It has recently been observed that MSC may also exert a profound immunosuppressive and anti-inflammatory effect both in vitro and in vivo with consequent potential use in autoimmune disorders. We present the case of a patient suffering from childhood-onset, multidrug resistant and steroid-dependent Crohn's disease who underwent systemic infusions of MSC, which led to a temporary reduction in CCR4, CCR7 and CXCR4 expression by T-cells, and a temporary decrease in switched memory B-cells, In addition, following MSC infusion, lower doses of steroids were needed to inhibit proliferation of the patient's peripheral blood mononuclear cells. Despite these changes, no significant clinical benefit was observed, and the patient required rescue therapy with infliximab and subsequent autologous hematopoietic stem cell transplantation. The results of biological and in vitro observations after MSC use and the clinical effects of infusion are discussed, and a brief description is provided of previous data on MSC-based therapy in autoimmune disorders.

Fever tree revisited: From malaria to autoinflammatory diseases. - Pastore, Serena; Vuch, Josef; Bianco, Anna Monica; Taddio, Andrea; Tommasini, Alberto (World J Clin Pediatr, 2015)
Over the centuries the idea of recurrent fevers has mainly been associated with malaria, but many other fevers, such as typhoid and diphtheria were cause for concern. It is only in recent times, with the more severe forms of fever from infectious origin becoming less frequent or a cause for worry that we started noticing recurrent fevers without any clear infectious cause, being described as having a pathogenesis of autoinflammatory nature. The use of molecular examinations in many cases can allow a diagnosis where the cause is monogenic. In other cases, however the pathogenesis is likely to be multifactorial and the diagnostic-therapeutic approach is strictly clinical. The old fever tree paradigm developed to describe fevers caused by malaria has been revisited here to describe today's periodic fevers from the periodic fever adenitis pharyngitis aphthae syndrome to the more rare autoinflammatory diseases. This model may allow us to place cases that are yet to be identified which are likely to be of multifactorial origin.

Food protein-induced enterocolitis syndrome caused by fish and/or shellfish in Italy. - Miceli Sopo, Stefano; Monaco, Serena; Badina, Laura; Barni, Simona; Longo, Giorgio; Novembre, Elio; Viola, Serena; Monti, Giovanna (Pediatr Allergy Immunol, 2015)
BACKGROUND: The study describes the demographic features, culprit foods, clinical features and outcomes for children presenting with acute fish and/or shellfish food protein-induced enterocolitis syndrome (FPIES) in four Italian paediatric allergy centres. METHODS: A retrospective/prospective study was undertaken. All children diagnosed with fish or shellfish FPIES were enrolled. The diagnosis of FPIES was based on Sicherer's or Miceli Sopo clinical criteria. Skin prick tests (SPT) were performed in all patients, at the time of diagnosis and prior to OFC. RESULTS: Seventy children were enrolled. Mean age at first episode was 14 months (range 6-46 months); mean age at diagnosis was 34 months (range 6-164 months). Sole and cod were the fish most commonly implicated. Fifty-seven of 70 (81%) children had FPIES exclusively to fish, 37 of 57 (65%) children had single-fish FPIES, 20 of 57 (35%) multiple-fish FPIES, nine of 70 (13%) presented adverse reactions exclusively to shellfish, and four of 70 (6%) presented adverse reactions to both fish and shellfish. Only four (5.7%) children presented episodes of acute FPIES with different foods (2 to cow's milk, 1 to egg, 1 to beef); in all cases, onset was prior to that of fish or shellfish FPIES. Fifteen of 70 (21%) children tolerated fish other than the offending fish. Twenty-four of 70 (34%) children achieved tolerance (age range 24-102 months). CONCLUSIONS: The chief peculiarities of acute fish and shellfish FPIES, compared to more frequent cow's milk or soy FPIES, are (i) later age of onset, (ii) longer persistence and (iii) possibility of tolerating fish other than the offending fish. Adverse reactions with shellfish are possible.

Genetic determinants for methotrexate response in juvenile idiopathic arthritis. - Pastore, Serena; Stocco, Gabriele; Favretto, Diego; De Iudicibus, Sara; Taddio, Andrea; d'Adamo, Pio; Malusà, Noelia; Addobbati, Riccardo; Decorti, Giuliana; Lepore, Loredana; Ventura, Alessandro (Front Pharmacol, 2015)
Juvenile idiopathic arthritis (JIAs) is the most common chronic rheumatic disease of childhood and is an important cause of disability. The folic acid analog methotrexate is the first choice disease-modifying anti-rheumatic drug in this disease, however, 35-45% of patients fail to respond. Molecular elements, such as variants in genes of pharmacological relevance, influencing response to methotrexate in JIA, would be important to individualize treatment strategies. Several studies have evaluated the effects of candidate genetic variants in the complex pathway of genes involved in methotrexate pharmacodynamics and pharmacokinetics, however, results are still contrasting and no definitive genetic marker of methotrexate response useful for the clinician to tailor therapy of children with JIA has been identified. Recently, genome-wide approaches have been applied, identifying new potential biological processes involved in methotrexate response in JIA such as TGF-beta signaling and calcium channels. If these genomic results are properly validated and integrated with innovative analyses comprising deep sequencing, epigenetics, and pharmacokinetics, they will greatly contribute to personalize therapy with methotrexate in children with JIA.

Genetic profiling of autoinflammatory disorders in patients with periodic fever: a prospective study. - De Pieri, Carlo; Vuch, Josef; De Martino, Eleonora; Bianco, Anna M; Ronfani, Luca; Athanasakis, Emmanouil; Bortot, Barbara; Crovella, Sergio; Taddio, Andrea; Severini, Giovanni M; Tommasini, Alberto (Pediatr Rheumatol Online J, 2015)
BACKGROUND: Periodic fever syndromes (PFS) are an emerging group of autoinflammatory disorders. Clinical overlap exists and multiple genetic analyses may be needed to assist diagnosis. We evaluated the diagnostic value of a 5-gene sequencing panel (5GP) in patients with undiagnosed PFS. METHODS: Simultaneous double strand Sanger sequencing of MEFV, MVK, TNFRSF1A, NLRP3, NLRP12 genes was performed in 42 patients with unexplained PFS. Clinical features were correlated with genetic results. RESULTS: None of 42 patients analyzed displayed a causative genotype. However, single or multiple genetic variants of uncertain significance were detected in 24 subjects. Only in 5 subjects a definite diagnosis was made by taking into account both genetic and clinical data (2 TRAPS syndrome; 2 FMF; 1 FCAS). Statistical analysis showed that patients carrying genetic variants in one or more of the five selected genes displayed a significantly lower response to glucocorticoids compared with subjects who had completely negative genetic results. CONCLUSIONS: The sequencing of multiple genes is of little help in the diagnostics of PFS and can often lead to results of uncertain interpretation, thus the clinically driven sequencing of single genes should remain the recommended approach. However, the presence of single or multiple genetic variants of uncertain significance, even if not allowing any specific diagnosis, correlated with a poorer response to glucocorticoids, possibly indicating a multifactorial subgroup of PFS with differential response to pharmacological treatment.
Keywords: Adolescent; Carrier Proteins; Child; Cryopyrin-Associated Periodic Syndromes; Cytoskeletal Proteins; Familial Mediterranean Fever; Female; Fever; Gene Expression Profiling; Genotype; Hereditary Autoinflammatory Diseases; Humans; Intracellular Signaling Peptides and Proteins; Logistic Models; Male; Mutation; Phosphotransferases (Alcohol Group Acceptor); Prospective Studies; Receptors, Tumor Necrosis Factor, Type I; Syndrome

Genetic studies of body mass index yield new insights for obesity biology. - Locke, Adam E; Kahali, Bratati; Berndt, Sonja I; Justice, Anne E; Pers, Tune H; Day, Felix R; Powell, Corey; Vedantam, Sailaja; Buchkovich, Martin L; Yang, Jian; Croteau-Chonka, Damien C; Esko, Tõnu; et al. (Nature, 2015)
Obesity is heritable and predisposes to many diseases. To understand the genetic basis of obesity better, here we conduct a genome-wide association study and Metabochip meta-analysis of body mass index (BMI), a measure commonly used to define obesity and assess adiposity, in up to 339,224 individuals. This analysis identifies 97 BMI-associated loci (P < 5 × 10(-8)), 56 of which are novel. Five loci demonstrate clear evidence of several independent association signals, and many loci have significant effects on other metabolic phenotypes. The 97 loci account for ∼2.7% of BMI variation, and genome-wide estimates suggest that common variation accounts for >20% of BMI variation. Pathway analyses provide strong support for a role of the central nervous system in obesity susceptibility and implicate new genes and pathways, including those related to synaptic function, glutamate signalling, insulin secretion/action, energy metabolism, lipid biology and adipogenesis.
Keywords: Adipogenesis; Adiposity; Age Factors; Body Mass Index; Continental Population Groups; Energy Metabolism; Europe; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glutamic Acid; Humans; Insulin; Male; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Synapses

Genome-wide association analysis on five isolated populations identifies variants of the HLA-DOA gene associated with white wine liking. - Pirastu, Nicola; Kooyman, Maarten; Traglia, Michela; Robino, Antonietta; Willems, Sara M; Pistis, Giorgio; Amin, Najaf; Sala, Cinzia; Karssen, Lennart C; van Duijn, Cornelia M; Toniolo, Daniela; Gasparini, Paolo (Eur J Hum Genet, 2015)
Wine is the most popular alcoholic beverage around the world and because of its importance in society has been widely studied. Understanding what drives its flavor has been a quest for decades but much is still unknown and will be determined at least in part by individual taste preferences. Recently studies in the genetics of taste have uncovered the role of different genes in the determination of food preferences giving new insight on its physiology. In this context we have performed a genome-wide association study on red and white wine liking using three isolated populations collected in Italy, and replicated our results on two additional populations coming from the Netherland and Central Asia for a total of 3885 samples. We have found a significant association (P=2.1 × 10(-8)) between white wine liking and rs9276975:C>T a polymorphism in the HLA-DOA gene encoding a non-canonical MHC II molecule, which regulates other MHC II molecules. The same association was also found with red wine liking (P=8.3 × 10(-6)). Sex-separated analysis have also revealed that the effect of HLA-DOA is twice as large in women as compared to men suggesting an interaction between this polymorphism and gender. Our results are one of the first examples of genome-wide association between liking of a commonly consumed food and gene variants. Moreover, our results suggest a role of the MHC system in the determination of food preferences opening new insight in this field in general.

Genome-wide association analysis on normal hearing function identifies PCDH20 and SLC28A3 as candidates for hearing function and loss. - Vuckovic, Dragana; Dawson, Sally; Scheffer, Deborah I; Rantanen, Taina; Morgan, Anna; Di Stazio, Mariateresa; Vozzi, Diego; Nutile, Teresa; Concas, Maria P; Biino, Ginevra; Nolan, Lisa; Bahl, Aileen; et al. (Hum Mol Genet, 2015)
Hearing loss and individual differences in normal hearing both have a substantial genetic basis. Although many new genes contributing to deafness have been identified, very little is known about genes/variants modulating the normal range of hearing ability. To fill this gap, we performed a two-stage meta-analysis on hearing thresholds (tested at 0.25, 0.5, 1, 2, 4, 8 kHz) and on pure-tone averages (low-, medium- and high-frequency thresholds grouped) in several isolated populations from Italy and Central Asia (total N = 2636). Here, we detected two genome-wide significant loci close to PCDH20 and SLC28A3 (top hits: rs78043697, P = 4.71E-10 and rs7032430, P = 2.39E-09, respectively). For both loci, we sought replication in two independent cohorts: B58C from the UK (N = 5892) and FITSA from Finland (N = 270). Both loci were successfully replicated at a nominal level of significance (P < 0.05). In order to confirm our quantitative findings, we carried out RT-PCR and reported RNA-Seq data, which showed that both genes are expressed in mouse inner ear, especially in hair cells, further suggesting them as good candidates for modulatory genes in the auditory system. Sequencing data revealed no functional variants in the coding region of PCDH20 or SLC28A3, suggesting that variation in regulatory sequences may affect expression. Overall, these results contribute to a better understanding of the complex mechanisms underlying human hearing function.

The Global Burden of Cancer 2013. - Fitzmaurice, Christina; Dicker, Daniel; Pain, Amanda; Hamavid, Hannah; Moradi-Lakeh, Maziar; MacIntyre, Michael F; Allen, Christine; Hansen, Gillian; Woodbrook, Rachel; Wolfe, Charles; Hamadeh, Randah R; Moore, Ami; et al. (JAMA Oncol, 2015)
IMPORTANCE: Cancer is among the leading causes of death worldwide. Current estimates of cancer burden in individual countries and regions are necessary to inform local cancer control strategies. OBJECTIVE: To estimate mortality, incidence, years lived with disability (YLDs), years of life lost (YLLs), and disability-adjusted life-years (DALYs) for 28 cancers in 188 countries by sex from 1990 to 2013. EVIDENCE REVIEW: The general methodology of the Global Burden of Disease (GBD) 2013 study was used. Cancer registries were the source for cancer incidence data as well as mortality incidence (MI) ratios. Sources for cause of death data include vital registration system data, verbal autopsy studies, and other sources. The MI ratios were used to transform incidence data to mortality estimates and cause of death estimates to incidence estimates. Cancer prevalence was estimated using MI ratios as surrogates for survival data; YLDs were calculated by multiplying prevalence estimates with disability weights, which were derived from population-based surveys; YLLs were computed by multiplying the number of estimated cancer deaths at each age with a reference life expectancy; and DALYs were calculated as the sum of YLDs and YLLs. FINDINGS: In 2013 there were 14.9 million incident cancer cases, 8.2 million deaths, and 196.3 million DALYs. Prostate cancer was the leading cause for cancer incidence (1.4 million) for men and breast cancer for women (1.8 million). Tracheal, bronchus, and lung (TBL) cancer was the leading cause for cancer death in men and women, with 1.6 million deaths. For men, TBL cancer was the leading cause of DALYs (24.9 million). For women, breast cancer was the leading cause of DALYs (13.1 million). Age-standardized incidence rates (ASIRs) per 100 000 and age-standardized death rates (ASDRs) per 100 000 for both sexes in 2013 were higher in developing vs developed countries for stomach cancer (ASIR, 17 vs 14; ASDR, 15 vs 11), liver cancer (ASIR, 15 vs 7; ASDR, 16 vs 7), esophageal cancer (ASIR, 9 vs 4; ASDR, 9 vs 4), cervical cancer (ASIR, 8 vs 5; ASDR, 4 vs 2), lip and oral cavity cancer (ASIR, 7 vs 6; ASDR, 2 vs 2), and nasopharyngeal cancer (ASIR, 1.5 vs 0.4; ASDR, 1.2 vs 0.3). Between 1990 and 2013, ASIRs for all cancers combined (except nonmelanoma skin cancer and Kaposi sarcoma) increased by more than 10% in 113 countries and decreased by more than 10% in 12 of 188 countries. CONCLUSIONS AND RELEVANCE: Cancer poses a major threat to public health worldwide, and incidence rates have increased in most countries since 1990. The trend is a particular threat to developing nations with health systems that are ill-equipped to deal with complex and expensive cancer treatments. The annual update on the Global Burden of Cancer will provide all stakeholders with timely estimates to guide policy efforts in cancer prevention, screening, treatment, and palliation.

Global, regional, and national comparative risk assessment of 79 behavioural, environmental and occupational, and metabolic risks or clusters of risks in 188 countries, 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Forouzanfar, Mohammad H; Alexander, Lily; Anderson, H Ross; Bachman, Victoria F; Biryukov, Stan; Brauer, Michael; Burnett, Richard; Casey, Daniel; Coates, Matthew M; Cohen, Aaron; Delwiche, Kristen; Estep, Kara; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease, Injuries, and Risk Factor study 2013 (GBD 2013) is the first of a series of annual updates of the GBD. Risk factor quantification, particularly of modifiable risk factors, can help to identify emerging threats to population health and opportunities for prevention. The GBD 2013 provides a timely opportunity to update the comparative risk assessment with new data for exposure, relative risks, and evidence on the appropriate counterfactual risk distribution. METHODS: Attributable deaths, years of life lost, years lived with disability, and disability-adjusted life-years (DALYs) have been estimated for 79 risks or clusters of risks using the GBD 2010 methods. Risk-outcome pairs meeting explicit evidence criteria were assessed for 188 countries for the period 1990-2013 by age and sex using three inputs: risk exposure, relative risks, and the theoretical minimum risk exposure level (TMREL). Risks are organised into a hierarchy with blocks of behavioural, environmental and occupational, and metabolic risks at the first level of the hierarchy. The next level in the hierarchy includes nine clusters of related risks and two individual risks, with more detail provided at levels 3 and 4 of the hierarchy. Compared with GBD 2010, six new risk factors have been added: handwashing practices, occupational exposure to trichloroethylene, childhood wasting, childhood stunting, unsafe sex, and low glomerular filtration rate. For most risks, data for exposure were synthesised with a Bayesian meta-regression method, DisMod-MR 2.0, or spatial-temporal Gaussian process regression. Relative risks were based on meta-regressions of published cohort and intervention studies. Attributable burden for clusters of risks and all risks combined took into account evidence on the mediation of some risks such as high body-mass index (BMI) through other risks such as high systolic blood pressure and high cholesterol. FINDINGS: All risks combined account for 57·2% (95% uncertainty interval [UI] 55·8-58·5) of deaths and 41·6% (40·1-43·0) of DALYs. Risks quantified account for 87·9% (86·5-89·3) of cardiovascular disease DALYs, ranging to a low of 0% for neonatal disorders and neglected tropical diseases and malaria. In terms of global DALYs in 2013, six risks or clusters of risks each caused more than 5% of DALYs: dietary risks accounting for 11·3 million deaths and 241·4 million DALYs, high systolic blood pressure for 10·4 million deaths and 208·1 million DALYs, child and maternal malnutrition for 1·7 million deaths and 176·9 million DALYs, tobacco smoke for 6·1 million deaths and 143·5 million DALYs, air pollution for 5·5 million deaths and 141·5 million DALYs, and high BMI for 4·4 million deaths and 134·0 million DALYs. Risk factor patterns vary across regions and countries and with time. In sub-Saharan Africa, the leading risk factors are child and maternal malnutrition, unsafe sex, and unsafe water, sanitation, and handwashing. In women, in nearly all countries in the Americas, north Africa, and the Middle East, and in many other high-income countries, high BMI is the leading risk factor, with high systolic blood pressure as the leading risk in most of Central and Eastern Europe and south and east Asia. For men, high systolic blood pressure or tobacco use are the leading risks in nearly all high-income countries, in north Africa and the Middle East, Europe, and Asia. For men and women, unsafe sex is the leading risk in a corridor from Kenya to South Africa. INTERPRETATION: Behavioural, environmental and occupational, and metabolic risks can explain half of global mortality and more than one-third of global DALYs providing many opportunities for prevention. Of the larger risks, the attributable burden of high BMI has increased in the past 23 years. In view of the prominence of behavioural risk factors, behavioural and social science research on interventions for these risks should be strengthened. Many prevention and primary care policy options are available now to act on key risks. FUNDING: Bill & Melinda Gates Foundation.

Global, regional, and national disability-adjusted life years (DALYs) for 306 diseases and injuries and healthy life expectancy (HALE) for 188 countries, 1990-2013: quantifying the epidemiological transition. - Murray, Christopher J L; Barber, Ryan M; Foreman, Kyle J; Abbasoglu Ozgoren, Ayse; Abd-Allah, Foad; Abera, Semaw F; Aboyans, Victor; Abraham, Jerry P; Abubakar, Ibrahim; Abu-Raddad, Laith J; Abu-Rmeileh, Niveen M; Achoki, Tom; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease Study 2013 (GBD 2013) aims to bring together all available epidemiological data using a coherent measurement framework, standardised estimation methods, and transparent data sources to enable comparisons of health loss over time and across causes, age-sex groups, and countries. The GBD can be used to generate summary measures such as disability-adjusted life-years (DALYs) and healthy life expectancy (HALE) that make possible comparative assessments of broad epidemiological patterns across countries and time. These summary measures can also be used to quantify the component of variation in epidemiology that is related to sociodemographic development. METHODS: We used the published GBD 2013 data for age-specific mortality, years of life lost due to premature mortality (YLLs), and years lived with disability (YLDs) to calculate DALYs and HALE for 1990, 1995, 2000, 2005, 2010, and 2013 for 188 countries. We calculated HALE using the Sullivan method; 95% uncertainty intervals (UIs) represent uncertainty in age-specific death rates and YLDs per person for each country, age, sex, and year. We estimated DALYs for 306 causes for each country as the sum of YLLs and YLDs; 95% UIs represent uncertainty in YLL and YLD rates. We quantified patterns of the epidemiological transition with a composite indicator of sociodemographic status, which we constructed from income per person, average years of schooling after age 15 years, and the total fertility rate and mean age of the population. We applied hierarchical regression to DALY rates by cause across countries to decompose variance related to the sociodemographic status variable, country, and time. FINDINGS: Worldwide, from 1990 to 2013, life expectancy at birth rose by 6·2 years (95% UI 5·6-6·6), from 65·3 years (65·0-65·6) in 1990 to 71·5 years (71·0-71·9) in 2013, HALE at birth rose by 5·4 years (4·9-5·8), from 56·9 years (54·5-59·1) to 62·3 years (59·7-64·8), total DALYs fell by 3·6% (0·3-7·4), and age-standardised DALY rates per 100 000 people fell by 26·7% (24·6-29·1). For communicable, maternal, neonatal, and nutritional disorders, global DALY numbers, crude rates, and age-standardised rates have all declined between 1990 and 2013, whereas for non-communicable diseases, global DALYs have been increasing, DALY rates have remained nearly constant, and age-standardised DALY rates declined during the same period. From 2005 to 2013, the number of DALYs increased for most specific non-communicable diseases, including cardiovascular diseases and neoplasms, in addition to dengue, food-borne trematodes, and leishmaniasis; DALYs decreased for nearly all other causes. By 2013, the five leading causes of DALYs were ischaemic heart disease, lower respiratory infections, cerebrovascular disease, low back and neck pain, and road injuries. Sociodemographic status explained more than 50% of the variance between countries and over time for diarrhoea, lower respiratory infections, and other common infectious diseases; maternal disorders; neonatal disorders; nutritional deficiencies; other communicable, maternal, neonatal, and nutritional diseases; musculoskeletal disorders; and other non-communicable diseases. However, sociodemographic status explained less than 10% of the variance in DALY rates for cardiovascular diseases; chronic respiratory diseases; cirrhosis; diabetes, urogenital, blood, and endocrine diseases; unintentional injuries; and self-harm and interpersonal violence. Predictably, increased sociodemographic status was associated with a shift in burden from YLLs to YLDs, driven by declines in YLLs and increases in YLDs from musculoskeletal disorders, neurological disorders, and mental and substance use disorders. In most country-specific estimates, the increase in life expectancy was greater than that in HALE. Leading causes of DALYs are highly variable across countries. INTERPRETATION: Global health is improving. Population growth and ageing have driven up numbers of DALYs, but crude rates have remained relatively constant, showing that progress in health does not mean fewer demands on health systems. The notion of an epidemiological transition--in which increasing sociodemographic status brings structured change in disease burden--is useful, but there is tremendous variation in burden of disease that is not associated with sociodemographic status. This further underscores the need for country-specific assessments of DALYs and HALE to appropriately inform health policy decisions and attendant actions. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Aged; Chronic Disease; Communicable Diseases; Female; Global Health; Health Transition; Humans; Life Expectancy; Male; Middle Aged; Mortality, Premature; Quality-Adjusted Life Years; Socioeconomic Factors; Wounds and Injuries

Identification of a novel frameshift mutation in the EDAR gene causing autosomal dominant hypohidrotic ectodermal dysplasia. - Callea, M; Willoughby, C E; Nieminen, P; Di Stazio, M; Bellacchio, E; Giglio, S; Sani, I; Vinciguerra, A; Maglione, M; Tadini, G; Clarich, G (J Eur Acad Dermatol Venereol, 2015)

Immunologic evidence of a strong association between non-Hodgkin lymphoma and simian virus 40. - Tognon, Mauro; Luppi, Mario; Corallini, Alfredo; Taronna, Angelo; Barozzi, Patrizia; Rotondo, John Charles; Comar, Manola; Casali, Maria Vittoria; Bovenzi, Massimo; D'Agostino, Antonio; Vinante, Fabrizio; Rigo, Antonella; et al. (Cancer, 2015)
BACKGROUND: Non-Hodgkin lymphoma (NHL), the most common cancer of the lymphatic system, is of unknown etiology. The identification of etiologic factors in the onset of NHL is a key event that could facilitate the prevention and cure of this malignancy. Simian virus 40 (SV40) has been considered an oncogenic agent in the onset/progression of NHL. METHODS: In this study, an indirect enzyme-linked immunosorbent assay with 2 synthetic peptides that mimic SV40 antigens of viral capsid proteins 1 to 3 was employed to detect specific antibodies against SV40. Serum samples were taken from 2 distinct cohorts of NHL-affected patients (NHL1 [n = 89] and NHL2 [n = 61]) along with controls represented by oncologic patients affected by breast cancer (BC; n = 78) and undifferentiated nasopharyngeal carcinoma (UNPC; n = 64) and 3 different cohorts of healthy subjects (HSs; HS1 [n = 130], HS2 [n = 83], and HS3 [n = 87]). RESULTS: Immunologic data indicated that in serum samples from NHL patients, antibodies against SV40 mimotopes were detectable with a prevalence of 40% in NHL1 patients and with a prevalence of 43% in NHL2 patients. In HSs of the same median age as NHL patients, the prevalence was 16% for the HS1 group (57 years) and 14% for the HS2 group (65 years). The difference was statistically significant (P < .0001 and P < .001). Interestingly, the difference between NHL1/NHL2 patients and BC patients (40%/43% vs 15%, P < .001) and between NHL1/NHL2 patients and UNPC patients (40%/43% vs 25%, P < .05) was significant. CONCLUSIONS: Our data indicate a strong association between NHL and SV40 and thus a need for innovative therapeutic approaches for this hematologic malignancy.
Keywords: Adult; Aged; Antibodies, Viral; Capsid Proteins; Enzyme-Linked Immunosorbent Assay; Female; Humans; Lymphoma, Non-Hodgkin; Male; Middle Aged; Polyomavirus Infections; Seroepidemiologic Studies; Simian virus 40; Tumor Virus Infections

Increased rate of deleterious variants in long runs of homozygosity of an inbred population from Qatar. - Mezzavilla, Massimo; Vozzi, Diego; Badii, Ramin; Alkowari, Moza Khalifa; Abdulhadi, Khalid; Girotto, Giorgia; Gasparini, Paolo (Hum Hered, 2015)
OBJECTIVE: The aim of this study is to evaluate the fraction of putatively deleterious variants within genomic runs of homozygosity (ROH) regions in an inbred and selected cohort of Qatari individuals. METHODS: High-density SNP array analysis was performed in 36 individuals, and for 14 of them whole-exome sequencing (WES) was also carried out. RESULTS: In all individuals, regions characterized by a high (hotspot) or low (coldspot) degree of homozygosity in all the analysed individuals were mapped, and the most frequent hotspot regions were selected. WES data were exploited to identify the single nucleotide variations (SNVs) harboured by genes located within both regions in each individual. Evolutionary conservation-based algorithms were employed to predict the potential deleteriousness of SNVs. The amount of in silico predicted deleterious SNVs was significantly different (p < 0.05) between homozygosity hotspot and coldspot regions. CONCLUSION: Genes located within ROH hotspot regions contain a significant burden of predicted putatively deleterious variants compared to genes located outside these regions, suggesting inbreeding as a possible mechanism allowing an enrichment of putatively deleterious variants at the homozygous state.
Keywords: Cohort Studies; Consanguinity; Homozygote; Humans; Mutation; Polymorphism, Single Nucleotide; Qatar

Large-scale genomic analyses link reproductive aging to hypothalamic signaling, breast cancer susceptibility and BRCA1-mediated DNA repair. - Day, Felix R; Ruth, Katherine S; Thompson, Deborah J; Lunetta, Kathryn L; Pervjakova, Natalia; Chasman, Daniel I; Stolk, Lisette; Finucane, Hilary K; Sulem, Patrick; Bulik-Sullivan, Brendan; Esko, Tõnu; Johnson, Andrew D; et al. (Nat Genet, 2015)
Menopause timing has a substantial impact on infertility and risk of disease, including breast cancer, but the underlying mechanisms are poorly understood. We report a dual strategy in ∼70,000 women to identify common and low-frequency protein-coding variation associated with age at natural menopause (ANM). We identified 44 regions with common variants, including two regions harboring additional rare missense alleles of large effect. We found enrichment of signals in or near genes involved in delayed puberty, highlighting the first molecular links between the onset and end of reproductive lifespan. Pathway analyses identified major association with DNA damage response (DDR) genes, including the first common coding variant in BRCA1 associated with any complex trait. Mendelian randomization analyses supported a causal effect of later ANM on breast cancer risk (∼6% increase in risk per year; P = 3 × 10(-14)), likely mediated by prolonged sex hormone exposure rather than DDR mechanisms.

Legius syndrome: case report and review of literature. - Benelli, Elisa; Bruno, Irene; Belcaro, Chiara; Ventura, Alessandro; Berti, Irene (Ital J Pediatr, 2015)
A 8-month-old child was referred to our Dermatologic Unit for suspected Neurofibromatosis type 1 (NF 1), because of the appearance, since few days after birth, of numerous café-au-lait spots (seven larger than 5 mm); no other sign evocative of NF 1 was found. Her family history was remarkable for the presence of multiple café-au-lait spots in the mother, the grandfather and two aunts. The family had been already examined for NF 1, but no sign evocative of the disease was found. We then suspected Legius syndrome, a dominant disease characterized by a mild neurofibromatosis 1 phenotype. The diagnosis was confirmed by the finding of a mutation in SPRED1 gene, a feedback regulator of RAS/MAPK signaling. Here, we discuss the differential diagnosis of cafè-au-lait spots and we briefly review the existing literature about Legius syndrome.

Long noncoding RNA GAS5: a novel marker involved in glucocorticoid response. - Lucafo, M; De Iudicibus, S; Di Silvestre, A; Pelin, M; Candussio, L; Martelossi, S; Tommasini, A; Piscianz, E; Ventura, A; Decorti, G (Curr Mol Med, 2015)
Glucocorticoids (GCs) exert their effects through regulation of gene expression after activation in the cytoplasm of the glucocorticoid receptor (GR) encoded by NR3C1 gene. A negative feedback mechanism resulting in GR autoregulation has been demonstrated through the binding of the activated receptor to intragenic sequences called GRE-like elements, contained in GR gene. The long noncoding RNA growth arrest-specific transcript 5 (GAS5) interacts with the activated GR suppressing its transcriptional activity. The aim of this study was to evaluate the possible role of GAS5 and NR3C1 gene expression in the antiproliferative effect of methylprednisolone in peripheral blood mononuclear cells and to correlate the expression with individual sensitivity to GCs. Subjects being poor responders to GCs presented higher levels of GAS5 and NR3C1 in comparison with good responders. We suggest that abnormal levels of GAS5 may alter GC effectiveness, probably interfering with the mechanism of GR autoregulation.
Keywords: Adult; Cell Proliferation; Female; Gene Expression Regulation; Glucocorticoids; Humans; Leukocytes, Mononuclear; Male; Methylprednisolone; Middle Aged; Receptors, Glucocorticoid; RNA, Long Noncoding; Transcription, Genetic

Making the first days of life safer: preventing sudden unexpected postnatal collapse while promoting breastfeeding. - Davanzo, Riccardo; De Cunto, Angela; Paviotti, Giulia; Travan, Laura; Inglese, Stefania; Brovedani, Pierpaolo; Crocetta, Anna; Calligaris, Chiara; Corubolo, Elisa; Dussich, Valentina; Verardi, Giuseppa; Causin, Enrica; et al. (J Hum Lact, 2015)
Early and prolonged skin-to-skin contact (SSC) after birth between a mother and her newborn has been shown to generate beneficial effects on the mother-infant relationship and breastfeeding. Close mother-infant body contact immediately after birth positively enhances exclusive breastfeeding during the hospital stay, with a dose-response relationship. Skin-to-skin contact may ease the infant's transition to extra-uterine life and helps regulate the infant's body temperature and nursing behavior. However, reports of sudden unexpected postnatal collapse (SUPC) soon after birth, in healthy term neonates, in association with SSC, have raised concerns about the safety of this practice. Based on available evidence, we developed a surveillance protocol in the delivery room and postnatal ward of the Institute for Maternal and Child Health of Trieste (Italy). The aim of our protocol is (a) to promote safe mother and infant bonding and (b) to establish successful breastfeeding, without increasing the risk of SUPC. As there is no known effective intervention to prevent SUPC, our protocol has been conceived as a potential best practice.

Modulation of genetic associations with serum urate levels by body-mass-index in humans. - Huffman, Jennifer E; Albrecht, Eva; Teumer, Alexander; Mangino, Massimo; Kapur, Karen; Johnson, Toby; Kutalik, Zoltán; Pirastu, Nicola; Pistis, Giorgio; Lopez, Lorna M; Haller, Toomas; Salo, Perttu; et al. (PLoS One, 2015)
We tested for interactions between body mass index (BMI) and common genetic variants affecting serum urate levels, genome-wide, in up to 42569 participants. Both stratified genome-wide association (GWAS) analyses, in lean, overweight and obese individuals, and regression-type analyses in a non BMI-stratified overall sample were performed. The former did not uncover any novel locus with a major main effect, but supported modulation of effects for some known and potentially new urate loci. The latter highlighted a SNP at RBFOX3 reaching genome-wide significant level (effect size 0.014, 95% CI 0.008-0.02, Pinter= 2.6 x 10-8). Two top loci in interaction term analyses, RBFOX3 and ERO1LB-EDARADD, also displayed suggestive differences in main effect size between the lean and obese strata. All top ranking loci for urate effect differences between BMI categories were novel and most had small magnitude but opposite direction effects between strata. They include the locus RBMS1-TANK (men, Pdifflean-overweight= 4.7 x 10-8), a region that has been associated with several obesity related traits, and TSPYL5 (men, Pdifflean-overweight= 9.1 x 10-8), regulating adipocytes-produced estradiol. The top-ranking known urate loci was ABCG2, the strongest known gout risk locus, with an effect halved in obese compared to lean men (Pdifflean-obese= 2 x 10-4). Finally, pathway analysis suggested a role for N-glycan biosynthesis as a prominent urate-associated pathway in the lean stratum. These results illustrate a potentially powerful way to monitor changes occurring in obesogenic environment.

Multicohort analysis of the maternal age effect on recombination. - Martin, Hilary C; Christ, Ryan; Hussin, Julie G; O'Connell, Jared; Gordon, Scott; Mbarek, Hamdi; Hottenga, Jouke-Jan; McAloney, Kerrie; Willemsen, Gonnecke; Gasparini, Paolo; Pirastu, Nicola; Montgomery, Grant W; et al. (Nat Commun, 2015)
Several studies have reported that the number of crossovers increases with maternal age in humans, but others have found the opposite. Resolving the true effect has implications for understanding the maternal age effect on aneuploidies. Here, we revisit this question in the largest sample to date using single nucleotide polymorphism (SNP)-chip data, comprising over 6,000 meioses from nine cohorts. We develop and fit a hierarchical model to allow for differences between cohorts and between mothers. We estimate that over 10 years, the expected number of maternal crossovers increases by 2.1% (95% credible interval (0.98%, 3.3%)). Our results are not consistent with the larger positive and negative effects previously reported in smaller cohorts. We see heterogeneity between cohorts that is likely due to chance effects in smaller samples, or possibly to confounders, emphasizing that care should be taken when interpreting results from any specific cohort about the effect of maternal age on recombination.

MultiMeta: an R package for meta-analyzing multi-phenotype genome-wide association studies. - Vuckovic, D; Gasparini, P; Soranzo, N; Iotchkova, V (Bioinformatics, 2015)
UNLABELLED: As new methods for multivariate analysis of genome wide association studies become available, it is important to be able to combine results from different cohorts in a meta-analysis. The R package MultiMeta provides an implementation of the inverse-variance-based method for meta-analysis, generalized to an n-dimensional setting. AVAILABILITY AND IMPLEMENTATION: The R package MultiMeta can be downloaded from CRAN. CONTACT: dragana.vuckovic@burlo.trieste.it; vi1@sanger.ac.uk SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.

New genetic loci link adipose and insulin biology to body fat distribution. - Shungin, Dmitry; Winkler, Thomas W; Croteau-Chonka, Damien C; Ferreira, Teresa; Locke, Adam E; Mägi, Reedik; Strawbridge, Rona J; Pers, Tune H; Fischer, Krista; Justice, Anne E; Workalemahu, Tsegaselassie; Wu, Joseph M W; et al. (Nature, 2015)
Body fat distribution is a heritable trait and a well-established predictor of adverse metabolic outcomes, independent of overall adiposity. To increase our understanding of the genetic basis of body fat distribution and its molecular links to cardiometabolic traits, here we conduct genome-wide association meta-analyses of traits related to waist and hip circumferences in up to 224,459 individuals. We identify 49 loci (33 new) associated with waist-to-hip ratio adjusted for body mass index (BMI), and an additional 19 loci newly associated with related waist and hip circumference measures (P < 5 × 10(-8)). In total, 20 of the 49 waist-to-hip ratio adjusted for BMI loci show significant sexual dimorphism, 19 of which display a stronger effect in women. The identified loci were enriched for genes expressed in adipose tissue and for putative regulatory elements in adipocytes. Pathway analyses implicated adipogenesis, angiogenesis, transcriptional regulation and insulin resistance as processes affecting fat distribution, providing insight into potential pathophysiological mechanisms.
Keywords: Adipocytes; Adipogenesis; Adipose Tissue; Age Factors; Body Fat Distribution; Body Mass Index; Continental Population Groups; Epigenesis, Genetic; Europe; Female; Genome, Human; Genome-Wide Association Study; Humans; Insulin; Insulin Resistance; Male; Models, Biological; Neovascularization, Physiologic; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Sex Characteristics; Transcription, Genetic; Waist-Hip Ratio

Orofacial granulomatosis in children: think about Crohn's disease. - Lazzerini, Marzia; Martelossi, Stefano; Cont, Gabriele; Bersanini, Chiara; Ventura, Giovanna; Fontana, Massimo; Zuin, Giovanna; Ventura, Alessandro; Taddio, Andrea (Dig Liver Dis, 2015)
BACKGROUND: The term orofacial granulomatosis is conventionally used to describe patients with granulomatous lesions affecting the orofacial tissues, in absence of intestinal lesions. Lip swelling and facial swelling are the most common clinical signs. Despite the fact that histologically it is not distinguishable from Crohn's disease, and that both diseases have a chronic/recurrent course, the relationship between orofacial granulomatosis and Crohn's disease is still debated. METHODS: Herein we present five cases of orofacial granulomatosis. RESULTS: All patients presented concomitant Crohn's disease, supporting the hypothesis that orofacial granulomatosis and Crohn's disease may be one single disease. Thalidomide was effective in inducing remission of oral and intestinal symptoms in all five cases and could be considered a valid treatment opportunity for these patients. CONCLUSIONS: Orofacial granulomatosis and Crohn's disease may be part of the same disease; both may respond to thalidomide.
Keywords: Adolescent; Biopsy; Child; Colonoscopy; Crohn Disease; Diagnosis, Differential; Female; Granulomatosis, Orofacial; Humans; Immunosuppressive Agents; Male; Thalidomide

Patients' Induced Pluripotent Stem Cells to Model Drug Induced Adverse Events: A Role in Predicting Thiopurine Induced Pancreatitis? - Stocco, Gabriele; Lanzi, Gaetana; Yue, Fengming; Giliani, Silvia; Sasaki, Katsunori; Tommasini, Alberto; Pelin, Marco; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana (Curr Drug Metab, 2015)
Induced pluripotent stem cells (iPSC) can be produced from adult cells by transfecting them with a definite set of pluripotency-associated genes. Under adequate growth conditions and stimulation iPSC can differentiate to almost every somatic lineage in the body. Patients' derived iPSC are an innovative model to study mechanisms of adverse drug reactions in individual patients and in cell types that cannot be easily obtained from human subjects. Proof-of concept studies with known toxicants have been performed for liver, cardiovascular and central nervous system cells: neurons obtained from iPSC have been used to elucidate the mechanism of chemotherapy-induced peripheral neuropathy by evaluating the effects of neurotoxic drugs such as vincristine. However, no study has been performed yet on pancreatic tissue and drug induced pancreatitis. Thiopurines (azathioprine and mercaptopurine) are immunosuppressive antimetabolite drugs, commonly used to treat Crohn's disease. About 5% of Crohn's disease patients treated with thiopurines develop pancreatitis, a severe idiosyncratic adverse event; these patients have to stop thiopurine administration and may require medical treatment, with significant personal and social costs. Molecular mechanism of thiopurine induced pancreatitis (TIP) is currently unknown and no fully validated biomarker is available to assist clinicians in preventing this adverse event. Hence, in this review we have reflected upon the probable research applications of exocrine pancreatic cells generated from patient specific iPS cells. Such pancreatic cells can provide excellent insights into the molecular mechanism of TIP. In particular three hypotheses on the mechanism of TIP could be explored: drug biotransformation, innate immunity and adaptative immunity.

Phenotypic and genetic characterization of a family carrying two Xq21.1-21.3 interstitial deletions associated with syndromic hearing loss. - Iossa, Sandra; Costa, Valerio; Corvino, Virginia; Auletta, Gennaro; Barruffo, Luigi; Cappellani, Stefania; Ceglia, Carlo; Cennamo, Giovanni; d'Adamo, Adamo Pio; D'Amico, Alessandra; Di Paolo, Nilde; Forte, Raimondo; et al. (Mol Cytogenet, 2015)
BACKGROUND: Sensorineural hearing impairment is a common pathological manifestation in patients affected by X-linked intellectual disability. A few cases of interstitial deletions at Xq21 with several different phenotypic characteristics have been described, but to date, a complete molecular characterization of the deletions harboring disease-causing genes is still missing. Thus, the aim of this study is to realize a detailed clinical and molecular analysis of a family affected by syndromic X-linked hearing loss with intellectual disability. RESULTS: Clinical analyses revealed a very complex phenotype that included inner ear malformations, vestibular problems, choroideremia and hypotonia with a peculiar pattern of phenotypic variability. Genomic analysis revealed, for the first time, the presence of two close interstitial deletions in the Xq21.1-21.3, harboring 11 protein coding, 9 non-coding genes and 19 pseudogenes. Among these, 3 protein coding genes have already been associated with X-linked hearing loss, intellectual disability and choroideremia. CONCLUSIONS: In this study we highlighted the presence of peculiar genotypic and phenotypic details in a family affected by syndromic X-linked hearing loss with intellectual disability. We identified two, previously unreported, Xq21.1-21.3 interstitial deletions. The two rearrangements, containing several genes, segregate with the clinical features, suggesting their role in the pathogenicity. However, not all the observed phenotypic features can be clearly associated with the known genes thus, further study is necessary to determine regions involved.

A pneumonia that does not improve. - Naviglio, Samuele; Chinello, Matteo; Ventura, Alessandro (Arch Dis Child Educ Pract Ed, 2015)
Keywords: Airway Obstruction; Bronchoscopy; Child, Preschool; Foreign Bodies; Humans; Pneumonia; Radiography, Thoracic

Population genetic differentiation of height and body mass index across Europe. - Robinson, Matthew R; Hemani, Gibran; Medina-Gomez, Carolina; Mezzavilla, Massimo; Esko, Tõnu; Shakhbazov, Konstantin; Powell, Joseph E; Vinkhuyzen, Anna; Berndt, Sonja I; Gustafsson, Stefan; Justice, Anne E; Kahali, Bratati; et al. (Nat Genet, 2015)
Across-nation differences in the mean values for complex traits are common, but the reasons for these differences are unknown. Here we find that many independent loci contribute to population genetic differences in height and body mass index (BMI) in 9,416 individuals across 14 European countries. Using discovery data on over 250,000 individuals and unbiased effect size estimates from 17,500 sibling pairs, we estimate that 24% (95% credible interval (CI) = 9%, 41%) and 8% (95% CI = 4%, 16%) of the captured additive genetic variance for height and BMI, respectively, reflect population genetic differences. Population genetic divergence differed significantly from that in a null model (height, P < 3.94 × 10(-8); BMI, P < 5.95 × 10(-4)), and we find an among-population genetic correlation for tall and slender individuals (r = -0.80, 95% CI = -0.95, -0.60), consistent with correlated selection for both phenotypes. Observed differences in height among populations reflected the predicted genetic means (r = 0.51; P < 0.001), but environmental differences across Europe masked genetic differentiation for BMI (P < 0.58).

Positron emission tomography-laparoscopy based method in the prediction of complete cytoreduction in platinum-sensitive recurrent ovarian cancer. - Fanfani, Francesco; Monterossi, Giorgia; Fagotti, Anna; Gallotta, Valerio; Costantini, Barbara; Vizzielli, Giuseppe; Petrillo, Marco; Carbone, Maria Vittoria; Scambia, Giovanni (Ann Surg Oncol, 2015)
BACKGROUND: This study was designed to evaluate the positron emission tomography-laparoscopy-based method in the prediction of complete/optimal cytoreduction in platinum sensitive recurrent epithelial ovarian cancer patients. METHODS: We analysed 223 consecutive recurrent epithelial ovarian cancer patients. Inclusion criteria were absence of extra-abdominal disease and Eastern Cooperative Oncology Group Performance Status ≤2. Complete and optimal secondary cytoreduction are defined as macroscopic absence or less than 1 cm of residual tumor at the end of surgery. RESULTS: Laparoscopy was feasible in 210 of 223 patients (94.2 %). Laparoscopy stated 127 (60.5 %) possible cytoreductions and 83 (39.5 %) systemic chemotherapies. In the same population, AGO score evaluation avowed 150 possible cytoreduction (71.5 %) and 60 unresectable women (28.5 %). Overall, 115 of 210 patients (54.7 %) underwent successful secondary cytoreduction: complete and optimal cytoreduction was obtained in 103 (89.5 %) and 12 (10.5 %) patients, respectively. Laparoscopy obtained a positive predictive value of 91.3 %. Laparoscopy recovered to secondary cytoreduction 13 of 60 patients (21.7 %) deemed as not resectable according to AGO score. Forty-eight of 150 AGO score positive patients (32 %) were judged nonresectable by laparoscopy. CONCLUSIONS: This study confirmed that laparoscopy could be effective for the selection of platinum-sensitive recurrent epithelial ovarian cancer patients suitable for complete cytoreduction.
Keywords: Adult; Aged; Algorithms; Cytoreduction Surgical Procedures; Female; Humans; Laparoscopy; Middle Aged; Neoplasm Recurrence, Local; Neoplasm Staging; Neoplasms, Glandular and Epithelial; Ovarian Neoplasms; Positron-Emission Tomography; Tomography, X-Ray Computed

Prevalence of celiac disease in patients with severe food allergy. - Pillon, R; Ziberna, F; Badina, L; Ventura, A; Longo, G; Quaglia, S; De Leo, L; Vatta, S; Martelossi, S; Patano, G; Not, T; Berti, I (Allergy, 2015)
The association between food allergy and celiac disease (CD) is still to be clarified. We screened for CD 319 patients with severe food allergy (IgE > 85 kU/l against food proteins and a history of severe allergic reactions) who underwent specific food oral immunotherapy (OIT), together with 128 children with mild allergy who recovered without OIT, and compared the prevalence data with our historical data regarding healthy schoolchildren. Sixteen patients (5%) with severe allergy and one (0.8%) with mild allergy tested positive for both genetic and serological CD markers, while the prevalence among the schoolchildren was 1%. Intestinal biopsies were obtained in 13/16 patients with severe allergy and in the one with mild allergy, confirming the diagnosis of CD. Sufferers from severe food allergy seem to be at a fivefold increased risk of CD. Our findings suggest that routine screening for CD should be recommended in patients with severe food allergy.

PSIP1/LEDGF: a new gene likely involved in sensorineural progressive hearing loss. - Girotto, Giorgia; Scheffer, Deborah I; Morgan, Anna; Vozzi, Diego; Rubinato, Elisa; Di Stazio, Mariateresa; Muzzi, Enrico; Pensiero, Stefano; Giersch, Anne B; Corey, David P; Gasparini, Paolo (Sci Rep, 2015)
Hereditary Hearing Loss (HHL) is an extremely heterogeneous disorder. Approximately 30 out of 80 known HHL genes are associated with autosomal dominant forms. Here, we identified PSIP1/LEDGF (isoform p75) as a novel strong candidate gene involved in dominant HHL. Using exome sequencing we found a frameshift deletion (c.1554_1555del leading to p.E518Dfs*2) in an Italian pedigree affected by sensorineural mild-to-moderate HHL but also showing a variable eye phenotype (i.e. uveitis, optic neuropathy). This deletion led to a premature stop codon (p.T519X) with truncation of the last 12 amino acids. PSIP1 was recently described as a transcriptional co-activator regulated by miR-135b in vestibular hair cells of the mouse inner ear as well as a possible protector against photoreceptor degeneration. Here, we demonstrate that it is ubiquitously expressed in the mouse inner ear. The PSIP1 mutation is associated with a peculiar audiometric slope toward the high frequencies. These findings indicate that PSIP1 likely plays an important role in HHL.

R705H mutation of MYH9 is associated with MYH9-related disease and not only with non-syndromic deafness DFNA17. - Verver, E; Pecci, A; De Rocco, D; Ryhänen, S; Barozzi, S; Kunst, H; Topsakal, V; Savoia, A (Clin Genet, 2015)
MYH9-related disease (MYH9-RD) is a rare autosomal dominant disease caused by mutation of MYH9, the gene encoding for the heavy chain of non-muscle myosin IIA (NMMHC-IIA). MYH9-RD patients have macrothrombocytopenia and granulocyte inclusions (pathognomonic sign of the disease) containing wild-type and mutant NMMHC-IIA. During life they might develop sensorineural hearing loss, cataract, glomerulonephritis, and elevation of liver enzymes. One of the MYH9 mutations, p.R705H, was previously reported to be associated with DFNA17, an autosomal dominant non-syndromic sensorineural hearing loss without any other features associated. We identified the same mutation in two unrelated families, whose four affected individuals had not only hearing impairment but also thrombocytopenia, giant platelets, leukocyte inclusions, as well as mild to moderate elevation of some liver enzymes. Our data suggest that DFNA17 should not be a separate genetic entity but part of the wide phenotypic spectrum of MYH9-RD characterized by congenital hematological manifestations and variable penetrance and expressivity of the extra-hematological features.

Rare coding variants and X-linked loci associated with age at menarche. - Lunetta, Kathryn L; Day, Felix R; Sulem, Patrick; Ruth, Katherine S; Tung, Joyce Y; Hinds, David A; Esko, Tõnu; Elks, Cathy E; Altmaier, Elisabeth; He, Chunyan; Huffman, Jennifer E; Mihailov, Evelin; et al. (Nat Commun, 2015)
More than 100 loci have been identified for age at menarche by genome-wide association studies; however, collectively these explain only ∼3% of the trait variance. Here we test two overlooked sources of variation in 192,974 European ancestry women: low-frequency protein-coding variants and X-chromosome variants. Five missense/nonsense variants (in ALMS1/LAMB2/TNRC6A/TACR3/PRKAG1) are associated with age at menarche (minor allele frequencies 0.08-4.6%; effect sizes 0.08-1.25 years per allele; P<5 × 10(-8)). In addition, we identify common X-chromosome loci at IGSF1 (rs762080, P=9.4 × 10(-13)) and FAAH2 (rs5914101, P=4.9 × 10(-10)). Highlighted genes implicate cellular energy homeostasis, post-transcriptional gene silencing and fatty-acid amide signalling. A frequently reported mutation in TACR3 for idiopathic hypogonatrophic hypogonadism (p.W275X) is associated with 1.25-year-later menarche (P=2.8 × 10(-11)), illustrating the utility of population studies to estimate the penetrance of reportedly pathogenic mutations. Collectively, these novel variants explain ∼0.5% variance, indicating that these overlooked sources of variation do not substantially explain the 'missing heritability' of this complex trait.

Relapse and metastasis of atypical teratoid/rhabdoid tumor in a boy with neurofibromatosis type 1 treated with recombinant human growth hormone. - Tornese, Gianluca; Faleschini, Elena; Matarazzo, Lorenza; Bibalo, Cristina; Zanazzo, Giulio Andrea; Rabusin, Marco; Tonini, Giorgio; Zennaro, Floriana; Ventura, Alessandro (Neuropediatrics, 2015)
Even though no increased recurrence rate seems to be reported in patients with brain tumors receiving recombinant human growth hormone (rhGH) replacement, in some patients multiple risk factors could put at higher risk for recurrence. In such cases, the decision to start rhGH therapy should be very cautious. A boy with neurofibromatosis type 1 developed an atypical teratoid/rhabdoid tumor (AT/RT) of right cerebellum, treated with surgery, radiotherapy, and chemotherapy. After 3 years of remission, he started rhGH for growth hormone deficiency, having a negative magnetic resonance imaging (MRI) scan. Ten weeks after starting therapy, the boy became symptomatic and MRI showed relapse of AT/RT in the right cerebellum and a new lesion in the brainstem. The boy died of progressive disease. In this case, the connection between AT/RT recurrence and the beginning of rhGH therapy, with a negative pretreatment MRI, cannot be excluded. Additional caution should be used for rhGH in patients with multiple risk factors.
Keywords: Brain Stem Neoplasms; Cerebellar Neoplasms; Child; Human Growth Hormone; Humans; Magnetic Resonance Imaging; Male; Neurofibromatosis 1; Recombinant Proteins; Recurrence; Rhabdoid Tumor; Risk Factors; Teratoma

Reply to Thalidomide Treatment of Pediatric Ulcerative Colitis: A New Use for an Old Drug. - Lazzerini, Marzia; Martelossi, Stefano; Ventura, Alessandro (Inflamm Bowel Dis, 2015)
Keywords: Crohn Disease; Female; Humans; Immunosuppressive Agents; Male; Thalidomide

Role of oxidative stress mediated by glutathione-s-transferase in thiopurines' toxic effects. - Pelin, Marco; De Iudicibus, Sara; Fusco, Laura; Taboga, Eleonora; Pellizzari, Giulia; Lagatolla, Cristina; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana; Stocco, Gabriele (Chem Res Toxicol, 2015)
Azathioprine (AZA), 6-mercaptopurine (6-MP), and 6-thioguanine (6-TG) are antimetabolite drugs, widely used as immunosuppressants and anticancer agents. Despite their proven efficacy, a high incidence of toxic effects in patients during standard-dose therapy is recorded. The aim of this study is to explain, from a mechanistic point of view, the clinical evidence showing a significant role of glutathione-S-transferase (GST)-M1 genotype on AZA toxicity in inflammatory bowel disease patients. To this aim, the human nontumor IHH and HCEC cell lines were chosen as predictive models of the hepatic and intestinal tissues, respectively. AZA, but not 6-MP and 6-TG, induced a concentration-dependent superoxide anion production that seemed dependent on GSH depletion. N-Acetylcysteine reduced the AZA antiproliferative effect in both cell lines, and GST-M1 overexpression increased both superoxide anion production and cytotoxicity, especially in transfected HCEC cells. In this study, an in vitro model to study thiopurines' metabolism has been set up and helped us to demonstrate, for the first time, a clear role of GST-M1 in modulating AZA cytotoxicity, with a close dependency on superoxide anion production. These results provide the molecular basis to shed light on the clinical evidence suggesting a role of GST-M1 genotype in influencing the toxic effects of AZA treatment.

Sensorineural hearing loss in very low birth weight infants with histological chorioamnionitis. - Vedovato, Stefania; Lo Iacono, Angela; Morando, Carla; Suppiej, Agnese; Orzan, Eva; Trevisanuto, Daniele; Visentin, Silvia; Cavallin, Francesco; Chiarelli, Silvia; Zanardo, Vincenzo (J Matern Fetal Neonatal Med, 2015)
OBJECTIVE: Histological chorioamnionitis (HCAM) has been associated with inflammatory diseases of preterm infants. Recently we have observed that it increased the risk of speech delay and hearing loss. So the aim of this study was to evaluate the relationship between sensorineural hearing loss (SNHL) of VLBW infants and HCAM. METHODS: We performed an observational study on VLBW infants admitted to the NICU of Padua. Each patient with HCAM was matched with one control without HCAM. All infants underwent hearing screening before discharge by means of automated transient-evoked otoacustic emissions and automated auditory brainstem responses, which were repeated at 3 and 6 months of age with tympanometry measurement. Incidence of SNHL at 6 months of age was compared in the 2 groups and risk factors for hearing loss were studied. RESULTS: Two of 77 (2.6%) newborns with HCAM e 6/73 (8.2%) without it presented SNHL at 6 months of corrected age (p = 0.16). Multivariable logistic regression analysis identified surgical ligation of patent ductus arteriosus (PDA) as independent predictors of SNHL (OR: 5.75, 95% CI 1.34-24.84, p = 0.02), whereas the effect of HCAM on SNHL was only near to statistical significance level. CONCLUSIONS: Surgical ligation of PDA is associated with an increased risk of SNHL in VLBW infants, regardless of HCAM.

Serum anti-tissue transglutaminase antibodies detected during febrile illness may not be produced by the intestinal mucosa. - De Leo, Luigina; Quaglia, Sara; Ziberna, Fabiana; Vatta, Serena; Martelossi, Stefano; Maschio, Massimo; Not, Tarcisio (J Pediatr, 2015)
Anti-transglutaminase antibodies are the diagnostic marker of celiac disease, and are considered to be synthesized only by intestinal B-lymphocytes. During an infectious disease, these antibodies are transiently detected in serum. We show that these infection-triggered antibodies may not originate in the intestinal mucosa and are not an indication of celiac disease.
Keywords: Autoantibodies; Celiac Disease; Child, Preschool; Diagnosis, Differential; Enzyme-Linked Immunosorbent Assay; Female; GTP-Binding Proteins; Humans; Intestinal Mucosa; Male; Transglutaminases

A Shining Scrotal Fountain. - Copertino, Marco; Benelli, Elisa; Gregori, Massimo; Barbi, Egidio; Ventura, Alessandro (J Pediatr, 2015)
Keywords: Child; Edema; Humans; Male; Penile Diseases; Scrotum

Sirolimus Therapy in Congenital Hyperinsulinism: A Successful Experience Beyond Infancy. - Minute, Marta; Patti, Giuseppa; Tornese, Gianluca; Faleschini, Elena; Zuiani, Chiara; Ventura, Alessandro (Pediatrics, 2015)
Congenital hyperinsulinism (CHI) due to diffuse involvement of the pancreas is a challenging and severe illness in children. Its treatment is based on chronic therapy with diazoxide and/or octreotide, followed by partial pancreatectomy, which is often not resolutive. Sirolimus, a mammalian target of rapamycin inhibitor, was reported to be effective in treating CHI in infants. We report here the case of an 8-year-old boy affected by a severe form of CHI due to a biallelic heterozygous ABCC8 mutation who responded to sirolimus with a dramatic improvement in his glucose blood level regulation and quality of life, with no serious adverse events after 6 months of follow-up. To the best of our knowledge, this is the first report of a successful intervention in an older child. It provides a promising basis for further studies comparing sirolimus with other treatments, particularly in older children.

Splenic Infarction in Acute Infectious Mononucleosis. - Naviglio, Samuele; Abate, Maria Valentina; Chinello, Matteo; Ventura, Alessandro (J Emerg Med, 2015)
BACKGROUND: The evaluation of a febrile patient with acute abdominal pain represents a frequent yet possibly challenging situation in the emergency department (ED). Splenic infarction is an uncommon complication of infectious mononucleosis, and may have a wide range of clinical presentations, from dramatic to more subtle. Its pathogenesis is still incompletely understood, yet it may be associated with the occurrence of transient prothrombotic factors. CASE REPORT: We report the case of a 14-year-old boy who presented with fever, sore throat, left upper quadrant abdominal pain, and splenomegaly, with no history of recent trauma. Laboratory tests revealed a markedly prolonged activated partial thromboplastin time and positive lupus anticoagulant. Abdominal ultrasonography showed several hypoechoic areas in the spleen consistent with multiple infarctions. Magnetic resonance imaging eventually confirmed the diagnosis. He was admitted for observation and supportive treatment, and was discharged in good condition after 7 days. WHY SHOULD AN EMERGENCY PHYSICIAN BE AWARE OF THIS?: Spontaneous splenic infarction should be considered in the differential list of patients presenting with left upper quadrant abdominal pain and features of infectious mononucleosis; the diagnosis, however, may not be straightforward, as clinical presentation may also be subtle, and abdominal ultrasonography, which is often used as a first-line imaging modality in pediatric EDs, has low sensitivity in this scenario and may easily miss it. Furthermore, although treatment is mainly supportive, close observation for possible complications is necessary.

Subcutaneous panniculitis-like T-cell lymphoma presenting with diffuse cutaneous edema in a 2-year-old child. - Chinello, Matteo; Naviglio, Samuele; Remotti, Daniele; Locasciulli, Anna; Ventura, Alessandro (J Pediatr Hematol Oncol, 2015)
Keywords: Child, Preschool; Edema; Humans; Lymphoma, T-Cell; Male; Panniculitis; Skin Diseases

Target sequencing approach intended to discover new mutations in non-syndromic intellectual disability. - Morgan, Anna; Gandin, Ilaria; Belcaro, Chiara; Palumbo, Pietro; Palumbo, Orazio; Biamino, Elisa; Dal Col, Valentina; Laurini, Erik; Pricl, Sabrina; Bosco, Paolo; Carella, Massimo; Ferrero, Giovanni Battista; et al. (Mutat Res, 2015)
The technological improvements over the last years made considerable progresses in the knowledge of the etiology of intellectual Disability (ID). However, at present very little is known about the genetic heterogeneity underlying the non-syndromic form of ID (NS-ID). To investigate the genetic basis of NS-ID we analyzed 43 trios and 22 isolated NS-ID patients using a targeted sequencing (TS) approach. 71 NS-ID genes have been selected and sequenced in all subjects. We found putative pathogenic mutations in 7 out of 65 patients. The pathogenic role of mutations was evaluated through sequence comparison and structural analysis was performed to predict the effect of alterations in a 3D computational model through molecular dynamics simulations. Additionally, a deep patient clinical re-evaluation has been performed after the molecular results. This approach allowed us to find novel pathogenic mutations with a detection rate close to 11% in our cohort of patients. This result supports the hypothesis that many NS-ID related genes still remain to be discovered and that NS-ID is a more complex phenotype compared to syndromic form, likely caused by a complex and broad interaction between genes alterations and environment factors.

Three cases of Bartonella quintana infection in children. - Magnolato, Andrea; Pederiva, Federica; Spagnut, Giulia; Maschio, Massimo; Ventura, Alessandro; Taddio, Andrea (Pediatr Infect Dis J, 2015)
We present 3 children affected by B. quintana infection treated at the IRCCS Burlo Garofolo of Trieste between March and April 2013. B. quintana infection is rare but it should be suspected in patients with fever and lymphadenopathy who do not respond to conventional antibiotic treatment. All patients had a complete recovery without sequelae or relapses.

Tinea Incognito. - Paloni, Giulia; Valerio, Enrico; Berti, Irene; Cutrone, Mario (J Pediatr, 2015)

To Extinguish the Fire from Outside the Cell or to Shutdown the Gas Valve Inside? Novel Trends in Anti-Inflammatory Therapies. - Marcuzzi, Annalisa; Piscianz, Elisa; Valencic, Erica; Monasta, Lorenzo; Vecchi Brumatti, Liza; Tommasini, Alberto (Int J Mol Sci, 2015)
Cytokines are the most important soluble mediators of inflammation. Rare pediatric diseases provided exemplar conditions to study the anti-inflammatory efficacy of new generation therapies (biologics/biopharmaceuticals) selectively targeting single cytokines. Monoclonal antibodies and recombinant proteins have revolutionized anti-inflammatory therapies in the last two decades, allowing the specific targeting of single cytokines. They are very effective in extinguishing inflammation from outside the cell, even with the risk of an excessive and prolonged immunosuppression. Small molecules can enter the cell and shutdown the valve of inflammation by directly targeting signal proteins involved in cytokine release or in response to cytokines. They are orally-administrable drugs whose dosage can be easily adjusted to obtain the desired anti-inflammatory effect. This could make these drugs more suitable for a wide range of diseases as stroke, gout, or neurological impairment, where inflammatory activation plays a pivotal role as trigger. Autoinflammatory diseases, which have previously put anti-cytokine proteins in the limelight, can again provide a valuable model to measure the real potential of small inhibitors as anti-inflammatory agents.

Treatment of asthma based on symptoms. - Bibalo, Cristina; Longo, Giorgio; Ventura, Alessandro (J Pediatr, 2015)
Keywords: Asthma; Female; Humans; Male; Spirometry

Two‑gene mutation in a single patient: Biochemical and functional analysis for a correct interpretation of exome results. - Bianco, Anna Monica; Faletra, Flavio; Vozzi, Diego; Girardelli, Martina; Knowles, Alessandra; Tommasini, Alberto; Zauli, Giorgio; Marcuzzi, Annalisa (Mol Med Rep, 2015)
Next-generation sequencing (NGS) has generated a large amount of sequence data with the requirement of frequent critical revisions of reported mutations. This innovative tool has proved to be effective in detecting pathogenic mutations; however, it requires a certain degree of experience to identify incidental findings. In the present study, whole exome sequencing analysis was performed for the molecular diagnosis and correct genotype/phenotype correlation between parents and a patient presenting with an atypical phenotype. In addition, mevalonic acid quantification and frequency analysis of detected variants in public databases and X‑chromosome inactivation (XCI) studies on the patient's mother were performed. V377I as well as the S135L mutations were identified on the mevalonate kinase deficiency gene and the levels of mevalonic acid in the patient were 5,496 µg/ml. A D59G variation, reported in ESP6500 in two healthy individuals, was found on the Martin Probst syndrome gene (RAB40AL). Based on XCI studies on the patient's mother, it is likely that RAB40AL escapes XCI, while still remaining balanced. In conclusion, the results of the present study indicated that the Martin Probst syndrome is an X‑linked condition, which is probably not caused by RAB40AL mutations. Although NGS is a powerful tool to identify pathogenic mutations, the analysis of genetic data requires expert critical revision of all detected variants.

Unusual onset of a case of chronic recurrent multifocal osteomyelitis. - Barrani, M; Massei, F; Scaglione, M; Paolicchi, A; Vitali, S; Ciancia, E M; Crovella, S; Caparello, M C; Consolini, R (Pediatr Rheumatol Online J, 2015)
BACKGROUND: Chronic recurrent multifocal osteomyelitis (CRMO) is a rare condition that commonly affects the clavicle and pelvis. CASE PRESENTATION: We report here a case a 12 years old girl with CRMO arising with recurrent episodes of left supraorbital headache, followed by the appearance of a periorbital dyschromia. Magnetic resonance imaging (MRI) of the skull and orbits revealed an important subacute inflammatory process. Few months after, the child presented a painful swelling of the left clavicle; the histological examination of the related biopsy allowed to establish the diagnosis of CRMO. CONCLUSION: CRMO presenting as acute headache involving neurocranium is rare; to our knowledge this is the first recognized case in the world literature. This pathological condition is frequently misdiagnosed as infection or neoplasm and needs a deep investigation for the differential diagnosis. The physical, laboratoristic and instrumental diagnostic investigations of the patient and the treatment employed are described in detail.

Usher syndrome: an effective sequencing approach to establish a genetic and clinical diagnosis. - Lenarduzzi, S; Vozzi, D; Morgan, A; Rubinato, E; D'Eustacchio, A; Osland, T M; Rossi, C; Graziano, C; Castorina, P; Ambrosetti, U; Morgutti, M; Girotto, G (Hear Res, 2015)
Usher syndrome is an autosomal recessive disorder characterized by retinitis pigmentosa, sensorineural hearing loss and, in some cases, vestibular dysfunction. The disorder is clinically and genetically heterogeneous and, to date, mutations in 11 genes have been described. This finding makes difficult to get a precise molecular diagnosis and offer patients accurate genetic counselling. To overcome this problem and to increase our knowledge of the molecular basis of Usher syndrome, we designed a targeted resequencing custom panel. In a first validation step a series of 16 Italian patients with known molecular diagnosis were analysed and 31 out of 32 alleles were detected (97% of accuracy). After this step, 31 patients without a molecular diagnosis were enrolled in the study. Three out of them with an uncertain Usher diagnosis were excluded. One causative allele was detected in 24 out 28 patients (86%) while the presence of both causative alleles characterized 19 patients out 28 (68%). Sixteen novel and 27 known alleles were found in the following genes: USH2A (50%), MYO7A (7%), CDH23 (11%), PCDH15 (7%) and USH1G (2%). Overall, on the 44 patients the protocol was able to characterize 74 alleles out of 88 (84%). These results suggest that our panel is an effective approach for the genetic diagnosis of Usher syndrome leading to: 1) an accurate molecular diagnosis, 2) better genetic counselling, 3) more precise molecular epidemiology data fundamental for future interventional plans.
Keywords: Adult; Alleles; Cadherins; Extracellular Matrix Proteins; Female; Genetic Counseling; High-Throughput Nucleotide Sequencing; Humans; Male; Middle Aged; Mutation; Myosins; Nerve Tissue Proteins; Usher Syndromes

Validation of the Italian translation of the affective neuroscience personality scales. - Pascazio, Lorenzo; Bembich, Stefano; Nardone, Ilaria B; Vecchiet, Cristina; Guarino, Giuseppina; Clarici, Andrea (Psychol Rep, 2015)
The theoretical perspective on affective neuroscience advanced by Panksepp, identified six basic innate affective systems: the SEEK, FEAR, ANGER, SADNESS, PLAY, and CARE systems. (3) It has been proposed that the fundamental elements of human personality and its variants may be based on the different expressions of these basic emotional systems and their combinations. A self-report inventory, the Affective Neuroscience Personality Scales (ANPS), has been devised with the aim of studying and evaluating personality from this perspective. This study reports data on the initial validation of ANPS Italian translation on a sample of 418 adult participants. Descriptive statistics for each scale were calculated, assessing also their internal consistency, as a measure of reliability and factorial validity. Acceptable internal consistency was found in all but one scale (SADNESS), and a second-order factor analysis identified a more general affective feature of personality hinging on relational characteristics, independent of the dimensions of general positive and negative affect.
Keywords: Adolescent; Adult; Affect; Aged; Aged, 80 and over; Female; Humans; Italy; Male; Middle Aged; Neurosciences; Personality; Personality Inventory; Psychometrics; Young Adult

Vitamin D receptor polymorphisms and expression profile in rheumatoid arthritis brazilian patients. - Cavalcanti, Catarina Addobbati Jordão; De Azevêdo Silva, Jaqueline; de Barros Pita, Will; Veit, Tiago Degani; Monticielo, Odirlei Andre; Xavier, Ricardo Machado; Brenol, João Carlos Tavares; Brenol, Cleiton Viegas; Fragoso, Thiago Sotero; Barbosa, Alexandre Domingues; Duarte, Ângela Luiza Branco Pinto; Oliveira, Renê Donizeti Ribeiro; et al. (Mol Biol Rep, 2015)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic inflammation and important joint commitment, being the most common systemic autoimmune disease worldwide. RA displays important genetic background with a variety of genes contributing to the immune balance breakdown. Recent studies have demonstrated that vitamin D, through its receptor (VDR), is able to regulate the immune balance and suppress the autoimmunity process, being a potential target in autoimmune diseases. In the present genetic association study, we assessed 5 Tag single nucleotide polymorphisms (SNPs) (rs11168268, rs2248098, rs1540339, rs4760648 and rs3890733), which cover most of the VDR gene, in three different Brazilian populations (from Northeast, Southeast and South Brazil). We also evaluated the VDR expression profile in whole blood and monocytes from RA patients. For genotyping study, 428 RA patients and 616 healthy controls were genotyped with fluorogenic allele specific probes on an ABI7500 platform. For gene expression study, VDR mRNA levels of 15 RA patients and 26 healthy individuals were assessed by RT-PCR. Our results showed that SNPs rs4760648 and rs3890733 are associated to RA susceptibility (p value = 0.0026, OR 1.31 and p value = 0.0091, OR 1.28 with statistical power = 0.999 and 0.993, respectively). Regarding RA clinical features, the studied SNPs did not show significant associations. The gene expression assays showed that VDR mRNA levels were down regulated in both whole blood (-3.3 fold) and monocytes (-3.2 fold) of RA patients when compared to healthy controls. Our results, the first reported for distinct Brazilian populations, support a role of the VDR gene in the susceptibility to RA.

Wharton's jelly derived mesenchymal stromal cells: Biological properties, induction of neuronal phenotype and current applications in neurodegeneration research. - Frausin, Stefano; Viventi, Serena; Verga Falzacappa, Lucia; Quattromani, Miriana Jlenia; Leanza, Giampiero; Tommasini, Alberto; Valencic, Erica (Acta Histochem, 2015)
Multipotent mesenchymal stromal cells, also known as mesenchymal stem cells (MSC), can be isolated from bone marrow or other tissues, including fat, muscle and umbilical cord. It has been shown that MSC behave in vitro as stem cells: they self-renew and are able to differentiate into mature cells typical of several mesenchymal tissues. Moreover, the differentiation toward non-mesenchymal cell lineages (e.g. neurons) has been reported as well. The clinical relevance of these cells is mainly related to their ability to spontaneously migrate to the site of inflammation/damage, to their safety profile thanks to their low immunogenicity and to their immunomodulation capacities. To date, MSCs isolated from the post-natal bone marrow have represented the most extensively studied population of adult MSCs, in view of their possible use in various therapeutical applications. However, the bone marrow-derived MSCs exhibit a series of limitations, mainly related to their problematic isolation, culturing and use. In recent years, umbilical cord (UC) matrix (i.e. Wharton's jelly, WJ) stromal cells have therefore emerged as a more suitable alternative source of MSCs, thanks to their primitive nature and the easy isolation without relevant ethical concerns. This review seeks to provide an overview of the main biological properties of WJ-derived MSCs. Moreover, the potential application of these cells for the treatment of some known dysfunctions in the central and peripheral nervous system will also be discussed.

A young soccer player with sudden pain after kicking the ball. - Lega, Sara; Rabach, Ingrid; Barbi, Egidio; Ventura, Alessandro (BMJ, 2015)
Keywords: Adolescent; Athletic Injuries; Emergency Medicine; Fractures, Bone; Humans; Ilium; Male; Soccer

Analysis of 339 pregnancies in 181 women with 13 different forms of inherited thrombocytopenia. - Noris, Patrizia; Schlegel, Nicole; Klersy, Catherine; Heller, Paula G; Civaschi, Elisa; Pujol-Moix, Núria; Fabris, Fabrizio; Favier, Rémi; Gresele, Paolo; Latger-Cannard, Véronique; Cuker, Adam; Nurden, Paquita; et al. (Haematologica, 2014)
Pregnancy in women with inherited thrombocytopenias is a major matter of concern as both the mothers and the newborns are potentially at risk of bleeding. However, medical management of this condition cannot be based on evidence because of the lack of consistent information in the literature. To advance knowledge on this matter, we performed a multicentric, retrospective study evaluating 339 pregnancies in 181 women with 13 different forms of inherited thrombocytopenia. Neither the degree of thrombocytopenia nor the severity of bleeding tendency worsened during pregnancy and the course of pregnancy did not differ from that of healthy subjects in terms of miscarriages, fetal bleeding and pre-term births. The degree of thrombocytopenia in the babies was similar to that in the mother. Only 7 of 156 affected newborns had delivery-related bleeding, but 2 of them died of cerebral hemorrhage. The frequency of delivery-related maternal bleeding ranged from 6.8% to 14.2% depending on the definition of abnormal blood loss, suggesting that the risk of abnormal blood loss was increased with respect to the general population. However, no mother died or had to undergo hysterectomy to arrest bleeding. The search for parameters predicting delivery-related bleeding in the mother suggested that hemorrhages requiring blood transfusion were more frequent in women with history of severe bleedings before pregnancy and with platelet count at delivery below 50 × 10(9)/L.
Keywords: Adult; Female; Humans; Infant, Newborn; Pregnancy; Pregnancy Complications, Hematologic; Retrospective Studies; Thrombocytopenia; Young Adult

Association analysis of bitter receptor genes in five isolated populations identifies a significant correlation between TAS2R43 variants and coffee liking. - Pirastu, Nicola; Kooyman, Maarten; Traglia, Michela; Robino, Antonietta; Willems, Sara M; Pistis, Giorgio; d'Adamo, Pio; Amin, Najaf; D'Eustacchio, Angela; Navarini, Luciano; Sala, Cinzia; Karssen, Lennart C; et al. (PLoS One, 2014)
Coffee, one of the most popular beverages in the world, contains many different physiologically active compounds with a potential impact on people's health. Despite the recent attention given to the genetic basis of its consumption, very little has been done in understanding genes influencing coffee preference among different individuals. Given its markedly bitter taste, we decided to verify if bitter receptor genes (TAS2Rs) variants affect coffee liking. In this light, 4066 people from different parts of Europe and Central Asia filled in a field questionnaire on coffee liking. They have been consequently recruited and included in the study. Eighty-eight SNPs covering the 25 TAS2R genes were selected from the available imputed ones and used to run association analysis for coffee liking. A significant association was detected with three SNP: one synonymous and two functional variants (W35S and H212R) on the TAS2R43 gene. Both variants have been shown to greatly reduce in vitro protein activity. Surprisingly the wild type allele, which corresponds to the functional form of the protein, is associated to higher liking of coffee. Since the hTAS2R43 receptor is sensible to caffeine, we verified if the detected variants produced differences in caffeine bitter perception on a subsample of people coming from the FVG cohort. We found a significant association between differences in caffeine perception and the H212R variant but not with the W35S, which suggests that the effect of the TAS2R43 gene on coffee liking is mediated by caffeine and in particular by the H212R variant. No other significant association was found with other TAS2R genes. In conclusion, the present study opens new perspectives in the understanding of coffee liking. Further studies are needed to clarify the role of the TAS2R43 gene in coffee hedonics and to identify which other genes and pathways are involved in its genetics.
Keywords: Coffee; Genetic Association Studies; Humans; Polymorphism, Single Nucleotide; Receptors, G-Protein-Coupled; Taste

Association between orofacial granulomatosis and Crohn's disease in children: systematic review. - Lazzerini, Marzia; Bramuzzo, Matteo; Ventura, Alessandro (World J Gastroenterol, 2014)
AIM: To review pediatric cases of orofacial granulomatosis (OFG), report disease characteristics, and explore the association between OFG and Crohn's disease. METHODS: We conducted a systematic review according to the PRISMA guidelines. We searched Medline, LILACS, Virtual Health Library, and Web of Knowledge in September 2013 for cases of OFG in the pediatric age range (< 18 years), with no language limitations. All relevant articles were accessed in full text. The manual search included references of retrieved articles. We extracted data on patients' characteristics, disease characteristics, association with other diseases, and treatment. We analyzed the data and reported the results in tables and text. RESULTS: We retrieved 173 reports of OFG in children. Mean age at onset was 11.1 ± 3.8 years (range: 2.0-18 years). Prevalence in males was significant higher than in females (P < 0.001), with a male:female ratio of 2:1. Gastrointestinal signs or symptoms were present in 26.0% of children at the time of OFG diagnosis. Overall, 70/173 (40.4%) children received a concomitant diagnosis of Crohn's disease. In about half (51.4%) of the cases the onset of OFG anticipated the diagnosis of Crohn's disease, with a mean time between the two diagnoses of 13.1 ± 11.6 mo (range: 3-36 mo). Overall, 21/173 (12.1%) of the children with OFG had perianal disease, while 11/173 (6.4%) had a family history of Crohn's disease. Both perianal disease and a family history of Crohn's disease were significantly associated with a higher risk of Crohn's disease diagnosis in children with OFG [relative risk (RR) = 3.10, 95% confidence interval (CI): 2.46-3.90; RR = 2.74, 95%CI: 2.24-3.36, P < 0.0001 for both). Treatment of OFG included steroids (70.8% of children) and other immunosuppressive drugs (42.7%), such as azathioprine, thalidomide and infliximab. CONCLUSION: High prevalence of Crohn's disease in children with OFG suggests that OFG may be a subtype of Crohn's disease.
Keywords: Adolescent; Age of Onset; Child; Child, Preschool; Crohn Disease; Female; Granulomatosis, Orofacial; Humans; Immunosuppressive Agents; Male; Prevalence; Risk Factors; Steroids; Treatment Outcome

Block of the mevalonate pathway triggers oxidative and inflammatory molecular mechanisms modulated by exogenous isoprenoid compounds. - Tricarico, Paola Maura; Kleiner, Giulio; Valencic, Erica; Campisciano, Giuseppina; Girardelli, Martina; Crovella, Sergio; Knowles, Alessandra; Marcuzzi, Annalisa (Int J Mol Sci, 2014)
Deregulation of the mevalonate pathway is known to be involved in a number of diseases that exhibit a systemic inflammatory phenotype and often neurological involvements, as seen in patients suffering from a rare disease called mevalonate kinase deficiency (MKD). One of the molecular mechanisms underlying this pathology could depend on the shortage of isoprenoid compounds and the subsequent mitochondrial damage, leading to oxidative stress and pro-inflammatory cytokines' release. Moreover, it has been demonstrated that cellular death results from the balance between apoptosis and pyroptosis, both driven by mitochondrial damage and the molecular platform inflammasome. In order to rescue the deregulated pathway and decrease inflammatory markers, exogenous isoprenoid compounds were administered to a biochemical model of MKD obtained treating a murine monocytic cell line with a compound able to block the mevalonate pathway, plus an inflammatory stimulus. Our results show that isoprenoids acted in different ways, mainly increasing the expression of the evaluated markers [apoptosis, mitochondrial dysfunction, nucleotide-binding oligomerization-domain protein-like receptors 3 (NALP3), cytokines and nitric oxide (NO)]. Our findings confirm the hypothesis that inflammation is triggered, at least partially, by the shortage of isoprenoids. Moreover, although further studies are necessary, the achieved results suggest a possible role for exogenous isoprenoids in the treatment of MKD.
Keywords: Animals; Apoptosis; Carotenoids; Carrier Proteins; Cell Line; Cytokines; Diterpenes; Humans; Mevalonate Kinase Deficiency; Mevalonic Acid; Mice; Mitochondria; Nitric Oxide; Phytol; Terpenes

Can Lactobacillus fermentum LF10 and Lactobacillus acidophilus LA02 in a slow-release vaginal product be useful for prevention of recurrent vulvovaginal candidiasis?: A clinical study. - Murina, Filippo; Graziottin, Alessandra; Vicariotto, Franco; De Seta, Francesco (J Clin Gastroenterol, 2014)
OBJECTIVE: To assess the effectiveness of the association of 2 specific strains, Lactobacillus fermentum LF10 (DSM 19187) and Lactobacillus acidophilus LA02 (DSM 21717), specifically formulated in slow-release effervescent tablets, in patients with recurrent vulvovaginal candidiasis. STUDY DESIGN: The study was a clinical trial of 58 women diagnosed with recurrent VVC (≥4 culture-confirmed episodes in a 12-mo period). All patients were given 200 mg of fluconazole orally as an induction dose for 3 alternate days during the first treatment week. Afterward, the patients were given a new product formulated in slow-release vaginal tablets containing at least 0.4 billion live cells of each of lactobacillus L. fermentum LF10 and L. acidophilus LA02 (first phase of the prophylactic period), on alternate days for 10 consecutive nights. Patients who were still free of symptoms were given 1 vaginal tablet every week for the next 10 weeks (second phase of the prophylactic period). Patients asymptomatic after the total duration of the observation phase (7 mo) were considered as responders. RESULTS: During the second 10-week prophylactic phase, 49 of 57 (86.0%) patients remained free of clinical recurrence, whereas symptomatic VVC occurred in 8 patients (14.0%). During the 7-month follow-up, 42 patients of 49 (85.7%) were symptom free at the end of the protocol, whereas clinical recurrences occurred in 7 women (14.3%). Overall, 42 of 58 women enrolled in the study (72.4%) experienced no clinical recurrence throughout the 7-month observation phase (responders). CONCLUSIONS: This study strengthens the evidence supporting the use of specific lactobacilli with well-demonstrated activities associated with the creation and maintenance of a vaginal biofilm that hinders the persistence of an infection caused by Candida.
Keywords: Administration, Intravaginal; Adult; Biofilms; Candidiasis, Vulvovaginal; Delayed-Action Preparations; Female; Humans; Italy; Lactobacillus acidophilus; Lactobacillus fermentum; Middle Aged; Probiotics; Recurrence; Tablets; Time Factors; Treatment Outcome; Vagina; Vulva; Young Adult

Childhood high-risk acute lymphoblastic leukemia in first remission: results after chemotherapy or transplant from the AIEOP ALL 2000 study. - Conter, Valentino; Valsecchi, Maria Grazia; Parasole, Rosanna; Putti, Maria Caterina; Locatelli, Franco; Barisone, Elena; Lo Nigro, Luca; Santoro, Nicola; Aricò, Maurizio; Ziino, Ottavio; Pession, Andrea; Testi, Anna Maria; et al. (Blood, 2014)
The outcome of high-risk (HR) acute lymphoblastic leukemia patients enrolled in the AIEOP-BFM ALL 2000 study in Italy is described. HR criteria were minimal residual disease (MRD) levels ≥10(-3) at day 78 (MRD-HR), no complete remission (CR) at day 33, t(4;11) translocation, and prednisone poor response (PPR). Treatment (2 years) included protocol I, 3 polychemotherapy blocks, delayed intensification (protocol IIx2 or IIIx3), cranial radiotherapy, and maintenance. A total of 312 HR patients had a 5-year event-free survival (EFS) of 58.9% (standard error [SE] = 2.8) and an overall survival of 68.9% (SE = 2.6). In hierarchical order, EFS was 45.9% (4.4) in 132 MRD-HR patients, 41.2% (11.9) in 17 patients with no CR at day 33, 36.4% (14.5) in 11 patients with t(4;11), and 74.0% (3.6) in 152 HR patients only for PPR. No statistically significant difference was found for disease-free survival in patients with very HR features [MRD-HR, no CR at day 33, t(4;11) translocation], given hematopoietic stem cell transplantation (HSCT) (n = 66) or chemotherapy only (n = 88), after adjusting for waiting time to HSCT (5.7 months). Patients at HR only for PPR have a favorable outcome. MRD-HR is associated with poor outcome despite intensive treatment and/or HSCT and may qualify for innovative therapies. The study was registered at www.clinicaltrials.gov as #NCT00613457.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Child; Child, Preschool; Combined Modality Therapy; Female; Hematopoietic Stem Cell Transplantation; Humans; Infant; Male; Neoplasm, Residual; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Radiotherapy; Remission Induction; Treatment Outcome

Class IV laser therapy as treatment for chemotherapy-induced oral mucositis in onco-haematological paediatric patients: a prospective study. - Chermetz, Maddalena; Gobbo, Margherita; Ronfani, Luca; Ottaviani, Giulia; Zanazzo, Giulio A; Verzegnassi, Federico; Treister, Nathaniel S; Di Lenarda, Roberto; Biasotto, Matteo; Zacchigna, Serena (Int J Paediatr Dent, 2014)
BACKGROUND: Oral mucositis is a debilitating side effect of chemotherapy. Laser therapy has recently demonstrated efficacy in the management of oral mucositis (OM). AIM: This prospective study was conducted to evaluate the efficacy of class IV laser therapy in patients affected by OM. DESIGN: Eighteen onco-haematological paediatric patients receiving chemotherapy and/or haematopoietic stem cell transplantation, prior to total body irradiation, affected by OM, were enrolled in this study. Patients were treated with class IV laser therapy for four consecutive days; the assessment of OM was performed through WHO Oral Mucositis Grading Objective Scale, and pain was evaluated through visual analogue scale. Patients completed a validated questionnaire, and photographs of lesions were taken during each session. Patients were re-evaluated 11 days after the first day of laser therapy. RESULTS: All patients demonstrated improvement in pain sensation, and all mucositis was fully resolved at the 11-day follow-up visit, with no apparent side effects. Laser therapy was well tolerated with remarkable reduction in pain associated with oral mucositis after 1-2 days of laser therapy. CONCLUSIONS: Given class IV laser therapy appears to be safe, non-invasive, and potentially effective, prospective, randomized, controlled trials are necessary to further assess efficacy and to determine optimal treatment parameters.

Clinical significance of hyper-IgA in a paediatric laboratory series. - Copetti, Valentina; Pastore, Serena; De Pieri, Carlo; Radillo, Oriano; Taddio, Andrea; Ventura, Alessandro; Tommasini, Alberto (Arch Dis Child, 2014)
The causes of extremely elevated IgA, whether isolated or associated with an increase in other classes of immunoglobulin, are poorly defined in paediatrics. We reviewed the diagnostic significance of very high IgA levels (greater than 3 SD above the mean for age) in a cohort of patients referred to a tertiary care children's hospital. Hyper-IgA was found in 91 of 6364 subjects (1.4%) and in 68 cases was not associated with an increased IgG and/or IgM level. Most subjects with hyper-IgA (73.5%) had a severe immune defect, a chronic rheumatic disease or inflammatory bowel disease, while these conditions were very rare in a control group with normal IgA values (8%). Although our results may in part reflect the experience of a tertiary care centre, we suggest that hyper-IgA in children should always arouse suspicion of a serious disease.
Keywords: Adolescent; Child; Child, Preschool; Female; Hospitals, Pediatric; Humans; Hypergammaglobulinemia; Immunoglobulin A; Infant; Italy; Male; Tertiary Care Centers

Common variants in UMOD associate with urinary uromodulin levels: a meta-analysis. - Olden, Matthias; Corre, Tanguy; Hayward, Caroline; Toniolo, Daniela; Ulivi, Sheila; Gasparini, Paolo; Pistis, Giorgio; Hwang, Shih-Jen; Bergmann, Sven; Campbell, Harry; Cocca, Massimiliano; Gandin, Ilaria; et al. (J Am Soc Nephrol, 2014)
Uromodulin is expressed exclusively in the thick ascending limb and is the most abundant protein excreted in normal urine. Variants in UMOD, which encodes uromodulin, are associated with renal function, and urinary uromodulin levels may be a biomarker for kidney disease. However, the genetic factors regulating uromodulin excretion are unknown. We conducted a meta-analysis of urinary uromodulin levels to identify associated common genetic variants in the general population. We included 10,884 individuals of European descent from three genetic isolates and three urban cohorts. Each study measured uromodulin indexed to creatinine and conducted linear regression analysis of approximately 2.5 million single nucleotide polymorphisms using an additive model. We also tested whether variants in genes expressed in the thick ascending limb associate with uromodulin levels. rs12917707, located near UMOD and previously associated with renal function and CKD, had the strongest association with urinary uromodulin levels (P<0.001). In all cohorts, carriers of a G allele of this variant had higher uromodulin levels than noncarriers did (geometric means 10.24, 14.05, and 17.67 μg/g creatinine for zero, one, or two copies of the G allele). rs12446492 in the adjacent gene PDILT (protein disulfide isomerase-like, testis expressed) also reached genome-wide significance (P<0.001). Regarding genes expressed in the thick ascending limb, variants in KCNJ1, SORL1, and CAB39 associated with urinary uromodulin levels. These data indicate that common variants in the UMOD promoter region may influence urinary uromodulin levels. They also provide insights into uromodulin biology and the association of UMOD variants with renal function.
Keywords: Creatinine; European Continental Ancestry Group; Genetic Variation; Humans; Polymorphism, Single Nucleotide; Uromodulin

Consanguinity and hereditary hearing loss in Qatar. - Girotto, Giorgia; Mezzavilla, Massimo; Abdulhadi, Khalid; Vuckovic, Dragana; Vozzi, Diego; Khalifa Alkowari, Moza; Gasparini, Paolo; Badii, Ramin (Hum Hered, 2014)
Qatar is a sovereign state located on the Eastern coast of the Arabian Peninsula in the Persian Gulf. Its native population consists of 3 major subgroups: people of Arabian origin or Bedouins, those from an Eastern or Persian ancestry and individuals with African admixture. Historically, all types of consanguineous marriages have been and still are common in the Qatari population, particularly among first and double-first cousins. Thus, there is a higher risk for most inherited diseases including hereditary hearing loss (HHL). In particular, a hearing loss prevalence of 5.2% has been reported in Qatar, with parental consanguinity being more common among affected individuals as compared with unaffected ones. Our recent molecular results confirm a high homogeneity and level of inbreeding in Qatari HHL patients. Among all HHL genes, GJB2, the major player worldwide, accounts for a minor proportion of cases and at least 3 additional genes have been found to be mutated in Qatari patients. Interestingly, one gene, BDP1, has been described to cause HHL only in this country. These results point towards an unexpected level of genetic heterogeneity despite the high level of inbreeding. This review provides an up-to-date picture of HHL in Qatar and of the impact of consanguinity on this disease.
Keywords: Consanguinity; Hearing Loss; Homozygote; Humans; Inheritance Patterns; Pedigree; Prevalence; Principal Component Analysis; Qatar; Transcription Factor TFIIIB

Diagnostic accuracy of ultrasonography for hand bony fractures in paediatric patients. - Neri, Elena; Barbi, Egidio; Rabach, Ingrid; Zanchi, Chiara; Norbedo, Stefania; Ronfani, Luca; Guastalla, Veronica; Ventura, Alessandro; Guastalla, Pierpaolo (Arch Dis Child, 2014)
OBJECTIVE: Hand fractures are common in childhood, and radiography is the standard diagnostic procedure. US has been used to evaluate bone injuries, mainly in adults for long-bone trauma; there are only a few studies about hand fractures in children. The purpose of this study was to evaluate and confirm the safety and applicability of the US diagnostic procedure in comparison to X-ray diagnosis. STUDY DESIGN: This cross-sectional study involved a convenience sample of young patients (between 2 and 17 years old) who were taken to the emergency department due to hand trauma. After clinical assessment, patients with a suspected hand fracture first underwent X-ray, and subsequently US examination by two different operators; a radiologist experienced in US and a trained emergency physician in "double-blind" fashion. US and radiographic findings were then compared, and sensitivity as well as specificity was calculated. RESULTS: A total of 204 patients were enrolled in the study. Seventy-nine fractures of phalanges or metacarpals were detected by standard radiography. When US imaging was performed by an expert radiologist, 72 fractures were detected with sensitivity and a specificity of 91.1% and 97.6%, respectively. Sensitivity and specificity were found to be (respectively) 91.5% and 96.8% when US was performed by the ED physicians. CONCLUSIONS: US imaging showed excellent sensitivity and specificity results in the diagnosis of hand fractures in children. The study also showed a great agreement between the results of the US carried out by the senior radiologist and those carried out by the paediatric emergency physician, suggesting that US can be performed by an ED physician, allowing a rapid and accurate evaluation in ED and could become the first diagnostic approach whenever a hand fracture is suspected.
Keywords: Adolescent; Child; Child, Preschool; Cross-Sectional Studies; Double-Blind Method; Emergency Service, Hospital; Female; Fractures, Bone; Hand Bones; Humans; Italy; Male; Sensitivity and Specificity

Differences in time course activation of dorsolateral prefrontal cortex associated with low or high risk choices in a gambling task. - Bembich, Stefano; Clarici, Andrea; Vecchiet, Cristina; Baldassi, Giulio; Cont, Gabriele; Demarini, Sergio (Front Hum Neurosci, 2014)
Prefrontal cortex plays an important role in decision making (DM), supporting choices in the ordinary uncertainty of everyday life. To assess DM in an unpredictable situation, a playing card task, such as the Iowa Gambling Task (IGT), has been proposed. This task is supposed to specifically test emotion-based learning, linked to the integrity of the ventromedial prefrontal cortex (VMPFC). However, the dorsolateral prefrontal cortex (DLPFC) has demonstrated a role in IGT performance too. Our aim was to study, by multichannel near-infrared spectroscopy, the contribution of DLPFC to the IGT execution over time. We tested the hypothesis that low and high risk choices would differentially activate DLPFC, as IGT execution progressed. We enrolled 11 healthy adults. To identify DLPFC activation associated with IGT choices, we compared regional differences in oxy-hemoglobin variation, from baseline to the event. The time course of task execution was divided in four periods, each one consisting of 25 choices, and DLPFC activation was distinctly analyzed for low and high risk choices in each period. We found different time courses in DLPFC activation, associated with low or high risk choices. During the first period, a significant DLPFC activation emerged with low risk choices, whereas, during the second period, we found a cortical activation with high risk choices. Then, DLPFC activation decreased to non-significant levels during the third and fourth period. This study shows that DLPFC involvement in IGT execution is differentiated over time and according to choice risk level. DLPFC is activated only in the first half of the task, earlier by low risk and later by high risk choices. We speculate that DLPFC may sustain initial and more cognitive functions, such as attention shifting and response inhibition. The lack of DLPFC activation, as the task progresses, may be due to VMPFC activation, not detectable by fNIRS, which takes over the IGT execution in its second half.

Expression and replication studies to identify new candidate genes involved in normal hearing function. - Girotto, Giorgia; Vuckovic, Dragana; Buniello, Annalisa; Lorente-Cánovas, Beatriz; Lewis, Morag; Gasparini, Paolo; Steel, Karen P (PLoS One, 2014)
Considerable progress has been made in identifying deafness genes, but still little is known about the genetic basis of normal variation in hearing function. We recently carried out a Genome Wide Association Study (GWAS) of quantitative hearing traits in southern European populations and found several SNPs with suggestive but none with significant association. In the current study, we followed up these SNPs to investigate which of them might show a genuine association with auditory function using alternative approaches. Firstly, we generated a shortlist of 19 genes from the published GWAS results. Secondly, we carried out immunocytochemistry to examine expression of these 19 genes in the mouse inner ear. Twelve of them showed distinctive cochlear expression patterns. Four showed expression restricted to sensory hair cells (Csmd1, Arsg, Slc16a6 and Gabrg3), one only in marginal cells of the stria vascularis (Dclk1) while the others (Ptprd, Grm8, GlyBP, Evi5, Rimbp2, Ank2, Cdh13) in multiple cochlear cell types. In the third step, we tested these 12 genes for replication of association in an independent set of samples from the Caucasus and Central Asia. Nine out of them showed nominally significant association (p<0.05). In particular, 4 were replicated at the same SNP and with the same effect direction while the remaining 5 showed a significant association in a gene-based test. Finally, to look for genotype-phenotype relationship, the audiometric profiles of the three genotypes of the most strongly associated gene variants were analyzed. Seven out of the 9 replicated genes (CDH13, GRM8, ANK2, SLC16A6, ARSG, RIMBP2 and DCLK1) showed an audiometric pattern with differences between different genotypes further supporting their role in hearing function. These data demonstrate the usefulness of this multistep approach in providing new insights into the molecular basis of hearing and may suggest new targets for treatment and prevention of hearing impairment.
Keywords: Adult; Animals; DNA Replication; Gene Expression Profiling; Genome-Wide Association Study; Genotype; Hair Cells, Auditory; Hearing; Humans; Mice; Phenotype; Polymorphism, Single Nucleotide; Stria Vascularis

F402L variant in NLRP12 in subjects with undiagnosed periodic fevers and in healthy controls. - De Pieri, Carlo; Vuch, Josef; Athanasakis, Emmanouil; Severini, Giovanni Maria; Crovella, Sergio; Bianco, Anna Monica; Tommasini, Alberto (Clin Exp Rheumatol, 2014)
Keywords: Cryopyrin-Associated Periodic Syndromes; Female; Humans; Intracellular Signaling Peptides and Proteins; Male; Mutation

Fate of lymphocytes after withdrawal of tofacitinib treatment. - Piscianz, Elisa; Valencic, Erica; Cuzzoni, Eva; De Iudicibus, Sara; De Lorenzo, Elisa; Decorti, Giuliana; Tommasini, Alberto (PLoS One, 2014)
Tofacitinib (Tofa) is an inhibitor of Janus Kinase 3, developed for the treatment of autoimmune diseases and for the prevention of transplant rejection. Due to its selective action on proliferating cells, Tofa can offer a way to block T cell activation, without toxic effects on resting cells. However, few studies have investigated the effects of Tofa on lymphocyte activation in vitro. Our aim was to study the action of Tofa on different lymphocyte subsets after in vitro stimulation and to track the behaviour of treated cells after interruption of the treatment. Peripheral blood lymphocytes were stimulated in vitro with mitogen and treated with two concentrations of Tofa. After a first period in culture, cells were washed and further incubated for an additional time. Lymphocyte subsets, activation phenotype and proliferation were assessed at the different time frames. As expected, Tofa was able to reduce the activation and proliferation of lymphocytes in the first four days of treatment. In addition the drug led to a relative decrease of Natural Killer, B cells and CD8 T cells compared to CD4 T cells. However, treated cells were still viable after the first period in culture and begun to proliferate, strikingly, in a dose dependent manner when the drug was removed from the environment by replacing the culture medium. This novel data does not necessarily predict a similar behaviour in vivo, but can warn about the clinical use of this drug when a discontinuation of treatment with Tofa is considered for any reason.
Keywords: Antigens, CD; B-Lymphocytes; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Cell Proliferation; Drug Administration Schedule; Humans; Janus Kinase 3; Killer Cells, Natural; Lymphocyte Activation; Lymphocyte Count; Phytohemagglutinins; Piperidines; Primary Cell Culture; Protein Kinase Inhibitors; Pyrimidines; Pyrroles

A general approach for haplotype phasing across the full spectrum of relatedness. - O'Connell, Jared; Gurdasani, Deepti; Delaneau, Olivier; Pirastu, Nicola; Ulivi, Sheila; Cocca, Massimiliano; Traglia, Michela; Huang, Jie; Huffman, Jennifer E; Rudan, Igor; McQuillan, Ruth; Fraser, Ross M; et al. (PLoS Genet, 2014)
Many existing cohorts contain a range of relatedness between genotyped individuals, either by design or by chance. Haplotype estimation in such cohorts is a central step in many downstream analyses. Using genotypes from six cohorts from isolated populations and two cohorts from non-isolated populations, we have investigated the performance of different phasing methods designed for nominally 'unrelated' individuals. We find that SHAPEIT2 produces much lower switch error rates in all cohorts compared to other methods, including those designed specifically for isolated populations. In particular, when large amounts of IBD sharing is present, SHAPEIT2 infers close to perfect haplotypes. Based on these results we have developed a general strategy for phasing cohorts with any level of implicit or explicit relatedness between individuals. First SHAPEIT2 is run ignoring all explicit family information. We then apply a novel HMM method (duoHMM) to combine the SHAPEIT2 haplotypes with any family information to infer the inheritance pattern of each meiosis at all sites across each chromosome. This allows the correction of switch errors, detection of recombination events and genotyping errors. We show that the method detects numbers of recombination events that align very well with expectations based on genetic maps, and that it infers far fewer spurious recombination events than Merlin. The method can also detect genotyping errors and infer recombination events in otherwise uninformative families, such as trios and duos. The detected recombination events can be used in association scans for recombination phenotypes. The method provides a simple and unified approach to haplotype estimation, that will be of interest to researchers in the fields of human, animal and plant genetics.
Keywords: Chromosome Mapping; Cohort Effect; Family; Genotype; Haplotypes; Humans; Models, Genetic; Pedigree; Phenotype; Recombination, Genetic

Genetic association study of QT interval highlights role for calcium signaling pathways in myocardial repolarization. - Arking, Dan E; Pulit, Sara L; Crotti, Lia; van der Harst, Pim; Munroe, Patricia B; Koopmann, Tamara T; Sotoodehnia, Nona; Rossin, Elizabeth J; Morley, Michael; Wang, Xinchen; Johnson, Andrew D; Lundby, Alicia; et al. (Nat Genet, 2014)
The QT interval, an electrocardiographic measure reflecting myocardial repolarization, is a heritable trait. QT prolongation is a risk factor for ventricular arrhythmias and sudden cardiac death (SCD) and could indicate the presence of the potentially lethal mendelian long-QT syndrome (LQTS). Using a genome-wide association and replication study in up to 100,000 individuals, we identified 35 common variant loci associated with QT interval that collectively explain ∼8-10% of QT-interval variation and highlight the importance of calcium regulation in myocardial repolarization. Rare variant analysis of 6 new QT interval-associated loci in 298 unrelated probands with LQTS identified coding variants not found in controls but of uncertain causality and therefore requiring validation. Several newly identified loci encode proteins that physically interact with other recognized repolarization proteins. Our integration of common variant association, expression and orthogonal protein-protein interaction screens provides new insights into cardiac electrophysiology and identifies new candidate genes for ventricular arrhythmias, LQTS and SCD.
Keywords: Adult; Aged; Arrhythmias, Cardiac; Calcium Signaling; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Ventricles; Humans; Long QT Syndrome; Male; Middle Aged; Myocardium; Polymorphism, Single Nucleotide

Genetic landscape of populations along the Silk Road: admixture and migration patterns. - Mezzavilla, Massimo; Vozzi, Diego; Pirastu, Nicola; Girotto, Giorgia; d'Adamo, Pio; Gasparini, Paolo; Colonna, Vincenza (BMC Genet, 2014)
BACKGROUND: The ancient Silk Road has been a trading route between Europe and Central Asia from the 2(nd) century BCE to the 15(th) century CE. While most populations on this route have been characterized, the genetic background of others remains poorly understood, and little is known about past migration patterns. The scientific expedition "Marco Polo" has recently collected genetic and phenotypic data in six regions (Georgia, Armenia, Azerbaijan, Uzbekistan, Kazakhstan, Tajikistan) along the Silk Road to study the genetics of a number of phenotypes. RESULTS: We characterized the genetic structure of these populations within a worldwide context. We observed a West-East subdivision albeit the existence of a genetic component shared within Central Asia and nearby populations from Europe and Near East. We observed a contribution of up to 50% from Europe and Asia to most of the populations that have been analyzed. The contribution from Asia dates back to ~25 generations and is limited to the Eastern Silk Road. Time and direction of this contribution are consistent with the Mongolian expansion era. CONCLUSIONS: We clarified the genetic structure of six populations from Central Asia and suggested a complex pattern of gene flow among them. We provided a map of migration events in time and space and we quantified exchanges among populations. Altogether these novel findings will support the future studies aimed at understanding the genetics of the phenotypes that have been collected during the Marco Polo campaign, they will provide insights into the history of these populations, and they will be useful to reconstruct the developments and events that have shaped modern Eurasians genomes.
Keywords: Asian Continental Ancestry Group; Commonwealth of Independent States; European Continental Ancestry Group; Gene Flow; Homozygote; Human Migration; Humans; Phenotype; Polymorphism, Single Nucleotide; Principal Component Analysis; Sequence Analysis, DNA

Genome-wide association study of sexual maturation in males and females highlights a role for body mass and menarche loci in male puberty. - Cousminer, Diana L; Stergiakouli, Evangelia; Berry, Diane J; Ang, Wei; Groen-Blokhuis, Maria M; Körner, Antje; Siitonen, Niina; Ntalla, Ioanna; Marinelli, Marcella; Perry, John R B; Kettunen, Johannes; Jansen, Rick; et al. (Hum Mol Genet, 2014)
Little is known about genes regulating male puberty. Further, while many identified pubertal timing variants associate with age at menarche, a late manifestation of puberty, and body mass, little is known about these variants' relationship to pubertal initiation or tempo. To address these questions, we performed genome-wide association meta-analysis in over 11 000 European samples with data on early pubertal traits, male genital and female breast development, measured by the Tanner scale. We report the first genome-wide significant locus for male sexual development upstream of myocardin-like 2 (MKL2) (P = 8.9 × 10(-9)), a menarche locus tagging a developmental pathway linking earlier puberty with reduced pubertal growth (P = 4.6 × 10(-5)) and short adult stature (p = 7.5 × 10(-6)) in both males and females. Furthermore, our results indicate that a proportion of menarche loci are important for pubertal initiation in both sexes. Consistent with epidemiological correlations between increased prepubertal body mass and earlier pubertal timing in girls, body mass index (BMI)-increasing alleles correlated with earlier breast development. In boys, some BMI-increasing alleles associated with earlier, and others with delayed, sexual development; these genetic results mimic the controversy in epidemiological studies, some of which show opposing correlations between prepubertal BMI and male puberty. Our results contribute to our understanding of the pubertal initiation program in both sexes and indicate that although mechanisms regulating pubertal onset in males and females may largely be shared, the relationship between body mass and pubertal timing in boys may be complex and requires further genetic studies.

A girl with photosensitivity and hepatic steatosis. - Pavan, Matteo; Gortani, Giulia; Rubinato, Elisa; Faletra, Flavio; Pastore, Serena; Ventura, Alessandro (J Pediatr, 2014)
Keywords: Child; Diagnosis, Differential; Fatty Liver; Female; Humans; Photosensitivity Disorders; Protoporphyria, Erythropoietic

Global, regional, and national incidence and mortality for HIV, tuberculosis, and malaria during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Murray, Christopher J L; Ortblad, Katrina F; Guinovart, Caterina; Lim, Stephen S; Wolock, Timothy M; Roberts, D Allen; Dansereau, Emily A; Graetz, Nicholas; Barber, Ryan M; Brown, Jonathan C; Wang, Haidong; Duber, Herbert C; et al. (Lancet, 2014)
BACKGROUND: The Millennium Declaration in 2000 brought special global attention to HIV, tuberculosis, and malaria through the formulation of Millennium Development Goal (MDG) 6. The Global Burden of Disease 2013 study provides a consistent and comprehensive approach to disease estimation for between 1990 and 2013, and an opportunity to assess whether accelerated progress has occured since the Millennium Declaration. METHODS: To estimate incidence and mortality for HIV, we used the UNAIDS Spectrum model appropriately modified based on a systematic review of available studies of mortality with and without antiretroviral therapy (ART). For concentrated epidemics, we calibrated Spectrum models to fit vital registration data corrected for misclassification of HIV deaths. In generalised epidemics, we minimised a loss function to select epidemic curves most consistent with prevalence data and demographic data for all-cause mortality. We analysed counterfactual scenarios for HIV to assess years of life saved through prevention of mother-to-child transmission (PMTCT) and ART. For tuberculosis, we analysed vital registration and verbal autopsy data to estimate mortality using cause of death ensemble modelling. We analysed data for corrected case-notifications, expert opinions on the case-detection rate, prevalence surveys, and estimated cause-specific mortality using Bayesian meta-regression to generate consistent trends in all parameters. We analysed malaria mortality and incidence using an updated cause of death database, a systematic analysis of verbal autopsy validation studies for malaria, and recent studies (2010-13) of incidence, drug resistance, and coverage of insecticide-treated bednets. FINDINGS: Globally in 2013, there were 1·8 million new HIV infections (95% uncertainty interval 1·7 million to 2·1 million), 29·2 million prevalent HIV cases (28·1 to 31·7), and 1·3 million HIV deaths (1·3 to 1·5). At the peak of the epidemic in 2005, HIV caused 1·7 million deaths (1·6 million to 1·9 million). Concentrated epidemics in Latin America and eastern Europe are substantially smaller than previously estimated. Through interventions including PMTCT and ART, 19·1 million life-years (16·6 million to 21·5 million) have been saved, 70·3% (65·4 to 76·1) in developing countries. From 2000 to 2011, the ratio of development assistance for health for HIV to years of life saved through intervention was US$4498 in developing countries. Including in HIV-positive individuals, all-form tuberculosis incidence was 7·5 million (7·4 million to 7·7 million), prevalence was 11·9 million (11·6 million to 12·2 million), and number of deaths was 1·4 million (1·3 million to 1·5 million) in 2013. In the same year and in only individuals who were HIV-negative, all-form tuberculosis incidence was 7·1 million (6·9 million to 7·3 million), prevalence was 11·2 million (10·8 million to 11·6 million), and number of deaths was 1·3 million (1·2 million to 1·4 million). Annualised rates of change (ARC) for incidence, prevalence, and death became negative after 2000. Tuberculosis in HIV-negative individuals disproportionately occurs in men and boys (versus women and girls); 64·0% of cases (63·6 to 64·3) and 64·7% of deaths (60·8 to 70·3). Globally, malaria cases and deaths grew rapidly from 1990 reaching a peak of 232 million cases (143 million to 387 million) in 2003 and 1·2 million deaths (1·1 million to 1·4 million) in 2004. Since 2004, child deaths from malaria in sub-Saharan Africa have decreased by 31·5% (15·7 to 44·1). Outside of Africa, malaria mortality has been steadily decreasing since 1990. INTERPRETATION: Our estimates of the number of people living with HIV are 18·7% smaller than UNAIDS's estimates in 2012. The number of people living with malaria is larger than estimated by WHO. The number of people living with HIV, tuberculosis, or malaria have all decreased since 2000. At the global level, upward trends for malaria and HIV deaths have been reversed and declines in tuberculosis deaths have accelerated. 101 countries (74 of which are developing) still have increasing HIV incidence. Substantial progress since the Millennium Declaration is an encouraging sign of the effect of global action. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Epidemics; Female; Global Health; HIV Infections; Humans; Incidence; Malaria; Male; Mortality; Organizational Objectives; Sex Distribution; Tuberculosis

Global, regional, and national levels and causes of maternal mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Kassebaum, Nicholas J; Bertozzi-Villa, Amelia; Coggeshall, Megan S; Shackelford, Katya A; Steiner, Caitlyn; Heuton, Kyle R; Gonzalez-Medina, Diego; Barber, Ryan; Huynh, Chantal; Dicker, Daniel; Templin, Tara; Wolock, Timothy M; et al. (Lancet, 2014)
BACKGROUND: The fifth Millennium Development Goal (MDG 5) established the goal of a 75% reduction in the maternal mortality ratio (MMR; number of maternal deaths per 100,000 livebirths) between 1990 and 2015. We aimed to measure levels and track trends in maternal mortality, the key causes contributing to maternal death, and timing of maternal death with respect to delivery. METHODS: We used robust statistical methods including the Cause of Death Ensemble model (CODEm) to analyse a database of data for 7065 site-years and estimate the number of maternal deaths from all causes in 188 countries between 1990 and 2013. We estimated the number of pregnancy-related deaths caused by HIV on the basis of a systematic review of the relative risk of dying during pregnancy for HIV-positive women compared with HIV-negative women. We also estimated the fraction of these deaths aggravated by pregnancy on the basis of a systematic review. To estimate the numbers of maternal deaths due to nine different causes, we identified 61 sources from a systematic review and 943 site-years of vital registration data. We also did a systematic review of reports about the timing of maternal death, identifying 142 sources to use in our analysis. We developed estimates for each country for 1990-2013 using Bayesian meta-regression. We estimated 95% uncertainty intervals (UIs) for all values. FINDINGS: 292,982 (95% UI 261,017-327,792) maternal deaths occurred in 2013, compared with 376,034 (343,483-407,574) in 1990. The global annual rate of change in the MMR was -0·3% (-1·1 to 0·6) from 1990 to 2003, and -2·7% (-3·9 to -1·5) from 2003 to 2013, with evidence of continued acceleration. MMRs reduced consistently in south, east, and southeast Asia between 1990 and 2013, but maternal deaths increased in much of sub-Saharan Africa during the 1990s. 2070 (1290-2866) maternal deaths were related to HIV in 2013, 0·4% (0·2-0·6) of the global total. MMR was highest in the oldest age groups in both 1990 and 2013. In 2013, most deaths occurred intrapartum or postpartum. Causes varied by region and between 1990 and 2013. We recorded substantial variation in the MMR by country in 2013, from 956·8 (685·1-1262·8) in South Sudan to 2·4 (1·6-3·6) in Iceland. INTERPRETATION: Global rates of change suggest that only 16 countries will achieve the MDG 5 target by 2015. Accelerated reductions since the Millennium Declaration in 2000 coincide with increased development assistance for maternal, newborn, and child health. Setting of targets and associated interventions for after 2015 will need careful consideration of regions that are making slow progress, such as west and central Africa. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Cause of Death; Female; Global Health; HIV Infections; Humans; Maternal Mortality; Models, Statistical; Organizational Objectives; Pregnancy; Pregnancy Complications, Infectious; Risk Factors; Socioeconomic Factors; Time Factors

Global, regional, and national levels of neonatal, infant, and under-5 mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Wang, Haidong; Liddell, Chelsea A; Coates, Matthew M; Mooney, Meghan D; Levitz, Carly E; Schumacher, Austin E; Apfel, Henry; Iannarone, Marissa; Phillips, Bryan; Lofgren, Katherine T; Sandar, Logan; Dorrington, Rob E; et al. (Lancet, 2014)
BACKGROUND: Remarkable financial and political efforts have been focused on the reduction of child mortality during the past few decades. Timely measurements of levels and trends in under-5 mortality are important to assess progress towards the Millennium Development Goal 4 (MDG 4) target of reduction of child mortality by two thirds from 1990 to 2015, and to identify models of success. METHODS: We generated updated estimates of child mortality in early neonatal (age 0-6 days), late neonatal (7-28 days), postneonatal (29-364 days), childhood (1-4 years), and under-5 (0-4 years) age groups for 188 countries from 1970 to 2013, with more than 29,000 survey, census, vital registration, and sample registration datapoints. We used Gaussian process regression with adjustments for bias and non-sampling error to synthesise the data for under-5 mortality for each country, and a separate model to estimate mortality for more detailed age groups. We used explanatory mixed effects regression models to assess the association between under-5 mortality and income per person, maternal education, HIV child death rates, secular shifts, and other factors. To quantify the contribution of these different factors and birth numbers to the change in numbers of deaths in under-5 age groups from 1990 to 2013, we used Shapley decomposition. We used estimated rates of change between 2000 and 2013 to construct under-5 mortality rate scenarios out to 2030. FINDINGS: We estimated that 6·3 million (95% UI 6·0-6·6) children under-5 died in 2013, a 64% reduction from 17·6 million (17·1-18·1) in 1970. In 2013, child mortality rates ranged from 152·5 per 1000 livebirths (130·6-177·4) in Guinea-Bissau to 2·3 (1·8-2·9) per 1000 in Singapore. The annualised rates of change from 1990 to 2013 ranged from -6·8% to 0·1%. 99 of 188 countries, including 43 of 48 countries in sub-Saharan Africa, had faster decreases in child mortality during 2000-13 than during 1990-2000. In 2013, neonatal deaths accounted for 41·6% of under-5 deaths compared with 37·4% in 1990. Compared with 1990, in 2013, rising numbers of births, especially in sub-Saharan Africa, led to 1·4 million more child deaths, and rising income per person and maternal education led to 0·9 million and 2·2 million fewer deaths, respectively. Changes in secular trends led to 4·2 million fewer deaths. Unexplained factors accounted for only -1% of the change in child deaths. In 30 developing countries, decreases since 2000 have been faster than predicted attributable to income, education, and secular shift alone. INTERPRETATION: Only 27 developing countries are expected to achieve MDG 4. Decreases since 2000 in under-5 mortality rates are accelerating in many developing countries, especially in sub-Saharan Africa. The Millennium Declaration and increased development assistance for health might have been a factor in faster decreases in some developing countries. Without further accelerated progress, many countries in west and central Africa will still have high levels of under-5 mortality in 2030. FUNDING: Bill & Melinda Gates Foundation, US Agency for International Development.
Keywords: Child Mortality; Child, Preschool; Global Health; Humans; Infant; Infant Mortality; Infant, Newborn; Organizational Objectives; Risk Factors; Socioeconomic Factors

Hemophagocytic lymphohistiocytosis in total parenteral nutrition dependent children: description of 5 cases and practical tips for management. - Pastore, Serena; Barbieri, Francesca; Di Leo, Grazia; Valencic, Erica; Tommasini, Alberto; Ventura, Alessandro (J Pediatr Hematol Oncol, 2014)
Although total parenteral nutrition (TPN) is mandatory in children with intestinal failure, this treatment is not risk free. The main complications of TPN include catheter-related sepsis, thrombosis, hepatic cholestasis and cirrhosis, metabolic bone disease, and, rarely, reactive hemophagocytic lymphohistiocytosis (HLH). The pathogenesis of HLH in patients with TPN is not known, although some authors hypothesized that it can result from the activation of macrophages because of "fat overload." We reported 5 cases of HLH that occurred in patients with 4 different underlying disorders, all requiring TPN for a long term. In our series, an underlying immunological defect or a serious infection (sepsis) can have triggered HLH. Therefore, it could be reasonable to hypothesize that besides TPN in itself, minor immune defects and infections may act together by overcoming a threshold of immune stimulation, which ultimately leads to HLH.
Keywords: Child, Preschool; Fatty Acids; Female; Humans; Infant; Intestinal Diseases; Lymphohistiocytosis, Hemophagocytic; Male; Parenteral Nutrition, Total; Steroids; Treatment Outcome

Hereditary hearing loss: a 96 gene targeted sequencing protocol reveals novel alleles in a series of Italian and Qatari patients. - Vozzi, D; Morgan, A; Vuckovic, D; D'Eustacchio, A; Abdulhadi, K; Rubinato, E; Badii, R; Gasparini, P; Girotto, G (Gene, 2014)
Deafness is a really common disorder in humans. It can begin at any age with any degree of severity. Hereditary hearing loss is characterized by a vast genetic heterogeneity with more than 140 loci described in humans but only 65 genes so far identified. Families affected by hearing impairment would have real advantages from an early molecular diagnosis that is of primary relevance in genetic counseling. In this perspective, here we report a family-based approach employing Ion Torrent DNA sequencing technology to analyze coding and UTR regions of 96 genes related to hearing function and loss in a first series of 12 families coming from Italy and Qatar. Using this approach we were able to find the causative gene in 4 out of these 12 families (33%). In particular 5 novel alleles were identified in the following genes LOXHD1, TMPRSS3, TECTA and MYO15A already associated with hearing impairment. Our study confirms the usefulness of a targeted sequencing approach despite larger numbers are required for further validation and for defining a molecular epidemiology picture of hearing loss in these two countries.
Keywords: Alleles; Amino Acid Sequence; Carrier Proteins; Extracellular Matrix Proteins; Female; Genetic Testing; GPI-Linked Proteins; Hearing Loss; Humans; Italy; Male; Membrane Proteins; Molecular Sequence Data; Mutation; Myosins; Neoplasm Proteins; Pedigree; Qatar; Sequence Analysis, DNA; Serine Endopeptidases; Untranslated Regions

Heterogeneity of mesenchymal stromal cells in lymphoproliferative disorders. - Campioni, Diana; Voltan, Rebecca; Tisato, Veronica; Zauli, Giorgio (Front Biosci (Landmark Ed), 2014)
Accumulating evidence indicates that bone marrow microenvironment plays an important role in the pathogenesis of some myeloid and lymphoid hematological malignancies (HM). Among different environmental associated parameters, those related to functional, cytogenetic and immunological integrity of mesenchymal stromal cells (MSC) are particularly relevant. Functional alterations and immunophenotypic abnormalities have been described in MSC obtained from HM patients. These data seem to confirm the defective biological pattern of MSC especially in myeloid diseases, while MSC cytogenetic profile in HM is still an open question, because it is not clear whether BM stromal cells are "culprit or bystander" displaying or not an abnormal karyotype. Contradictory findings were reported in different HM but the functional implications of altered MSC karyotype need to be further addressed also in light of a clinical use of MSC. A "pathological" in vivo supportive function of endogenous MSC, which provide important survival and drug resistance signals to leukemic cells especially in lymphoproliferative disorders, is suggested. Thus, the mechanisms underlying these protective versus cytotoxic effects exerted by MSC on leukemic cells need further investigations.
Keywords: Humans; Immunophenotyping; Karyotyping; Lymphoproliferative Disorders; Mesenchymal Stromal Cells

Human recombinant lysozyme downregulates advanced glycation endproduct-induced interleukin-6 production and release in an in-vitro model of human proximal tubular epithelial cells. - Gallo, Davide; Cocchietto, Moreno; Masat, Elisa; Agostinis, Chiara; Harei, Elisa; Veronesi, Paolo; Sava, Gianni (Exp Biol Med (Maywood), 2014)
Diabetic nephropathy is the leading cause of chronic renal disease and one of the major causes of cardiovascular mortality. Evidence suggests that its progression is due to the chronic hyperglycemia consequent to the production and accumulation of advanced glycation endproducts (AGEs). Lysozyme was shown to posses AGE-sequestering properties and the capacity to reduce the severity of the early stage manifestations of the diabetic nephropathy. This study was aimed to contribute to the understanding the molecular mechanisms of lysozyme effectiveness in the diabetic nephropathy, using an in-vitro cellular model, represented by the HK-2 cells, human proximal tubular epithelial cells. Lysozyme significantly reduced the AGE-induced IL-6 mRNA and an ELISA assay showed also a decreased release of the functional protein with a dose-dependent trend. In addition, lysozyme prevented macrophage recruitment, suggesting its capacity to elicit an anti-inflammatory action. We may conclude that the protective action of lysozyme on the nephrotoxic effects of AGE may depend, at least in part, on its ability to prevent the production and release of inflammatory mediators, such as IL-6 and to reduce macrophage recruitment in the inflammatory sites.
Keywords: Cell Line; Cell Movement; Cell Survival; Chemokine CX3CL1; Diabetic Nephropathies; Down-Regulation; Epithelial Cells; Glycosylation End Products, Advanced; Humans; Inflammation Mediators; Interleukin-18; Interleukin-6; Kidney Tubules, Proximal; Macrophage Activation; Macrophages; Muramidase; Recombinant Proteins; RNA, Messenger; Tumor Necrosis Factor-alpha; U937 Cells

Immunomodulation mediated by a herbal syrup containing a standardized Echinacea root extract: a pilot study in healthy human subjects on cytokine gene expression. - Dapas, B; Dall'Acqua, S; Bulla, R; Agostinis, C; Perissutti, B; Invernizzi, S; Grassi, G; Voinovich, D (Phytomedicine, 2014)
In this study, the immunomodulatory effect of a triply standardized Echinacea angustifolia root extract (Polinacea(®)) was evaluated in 10 healthy subjects. Ten ml of syrup containing one hundred mg of extract (corresponding to 4.7 mg of Echinacoside and 8.0mg of a high molecular weight-20,000 Da- polysaccharide) were administered as a herbal syrup once a day for one month. The immunomodulatory effect was evaluated before and after herbal syrup administration evaluating the expression levels of the cytokines IL-2, IL-8, IL-6 and TNF-α. Cytokine expression was studied in lympho-monocytes and in plasma samples measuring the mRNA and protein levels, respectively. The results were analysed by ANOVA and non-parametric Friedman rank sum tests; when possible it was adopted a pair-wise comparisons at different post-treatment times, using the paired t-tests with Holm correction. The correlation between the variations of cytokine plasma levels and the respective mRNA was carried out using a linear regression model. In lympho-monocytes our data indicate the up-regulation of the mRNA levels of IL-2 and IL-8 and the down regulation of the mRNA levels of the pro-inflammatory cytokines TNF-α and IL6. The differential regulation was maximal after 14 days of treatment. IL-2 up-regulation and IL-6 down-regulation were also confirmed at the protein level in plasma. Finally, the up-regulation of the mRNA of IL-2/IL-8 and the down-regulation of IL-6 positively correlated with the protein levels detected in the plasma. In conclusion, this pilot study suggests a relevant role for the standardized Echinacea angustifolia root extract in the control of cytokine expression. This first demonstration of the immuno-modulating activity of Echinacea angustifolia root extract in the healthy subject, supports at least in part the common use of such products as health promoting supplement.
Keywords: Adult; Cytokines; Down-Regulation; Echinacea; Female; Glycosides; Healthy Volunteers; Humans; Immunomodulation; Interleukin-2; Interleukin-6; Interleukin-8; Lymphocytes; Male; Middle Aged; Monocytes; Pilot Projects; Plant Extracts; Plant Roots; Tumor Necrosis Factor-alpha

In vitro endothelial cell proliferation assay reveals distinct levels of proangiogenic cytokines characterizing sera of healthy subjects and of patients with heart failure. - Voltan, Rebecca; Zauli, Giorgio; Rizzo, Paola; Fucili, Alessandro; Pannella, Micaela; Marci, Roberto; Tisato, Veronica; Ferrari, Roberto; Secchiero, Paola (Mediators Inflamm, 2014)
Although myocardial angiogenesis is thought to play an important role in heart failure (HF), the involvement of circulating proinflammatory and proangiogenic cytokines in the pathogenesis and/or prognosis of HF has not been deeply investigated. By using a highly standardized proliferation assay with human endothelial cells, we first demonstrated that sera from older (mean age 52 ± 7.6 years; n = 46) healthy donors promoted endothelial cell proliferation to a significantly higher extent compared to sera obtained from younger healthy donors (mean age 29 ± 8.6 years; n = 20). The promotion of endothelial cell proliferation was accompanied by high serum levels of several proangiogenic cytokines. When we assessed endothelial cell proliferation in response to HF patients' sera, we observed that a subset of sera (n = 11) promoted cell proliferation to a significantly lesser extent compared to the majority of sera (n = 18). Also, in this case, the difference between the patient groups in the ability to induce endothelial cell proliferation correlated to significant (P < 0.05) differences in serum proangiogenic cytokine levels. Unexpectedly, HF patients associated to the highest endothelial proliferation index showed the worst prognosis as evaluated in terms of subsequent cardiovascular events in the follow-up, suggesting that high levels of circulating proangiogenic cytokines might be related to a worse prognosis.
Keywords: Adult; Cell Proliferation; Cells, Cultured; Chemokines; Cytokines; Heart Failure; Human Umbilical Vein Endothelial Cells; Humans; Middle Aged; Neovascularization, Pathologic; Prognosis

In vivo detection of polyomaviruses JCV and SV40 in mesenchymal stem cells from human umbilical cords. - Comar, Manola; Delbue, Serena; Zanotta, Nunzia; Valencic, Erica; Piscianz, Elisa; Del Savio, Rossella; Tesser, Alessandra; Tommasini, Alberto; Ferrante, Pasquale (Pediatr Blood Cancer, 2014)
BACKGROUND: Multipotent stromal cells are present in the Wharton's jelly matrix (WJSC) of the umbilical cord and can be used as an allogeneic source of cells to treat immunological disorders. Recently it was demonstrated that adult bone marrow (BM)-derived mesenchimal stromal cells (MSC) are susceptible to infection with viruses showing potential oncogenic properties, such as the polyomavirus JC (JCV). The aim of this study was to investigate the presence of human polyomaviruses (JCV, BK Virus-BKV, SV40, and Merkel cell polyomavirus-MCPyV) in WJSC, and explore the risk of infection. PROCEDURE: MSC samples from 35 umbilical cords were investigated by quantitative Real Time PCRs for the presence of DNA sequences of JCV, BKV, SV40, and MCPyV. RESULTS: JCV DNA was detected in 1/35 (2.8%) of MSC samples, while SV40 DNA was found in 3/35 (8.6%) of the examined samples. None of the samples showed sequences of BKV and MCPyV. CONCLUSIONS: The present study demonstrates the in vivo ability of polyomaviruses to infect WJSC. Since the therapeutic approach with the WJSC has high potentiality and a more intensive use can be easily hypothesized, the need to develop consensus guidelines to detect rare viral infections in MSC is pressing.
Keywords: DNA, Viral; Female; Fetal Blood; Humans; JC Virus; Male; Mesenchymal Stromal Cells; Polyomavirus Infections; Simian virus 40; Tumor Virus Infections

Influence of HLA-G polymorphisms in human immunodeficiency virus infection and hepatitis C virus co-infection in Brazilian and Italian individuals. - da Silva, G K; Vianna, Priscila; Veit, Tiago Degani; Crovella, Sergio; Catamo, Eulalia; Cordero, Elvira Alicia Aparicio; Mattevi, Vanessa Suñé; Lazzaretti, Rosmeri Kuhmmer; Sprinz, Eduardo; Kuhmmer, Regina; Chies, José Artur Bogo (Infect Genet Evol, 2014)
OBJECTIVE: This study aimed to investigate the role of Human Leukocyte Antigen (HLA)-G in the susceptibility to HIV-1 infection through the analysis of the HLA-G 3' untranslated region (UTR) polymorphisms 14 bp insertion/deletion (rs66554220) and +3142C>G (rs1063320). DESIGN: We analyzed 582 HIV-1 infected patients and 626 uninfected individuals from Brazil and Italy in a case-control study. METHODS: HLA-G polymorphisms were genotyped using PCR, PCR-RFLP assays or direct sequencing. All analyses were stratified by ethnicity. Genotypic, allelic and diplotypic frequencies were compared between HIV-1 infected subjects and controls using Chi-square or Fischer exact tests. Also, haplotypic frequencies were estimated using MLocus software. RESULTS: African-derived HIV-infected individuals presented a higher frequency of the 14 bp insertion allele as compared to non-infected individuals (0.468 versus 0.373, respectively; p(Bonf) = 0.010). A higher frequency of the 14 bp insertion +3142G (insG) haplotype (0.456 versus 0.346, p<0.001) and the insG/insG diplotype (OR=1.88, 95%CI = 1.08-3.23, p=0.021) was observed among African-derived patients as compared to uninfected controls. Also, we observed a higher frequency of the ins/ins genotype among African-derived HIV patients co-infected with HCV (OR=2.78, 95%CI = 1.20-6.49, p = 0.008). CONCLUSIONS: Our data point out to an increased frequency of alleles and genotypes associated with low HLA-G expression among African-derived patients, suggesting a potential role for HLA-G in the susceptibility to HIV-1 infection and HCV co-infection in those individuals.
Keywords: 3' Untranslated Regions; Adolescent; Adult; African Continental Ancestry Group; Aged; Brazil; Coinfection; Gene Frequency; Genetic Variation; Haplotypes; Hepatitis C; HIV Infections; HLA-G Antigens; Humans; Italy; Male; Middle Aged; Polymorphism, Single Nucleotide; Young Adult

Inhibition of mesenchymal stromal cells by pre-activated lymphocytes and their culture media. - Valencic, Erica; Loganes, Claudia; Cesana, Stefania; Piscianz, Elisa; Gaipa, Giuseppe; Biagi, Ettore; Tommasini, Alberto (Stem Cell Res Ther, 2014)
INTRODUCTION: Despite having a proven immunosuppressive potential in vitro, human mesenchymal stromal cells (MSCs) are reported to display variable efficacy in vivo and, in fact, their proven benefit in the clinical practice is still limited and controversial. METHODS: The interplay between clinical grade MSCs and pre-activated donor lymphocytes or selected lymphocyte subsets was studied in vitro. The kinetics of MSC growth and viability was evaluated by adhesion-dependent changes of culture plate impedance and biochemically by a colorimetric assay. Activation of natural killer (NK) cells was assessed as well, using a flow cytometry assay. RESULTS: A strong inhibition of MSC growth was rapidly induced by the addition of pre-activated lymphocytes but not of resting lymphocytes. Inhibition seems not to be attributable to a single cell population, as similar results can be obtained by depleting NK cells or by using either selected CD4+ or CD8+ lymphocytes. In addition, conditioned medium (CM) from activated lymphocytes was able to inhibit MSC growth in a dose-dependent manner. Furthermore, licensing with IFN-γ partially protected MSCs from pre-activated lymphocytes but not from their CM. These results suggest an inhibitory role of lymphocyte-activation-derived substances. However, the identification of a single molecule responsible for MSC inhibition remained elusive, even if preliminary experiments showed that ATP and, to a lesser extent, TNF-α might play a role. CONCLUSIONS: These results suggest that survival of MSCs can be affected by soluble mediators released by activated lymphocytes. Thus it can be hypothesized that MSC immunosuppressive action in vivo could be impaired by ongoing immune activation through the release of inflammatory mediators.
Keywords: CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Cell Proliferation; Cell Survival; Cells, Cultured; Coculture Techniques; Culture Media, Conditioned; Cytokines; Humans; Killer Cells, Natural; Lymphocyte Activation; Mesenchymal Stromal Cells

Intestinal-mucosa anti-transglutaminase antibody assays to test for genetic gluten intolerance. - Quaglia, Sara; De Leo, Luigina; Ziberna, Fabiana; Vatta, Serena; Villanacci, Vincenzo; Granzotto, Marilena; Petix, Vincenzo; Martelossi, Stefano; Di Leo, Grazia; Torelli, Lucio; Not, Tarcisio (Cell Mol Immunol, 2014)
Keywords: Celiac Disease; Cell Surface Display Techniques; Child; Diet, Gluten-Free; Disease Progression; Early Diagnosis; Female; Follow-Up Studies; HLA-DQ Antigens; Humans; Immunoassay; Immunoglobulin A; Intestinal Mucosa; Male; Prospective Studies; Transglutaminases

Inverse correlation between circulating levels of TNF-related apoptosis-inducing ligand and 17β-estradiol. - Zauli, Giorgio; Tisato, Veronica; Melloni, Elisabetta; Volpato, Stefano; Cervellati, Carlo; Bonaccorsi, Gloria; Radillo, Oriano; Marci, Roberto; Secchiero, Paola (J Clin Endocrinol Metab, 2014)
CONTEXT: The regulation of the circulating levels of TNF-related apoptosis-inducing ligand (TRAIL), a cytokine of the TNF family, playing a key role in the immune surveillance against cancer, is incompletely understood. OBJECTIVE: The objective of the study was to investigate the potential link between TRAIL and 17β-estradiol. DESIGN, SETTING, AND PARTICIPANTS: Circulating TRAIL levels were measured by an ELISA in plasma samples (n = 246) of healthy, age-matched (range 30-70 y) men and women and in the sera (n = 180) of females belonging to different physiopathological conditions (childhood, pregnancy, under gonadotropin treatment, menopause) characterized by different levels of circulating 17β-estradiol. RESULTS: TRAIL plasma levels in women with aged younger than 50 years were significantly lower compared with age-matched men, whereas in woman 50 years old or older, TRAIL levels were significantly higher compared with the age-matched men and with the younger women. Moreover, an analysis of women with different conditions revealed a significant inverse correlation between the serum levels of TRAIL and 17β-estradiol, with the lowest levels of TRAIL being observed during pregnancy and the highest in childhood and in postmenopausal women. Moreover, gonadotropin treatment in women undergoing assisted reproduction was accompanied by an acute decrease of serum TRAIL levels. Finally, in vitro treatment with 17β-estradiol decreased the TRAIL expression levels in peripheral blood mononuclear cells. CONCLUSIONS: Our data suggest that 17β-estradiol plays a role in regulating TRAIL circulating levels. The demonstration that postmenopausal women exhibit the highest TRAIL levels is of particular interest in light of a previous large study population showing that TRAIL is positively correlated to the overall survival.
Keywords: Adult; Aged; Case-Control Studies; Child; Child, Preschool; Estradiol; Female; Humans; Infant; Male; Middle Aged; Pregnancy; Sex Factors; TNF-Related Apoptosis-Inducing Ligand; Young Adult

Long-term follow-up in children with benign convulsions associated with gastroenteritis. - Verrotti, Alberto; Moavero, Romina; Vigevano, Federico; Cantonetti, Laura; Guerra, Azzurra; Spezia, Elisabetta; Tricarico, Antonella; Nanni, Giuliana; Agostinelli, Sergio; Chiarelli, Francesco; Parisi, Pasquale; Capovilla, Giuseppe; et al. (Eur J Paediatr Neurol, 2014)
BACKGROUND: The outcome of benign convulsions associated with gastroenteritis (CwG) has generally been reported as being excellent. However, these data need to be confirmed in studies with longer follow-up evaluations. AIM: To assess the long-term neurological outcome of a large sample of children presenting with CwG. METHODS: We reviewed clinical features of 81 subjects presenting with CwG (1994-2010) from three different Italian centers with a follow-up period of at least 3 years. RESULTS: Follow-up period ranged from 39 months to 15 years (mean 9.8 years). Neurological examination and cognitive level at the last evaluation were normal in all the patients. A mild attention deficit was detected in three cases (3.7%). Fourteen children (17.3%) received chronic anti-epileptic therapy. Interictal EEG abnormalities detected at onset in 20 patients (24.7%) reverted to normal. Transient EEG epileptiform abnormalities were detected in other three cases (3.7%), and a transient photosensitivity in one (1.2%). No recurrence of CwG was observed. Three patients (3.7%) presented with a febrile seizure and two (2.5%) with an unprovoked seizure, but none developed epilepsy. CONCLUSIONS: The long-term evaluation of children with CwG confirms the excellent prognosis of this condition, with normal psychomotor development and low risk of relapse and of subsequent epilepsy.
Keywords: Adolescent; Anticonvulsants; Attention Deficit Disorder with Hyperactivity; Child; Child, Preschool; Electroencephalography; Epilepsy; Female; Gastroenteritis; Humans; Longitudinal Studies; Male; Neurologic Examination; Retrospective Studies

Making the first days of life safer: time for a new protocol? - Paviotti, G; Demarini, S; Verardi, G; De Cunto, A; Davanzo, R (J Perinatol, 2014)
Keywords: Beds; Female; Humans; Infant Care; Male

Medical treatments for endometriosis-associated pelvic pain. - Zito, Gabriella; Luppi, Stefania; Giolo, Elena; Martinelli, Monica; Venturin, Irene; Di Lorenzo, Giovanni; Ricci, Giuseppe (Biomed Res Int, 2014)
The main sequelae of endometriosis are represented by infertility and chronic pelvic pain. Chronic pelvic pain causes disability and distress with a very high economic impact. In the last decades, an impressive amount of pharmacological agents have been tested for the treatment of endometriosis-associated pelvic pain. However, only a few of these have been introduced into clinical practice. Following the results of the controlled studies available, to date, the first-line treatment for endometriosis associated pain is still represented by oral contraceptives used continuously. Progestins represent an acceptable alternative. In women with rectovaginal lesions or colorectal endometriosis, norethisterone acetate at low dosage should be preferred. GnRH analogues may be used as second-line treatment, but significant side effects should be taken into account. Nonsteroidal anti-inflammatory drugs are widely used, but there is inconclusive evidence for their efficacy in relieving endometriosis-associated pelvic pain. Other agents such as GnRH antagonist, aromatase inhibitors, immunomodulators, selective progesterone receptor modulators, and histone deacetylase inhibitors seem to be very promising, but there is not enough evidence to support their introduction into routine clinical practice. Some other agents, such as peroxisome proliferator activated receptors-γ ligands, antiangiogenic agents, and melatonin have been proven to be efficacious in animal studies, but they have not yet been tested in clinical studies.
Keywords: Endometriosis; Female; Gonadotropin-Releasing Hormone; Histone Deacetylase Inhibitors; Hormone Antagonists; Humans; Pain Management; Pelvic Pain; Progestins

Mevalonate kinase deficiency and IBD: shared genetic background. - Bianco, Anna Monica; Girardelli, Martina; Vozzi, Diego; Crovella, Sergio; Kleiner, Giulio; Marcuzzi, Annalisa (Gut, 2014)
Keywords: Genetic Predisposition to Disease; Humans; Inflammatory Bowel Diseases

Midline 1 directs lytic granule exocytosis and cytotoxicity of mouse killer T cells. - Boding, Lasse; Hansen, Ann K; Meroni, Germana; Johansen, Bo B; Braunstein, Thomas H; Bonefeld, Charlotte M; Kongsbak, Martin; Jensen, Benjamin A H; Woetmann, Anders; Thomsen, Allan R; Odum, Niels; von Essen, Marina R; et al. (Eur J Immunol, 2014)
Midline 1 (MID1) is a microtubule-associated ubiquitin ligase that regulates protein phosphatase 2A activity. Loss-of-function mutations in MID1 lead to the X-linked Opitz G/BBB syndrome characterized by defective midline development during embryogenesis. Here, we show that MID1 is strongly upregulated in murine cytotoxic lymphocytes (CTLs), and that it controls TCR signaling, centrosome trafficking, and exocytosis of lytic granules. In accordance, we find that the killing capacity of MID1(-/-) CTLs is impaired. Transfection of MID1 into MID1(-/-) CTLs completely rescued lytic granule exocytosis, and vice versa, knockdown of MID1 inhibited exocytosis of lytic granules in WT CTLs, cementing a central role for MID1 in the regulation of granule exocytosis. Thus, MID1 orchestrates multiple events in CTL responses, adding a novel level of regulation to CTL activation and cytotoxicity.
Keywords: Animals; Blotting, Western; Cytotoxicity, Immunologic; Exocytosis; Flow Cytometry; Mice; Mice, Knockout; Mice, Transgenic; Proteins; Reverse Transcriptase Polymerase Chain Reaction; Secretory Vesicles; T-Lymphocytes, Cytotoxic

Molecular analysis of Fanconi anemia: the experience of the Bone Marrow Failure Study Group of the Italian Association of Pediatric Onco-Hematology. - De Rocco, Daniela; Bottega, Roberta; Cappelli, Enrico; Cavani, Simona; Criscuolo, Maria; Nicchia, Elena; Corsolini, Fabio; Greco, Chiara; Borriello, Adriana; Svahn, Johanna; Pillon, Marta; Mecucci, Cristina; et al. (Haematologica, 2014)
Fanconi anemia is an inherited disease characterized by congenital malformations, pancytopenia, cancer predisposition, and sensitivity to cross-linking agents. The molecular diagnosis of Fanconi anemia is relatively complex for several aspects including genetic heterogeneity with mutations in at least 16 different genes. In this paper, we report the mutations identified in 100 unrelated probands enrolled into the National Network of the Italian Association of Pediatric Hematoly and Oncology. In approximately half of these cases, mutational screening was carried out after retroviral complementation analyses or protein analysis. In the other half, the analysis was performed on the most frequently mutated genes or using a next generation sequencing approach. We identified 108 distinct variants of the FANCA, FANCG, FANCC, FANCD2, and FANCB genes in 85, 9, 3, 2, and 1 families, respectively. Despite the relatively high number of private mutations, 45 of which are novel Fanconi anemia alleles, 26% of the FANCA alleles are due to 5 distinct mutations. Most of the mutations are large genomic deletions and nonsense or frameshift mutations, although we identified a series of missense mutations, whose pathogenetic role was not always certain. The molecular diagnosis of Fanconi anemia is still a tiered procedure that requires identifying candidate genes to avoid useless sequencing. Introduction of next generation sequencing strategies will greatly improve the diagnostic process, allowing a rapid analysis of all the genes.
Keywords: Amino Acid Substitution; Cell Line; Cohort Studies; Computational Biology; Databases, Nucleic Acid; Fanconi Anemia; Fanconi Anemia Complementation Group Proteins; Founder Effect; Genotype; Humans; Italy; Mosaicism; Mutation; Polymorphism, Single Nucleotide

Multiple Ileo-Ileal Intussusceptions Caused by Eosinophilic Enteropathy. - Bramuzzo, Matteo; Martelossi, Stefano; Villanacci, Vincenzo; Maschio, Massimo; Costa, Stefano; Ventura, Alessandro (J Pediatr Gastroenterol Nutr, 2014)

MYH9-related disease: a novel prognostic model to predict the clinical evolution of the disease based on genotype-phenotype correlations. - Pecci, Alessandro; Klersy, Catherine; Gresele, Paolo; Lee, Kieran J D; De Rocco, Daniela; Bozzi, Valeria; Russo, Giovanna; Heller, Paula G; Loffredo, Giuseppe; Ballmaier, Matthias; Fabris, Fabrizio; Beggiato, Eloise; et al. (Hum Mutat, 2014)
MYH9-related disease (MYH9-RD) is a rare autosomal-dominant disorder caused by mutations in the gene for nonmuscle myosin heavy chain IIA (NMMHC-IIA). MYH9-RD is characterized by a considerable variability in clinical evolution: patients present at birth with only thrombocytopenia, but some of them subsequently develop sensorineural deafness, cataract, and/or nephropathy often leading to end-stage renal disease (ESRD). We searched for genotype-phenotype correlations in the largest series of consecutive MYH9-RD patients collected so far (255 cases from 121 families). Association of genotypes with noncongenital features was assessed by a generalized linear regression model. The analysis defined disease evolution associated to seven different MYH9 genotypes that are responsible for 85% of MYH9-RD cases. Mutations hitting residue R702 demonstrated a complete penetrance for early-onset ESRD and deafness. The p.D1424H substitution associated with high risk of developing all the noncongenital manifestations of disease. Mutations hitting a distinct hydrophobic seam in the NMMHC-IIA head domain or substitutions at R1165 associated with high risk of deafness but low risk of nephropathy or cataract. Patients with p.E1841K, p.D1424N, and C-terminal deletions had low risk of noncongenital defects. These findings are essential to patients' clinical management and genetic counseling and are discussed in view of molecular pathogenesis of MYH9-RD.
Keywords: Adult; Age of Onset; Amino Acid Substitution; Cataract; Female; Genetic Association Studies; Genotype; Hearing Loss, Sensorineural; Humans; Italy; Linear Models; Male; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Phenotype; Risk Factors; Thrombocytopenia

Next generation sequencing in nonsyndromic intellectual disability: from a negative molecular karyotype to a possible causative mutation detection. - Athanasakis, Emmanouil; Licastro, Danilo; Faletra, Flavio; Fabretto, Antonella; Dipresa, Savina; Vozzi, Diego; Morgan, Anna; d'Adamo, Adamo P; Pecile, Vanna; Biarnés, Xevi; Gasparini, Paolo (Am J Med Genet A, 2014)
The identification of causes underlying intellectual disability (ID) is one of the most demanding challenges for clinical Geneticists and Researchers. Despite molecular diagnostics improvements, the vast majority of patients still remain without genetic diagnosis. Here, we report the results obtained using Whole Exome and Target Sequencing on nine patients affected by isolated ID without pathological copy number variations, which were accurately selected from an initial cohort of 236 patients. Three patterns of inheritance were used to search for: (1) de novo, (2) X-linked, and (3) autosomal recessive variants. In three of the nine proband-parent trios analyzed, we identified and validated two de novo and one X-linked potentially causative mutations located in three ID-related genes. We proposed three genes as ID candidate, carrying one de novo and three X-linked mutations. Overall, this systematic proband-parent trio approach using next generation sequencing could explain a consistent percentage of patients with isolated ID, thus increasing our knowledge on the molecular bases of this disease and opening new perspectives for a better diagnosis, counseling, and treatment.
Keywords: Computational Biology; Exome; Female; Genes, Recessive; Genes, X-Linked; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Intellectual Disability; Karyotype; Male; Mutation; Workflow

No evidence of Polyomavirus and EBV infections in Italian patients with mixed cryoglobulinemia infected chronically with HCV. - Comar, Manola; Zanotta, Nunzia; Del Savio, Rossella; Vascotto, Fulvia; Calabrese, Nadia; Zorat, Francesca; Pozzato, Gabriele (J Med Virol, 2014)
Mixed cryoglobulinemia is a lymphoproliferative disorder associated with hepatitis C virus (HCV). In patients chronically affected by HCV the prevalence of mixed cryoglobulinemia is variable ranging from 0% to 56%. To verify whether polyomaviruses (PyV) play a role in this disorder a total of 222 blood samples from 63 HCV chronic patients, 43 with mixed cryoglobulinemia, 59 chronic lymphocytic leukemia, 50 polytransfused patients, and 50 blood donors were evaluated for Merkel (MCPyV), BKV, JCV, and SV40. EBV was additionally included in the analysis since association with this disorder has been reported. Mixed cryoglobulinemia patients infected chronically with HCV resulted negative for both PyV and EBV. MCPyV was found in 1 subject with Merkel Cell Carcinoma, in 10% of polytransfused and in 10% of blood donors while EBV was detected in 22% of polytransfused, 10% of B-cell lymphatic leukemia patients and 4% of blood donors (P < 0.01). Taken together, the absence of PyV and EBV in HCV-mixed cryoglobulinemia patients seems to exclude a direct involvement of these viruses in the pathogenesis of this disease while the presence of MCPyV in healthy individuals, at the same rate as in polytransfused patients, may reinforce data on a minimal role of this virus in other human pathologies.
Keywords: Adult; Base Sequence; Cryoglobulinemia; DNA, Viral; Epstein-Barr Virus Infections; Female; Hepacivirus; Hepatitis C, Chronic; Herpesvirus 4, Human; Humans; Italy; Leukemia, B-Cell; Male; Middle Aged; Polyomavirus; Polyomavirus Infections; Sequence Analysis, DNA; Vaginal Smears; Young Adult

Novel missense mutation in the NOD2 gene in a patient with early onset ulcerative colitis: causal or chance association? - Girardelli, Martina; Vuch, Josef; Tommasini, Alberto; Crovella, Sergio; Bianco, Anna Monica (Int J Mol Sci, 2014)
Deregulated immune response to gut microflora in genetically predisposed individuals is typical for inflammatory bowel diseases. It is reasonable to assume that genetic association with the disease will be more pronounced in subjects with early onset than adult onset. The nucleotide-binding oligomerization domain containing-2 gene, commonly involved in multifactorial risk of Crohn's disease, and interleukin 10 receptor genes, associated with rare forms of early onset inflammatory bowel diseases, were sequenced in an early onset patient. We identified a novel variant in the NOD2 gene (c.2857A > G p.K953E) and two already described missense variants in the IL10RA gene (S159G and G351R). The new NOD2 missense variant was examined in silico with two online bioinformatics tools to predict the potentially deleterious effects of the mutation. Although cumulative effect of these variations in the early onset of the disease can be only hypothesized, we demonstrated that family information and in silico studies can be used to predict association with the disease.
Keywords: Age of Onset; Amino Acid Sequence; Base Sequence; Child; Colitis, Ulcerative; Crohn Disease; DNA Mutational Analysis; Genetic Predisposition to Disease; Genotype; Humans; Interleukin-10 Receptor alpha Subunit; Interleukin-10 Receptor beta Subunit; Molecular Sequence Data; Mutation, Missense; Nod2 Signaling Adaptor Protein; Polymorphism, Single Nucleotide; Risk Factors; Sequence Homology, Amino Acid

A novel P2RX2 mutation in an Italian family affected by autosomal dominant nonsyndromic hearing loss. - Faletra, Flavio; Girotto, Giorgia; d'Adamo, Adamo Pio; Vozzi, Diego; Morgan, Anna; Gasparini, Paolo (Gene, 2014)
Hereditary hearing loss (HHL) is a common disorder accounting for at least 60% of prelingual deafness. It is characterized by a large genetic heterogeneity, and despite the presence of a major gene, still there is a need to search for new causative mutations/genes. Very recently, a mutation within ATP-gated P2X(2) receptor (ligand-gated ion channel, purinergic receptor 2) gene (P2RX2) at DNFA41 locus has been reported leading to a bilateral and symmetrical sensorineural non-syndromic autosomal dominant HHL in two Chinese families. We performed a linkage analysis in a large Italian family with a dominant pattern of inheritance showing a significant 3.31 LOD score in a 2Mb region overlapping with the DNFA41 locus. Molecular analyses of P2RX2 identified a novel missense mutation (p.Gly353Arg) affecting a residue highly conserved across species. Visual inspection of the protein structure as obtained from comparative modeling suggests that substitution of the small glycine residue with a charged bulky residue such as an arginine that is close to the 'neck' of the region responsible for ion channel gating should have a high energetic cost and should lead to a severely destabilization of the fold. The identification of a second most likely causative mutation in P2RX2 gene further supports the possible role of this gene in causing autosomal dominant HHL.
Keywords: Amino Acid Sequence; Deafness; European Continental Ancestry Group; Female; Genotype; Hearing Loss, Sensorineural; Humans; Italy; Male; Molecular Sequence Data; Mutation, Missense; Pedigree; Receptors, Purinergic P2X2

The p53 transcriptional pathway is preserved in ATMmutated and NOTCH1mutated chronic lymphocytic leukemias. - Athanasakis, Emmanouil; Melloni, Elisabetta; Rigolin, Gian Matteo; Agnoletto, Chiara; Voltan, Rebecca; Vozzi, Diego; Piscianz, Elisa; Segat, Ludovica; dal Monego, Simeone; Cuneo, Antonio; Secchiero, Paola; Zauli, Giorgio (Oncotarget, 2014)
By using next generation sequencing, we have analyzed 108 B chronic lymphocytic leukemia (B-CLL) patients. Among genes involved in the TP53 pathway, we found frequent mutations in ATM (n=18), TP53 (n=10) and NOTCH1 (n=10) genes, rare mutations of NOTCH2 (n=2) and CDKN1A/p21 (n=1) and no mutations in BAX, MDM2, TNFRSF10A and TNFRSF10B genes. The in vitro treatment of primary B-CLL cells with the activator of p53 Nutlin-3 induced the transcription of p53 target genes, without significant differences between the B-CLL without mutations and those harboring either ATM or NOTCH1mutations. On the other hand, the subgroup of TP53mutated B-CLL exhibited a significantly lower induction of the p53 target genes in response to Nutlin-3 as compared to the other B-CLL samples. However, among the TP53mutated B-CLL, those showing mutations in the high hot spot region of the DNA binding domain [273-280 aa] maintained a significantly higher p53-dependent transcriptional activity as compared to the other TP53mutated B-CLL samples. Since the ability to elicit a p53-dependent transcriptional activity in vitro has a positive prognostic significance, our data suggest that ATMmutated, NOTCH1mutated and surprisingly, also a subset of TP53mutated B-CLL patients might benefit from therapeutic combinations including small molecule activator of the p53 pathway.
Keywords: Aged; Aged, 80 and over; Ataxia Telangiectasia Mutated Proteins; Base Sequence; Female; Genes, p53; Humans; Leukemia, Lymphocytic, Chronic, B-Cell; Male; Models, Molecular; Molecular Sequence Data; Mutation; Receptor, Notch1; Signal Transduction; Tumor Suppressor Protein p53

Parent-of-origin-specific allelic associations among 106 genomic loci for age at menarche. - Perry, John R B; Day, Felix; Elks, Cathy E; Sulem, Patrick; Thompson, Deborah J; Ferreira, Teresa; He, Chunyan; Chasman, Daniel I; Esko, Tõnu; Thorleifsson, Gudmar; Albrecht, Eva; Ang, Wei Q; et al. (Nature, 2014)
Age at menarche is a marker of timing of puberty in females. It varies widely between individuals, is a heritable trait and is associated with risks for obesity, type 2 diabetes, cardiovascular disease, breast cancer and all-cause mortality. Studies of rare human disorders of puberty and animal models point to a complex hypothalamic-pituitary-hormonal regulation, but the mechanisms that determine pubertal timing and underlie its links to disease risk remain unclear. Here, using genome-wide and custom-genotyping arrays in up to 182,416 women of European descent from 57 studies, we found robust evidence (P < 5 × 10(-8)) for 123 signals at 106 genomic loci associated with age at menarche. Many loci were associated with other pubertal traits in both sexes, and there was substantial overlap with genes implicated in body mass index and various diseases, including rare disorders of puberty. Menarche signals were enriched in imprinted regions, with three loci (DLK1-WDR25, MKRN3-MAGEL2 and KCNK9) demonstrating parent-of-origin-specific associations concordant with known parental expression patterns. Pathway analyses implicated nuclear hormone receptors, particularly retinoic acid and γ-aminobutyric acid-B2 receptor signalling, among novel mechanisms that regulate pubertal timing in humans. Our findings suggest a genetic architecture involving at least hundreds of common variants in the coordinated timing of the pubertal transition.
Keywords: Adolescent; Age Factors; Alleles; Body Mass Index; Breast Neoplasms; Cardiovascular Diseases; Child; Diabetes Mellitus, Type 2; Europe; Female; Genetic Loci; Genome-Wide Association Study; Genomic Imprinting; Humans; Hypothalamo-Hypophyseal System; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Obesity; Ovary; Parents; Polymorphism, Single Nucleotide; Potassium Channels, Tandem Pore Domain; Proteins; Quantitative Trait Loci; Receptors, GABA-B; Receptors, Retinoic Acid; Ribonucleoproteins

Pharmacogenetics of azathioprine in inflammatory bowel disease: a role for glutathione-S-transferase? - Stocco, Gabriele; Pelin, Marco; Franca, Raffaella; De Iudicibus, Sara; Cuzzoni, Eva; Favretto, Diego; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana (World J Gastroenterol, 2014)
Azathioprine is a purine antimetabolite drug commonly used to treat inflammatory bowel disease (IBD). In vivo it is active after reaction with reduced glutathione (GSH) and conversion to mercaptopurine. Although this reaction may occur spontaneously, the presence of isoforms M and A of the enzyme glutathione-S-transferase (GST) may increase its speed. Indeed, in pediatric patients with IBD, deletion of GST-M1, which determines reduced enzymatic activity, was recently associated with reduced sensitivity to azathioprine and reduced production of azathioprine active metabolites. In addition to increase the activation of azathioprine to mercaptopurine, GSTs may contribute to azathioprine effects even by modulating GSH consumption, oxidative stress and apoptosis. Therefore, genetic polymorphisms in genes for GSTs may be useful to predict response to azathioprine even if more in vitro and clinical validation studies are needed.
Keywords: 6-Mercaptopurine; Animals; Apoptosis; Azathioprine; Glutathione; Glutathione Transferase; Humans; Immunosuppressive Agents; Inflammatory Bowel Diseases; Oxidative Stress; Pharmacogenetics; Polymorphism, Genetic

Piccolipiù, a multicenter birth cohort in Italy: protocol of the study. - Farchi, Sara; Forastiere, Francesco; Vecchi Brumatti, Liza; Alviti, Sabrina; Arnofi, Antonio; Bernardini, Tommaso; Bin, Maura; Brescianini, Sonia; Colelli, Valentina; Cotichini, Rodolfo; Culasso, Martina; De Bartolo, Paolo; et al. (BMC Pediatr, 2014)
BACKGROUND: The fetal and infant life are periods of rapid development, characterized by high susceptibility to exposures. Birth cohorts provide unique opportunities to study early-life exposures in association with child development and health, as well as, with longer follow-up, the early life origin of adult diseases. Piccolipiù is an Italian birth cohort recently set up to investigate the effects of environmental exposures, parental conditions and social factors acting during pre-natal and early post-natal life on infant and child health and development. We describe here its main characteristics. METHODS/DESIGN: Piccolipiù is a prospective cohort of expected 3000 newborns, who will be recruiting in six maternity units of five Italian cities (Florence, Rome, Trieste, Turin and Viareggio) since October 2011. Mothers are contacted during pregnancy or at delivery and are offered to participate in the study. Upon acceptance, their newborns are recruited at birth and followed up until at least 18 years of age. At recruitment, the mothers donate a blood sample and complete a baseline questionnaire. Umbilical cord blood, pieces of umbilical cord and heel blood spots are also collected. Postnatal follow-up currently occurs at 6, 12, and 24 months of age using on-line or postal self administered questionnaire; further questionnaires and medical examinations are envisaged. Questionnaires collect information on several factors, including mother's and/or child's environmental exposures, anthropometric measures, reproductive factors, diet, supplements, medical history, cognitive development, mental health and socioeconomic factors. Health promotion materials are also offered to parents. DISCUSSION: Piccolipiù will broaden our understanding of the contribution of early-life factors to infant and child health and development. Several hypotheses on the developmental origins of health can be tested or piloted using the data collected from the Piccolipiù cohort. By pooling these data with those collected by other existing birth cohorts it will be possible to validate previous findings and to study rare exposures and outcomes.
Keywords: Adolescent; Child; Child Development; Child Welfare; Child, Preschool; Cohort Studies; Environmental Exposure; Humans; Infant; Infant, Newborn; Italy; Prospective Studies; Socioeconomic Factors

Polyubiquitinated proteins, proteasome, and glycogen characterize the particle-rich cytoplasmic structure (PaCS) of neoplastic and fetal cells. - Necchi, Vittorio; Sommi, Patrizia; Vitali, Agostina; Vanoli, Alessandro; Savoia, Anna; Ricci, Vittorio; Solcia, Enrico (Histochem Cell Biol, 2014)
A particle-rich cytoplasmic structure (PaCS) concentrating ubiquitin-proteasome system (UPS) components and barrel-like particles in clear, cytoskeleton- and organelle-free areas has recently been described in some neoplasms and in genetic or infectious diseases at risk of neoplasia. Ultrastructurally similar particulate cytoplasmic structures, interpreted as glycogen deposits, have previously been reported in clear-cell neoplasms and some fetal tissues. It remains to be investigated whether the two structures are the same, colocalize UPS components and polysaccharides, and have a role in highly proliferative cells such as fetal and neoplastic cells. We used immunogold electron microscopy and confocal immunofluorescence microscopy to examine human and mouse fetal tissues and human neoplasms. Fetal and neoplastic cells both showed colocalization of polyubiquitinated proteins, 19S and 20S proteasomes, and polysaccharides, both glycogen and chondroitin sulfate, inside cytoplasmic structures showing all distinctive features of PaCSs. Poorly demarcated and/or hybrid (ribosomes admixed) UPS- and glycogen-enriched areas, likely stages in PaCS development, were also seen in some fetal cells, with special reference to those, like primary alveolar pulmonary cells or pancreatic centroacinar cells, having a crucial role in organogenesis. UPS- and glycogen-rich PaCSs developed extensively in clear-cell neoplasms of the kidney, ovary, pancreas, and other organs, as well as, in infantile, development-related tumors replicating fetal patterns, such as choroid plexus papilloma. UPS-mediated, ATP-dependent proteolysis and its potential energy source, glycogen metabolism, may have a crucial, synergic role in embryo-/organogenesis and carcinogenesis.
Keywords: Cytoplasm; Fetus; Glycogen; Humans; Immunohistochemistry; Microscopy, Confocal; Microscopy, Electron, Transmission; Neoplasms; Proteasome Endopeptidase Complex; Ubiquitinated Proteins

A randomized trial of hyperimmune globulin to prevent congenital cytomegalovirus. - Revello, Maria Grazia; Lazzarotto, Tiziana; Guerra, Brunella; Spinillo, Arsenio; Ferrazzi, Enrico; Kustermann, Alessandra; Guaschino, Secondo; Vergani, Patrizia; Todros, Tullia; Frusca, Tiziana; Arossa, Alessia; Furione, Milena; et al. (N Engl J Med, 2014)
BACKGROUND: Congenital infection with human cytomegalovirus (CMV) is a major cause of morbidity and mortality. In an uncontrolled study published in 2005, administration of CMV-specific hyperimmune globulin to pregnant women with primary CMV infection significantly reduced the rate of intrauterine transmission, from 40% to 16%. METHODS: We evaluated the efficacy of hyperimmune globulin in a phase 2, randomized, placebo-controlled, double-blind study. A total of 124 pregnant women with primary CMV infection at 5 to 26 weeks of gestation were randomly assigned within 6 weeks after the presumed onset of infection to receive hyperimmune globulin or placebo every 4 weeks until 36 weeks of gestation or until detection of CMV in amniotic fluid. The primary end point was congenital infection diagnosed at birth or by means of amniocentesis. RESULTS: A total of 123 women could be evaluated in the efficacy analysis (1 woman in the placebo group withdrew). The rate of congenital infection was 30% (18 fetuses or infants of 61 women) in the hyperimmune globulin group and 44% (27 fetuses or infants of 62 women) in the placebo group (a difference of 14 percentage points; 95% confidence interval, -3 to 31; P=0.13). There was no significant difference between the two groups or, within each group, between the women who transmitted the virus and those who did not, with respect to levels of virus-specific antibodies, T-cell-mediated immune response, or viral DNA in the blood. The clinical outcome of congenital infection at birth was similar in the two groups. The number of obstetrical adverse events was higher in the hyperimmune globulin group than in the placebo group (13% vs. 2%). CONCLUSIONS: In this study involving 123 women who could be evaluated, treatment with hyperimmune globulin did not significantly modify the course of primary CMV infection during pregnancy. (Funded by Agenzia Italiana del Farmaco; CHIP ClinicalTrials.gov number, NCT00881517; EudraCT no. 2008-006560-11.).
Keywords: Adult; Amniocentesis; Cytomegalovirus; Cytomegalovirus Infections; Female; Fetal Diseases; Humans; Immunoglobulins; Infectious Disease Transmission, Vertical; Pregnancy; Pregnancy Complications, Infectious

Rituximab in steroid-dependent or frequently relapsing idiopathic nephrotic syndrome. - Ruggenenti, Piero; Ruggiero, Barbara; Cravedi, Paolo; Vivarelli, Marina; Massella, Laura; Marasà, Maddalena; Chianca, Antonietta; Rubis, Nadia; Ene-Iordache, Bogdan; Rudnicki, Michael; Pollastro, Rosa Maria; Capasso, Giovambattista; et al. (J Am Soc Nephrol, 2014)
The outcome of steroid-dependent or frequently relapsing nephrotic syndrome of minimal change disease (MCD), mesangial proliferative GN (MesGN), or FSGS may be poor and with major treatment toxicity. This academic, multicenter, off-on trial (ClinicalTrials.gov #NCT00981838) primarily evaluated the effects of rituximab therapy followed by immunosuppression withdrawal on disease recurrence in 10 children and 20 adults with MCD/MesGN (n=22) or FSGS who had suffered ≥2 recurrences over the previous year and were in steroid-induced remission for ≥1 month. Participants received one dose (n=28) or two doses of rituximab (375 mg/m(2) intravenously). At 1 year, all patients were in remission: 18 were treatment-free and 15 never relapsed. Compared with the year before rituximab treatment, total relapses decreased from 88 to 22 and the per-patient median number of relapses decreased from 2.5 (interquartile range [IQR], 2-4) to 0.5 (IQR, 0-1; P<0.001) during 1 year of follow-up. Reduction was significant across subgroups (children, adults, MCD/MesGN, and FSGS; P<0.01). After rituximab, the per-patient steroid maintenance median dose decreased from 0.27 mg/kg (IQR, 0.19-0.60) to 0 mg/kg (IQR, 0-0.23) (P<0.001), and the median cumulative dose to achieve relapse remission decreased from 19.5 mg/kg (IQR, 13.0-29.2) to 0.5 mg/kg (IQR, 0-9.4) (P<0.001). Furthermore, the mean estimated GFR increased from 111.3±25.7 to 121.8±29.2 ml/min per 1.73 m(2) (P=0.01), with the largest increases in children and in FSGS subgroups. The mean height z score slope stabilized in children (P<0.01). Treatment was well tolerated. Rituximab effectively and safely prevented recurrences and reduced the need for immunosuppression in steroid-dependent or frequently relapsing nephrotic syndrome, and halted disease-associated growth deficit in children.
Keywords: Adolescent; Adrenal Cortex Hormones; Adult; Antibodies, Monoclonal, Murine-Derived; Child; Female; Glomerulonephritis, Membranoproliferative; Glomerulosclerosis, Focal Segmental; Humans; Male; Middle Aged; Nephrosis, Lipoid; Nephrotic Syndrome; Recurrence; Rituximab

Salt-inducible kinase 3, SIK3, is a new gene associated with hearing. - Wolber, Lisa E; Girotto, Giorgia; Buniello, Annalisa; Vuckovic, Dragana; Pirastu, Nicola; Lorente-Cánovas, Beatriz; Rudan, Igor; Hayward, Caroline; Polasek, Ozren; Ciullo, Marina; Mangino, Massimo; Steves, Claire; et al. (Hum Mol Genet, 2014)
Hearing function is known to be heritable, but few significant and reproducible associations of genetic variants have been identified to date in the adult population. In this study, genome-wide association results of hearing function from the G-EAR consortium and TwinsUK were used for meta-analysis. Hearing ability in eight population samples of Northern and Southern European ancestry (n = 4591) and the Silk Road (n = 348) was measured using pure-tone audiometry and summarized using principal component (PC) analysis. Genome-wide association analyses for PC1-3 were conducted separately in each sample assuming an additive model adjusted for age, sex and relatedness of subjects. Meta-analysis was performed using 2.3 million single-nucleotide polymorphisms (SNPs) tested against each of the three PCs of hearing ability in 4939 individuals. A single SNP lying in intron 6 of the salt-inducible kinase 3 (SIK3) gene was found to be associated with hearing PC2 (P = 3.7×10(-8)) and further supported by whole-genome sequence in a subset. To determine the relevance of this gene in the ear, expression of the Sik3 protein was studied in mouse cochlea of different ages. Sik3 was expressed in murine hair cells during early development and in cells of the spiral ganglion during early development and adulthood. Our results suggest a developmental role of Sik3 in hearing and may be required for the maintenance of adult auditory function.
Keywords: Age Factors; Animals; Cochlea; European Continental Ancestry Group; Genome-Wide Association Study; Hearing; Humans; Mice, Inbred C57BL; Polymorphism, Single Nucleotide; Protein Kinases

Severe inflammatory bowel disease associated with congenital alteration of transforming growth factor beta signaling. - Naviglio, Samuele; Arrigo, Serena; Martelossi, Stefano; Villanacci, Vincenzo; Tommasini, Alberto; Loganes, Claudia; Fabretto, Antonella; Vignola, Silvia; Lonardi, Silvia; Ventura, Alessandro (J Crohns Colitis, 2014)
Transforming growth factor beta is a pleiotropic cytokine which plays a central role in the homeostasis of the immune system. A complex dysregulation of its signaling occurs in Loeys-Dietz syndrome, a monogenic disorder caused by mutations of transforming growth factor beta receptors type 1 or type 2, characterized by skeletal involvement, craniofacial abnormalities, and arterial tortuosity with a strong predisposition for aneurysm and dissection. In addition, several immunologic abnormalities have been described in these patients, including an increased risk of allergic disorders as well as eosinophilic gastrointestinal disorders. The occurrence of inflammatory bowel disorders has been also reported, but it is poorly documented. We describe two unrelated children with Loeys-Dietz syndrome affected by severe chronic inflammatory colitis appearing at an early age. The intestinal disease presented similar features in both patients, including a histopathological picture of non-eosinophilic chronic ulcerative colitis, striking elevation of inflammatory markers, and a distinctly severe clinical course leading to failure to thrive, with resistance to multiple immunosuppressive treatments. One of the patients also presented autoimmune thyroiditis. Our report confirms that chronic ulcerative colitis may be associated with Loeys-Dietz syndrome. This finding suggests that an alteration of transforming growth factor beta signaling may by itself predispose to inflammatory colitis in humans, and represent an invaluable model to understand inflammatory bowel diseases.
Keywords: Child, Preschool; Colon; Colonoscopy; Female; Humans; Infant; Inflammatory Bowel Diseases; Loeys-Dietz Syndrome; Male; Signal Transduction; Transforming Growth Factor beta

Teleradiology for remote consultation using iPad improves the use of health system human resources for paediatric fractures: prospective controlled study in a tertiary care hospital in Italy. - Zennaro, Floriana; Grosso, Daniele; Fascetta, Riccardo; Marini, Marta; Odoni, Luca; Di Carlo, Valentina; Dibello, Daniela; Vittoria, Francesca; Lazzerini, Marzia (BMC Health Serv Res, 2014)
BACKGROUND: The growing cost of health care and lack of specialised staff have set e-Health high on the European political agenda. In a prospective study we evaluated the effect of providing images for remote consultation through an iPad on the number of in-hospital orthopaedic consultations for children with bone fractures. METHODS: Children from 0 to 18 years diagnosed with a bone fracture by the radiologist during the hours when an orthopaedic service is provided only on-call were eligible for enrollment. Cases were enrolled prospectively during September and October 2013. A standard approach (verbal information only, no X-Ray provided remotely) was compared to an experimental approach (standard approach plus the provision of X-ray for remote consultation through an iPad). The primary outcome was the number of orthopaedic in-hospital consultations that occurred. Other outcomes included: immediate activation of other services; time needed for decision-making; technical difficulties; quality of images and diagnostic confidence (on a likert scale of 1 to 10). RESULTS: Forty-two children were enrolled in the study. Number of in-hospital consultancies dropped from 32/42 (76.1%) when no X-ray was provided to 16/42 (38%) when the X-rays was provided (p < 0.001). With remote X-ray consultation in 14/42 (33.3%) cases services such as surgery and plaster room could be immediately activated, compared to no service activated without teleradiology (p < 0.001). Average time for decision making was 23.4 ± 21.8 minutes with remote X-ray consultation, compared to 56.2 ± 16.1 when the X-ray was not provided (p < 0.001). The comparison between images on the iPad and on the standard system for X- Ray visualisation resulted in a non statistically significant difference in the quality of images (average score 9.89 ± 0.37 vs 9.91 ± 0.30; p = 0.79), and in non statistically significant difference in diagnostic confidence (average score 9.91 ± 0.32 vs 9.92 ± 0.31; p = 0.88). CONCLUSIONS: Remote X-ray consultation through Aycan OsiriX PRO and iPad should be considered as a means for reducing the need of in-hospital orthopaedic consultation during on-call times, and potentially decrease the cost of care for the health system. In the future, alternative systems less expensive than Aycan OsiriX PRO should be further developed and tested.
Keywords: Adolescent; Child; Child, Preschool; Computers, Handheld; Decision Making; Fractures, Bone; Humans; Infant; Infant, Newborn; Italy; Prospective Studies; Remote Consultation; Teleradiology; Time Factors

TNF-α SNP rs1800629 and risk of relapse in childhood acute lymphoblastic leukemia: relation to immunophenotype. - Franca, Raffaella; Rebora, Paola; Athanasakis, Emmanouil; Favretto, Diego; Verzegnassi, Federico; Basso, Giuseppe; Tommasini, Alberto; Valsecchi, Maria Grazia; Decorti, Giuliana; Rabusin, Marco (Pharmacogenomics, 2014)
AIM: In the AIEOP-BFM ALL (Associazione Italiana Ematologia Oncologia Pediatrica-Berlin Frankfurt Münster acute lymphoblastic leukemia) 2000 protocol, 70% of relapsed patients had favorable prognostic features and fell within less intensive polychemotherapeutic regimens, suggesting the need for better assessing lower risk stratification. MATERIALS & METHODS: A novel two-phase study design selected 614 children to be genotyped for TNF-α SNP rs1800629 (-308G>A). A weighted Cox model was applied to evaluate the SNP effect on hazard of relapse, adjusting for immunophenotype, risk group, age and gender and including interaction terms. RESULTS: Significant interaction was found with immunophenotypes (p = 0.0007, with minor allele genotypes being adverse genetic markers in B-cell acute lymphoblastic leukemia and protective ones in T-cell acute lymphoblastic leukemia), and also with risk protocols (p = 0.0041, with minor allele genotypes as prognostic factor of relapse for standard risk patients [only one T-cell acute lymphoblastic leukemia in the subgroup analyzed]). CONCLUSION: The presence of at least one A allele in TNF-α SNP rs1800629 should suggest a closer monitoring in B-cell acute lymphoblastic leukemia standard risk patients.
Keywords: Adolescent; Antineoplastic Agents; Child; Child, Preschool; Drug Resistance, Neoplasm; Female; Genotype; Humans; Infant; Leukemia, Lymphocytic, Chronic, B-Cell; Male; Phenotype; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Precursor T-Cell Lymphoblastic Leukemia-Lymphoma; Recurrence; Risk Assessment; Steroids; Tumor Necrosis Factor-alpha

Trans-ethnic meta-analysis of white blood cell phenotypes. - Keller, Margaux F; Reiner, Alexander P; Okada, Yukinori; van Rooij, Frank J A; Johnson, Andrew D; Chen, Ming-Huei; Smith, Albert V; Morris, Andrew P; Tanaka, Toshiko; Ferrucci, Luigi; Zonderman, Alan B; Lettre, Guillaume; et al. (Hum Mol Genet, 2014)
White blood cell (WBC) count is a common clinical measure used as a predictor of certain aspects of human health, including immunity and infection status. WBC count is also a complex trait that varies among individuals and ancestry groups. Differences in linkage disequilibrium structure and heterogeneity in allelic effects are expected to play a role in the associations observed between populations. Prior genome-wide association study (GWAS) meta-analyses have identified genomic loci associated with WBC and its subtypes, but much of the heritability of these phenotypes remains unexplained. Using GWAS summary statistics for over 50 000 individuals from three diverse populations (Japanese, African-American and European ancestry), a Bayesian model methodology was employed to account for heterogeneity between ancestry groups. This approach was used to perform a trans-ethnic meta-analysis of total WBC, neutrophil and monocyte counts. Ten previously known associations were replicated and six new loci were identified, including several regions harboring genes related to inflammation and immune cell function. Ninety-five percent credible interval regions were calculated to narrow the association signals and fine-map the putatively causal variants within loci. Finally, a conditional analysis was performed on the most significant SNPs identified by the trans-ethnic meta-analysis (MA), and nine secondary signals within loci previously associated with WBC or its subtypes were identified. This work illustrates the potential of trans-ethnic analysis and ascribes a critical role to multi-ethnic cohorts and consortia in exploring complex phenotypes with respect to variants that lie outside the European-biased GWAS pool.
Keywords: African Americans; Asian Continental Ancestry Group; Bayes Theorem; European Continental Ancestry Group; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Leukocyte Count; Leukocytes; Linkage Disequilibrium; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Use of placebo in a trial of thalidomide for pediatric Crohn disease--reply. - Lazzerini, Marzia; Martelossi, Stefano; Ventura, Alessandro (JAMA, 2014)
Keywords: Crohn Disease; Female; Humans; Immunosuppressive Agents; Male; Thalidomide

Amenorrhea in women treated with thalidomide: report of two cases and literature review. - Lazzerini, Marzia; Bramuzzo, Matteo; Martelossi, Stefano; Magazzù, Giuseppe; Pellegrino, Salvatore; Ventura, Alessandro (Inflamm Bowel Dis, 2013)
Keywords: Adolescent; Amenorrhea; Colitis, Ulcerative; Crohn Disease; Female; Humans; Review Literature as Topic; Thalidomide

Genome-wide association analyses identify 18 new loci associated with serum urate concentrations. - Köttgen, Anna; Albrecht, Eva; Teumer, Alexander; Vitart, Veronique; Krumsiek, Jan; Hundertmark, Claudia; Pistis, Giorgio; Ruggiero, Daniela; O'Seaghdha, Conall M; Haller, Toomas; Yang, Qiong; Tanaka, Toshiko; et al. (Nat Genet, 2013)
Elevated serum urate concentrations can cause gout, a prevalent and painful inflammatory arthritis. By combining data from >140,000 individuals of European ancestry within the Global Urate Genetics Consortium (GUGC), we identified and replicated 28 genome-wide significant loci in association with serum urate concentrations (18 new regions in or near TRIM46, INHBB, SFMBT1, TMEM171, VEGFA, BAZ1B, PRKAG2, STC1, HNF4G, A1CF, ATXN2, UBE2Q2, IGF1R, NFAT5, MAF, HLF, ACVR1B-ACVRL1 and B3GNT4). Associations for many of the loci were of similar magnitude in individuals of non-European ancestry. We further characterized these loci for associations with gout, transcript expression and the fractional excretion of urate. Network analyses implicate the inhibins-activins signaling pathways and glucose metabolism in systemic urate control. New candidate genes for serum urate concentration highlight the importance of metabolic control of urate production and excretion, which may have implications for the treatment and prevention of gout.
Keywords: Analysis of Variance; European Continental Ancestry Group; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Glucose; Gout; Humans; Inhibins; Polymorphism, Single Nucleotide; Signal Transduction; Uric Acid

Human colostrum and breast milk contain high levels of TNF-related apoptosis-inducing ligand (TRAIL). - Davanzo, Riccardo; Zauli, Giorgio; Monasta, Lorenzo; Vecchi Brumatti, Liza; Abate, Maria Valentina; Ventura, Giovanna; Rimondi, Erika; Secchiero, Paola; Demarini, Sergio (J Hum Lact, 2013)
BACKGROUND: TNF-related apoptosis inducing ligand (TRAIL) is a pleiotropic cytokine, which plays a key role in the immune system as well as in controlling the balance of apoptosis and proliferation in various organs and tissues. OBJECTIVE: To investigate the presence and levels of soluble TRAIL in human colostrum and milk. METHODS: The levels of soluble human TRAIL were measured in human colostrum (day 2 after delivery) and breast milk (day 5 after delivery). The presence of TRAIL was also measured in infant formula. RESULTS: Levels of soluble TRAIL in the colostrum and mature human milk were, respectively, at least 400 and 100 fold higher than those detected in human serum. No TRAIL was detected in formula. CONCLUSION: Human soluble TRAIL is present at extremely high levels in human colostrum and human milk and might have a significant role in mediating the anti-cancer activity of human milk.
Keywords: Adult; Apgar Score; Colostrum; Female; Gestational Age; Humans; Infant Formula; Infant, Newborn; Milk, Human; TNF-Related Apoptosis-Inducing Ligand

Infantile bilateral glaucoma in a child with ectodermal dysplasia. - Callea, Michele; Vinciguerra, Agatino; Willoughby, Colin E; Deroma, Laura; Clarich, Gabriella (Ophthalmic Genet, 2013)
Ectodermal dysplasia is a rare disease which affects at least two ectodermal-derived structures such as hair, nails, skin, sweat glands and teeth. Approximately 200 different conditions have been classified as an ectodermal dysplasia and X-linked hypohidrotic ectodermal dysplasia (XHED) represents the commonest form. Clinically, XHED is characterized by hypotrichosis, hypohidrosis and hypodontia. A variety of ocular manifestations have been reported in XHED, the most common being dryness of eyes due to tear deficiency and instability of the film secondary to the absence of meibomian gland function. Here we report a child with the distinctive clinical features of XHED confirmed with molecular diagnosis who presented with infantile bilateral glaucoma, in addition to the classical ocular involvement in XHED.
Keywords: Antihypertensive Agents; Child; Ectodermal Dysplasia; Ectodysplasins; Humans; Hydrophthalmos; Intraocular Pressure; Male; Mutation; Polymorphism, Single Nucleotide; Tonometry, Ocular

More on prolonged pacifier usage and risk of dental problems: an Italian survey of current clinical practice. - De Cunto, Angela; Minen, Federico; Ventura, Alessandro (J Pediatr Nurs, 2013)
Keywords: Female; Guidelines as Topic; Humans; Male; Pacifiers; Sudden Infant Death

Pain in cognitively impaired children: a focus for general pediatricians. - Massaro, M; Pastore, S; Ventura, A; Barbi, E (Eur J Pediatr, 2013)
UNLABELLED: Pain in children with cognitive impairment and cerebral palsy is a particularly relevant issue due to its high prevalence and impact on quality of life. We review available evidence about prevalence of pain, causes and specific treatment, recognition and use of specific pain scales, physiology, and consequences of pain in this subset of patients. CONCLUSIONS: Pain is very common and is a critical determinant of quality of life in children with cognitive impairment and cerebral palsy. The diseases and associated complications that frequently expose these patients to pain can be treated and pain prevented. For patients with communication difficulties, appropriate, effective, validated tools are available and should be used to diagnose pain in itself, to >choose analgesic treatment and to determine effectiveness of these therapies. The level of awareness of pediatricians towards this issue seems to be quite low.
Keywords: Analgesics; Cerebral Palsy; Child; Cognition Disorders; Humans; Pain; Pain Measurement; Quality of Life

Safety and efficacy of infliximab and adalimumab for refractory uveitis in juvenile idiopathic arthritis: 1-year followup data from the Italian Registry. - Zannin, Maria E; Birolo, Carolina; Gerloni, Valeria M; Miserocchi, Elisabetta; Pontikaki, Irene; Paroli, Maria P; Bracaglia, Claudia; Shardlow, Alison; Parentin, Fulvio; Cimaz, Rolando; Simonini, Gabriele; Falcini, Fernanda; et al. (J Rheumatol, 2013)
OBJECTIVE: To evaluate safety and efficacy of adalimumab (ADA) and infliximab (IFX) for the treatment of juvenile idiopathic arthritis-related anterior uveitis (JIA-AU). METHODS: Starting January 2007, patients with JIA-AU treated with IFX and ADA were managed by a standard protocol and data were entered into the National Italian Registry (NIR). At baseline, all patients were refractory to standard immunosuppressive treatment and/or were corticosteroid-dependent. Data recorded every 3 months included uveitis course, number/type of ocular complications, drug-related adverse events (AE), treatment change or withdrawal, and laboratory measures. Data of patients treated for at least 1 year were retrieved from the NIR and analyzed using descriptive statistics. Treatment efficacy was based on change in uveitis course and in number of ocular complications. RESULTS: Up to December 2009, data for 108 patients with JIA-AU treated with anti-tumor necrosis factor-α agents were recorded in the NIR and data from 91, with at least 12 months' followup, were included in the study. Forty-eight patients were treated with IFX, 43 with ADA. Forty-seven patients (55.3%) achieved remission of AU, 28 (32.9%) had recurrent AU, and 10 (11.8%) maintained a chronic course. A higher remission rate was observed with ADA (67.4% vs 42.8% with IFX; p = 0.025). Ocular complications decreased from 0.47 to 0.32 per subject. Five patients experienced resolution of structural complications. No patient reported serious AE; 8 (8.8%) experienced 11 minor AE (9 with IFX, 2 with ADA). CONCLUSION: IFX and ADA appear to be effective and safe for treatment of refractory JIA-related uveitis, with a better performance of ADA in the medium-term period.
Keywords: Adolescent; Antibodies, Monoclonal; Antibodies, Monoclonal, Humanized; Antirheumatic Agents; Arthritis, Juvenile; Child; Child, Preschool; Female; Follow-Up Studies; Humans; Infant; Italy; Male; Registries; Treatment Outcome; Tumor Necrosis Factor-alpha; Uveitis

Is treatment with hydroxychloroquine effective in surfactant protein C deficiency? - Rabach, Ingrid; Poli, Furio; Zennaro, Floriana; Germani, Claudio; Ventura, Alessandro; Barbi, Egidio (Arch Bronconeumol, 2013)
We present the case of two twin brothers with surfactant protein C deficiency who were treated with hydroxychloroquine for three years, with apparent success. The exact physiopathology of this disease is not known and there is no specific treatment for it. There is merely news from a few previous descriptions in the literature about the use of hydroxychloroquine for surfactant protein C deficiency with satisfactory results. Two years after the treatment was withdrawn, the twins were evaluated once again: they presented no new infections, growth and general state were normal and chest CT showed a notable additional reduction in the interstitial pneumopathy. These data seem to cast some doubt on the efficacy of hydroxychloroquine, and they suggest that the clinical improvement was simply the natural evolution of the disease.
Keywords: Disease Progression; Diseases in Twins; Dyspnea; Failure to Thrive; Humans; Hydroxychloroquine; Infant, Newborn; Male; Pulmonary Alveolar Proteinosis; Pulmonary Surfactant-Associated Protein C; Respiratory Insufficiency; Tomography, X-Ray Computed; Twins, Monozygotic

Type 1 diabetes mellitus and celiac disease: usefulness of gluten-free diet. - Pascolo, Paola; Faleschini, Elena; Tonini, Giorgio; Ventura, Alessandro (Acta Diabetol, 2013)

Activation of the p53 pathway induces α-smooth muscle actin expression in both myeloid leukemic cells and normal macrophages. - Secchiero, Paola; Rimondi, Erika; di Iasio, Maria Grazia; Voltan, Rebecca; Gonelli, Arianna; Zauli, Giorgio (J Cell Physiol, 2012)
A range of cell types of mesenchymal origin express α-smooth muscle actin (α-SMA), a protein that plays a key role in controlling cell motility and differentiation along the fibrocyte and myofibroblast lineages. Although α-SMA is often expressed in stromal cells associated to a variety of cancers including hematological malignancies, up to now the role of anti-cancer drugs on α-SMA has not been deeply investigated. In this study, we demonstrated that Nutlin-3, the small molecule inhibitor of the MDM2/p53 interactions, significantly up-regulated the mRNA and protein levels of α-SMA in normal macrophages as well as in p53(wild-type) but not in p53(mutated/null) myeloid leukemic cells. The p53-dependence of α-SMA up-regulation induced by Nutlin-3 was demonstrated in experiments performed with siRNA for p53. Of note, Nutlin-3 mediated up-regulation of α-SMA in OCI leukemic cells was accompanied by cell adhesion to plastic substrate and by reduced cell migratory response in transwell assays. Notably, the role of α-SMA induction in the modulation of myeloid cell migration was clearly documented in α-SMA gene knockdown experiments. In addition, Nutlin-3 significantly up-regulated α-SMA expression in primary endothelial cells, but not in fibroblasts and mesenchymal stem cells (MSC). Conversely, transforming growth factor-β1 up-regulated α-SMA in fibroblasts and MSC, but not in macrophages and endothelial cells. Taken together, these data indicate that Nutlin-3 is a potent inducer of α-SMA in both normal and leukemic myeloid cells as well as in endothelial cells.
Keywords: Actins; Cell Movement; Cells, Cultured; Endothelial Cells; Fibroblasts; Humans; Imidazoles; Leukemia, Myeloid; Macrophages; Mesenchymal Stromal Cells; Piperazines; Proto-Oncogene Proteins c-mdm2; RNA, Small Interfering; Signal Transduction; Transforming Growth Factor beta1; Tumor Suppressor Protein p53

Acute and recurrent pancreatitis in children: exploring etiological factors. - Minen, Federico; De Cunto, Angela; Martelossi, Stefano; Ventura, Alessandro (Scand J Gastroenterol, 2012)
OBJECTIVE: Etiologies of acute pancreatitis (AP) in children are more variable than in adults, including drugs, traumas, infections and multisystem disorders as well as biliary anomalies. While causes of pancreatitis have been extensively analyzed, different series reported different causes. The aims of this study were: 1) to assess the etiological factors of acute and recurrent pancreatitis in a pediatric population from a tertiary care hospital; 2) to assess the usefulness of imaging studies in diagnosing etiologies of pancreatitis. MATERIAL AND METHODS: Thirty-four children (median age 11 years, 23 males) with AP and 11 with recurrent pancreatitis were retrospectively studied to assess etiology of pancreatitis in children. RESULTS: The most common etiologies of AP were medications (11/34) and biliary tract diseases (9/34), whereas systemic diseases accounted for a small percentage of case. Among patients with recurrent episodes, biliary anomalies were the most common cause (6/11), whereas only 2 out of 11 patients with recurrent pancreatitis presented a hereditary cause. CONCLUSIONS: This study highlights that etiologies of AP in children are variable. Epidemiology of AP could be influenced by single center's characteristics. Anatomic anomalies should be ruled out and genetic causes should be considered in recurrent cases.
Keywords: Adolescent; Azathioprine; Biliary Tract; Biliary Tract Diseases; Carrier Proteins; Child; Child, Preschool; Cholangiography; Cholangiopancreatography, Endoscopic Retrograde; Drug-Related Side Effects and Adverse Reactions; Female; Humans; Immunosuppressive Agents; Magnetic Resonance Imaging; Male; Pancreatitis; Recurrence; Retrospective Studies; Tomography, X-Ray Computed

Acute febrile cholestatic jaundice in children: keep in mind Kawasaki disease. - Taddio, Andrea; Pellegrin, Maria Chiara; Centenari, Chiara; Filippeschi, Irene Pellegrini; Ventura, Alessandro; Maggiore, Giuseppe (J Pediatr Gastroenterol Nutr, 2012)
Kawasaki disease (KD) is characterized by persistent fever in addition to 4 of 5 signs of mucocutaneous inflammation. Although gastrointestinal involvement does not belong to the classic diagnostic criteria, it has been often associated with KD onset. We reviewed patients who were admitted for febrile cholestatic jaundice between 2003 and 2010 in 2 tertiary pediatric care centers. KD was the second most frequent cause (21%) after viral infections. Considering the relative high frequency of this condition, a high index of suspicion of KD should be maintained in patients presenting with febrile cholestatic jaundice.
Keywords: Child; Child, Preschool; Diagnosis, Differential; Female; Fever; Humans; Infant; Jaundice, Obstructive; Male; Mucocutaneous Lymph Node Syndrome; Virus Diseases

Adverse effects during specific oral tolerance induction: in home phase. - Barbi, E; Longo, G; Berti, I; Matarazzo, L; Rubert, L; Saccari, A; Lenisa, I; Ronfani, L; Radillo, O; Ventura, A (Allergol Immunopathol (Madr), 2012)
BACKGROUND: Specific oral tolerance induction (SOTI) is a promising approach for severe food allergies. There are little data in the literature regarding the home-phase of SOTI, not only with regard to type and frequency of adverse reactions but also regarding the most suitable treatment and protocol. AIMS: To define the incidence and severity of adverse reactions, possible risk factors, and the safety and effectiveness of the home-phase of an original SOTI protocol in a large group of children with severe cow's milk (CM) allergy, after the hospital "rush" phase. METHODS: The study was conducted by recording in-home phase adverse events, success and failure as reported by parents, and calling families. Adverse reactions were treated following the International Guidelines, arbitrarily modified by introducing nebulised epinephrine for respiratory reactions, oral beclomethasone for acute gastric pain and oral cromolyn for recurrent gastric pain. RESULTS: Out of 140 patients, 132 were contacted; eight were inaccessible (follow-up 2-84 months). The number of adverse reactions was 1 in every 100 doses. The reactions were treated with nebulised epinephrine (221 reactions), IM epinephrine (6 reactions), and other drugs. Patients with high specific IgE levels (greater than 100 kU(A)/L) and lower CM dose (less than 5 ml) at the end of in-hospital phase showed a higher risk both for number of reactions and use of nebulised epinephrine. CONCLUSIONS: The home phase of SOTI was characterised by a significant number of adverse reactions, mostly managed with an acceptable rate of side effects. Nebulised epinephrine played a pivotal role in respiratory reactions.
Keywords: Adolescent; Adult; Age Factors; Allergens; Child; Child, Preschool; Desensitization, Immunologic; Epinephrine; Female; Food Hypersensitivity; Humans; Immune Tolerance; Immunoglobulin E; Male; Milk Hypersensitivity; Nebulizers and Vaporizers

Adverse effects during specific oral tolerance induction: in-hospital "rush" phase. - Barbi, E; Longo, G; Berti, I; Neri, E; Saccari, A; Rubert, L; Matarazzo, L; Montico, M; Ventura, A (Eur Ann Allergy Clin Immunol, 2012)
BACKGROUND: Specific oral tolerance induction (SOTI) is a promising approach in the treatment of severe food allergies. Different protocols have demonstrated its efficacy. Nevertheless, SOTI is still considered an experimental method and should be limited to highly controlled settings. AIMS: To define the incidence and severity of adverse reactions, possible risk factors, and the safety and effectiveness of nebulized epinephrine as a first-line treatment of respiratory reactions during in-hospital SOTI for cow's milk allergy. MATERIALS AND METHODS: A retrospective study was conducted by reviewing the medical records of patients admitted for SOTI beginning in 2001. Reactions were classified as mild, moderate and severe on a partially modified Clark scale. Adverse reactions were treated following the International Guidelines with the introduction of nebulized epinephrine for level four reactions. RESULTS: Of 209 patients, 17 were excluded due to the absence of objective reactions. The remaining 192 were classified as follows: Mild Reactions (Clark Scale 1 to 3): 100 patients received either no treatment, oral antihistamines or nebulized steroids; Moderate Reactions (Clark Scale 4): 87 patients treated with nebulized epinephrine and, depending on their symptoms, oral antihistamines, corticosteroids (nebulized, oral or IV) or nebulized beta 2 agonists; Severe Reactions (Clark Scale 5): 5 children, 4 of whom initially underwent one nebulization of epinephrine and eventually required an IM dose. The fifth patient was immediately treated with IM epinephrine due to hypotension. DISCUSSION: adverse reactions during this in-hospital SOTI protocol were frequent but easily manageable. Nebulized epinephrine can play a relevant role in the treatment of respiratory reactions.
Keywords: Administration, Inhalation; Anaphylaxis; Animals; Bronchodilator Agents; Child; Desensitization, Immunologic; Epinephrine; Humans; Milk; Milk Hypersensitivity; Retrospective Studies

Anti-leukemic activity of dasatinib in both p53(wild-type) and p53(mutated) B malignant cells. - Bosco, Raffaella; Rabusin, Marco; Voltan, Rebecca; Celeghini, Claudio; Corallini, Federica; Capitani, Silvano; Secchiero, Paola (Invest New Drugs, 2012)
The multi-kinase inhibitor dasatinib induced a variable but significant decrease of viability in both p53(wild-type) (EHEB, JVM-2, JVM-3) and p53(mutated) (MEC-1, MEC-2, BJAB) prolymphocytic B leukemic cells, due to a combination of cell cycle block in G1 and apoptosis. Antibody phospho-kinase array analysis revealed that dasatinib inhibited the phosphorylation of various kinases, including ERK1/2 and p38/MAPK as well as of STAT3 transcription factors, in both p53(wild-type) and p53(mutated) cells. Therefore, dasatinib might offer a novel therapeutic strategy not only for p53(wild-type), but also for p53(mutated) B malignancies that have the worst prognosis and urgently need innovative therapeutic approaches.
Keywords: Antineoplastic Agents; Apoptosis; B-Lymphocytes; Cell Line, Tumor; Cell Survival; G1 Phase Cell Cycle Checkpoints; Granulocyte Precursor Cells; Humans; Leukemia, Prolymphocytic, B-Cell; Mitogen-Activated Protein Kinase 1; Mitogen-Activated Protein Kinase 3; Mutation; p38 Mitogen-Activated Protein Kinases; Phosphorylation; Protein Kinase Inhibitors; Pyrimidines; STAT3 Transcription Factor; Thiazoles; Time Factors; Tumor Suppressor Protein p53

Application of reticulated platelets to transfusion management during autologous stem cell transplantation. - Parco, Sergio; Vascotto, Fulvia (Onco Targets Ther, 2012)
BACKGROUND: The immature (or reticulated) platelet fraction (IPF) is rich in nucleic acids, especially RNA, and can be used as a predictive factor for platelet recovery in platelet immunomediated consumption or in postchemotherapy myelosuppression. Our aim was to determine if transfusions with IPF-rich solutions, during autologous peripheral blood stem cell transplantation, reduce the occurrence of bleeding and hemorrhagic complications. PATIENTS AND METHODS: Transfusions were administered to 40 children, affected with hematological pathologies, who underwent autologous peripheral hematopoietic progenitor cell transplantation. There were two groups of 20 patients, one group treated with IPF-poor and the other with IPF-rich solutions. In the two groups, the conditioning regimen was the same for the same pathology (hematological pathologies: 14 acute lymphoblastic leukemia; twelve acute myelocytic leukemia; four non-Hodgkin's lymphoma; two Hodgkin's lymphoma; eight solid tumors). A new automated analyzer was used to quantify the IPF: the XE2100 (Sysmex, Kobe, Japan) blood cell counter with upgraded software. RESULTS: The 20 patients who received solutions with a high percentage of IPF (3%-9% of total number of infused platelets) required fewer transfusions than the 20 patients who received transfusions with a low percentage of IPF (0%-1% of total number of infused platelets): 83 versus 129 (mean of number of transfusions 4.15 versus 6.45) and a significant difference was found between the two groups by using the Mann-Whitney test (P < 0.001). The prophylactic transfusions decreased from three to two per week. There was only one case of massive hemorrhage. CONCLUSION: The use of IPF solutions reduces the number of transfusions and bleedings after peripheral blood stem cell transplantation in pediatric patients.

Asbestos and SV40 in malignant pleural mesothelioma from a hyperendemic area of north-eastern Italy. - Comar, Manola; Zanotta, Nunzia; Pesel, Giuliano; Visconti, Patrizia; Maestri, Iva; Rinaldi, Rosa; Crovella, Sergio; Cortale, Maurizio; De Zotti, Renata; Bovenzi, Massimo (Tumori, 2012)
AIMS AND BACKGROUND: Malignant mesothelioma is a fatal cancer of increasing incidence in north-eastern Italy. Together with asbestos, the polyomavirus SV40 was hypothesized to contribute to the onset of malignant mesothelioma. To investigate the putative role of SV40 in the individual susceptibility to asbestos-induced malignant mesothelioma, we conducted a molecular epidemiological study on a series of malignant mesothelioma patients from an area in north-eastern Italy hyperendemic for malignant pleural mesothelioma. METHODS AND STUDY DESIGN: We collected 63 mesothelioma samples from incidence cases of patients diagnosed with malignant pleural mesothelioma in the period 2009-2010. DNA was extracted from patients' tissue biopsies using the BioRobot EZ1 Qiagen workstation. SV40 sequence detection and quantification was performed by specific real time PCR. The 74.6% of the 63 enrolled patients had a history of asbestos exposure. The epithelioid histotype was more prevalent in males (64.0%) and the mixed in females (61.5%) who showed significantly higher cancer co-morbidity (46.1% vs 12%, P = 0.005). SV40 was detected in 22% of MM tumors, with a low viral load. In SV40-positive patients, a threefold increased risk of asbestos exposure was observed, more evident in females (OR 4.32) than in males (OR 1.20). CONCLUSIONS: Our findings indicate that a high prevalence of SV40 was present in malignant mesothelioma incident cases from an area hyperendemic for malignant mesothelioma in north-eastern Italy. Although asbestos is considered the main risk factor in malignant mesothelioma onset, a role for SV40 could be hypothesized.
Keywords: Adult; Aged; Asbestos; Carcinogens; Disease Susceptibility; DNA, Viral; Endemic Diseases; Female; Humans; Italy; Male; Mesothelioma; Middle Aged; Pleural Neoplasms; Polyomavirus Infections; Real-Time Polymerase Chain Reaction; Risk Factors; Simian virus 40; Tumor Virus Infections; Viral Load

Association between BclI polymorphism in the NR3C1 gene and in vitro individual variations in lymphocyte responses to methylprednisolone. - Cuzzoni, Eva; De Iudicibus, Sara; Bartoli, Fiora; Ventura, Alessandro; Decorti, Giuliana (Br J Clin Pharmacol, 2012)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT: In vitro lymphocyte steroid sensitivity has been suggested as a useful tool to predict in vivo response to glucocorticoid treatment in different inflammatory chronic diseases. A correlation between genetic polymorphisms and clinical response to glucocorticoids has been demonstrated in these patients. WHAT THIS STUDY ADDS: The BclI polymorphism in the glucocorticoid receptor (NR3C1) gene is associated with higher methylprednisolone potency in vitro. The combined evaluation of the in vitro sensitivity to methylprednisolone and BclI polymorphism could represent an aid for physicians to adjust therapy a priori. AIM To evaluate the association between the in vitro sensitivity of peripheral blood mononuclear cells (PBMCs) to methylprednisolone (MP) and the presence of genetic polymorphisms involved in glucocorticoid (GC) response. METHODS: In vitro MP inhibition of the proliferation of lymphocytes stimulated with concanavalin A was determined. Non linear regression of dose-response data was performed computing the MP concentration required to reduce proliferation to 50% (IC(50) ). The maximum inhibition achievable at the highest MP concentration (I(max) ) was also calculated. Moreover, the Taqman technique was used to analyze the BclI polymorphism in the NR3C1 gene and the Leu155His polymorphism in the NALP1 gene. RESULTS: A significant association between the BclI mutated genotype and an increased in vitro sensitivity to GCs was observed. CONCLUSIONS: The a priori evaluation of the BclI polymorphism, associated with a lymphocyte proliferation assay, could represent a useful diagnostic tool for the optimization of steroid treatment.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Adult; Apoptosis Regulatory Proteins; Cyclin D1; Dose-Response Relationship, Drug; Female; Genotype; Glucocorticoids; Humans; Lymphocytes; Male; Methylprednisolone; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Glucocorticoid; Young Adult

Association of MBL2 gene exon 1 variants with autoimmune thyroid disease in Brazilian patients. - Filho, C B; Rodrigues, F F; Segat, L; Fonseca, A M; Araujo, J; Arahata, C; Pontes, L; Vilar, L; de Lima Filho, J L; Crovella, S (Int J Immunogenet, 2012)
We investigated the association between MBL2 gene exon 1 functional polymorphisms and autoimmune thyroid disease (AITD) in 163 Brazilian patients (87 with Hashimoto thyroiditis, HT; 76 with Graves' disease) and 214 healthy controls. Individuals carrying MBL2 O allele are at higher risk of developing AITD (OR = 1.58, 95% CI: 1.11-2.26; P-value = 0.009) and HT (OR = 1.67, 95% CI: 1.09-2.55; P-value = 0.013) as suggesting a possible role for mannose-binding lectin in influencing disease susceptibility.
Keywords: Adolescent; Adult; Brazil; Case-Control Studies; Child; Child, Preschool; Exons; Female; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Testing; Graves Disease; Hashimoto Disease; Humans; Infant; Male; Mannose-Binding Lectin; Middle Aged; Polymorphism, Single Nucleotide; Young Adult

Autologous cord blood harvesting in North Eastern Italy: ethical questions and emerging hopes for curing diabetes and celiac disease. - Parco, Sergio; Vascotto, Fulvia (Int J Gen Med, 2012)
BACKGROUND: The Friuli Venezia Giulia (FVG), a region of North Eastern Italy, has passed legislation (Decree No 2324/2010) to regulate the banking of umbilical cord blood samples for personal, autologous, or family-directed use, and to implement the Agreement of the State-Regions Permanent Conference (Decree No 62/CSR/2010). This paper aims to identify the formalities and the reasons why families collect and bank their cord blood in foreign banks for both personal and private use. METHODS: To this end, at the Institute for Maternal and Child Health of Trieste (the regional capital city of the FVG), Italy, which assists about 1800 pregnant women a year, 129 questionnaires, drafted from January 2010 to December 2011 and concerning the granting of authorization to export samples, were examined. RESULTS: The collected data showed that 75% of involved families had resorted to anonymous public collection, which is available to anyone with therapeutic needs, and provided compatibility and hematologic protocols recognized by the scientific and international community (main indications: leukemia, hemoglobinopaties, and inherited hematologic and immunologic disorders). Conversely, 25.0% requested private storage at a foreign bank for personal or family-dedicated use. The principal motivation by disease was for treatment for diabetes (22.4%) and celiac disease (19.7%) (a multiorgan disease for which the FVG region has provided safeguards by approving a specific law granting support to families; Decree No 561/2007). For these two types of disease we found that information was received from the internet and not from general medical physicians, with a significant difference found using the χ(2) test (P < 0.01). CONCLUSION: The indication of treating these diseases with cord blood stem cell transplantation appears to be well grounded and encouraging, and has recently been corroborated by the international literature; however, the economic and social motivations promoting cord blood storage, for a fee, in the event of diseases that are still under study, require accurate information through general medical physicians on the actual possibilities of treatment.

A boy with acute strabismus. - Poropat, Federico; Ventura, Giovanna; Murru, Flora M; Orzan, Eva; Maschio, Massimo (J Pediatr, 2012)
Keywords: Acute Disease; Child; Humans; Magnetic Resonance Imaging; Male; Mucocele; Strabismus

A child with edema, lower limb deformity, and recurrent diarrhea. - Gortani, Giulia; Maschio, Massimo; Ventura, Alessandro (J Pediatr, 2012)
Keywords: Bone Retroversion; Capsule Endoscopy; Child, Preschool; Diarrhea; Edema; Humans; Knee Joint; Lymphangiectasis, Intestinal; Lymphedema; Male; Recurrence

A child with severe pneumomediastinum and ABCA3 gene mutation: a puzzling connection. - Copertino, Marco; Barbi, Egidio; Poli, Furio; Zennaro, Floriana; Ferrari, Maurizio; Carrera, Paola; Ventura, Alessandro (Arch Bronconeumol, 2012)
Keywords: Anemia; ATP-Binding Cassette Transporters; Child, Preschool; Dyspnea; Genetic Predisposition to Disease; Heterozygote; Humans; Intensive Care; Leukocytosis; Male; Mediastinal Emphysema; Mutation, Missense; Point Mutation; Pulmonary Emphysema; Respiratory Tract Infections; Subcutaneous Emphysema; Tomography, X-Ray Computed

Coeliac disease diagnosis: ESPGHAN 1990 criteria or need for a change? Results of a questionnaire. - Ribes-Koninckx, C; Mearin, M L; Korponay-Szabó, I R; Shamir, R; Husby, S; Ventura, A; Branski, D; Catassi, C; Koletzko, S; Mäki, M; Troncone, R; Zimmer, K P (J Pediatr Gastroenterol Nutr, 2012)
BACKGROUND AND OBJECTIVES: A revision of criteria for diagnosing coeliac disease (CD) is being conducted by The European Society for Pediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN). In parallel, we have performed a survey aimed to evaluate present practices for CD among paediatric gastroenterologists and to learn their views on the need for modification of present criteria for CD diagnosis. PATIENTS AND METHODS: Questionnaires were distributed to experienced paediatric gastroenterologists (ESPGHAN members) via the Internet. RESULTS: Overall, 95 valid questionnaires were available for analysis, pertaining to 28 different countries, with the majority of responders treating patients with CD for >15 years. Only about 12% of the responders comply with present criteria, noncompliance being related mainly to the challenge policy. Approximately 90% request a revision and modification of the present criteria. Forty-four percent want to omit the small bowel biopsy in symptomatic children with positive anti-tissue transglutaminase immunoglobulin (Ig) A or endomysial IgA antibodies, especially if they are DQ2/DQ8 positive. For silent cases detected by screening with convincingly positive anti-tissue transglutaminase IgA or EMA IgA, about 30% consider that no small bowel biopsy should be required in selected cases. Adding human leukocyte antigen typing in the diagnostic workup was asked for by 42% of the responders. As for gluten challenge, a new policy is advocated restricting its obligation to cases whenever the diagnosis is doubtful or unclear. CONCLUSIONS: Based on these opinions, revision of the ESPGHAN criteria for diagnosing CD is urgently needed.
Keywords: Adolescent; Adult; Biopsy; Celiac Disease; Child; Child, Preschool; Glutens; Guideline Adherence; Guidelines as Topic; Health Care Surveys; Humans; Immunoglobulin A; Intestine, Small; Physician's Practice Patterns; Questionnaires; Societies, Medical; Transglutaminases; Young Adult

Comments to the editor concerning the paper entitled "Preclinical renal cancer chemopreventive efficacy of geraniol by modulation of multiple molecular pathways" Shiekh Tanveer Ahmad et al. - Vuch, Josef; Marcuzzi, Annalisa; Zanin, Valentina; Crovella, Sergio (Toxicology, 2012)
Keywords: Animals; Antineoplastic Agents; Kidney Neoplasms; Male; Signal Transduction; Terpenes

Dealing with abdominal pain in children affected by systemic lupus erythematosus. - Taddio, Andrea; Rosé, Carlos; Lepore, Loredana; Ventura, Alessandro (Semin Arthritis Rheum, 2012)
Keywords: Abdominal Pain; Female; Humans; Lupus Erythematosus, Systemic; Male

Delayed diagnosis of glycogen storage disease type III. - Minen, Federico; Cont, Gabriele; De Cunto, Angela; Martelossi, Stefano; Ventura, Alessandro; Maggiore, Giuseppe; Faletra, Flavio; Gasparini, Paolo; Cassandrini, Denise (J Pediatr Gastroenterol Nutr, 2012)
Keywords: Delayed Diagnosis; Diagnostic Errors; Glycogen Storage Disease Type I; Glycogen Storage Disease Type III; Humans; Infant; Liver; Male

Diagnosed child, treated child: food challenge as the first step toward tolerance induction in cow's milk protein allergy. - Longo, G; Berti, I; Barbi, E; Calligaris, L; Matarazzo, L; Radillo, O; Ronfani, L; Ventura, A (Eur Ann Allergy Clin Immunol, 2012)
BACKGROUND: Food challenge is required to assess tolerance in cow milk (CM) allergy. A positive challenge contraindicates the reintroduction of CM. Specific oral tolerance induction (SOTI) is a promising treatment. METHODS: All children admitted for a challenge were prospectively enrolled. To those tolerating between 2 and 150 ml a SOTI protocol was offered. Outcome, adverse reactions, parents' satisfaction were recorded. RESULTS: Out of 245 challenged patients, 175 reacted 122 out of 125, able to tolerate a minimum dose of 2 ml, underwent SOTI. After one year 75.4% were in an unrestricted diet, 16.1% tolerated between 5 and 150 ml, 8.5% stopped SOTI. Side effects were mild, parents' satisfaction was very high. CONCLUSIONS: The majority of children tolerating limited amounts of CM at the challenge acquires tolerance with SOTI without relevant side effects. Maintaining on an exclusion diet partially tolerant children should be considered debatable.
Keywords: Administration, Oral; Adolescent; Animals; Cattle; Child; Child, Preschool; Humans; Immune Tolerance; Infant; Milk Hypersensitivity; Milk Proteins; Self Administration

The dietary paradox in food allergy: yesterday's mistakes, today's evidence and lessons for tomorrow. - Badina, Laura; Barbi, Egidio; Berti, Irene; Radillo, Oriano; Matarazzo, Lorenza; Ventura, Alessandro; Longo, Giorgio (Curr Pharm Des, 2012)
During the last decades the prevalence of food allergy has significantly increased among children and antigen avoidance still remains the standard care for the management of this condition. Most reactions are IgE-mediated with a high risk of anaphylaxis requiring emergency medications in case of inadvertent ingestion. Recent studies showed that continuous administration of the offending food, rather than an elimination diet, could promote the development and maintenance of oral tolerance. Indeed, intestinal transit of food proteins and their interaction with gut-associated lymphoid tissue (GALT) is the essential prerequisite for oral tolerance. On the contrary, low-dose cutaneous exposure to environmental foods in children with atopic dermatitis and altered skin barrier facilitates allergic sensitization. The timing and the amount of cutaneous and oral exposure determine whether a child will have allergy or tolerance. Furthermore, previous preventive strategies such as the elimination diet during pregnancy and breastfeeding, prolonged exclusive breastfeeding and delayed weaning to solid foods did not succeed in preventing the development of food allergy. On the other hand, there could be an early narrow window of immunological opportunity to expose children to allergenic foods and induce natural tolerance. Finally, the gradual exposure to the offending food through special protocols of specific oral tolerance induction (SOTI) may be a promising approach to a proactive treatment of food allergy.
Keywords: Anaphylaxis; Antigens; Breast Feeding; Child; Dermatitis, Atopic; Female; Food Hypersensitivity; Humans; Immunoglobulin E; Pregnancy; Time Factors

The effect of clodronate on a mevalonate kinase deficiency cellular model. - Zanin, Valentina; Marcuzzi, Annalisa; Piscianz, Elisa; Vuch, Josef; Bianco, Anna Monica; Monasta, Lorenzo; Decorti, Giuliana; Crovella, Sergio (Inflamm Res, 2012)
BACKGROUND: A potential anti-inflammatory effect of clodronate--an aminobisphosphonate--was described to antagonize the pro-inflammatory effects of the block in the mevalonate pathway, the main feature of a rare auto-inflammatory disease called mevalonate kinase deficiency (MKD). OBJECTIVE: In this study we evaluated the potential anti-inflammatory effect of clodronate in MKD--a still orphan drug pediatric disease. METHODS: We studied some biological parameters, nitric oxide production using Griess reagents and programmed cell death by flow cytometry, as common inflammatory parameters in MKD, in the presence of different doses of clodronate (1, 10 and 100 μM). RESULTS: In our cellular model and in monocytes from patients with MKD, clodronate induced an increase in programed cell death and nitric oxide production in comparison with non-treated cells. CONCLUSION: Our findings suggest that clodronate does not have an anti-inflammatory effect as previously reported but that it increases the epiphenomena of this pediatric disease.
Keywords: Adolescent; Adult; Alendronate; Animals; Anti-Inflammatory Agents; Apoptosis; Cell Line; Cells, Cultured; Child; Clodronic Acid; Female; Humans; Inflammation; Lipopolysaccharides; Male; Mevalonate Kinase Deficiency; Mice; Models, Biological; Monocytes; Nitric Oxide; Young Adult

Efficacy of rifaximin vaginal tablets in treatment of bacterial vaginosis: a molecular characterization of the vaginal microbiota. - Cruciani, Federica; Brigidi, Patrizia; Calanni, Fiorella; Lauro, Vittoria; Tacchi, Raffaella; Donders, Gilbert; Peters, Klaus; Guaschino, Secondo; Vitali, Beatrice (Antimicrob Agents Chemother, 2012)
Bacterial vaginosis (BV) is a common vaginal disorder characterized by an alteration of the vaginal bacterial morphotypes, associated with sexually transmitted infections and adverse pregnancy outcomes. The purpose of the present study was to evaluate the impact of different doses of rifaximin vaginal tablets (100 mg/day for 5 days, 25 mg/day for 5 days, and 100 mg/day for 2 days) on the vaginal microbiota of 102 European patients with BV enrolled in a multicenter, double-blind, randomized, placebo-controlled study. An integrated molecular approach based on quantitative PCR (qPCR) and PCR-denaturing gradient gel electrophoresis (PCR-DGGE) was used to investigate the effects of vaginal tablets containing the antibiotic. An increase in members of the genus Lactobacillus and a decrease in the BV-related bacterial groups after the antibiotic treatment were demonstrated by qPCR. PCR-DGGE profiles confirmed the capability of rifaximin to modulate the composition of the vaginal microbial communities and to reduce their complexity. This molecular analysis supported the clinical observation that rifaximin at 25 mg/day for 5 days represents an effective treatment to be used in future pivotal studies for the treatment of BV.
Keywords: Adolescent; Adult; Anti-Bacterial Agents; Double-Blind Method; Female; Humans; Lactobacillus; Metagenome; Middle Aged; Rifamycins; RNA, Ribosomal, 16S; Vagina; Vaginal Creams, Foams, and Jellies; Vaginosis, Bacterial; Young Adult

Endothelial cells obtained from patients affected by chronic venous disease exhibit a pro-inflammatory phenotype. - Tisato, Veronica; Zauli, Giorgio; Voltan, Rebecca; Gianesini, Sergio; di Iasio, Maria Grazia; Volpi, Ilaria; Fiorentini, Guido; Zamboni, Paolo; Secchiero, Paola (PLoS One, 2012)
BACKGROUND: The inflammatory properties of vein endothelium in relation to chronic venous disease (CVD) have been poorly investigated. Therefore, new insights on the characteristics of large vein endothelium would increase our knowledge of large vessel physiopathology. METHODOLOGY/PRINCIPAL FINDINGS: Surgical specimens of veins were obtained from the tertiary venous network (R3) and/or saphenous vein (SF) of patients affected by CVD and from control individuals. Highly purified venous endothelial cell (VEC) cultures obtained from CVD patients were characterized for morphological, phenotypic and functional properties compared to control VEC. An increase of CD31/PECAM-1, CD146 and ICAM-1 surface levels was documented at flow cytometry in pathological VEC with respect to normal controls. Of note, the strongest expression of these pro-inflammatory markers was observed in VEC obtained from patients with more advanced disease. Similarly, spontaneous cell proliferation and resistance to starvation was higher in pathological than in normal VEC, while the migratory response of VEC showed an opposite trend, being significantly lower in VEC obtained from pathological specimens. In addition, in keeping with a higher baseline transcriptional activity of NF-kB, the release of the pro-inflammatory cytokines osteoprotegerin (OPG) and vascular endothelial growth factor (VEGF) was higher in pathological VEC cultures with respect to control VEC. Interestingly, there was a systemic correlation to these in vitro data, as demonstrated by higher serum OPG and VEGF levels in CVD patients with respect to normal healthy controls. CONCLUSION/SIGNIFICANCE: Taken together, these data indicate that large vein endothelial cells obtained from CVD patients exhibit a pro-inflammatory phenotype, which might significantly contribute to systemic inflammation in CVD patients.
Keywords: Adult; Antigens, CD146; Antigens, CD31; Body Mass Index; Cell Culture Techniques; Endothelial Cells; Female; Flow Cytometry; Humans; Inflammation; Intercellular Adhesion Molecule-1; Kinetics; Male; Microscopy, Electron, Scanning; Middle Aged; Phenotype; Saphenous Vein; Vascular Diseases

European Society for Pediatric Gastroenterology, Hepatology, and Nutrition guidelines for the diagnosis of coeliac disease. - Husby, S; Koletzko, S; Korponay-Szabó, I R; Mearin, M L; Phillips, A; Shamir, R; Troncone, R; Giersiepen, K; Branski, D; Catassi, C; Lelgeman, M; Mäki, M; et al. (J Pediatr Gastroenterol Nutr, 2012)
OBJECTIVE: Diagnostic criteria for coeliac disease (CD) from the European Society for Paediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) were published in 1990. Since then, the autoantigen in CD, tissue transglutaminase, has been identified; the perception of CD has changed from that of a rather uncommon enteropathy to a common multiorgan disease strongly dependent on the haplotypes human leukocyte antigen (HLA)-DQ2 and HLA-DQ8; and CD-specific antibody tests have improved. METHODS: A panel of 17 experts defined CD and developed new diagnostic criteria based on the Delphi process. Two groups of patients were defined with different diagnostic approaches to diagnose CD: children with symptoms suggestive of CD (group 1) and asymptomatic children at increased risk for CD (group 2). The 2004 National Institutes of Health/Agency for Healthcare Research and Quality report and a systematic literature search on antibody tests for CD in paediatric patients covering the years 2004 to 2009 was the basis for the evidence-based recommendations on CD-specific antibody testing. RESULTS: In group 1, the diagnosis of CD is based on symptoms, positive serology, and histology that is consistent with CD. If immunoglobulin A anti-tissue transglutaminase type 2 antibody titers are high (>10 times the upper limit of normal), then the option is to diagnose CD without duodenal biopsies by applying a strict protocol with further laboratory tests. In group 2, the diagnosis of CD is based on positive serology and histology. HLA-DQ2 and HLA-DQ8 testing is valuable because CD is unlikely if both haplotypes are negative. CONCLUSIONS: The aim of the new guidelines was to achieve a high diagnostic accuracy and to reduce the burden for patients and their families. The performance of these guidelines in clinical practice should be evaluated prospectively.
Keywords: Adolescent; Celiac Disease; Child; Duodenum; HLA-DQ Antigens; Humans; Immunoglobulin A; Transglutaminases

Evidence of inbreeding depression on human height. - McQuillan, Ruth; Eklund, Niina; Pirastu, Nicola; Kuningas, Maris; McEvoy, Brian P; Esko, Tõnu; Corre, Tanguy; Davies, Gail; Kaakinen, Marika; Lyytikäinen, Leo-Pekka; Kristiansson, Kati; Havulinna, Aki S; et al. (PLoS Genet, 2012)
Stature is a classical and highly heritable complex trait, with 80%-90% of variation explained by genetic factors. In recent years, genome-wide association studies (GWAS) have successfully identified many common additive variants influencing human height; however, little attention has been given to the potential role of recessive genetic effects. Here, we investigated genome-wide recessive effects by an analysis of inbreeding depression on adult height in over 35,000 people from 21 different population samples. We found a highly significant inverse association between height and genome-wide homozygosity, equivalent to a height reduction of up to 3 cm in the offspring of first cousins compared with the offspring of unrelated individuals, an effect which remained after controlling for the effects of socio-economic status, an important confounder (χ(2) = 83.89, df = 1; p = 5.2 × 10(-20)). There was, however, a high degree of heterogeneity among populations: whereas the direction of the effect was consistent across most population samples, the effect size differed significantly among populations. It is likely that this reflects true biological heterogeneity: whether or not an effect can be observed will depend on both the variance in homozygosity in the population and the chance inheritance of individual recessive genotypes. These results predict that multiple, rare, recessive variants influence human height. Although this exploratory work focuses on height alone, the methodology developed is generally applicable to heritable quantitative traits (QT), paving the way for an investigation into inbreeding effects, and therefore genetic architecture, on a range of QT of biomedical importance.
Keywords: Adult; Aged; Body Height; Consanguinity; Databases, Genetic; Family; Female; Genes, Recessive; Genetic Heterogeneity; Genome-Wide Association Study; Homozygote; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

Exhaled nitric oxide as a guide to management of asthma in pregnancy. - Bibalo, Chiara; Badina, Laura; Longo, Giorgio; Ventura, Alessandro (Lancet, 2012)
Keywords: Asthma; Breath Tests; Female; Glucocorticoids; Humans; Nitric Oxide; Pregnancy; Pregnancy Complications

From bone marrow transplantation to cellular therapies: possible therapeutic strategies in managing autoimmune disorders. - Taddio, Andrea; Biondi, Andrea; Piscianz, Elisa; Valencic, Erica; Biagi, Ettore; Badolato, Raffaele (Curr Pharm Des, 2012)
Chronic inflammatory disorders occurring in childhood represent a serious therapeutic challenge. However, available therapies seem not to be targeted on the pathogenic mechanism of the disease and are often not actively affecting the natural history of the disease. Emerging treatments might be of some benefit to many patients who did not respond to conventional therapeutic options. Biological therapies with monoclonal antibodies and other recombinant proteins have been introduced in clinical practice. At the same time, mesenchymal stromal cells (MSC) have gained attention as a savage treatment in patients subjected to hematopoietic stem cell transplantation who develop severe graft versus host disease (GvHD); in addition, recent reports from clinical trials on larger cohorts of patients support their use as second-line treatment after failure of corticosteroid treatment. For analogy, they have been proposed for the treatment of intractable autoimmune disorders. Hematopoietic stem cell transplantation (HSCT) has been shown to be effective for treatment of rheumatic disorder cases that were resistant to traditional therapies especially if combined with cell manipulation techniques, such as selection of regulatory T cell and depletion of harmful lymphocytes. We herein present the rationale of different strategies, the preliminary data obtained in clinical trials, unsolved problems and possible next developments of novel treatment protocols of autoimmune disorders.
Keywords: Autoimmune Diseases; Bone Marrow Transplantation; Child; Chronic Disease; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Humans; Inflammation; Lymphocytes; Mesenchymal Stem Cell Transplantation; T-Lymphocytes, Regulatory; Treatment Outcome

Genome-wide association and functional follow-up reveals new loci for kidney function. - Pattaro, Cristian; Köttgen, Anna; Teumer, Alexander; Garnaas, Maija; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (PLoS Genet, 2012)
Chronic kidney disease (CKD) is an important public health problem with a genetic component. We performed genome-wide association studies in up to 130,600 European ancestry participants overall, and stratified for key CKD risk factors. We uncovered 6 new loci in association with estimated glomerular filtration rate (eGFR), the primary clinical measure of CKD, in or near MPPED2, DDX1, SLC47A1, CDK12, CASP9, and INO80. Morpholino knockdown of mpped2 and casp9 in zebrafish embryos revealed podocyte and tubular abnormalities with altered dextran clearance, suggesting a role for these genes in renal function. By providing new insights into genes that regulate renal function, these results could further our understanding of the pathogenesis of CKD.
Keywords: African Americans; Aged; Animals; Caspase 9; Cyclin-Dependent Kinases; DEAD-box RNA Helicases; DNA Helicases; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Knockdown Techniques; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Phosphoric Diester Hydrolases; Zebrafish

Genomic profiling by whole-genome single nucleotide polymorphism arrays in Wilms tumor and association with relapse. - Perotti, Daniela; Spreafico, Filippo; Torri, Federica; Gamba, Beatrice; d'Adamo, Pio; Pizzamiglio, Sara; Terenziani, Monica; Catania, Serena; Collini, Paola; Nantron, Marilina; Pession, Andrea; Bianchi, Maurizio; et al. (Genes Chromosomes Cancer, 2012)
Despite the excellent survival rate of Wilms tumor (WT) patients, only approximately one-half of children who suffer tumor recurrence reach second durable remission. This underlines the need for novel markers to optimize initial treatment. We investigated 77 tumors using Illumina 370CNV-QUAD genotyping BeadChip arrays and compared their genomic profiles to detect copy number (CN) abnormalities and allelic ratio anomalies associated with the following clinicopathological variables: relapse (yes vs. no), age at diagnosis (≤ 24 months vs. >24 months), and disease stage (low stage, I and II, vs. high stage, III and IV). We found that CN gains at chromosome region 1q21.1-q31.3 were significantly associated with relapse. Additional genetic events, including allelic imbalances at chromosome arms 1p, 1q, 3p, 3q, and 14q were also found to occur at higher frequency in relapsing tumors. Interestingly, allelic imbalances at 1p and 14q also showed a borderline association with higher tumor stages. No genetic events were found to be associated with age at diagnosis. This is the first genome wide analysis with single nucleotide polymorphism (SNP) arrays specifically investigating the role of genetic anomalies in predicting WT relapse on cases prospectively enrolled in the same clinical trial. Our study, besides confirming the role of 1q gains, identified a number of additional candidate genetic markers, warranting further molecular investigations.
Keywords: Adolescent; Allelic Imbalance; Child; Child, Preschool; Chromosome Aberrations; DNA Copy Number Variations; Female; Genetic Markers; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Infant; Kaplan-Meier Estimate; Male; Polymorphism, Single Nucleotide; Prospective Studies; Recurrence; Wilms Tumor

Haematopoietic SCT in severe autoimmune diseases: updated guidelines of the European Group for Blood and Marrow Transplantation. - Snowden, J A; Saccardi, R; Allez, M; Ardizzone, S; Arnold, R; Cervera, R; Denton, C; Hawkey, C; Labopin, M; Mancardi, G; Martin, R; Moore, J J; et al. (Bone Marrow Transplant, 2012)
In 1997, the first consensus guidelines for haematopoietic SCT (HSCT) in autoimmune diseases (ADs) were published, while an international coordinated clinical programme was launched. These guidelines provided broad principles for the field over the following decade and were accompanied by comprehensive data collection in the European Group for Blood and Marrow Transplantation (EBMT) AD Registry. Subsequently, retrospective analyses and prospective phase I/II studies generated evidence to support the feasibility, safety and efficacy of HSCT in several types of severe, treatment-resistant ADs, which became the basis for larger-scale phase II and III studies. In parallel, there has also been an era of immense progress in biological therapy in ADs. The aim of this document is to provide revised and updated guidelines for both the current application and future development of HSCT in ADs in relation to the benefits, risks and health economic considerations of other modern treatments. Patient safety considerations are central to guidance on patient selection and HSCT procedural aspects within appropriately experienced and Joint Accreditation Committee of International Society for Cellular Therapy and EBMT accredited centres. A need for prospective interventional and non-interventional studies, where feasible, along with systematic data reporting, in accordance with EBMT policies and procedures, is emphasized.
Keywords: Autoimmune Diseases; Clinical Trials, Phase I as Topic; Clinical Trials, Phase II as Topic; European Union; Female; Hematopoietic Stem Cell Transplantation; Humans; Male; Risk Factors; Safety; Severity of Illness Index

High prevalence of serum antibodies reacting with simian virus 40 capsid protein mimotopes in patients affected by malignant pleural mesothelioma. - Mazzoni, Elisa; Corallini, Alfredo; Cristaudo, Alfonso; Taronna, Angelo; Tassi, Gianfranco; Manfrini, Marco; Comar, Manola; Bovenzi, Massimo; Guaschino, Roberto; Vaniglia, Francesca; Magnani, Corrado; Casali, Ferruccio; et al. (Proc Natl Acad Sci U S A, 2012)
Human malignant pleural mesothelioma (MPM) is considered a rare tumor, but recent estimations indicate that one-quarter million people will die of this neoplasm in Europe in the next three decades. The mineral asbestos is considered the main causative agent of this neoplasm. MPM is largely unresponsive to conventional chemotherapy/radiotherapy. In addition to asbestos exposure, genetic predisposition to asbestos carcinogenesis and to simian virus (SV)40 infection has also been suggested. SV40 is a DNA tumor virus found in some studies to be associated at high prevalence with MPM. SV40 sequences have also been detected, although at a lower prevalence than in MPM, in blood specimens from healthy donors. However, some studies have failed to reveal SV40 footprints in MPM and its association with this neoplasm. These conflicting results indicate the need for further investigations with new approaches. We report on the presence of antibodies in serum samples from patients affected by MPM that specifically react with two different SV40 mimotopes. The two SV40 peptides used in indirect ELISAs correspond to viral capsid proteins. ELISA with the two SV40 mimotopes gave overlapping results. Our data indicate that in serum samples from MPM-affected patients (n = 97), the prevalence of antibodies against SV40 viral capsid protein antigens is significantly higher (26%, P = 0.043) than in the control group (15%) represented by healthy subjects (n = 168) with the same median age (66 y) and sex. Our results suggest that SV40 is associated with a subset of MPM and circulates in humans.
Keywords: Amino Acid Sequence; Antibodies, Viral; Capsid Proteins; Enzyme-Linked Immunosorbent Assay; Female; Humans; Male; Mesothelioma; Molecular Sequence Data; Pleural Neoplasms; Pregnancy; Simian virus 40

Immunomodulatory drugs in autoimmune lymphoproliferative syndrome (ALPS). - Tommasini, Alberto; Valencic, Erica; Piscianz, Elisa; Rabusin, Marco (Pediatr Blood Cancer, 2012)
Keywords: Antineoplastic Agents; Autoimmune Lymphoproliferative Syndrome; Diseases in Twins; Humans; Male; Pentostatin

Integration of genome-wide association studies with biological knowledge identifies six novel genes related to kidney function. - Chasman, Daniel I; Fuchsberger, Christian; Pattaro, Cristian; Teumer, Alexander; Böger, Carsten A; Endlich, Karlhans; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (Hum Mol Genet, 2012)
In conducting genome-wide association studies (GWAS), analytical approaches leveraging biological information may further understanding of the pathophysiology of clinical traits. To discover novel associations with estimated glomerular filtration rate (eGFR), a measure of kidney function, we developed a strategy for integrating prior biological knowledge into the existing GWAS data for eGFR from the CKDGen Consortium. Our strategy focuses on single nucleotide polymorphism (SNPs) in genes that are connected by functional evidence, determined by literature mining and gene ontology (GO) hierarchies, to genes near previously validated eGFR associations. It then requires association thresholds consistent with multiple testing, and finally evaluates novel candidates by independent replication. Among the samples of European ancestry, we identified a genome-wide significant SNP in FBXL20 (P = 5.6 × 10(-9)) in meta-analysis of all available data, and additional SNPs at the INHBC, LRP2, PLEKHA1, SLC3A2 and SLC7A6 genes meeting multiple-testing corrected significance for replication and overall P-values of 4.5 × 10(-4)-2.2 × 10(-7). Neither the novel PLEKHA1 nor FBXL20 associations, both further supported by association with eGFR among African Americans and with transcript abundance, would have been implicated by eGFR candidate gene approaches. LRP2, encoding the megalin receptor, was identified through connection with the previously known eGFR gene DAB2 and extends understanding of the megalin system in kidney function. These findings highlight integration of existing genome-wide association data with independent biological knowledge to uncover novel candidate eGFR associations, including candidates lacking known connections to kidney-specific pathways. The strategy may also be applicable to other clinical phenotypes, although more testing will be needed to assess its potential for discovery in general.
Keywords: Amino Acid Transport Systems, Basic; Antigens, CD98 Heavy Chain; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inhibin-beta Subunits; Intracellular Signaling Peptides and Proteins; Low Density Lipoprotein Receptor-Related Protein-2; Membrane Proteins; Polymorphism, Single Nucleotide

Letter: inflammatory bowel disease, complementary and alternative medicine, and genetics. - Bianco, A M; Vuch, J; Girardelli, M; Zanin, V; Marcuzzi, A; Crovella, S (Aliment Pharmacol Ther, 2012)
Keywords: Complementary Therapies; Female; Humans; Inflammatory Bowel Diseases; Male; Medication Adherence

Letter: TPMT activity and age in IBD patients. - Stocco, G; De Iudicibus, S; Cuzzoni, E; Decorti, G; Martelossi, S; Ventura, A (Aliment Pharmacol Ther, 2012)
Keywords: Azathioprine; Humans; Immunosuppressive Agents; Inflammatory Bowel Diseases; Thioguanine

Lovastatin-induced apoptosis is modulated by geranylgeraniol in a neuroblastoma cell line. - Marcuzzi, Annalisa; Zanin, Valentina; Piscianz, Elisa; Tricarico, Paola Maura; Vuch, Josef; Girardelli, Martina; Monasta, Lorenzo; Bianco, Anna Monica; Crovella, Sergio (Int J Dev Neurosci, 2012)
Mevalonic aciduria (MA), the most severe form of mevalonate kinase deficiency (MKD), is still an orphan drug disease and the pathogenetic mechanisms underlying neuronal dysfunction is still poorly understood. In our study we have investigated the apoptotic mechanism mediated by the exposure of the cultured neuroblastoma cell line, SH-SY5Y, to lovastatin in absence or in presence of the isoprenoid, geranylgeraniol, with the aim of unraveling the pathogenesis of MA. Lovastatin, blocks the mevalonate pathway inhibiting the 3-hydroxy-3-methylglutaryl-CoA reductase (HMG-CR), an enzyme of the mevalonate pathway upstream the mevalonate kinase enzyme, reproducing biochemical features similar to those found in MKD. We demonstrate that apoptosis in neuronal lovastatin treated-cells is induced by the mitochondrial pathway, with caspase-9 as the initiator and caspase-3 as the effector caspase. The presence of geranylgeraniol modulates both the caspase-9 and caspase-3 activity in a dose-dependent way, confirming that this isoprenoid enters the mevalonate pathway, is metabolized and finally is able to by-pass the statin biochemical block reconstituting the mevalonate pathway. According to our findings, it should not be the time course adopted that modulates the apoptotic response but rather the isoprenoid itself. Being aware that our results have been obtained using a biochemical model of MKD, and not cells from patients with the disease, we believe our findings increase the knowledge of MA pathogenesis, and may possibly contribute to the development of novel therapeutic strategies.
Keywords: Analysis of Variance; Apoptosis; Caspases; Cell Line, Tumor; Diterpenes; Dose-Response Relationship, Drug; Drug Interactions; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Lovastatin; Neuroblastoma; Time Factors

Managing children under 36 months of age with febrile urinary tract infection: a new approach. - Pennesi, Marco; L'erario, Ines; Travan, Laura; Ventura, Alessandro (Pediatr Nephrol, 2012)
BACKGROUND: Recent guidelines on urinary tract infection (UTI) agree on reducing the number of invasive procedures. None of these has been validated by a long-term study. We describe our 11-years experience in the application of a diagnostic protocol that uses a reduced number of invasive procedures. METHODS: We reviewed retrospectively the records of 406 children aged between 1 and 36 months at their first UTI. All patients underwent renal ultrasound (RUS). Children with abnormal RUS and those with UTI recurrences underwent voiding cystourethrography (VCUG) and dimercaptosuccinic acid (DMSA) renal scans. RESULTS: RUS after the first UTI was pathological in 7.4% children; 4.4 % had a second UTI. We performed 48 VCUG: 14 patients (29%) had vesicoureteral reflux (VUR), 12 of which showed an abnormal RUS while 2 had recurrent UTI. After DMSA renal scan renal damage appeared in only 6 of them (12.5%); all these children showed grade IV VUR. CONCLUSIONS: The application of our guidelines leads to a decrease in invasive examinations without missing any useful diagnoses or compromising the child's health.
Keywords: Anti-Bacterial Agents; Child, Preschool; Female; Humans; Infant; Male; Pediatrics; Recurrence; Retrospective Studies; Urinary Tract Infections

MCL1 down-regulation plays a critical role in mediating the higher anti-leukaemic activity of the multi-kinase inhibitor Sorafenib with respect to Dasatinib. - Secchiero, Paola; Melloni, Elisabetta; Voltan, Rebecca; Norcio, Alessia; Celeghini, Claudio; Zauli, Giorgio (Br J Haematol, 2012)
Keywords: Antineoplastic Agents; Benzenesulfonates; Cell Line, Tumor; Down-Regulation; Humans; Leukemia, Myeloid, Acute; Myeloid Cell Leukemia Sequence 1 Protein; Niacinamide; Phenylurea Compounds; Protein Kinase Inhibitors; Proto-Oncogene Proteins c-bcl-2; Pyridines; Pyrimidines; Thiazoles

Mesenchymal stem cells display hepato-protective activity in lymphoma bearing xenografts. - Secchiero, Paola; Corallini, Federica; Zavan, Barbara; Tripodo, Claudio; Vindigni, Vincenzo; Zauli, Giorgio (Invest New Drugs, 2012)
A disseminated model of non-Hodgkin's lymphoma with prevalent liver metastasis was generated by intraperitoneal (i.p.) injection of EBV(+) B lymphoblastoid SKW6.4 in nude-SCID mice. The survival of SKW6.4 xenografts (median survival = 27 days) was significantly improved when hyaluronan scaffolds embedded with mesenchimal stem cells (MSC) were implanted in the abdominal area 4 days after SKW6.4 injection (median survival = 39.5 days). Mice implanted with MSC showed a significant improvement of hepatic functionality in lymphoma xenografts, as demonstrated by measurement of serum ALT/AST levels. Co-culture of MSC with lymphoma cells enhanced the release of hepatocyte growth factor (HGF) by MSC. These data suggest that hyaluronan-embedded MSC exert anti-lymphoma activity by ameliorating hepatic functionality.
Keywords: Alanine Transaminase; Animals; Aspartate Aminotransferases; Biological Markers; Cell Communication; Cell Line, Tumor; Cell Survival; Coculture Techniques; Hepatocyte Growth Factor; Humans; Hyaluronic Acid; Liver; Liver Neoplasms; Lymphoma, Non-Hodgkin; Mesenchymal Stem Cell Transplantation; Mesenchymal Stromal Cells; Mice; Mice, Nude; Mice, SCID; Time Factors; Tissue Scaffolds; Xenograft Model Antitumor Assays

Meta-analyses identify 13 loci associated with age at menopause and highlight DNA repair and immune pathways. - Stolk, Lisette; Perry, John R B; Chasman, Daniel I; He, Chunyan; Mangino, Massimo; Sulem, Patrick; Barbalic, Maja; Broer, Linda; Byrne, Enda M; Ernst, Florian; Esko, Tõnu; Franceschini, Nora; et al. (Nat Genet, 2012)
To newly identify loci for age at natural menopause, we carried out a meta-analysis of 22 genome-wide association studies (GWAS) in 38,968 women of European descent, with replication in up to 14,435 women. In addition to four known loci, we identified 13 loci newly associated with age at natural menopause (at P < 5 × 10(-8)). Candidate genes located at these newly associated loci include genes implicated in DNA repair (EXO1, HELQ, UIMC1, FAM175A, FANCI, TLK1, POLG and PRIM1) and immune function (IL11, NLRP11 and PRRC2A (also known as BAT2)). Gene-set enrichment pathway analyses using the full GWAS data set identified exoDNase, NF-κB signaling and mitochondrial dysfunction as biological processes related to timing of menopause.
Keywords: Age Factors; DNA Helicases; DNA Primase; DNA Repair; DNA Repair Enzymes; DNA-Directed DNA Polymerase; European Continental Ancestry Group; Exodeoxyribonucleases; Female; Genetic Loci; Genome-Wide Association Study; Humans; Immunity; Menopause; Polymorphism, Single Nucleotide; Proteins

miR-EdiTar: a database of predicted A-to-I edited miRNA target sites. - Laganà, Alessandro; Paone, Alessio; Veneziano, Dario; Cascione, Luciano; Gasparini, Pierluigi; Carasi, Stefania; Russo, Francesco; Nigita, Giovanni; Macca, Valentina; Giugno, Rosalba; Pulvirenti, Alfredo; Shasha, Dennis; et al. (Bioinformatics, 2012)
MOTIVATION: A-to-I RNA editing is an important mechanism that consists of the conversion of specific adenosines into inosines in RNA molecules. Its dysregulation has been associated to several human diseases including cancer. Recent work has demonstrated a role for A-to-I editing in microRNA (miRNA)-mediated gene expression regulation. In fact, edited forms of mature miRNAs can target sets of genes that differ from the targets of their unedited forms. The specific deamination of mRNAs can generate novel binding sites in addition to potentially altering existing ones. RESULTS: This work presents miR-EdiTar, a database of predicted A-to-I edited miRNA binding sites. The database contains predicted miRNA binding sites that could be affected by A-to-I editing and sites that could become miRNA binding sites as a result of A-to-I editing. AVAILABILITY: miR-EdiTar is freely available online at http://microrna.osumc.edu/mireditar. CONTACT: alessandro.lagana@osumc.edu or carlo.croce@osumc.edu SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Adenosine; Binding Sites; Databases, Genetic; Gene Expression Regulation; Humans; Inosine; Internet; MicroRNAs; Nucleic Acid Conformation; RNA Editing

Molecular analysis of HEXA gene in Argentinean patients affected with Tay-Sachs disease: possible common origin of the prevalent c.459+5A>G mutation. - Zampieri, Stefania; Montalvo, Annalisa; Blanco, Mariana; Zanin, Irene; Amartino, Hernan; Vlahovicek, Kristian; Szlago, Marina; Schenone, Andrea; Pittis, Gabriela; Bembi, Bruno; Dardis, Andrea (Gene, 2012)
Tay-Sachs disease (TSD) is a recessively inherited disorder caused by the deficient activity of hexosaminidase A due to mutations in the HEXA gene. Up to date there is no information regarding the molecular genetics of TSD in Argentinean patients. In the present study we have studied 17 Argentinean families affected by TSD, including 20 patients with the acute infantile form and 3 with the sub-acute form. Overall, we identified 14 different mutations accounting for 100% of the studied alleles. Eight mutations were novel: 5 were single base changes leading to drastic residue changes or truncated proteins, 2 were small deletions and one was an intronic mutation that may cause a splicing defect. Although the spectrum of mutations was highly heterogeneous, a high frequency of the c.459+5G>A mutation, previously described in different populations was found among the studied cohort. Haplotype analysis suggested that in these families the c.459+5G>A mutation might have arisen by a single mutational event.
Keywords: Child; Cohort Studies; Female; Hexosaminidase A; Humans; Infant; Male; Mutation; Tay-Sachs Disease

Molecular diagnosis of Usher syndrome: application of two different next generation sequencing-based procedures. - Licastro, Danilo; Mutarelli, Margherita; Peluso, Ivana; Neveling, Kornelia; Wieskamp, Nienke; Rispoli, Rossella; Vozzi, Diego; Athanasakis, Emmanouil; D'Eustacchio, Angela; Pizzo, Mariateresa; D'Amico, Francesca; Ziviello, Carmela; et al. (PLoS One, 2012)
Usher syndrome (USH) is a clinically and genetically heterogeneous disorder characterized by visual and hearing impairments. Clinically, it is subdivided into three subclasses with nine genes identified so far. In the present study, we investigated whether the currently available Next Generation Sequencing (NGS) technologies are already suitable for molecular diagnostics of USH. We analyzed a total of 12 patients, most of which were negative for previously described mutations in known USH genes upon primer extension-based microarray genotyping. We enriched the NGS template either by whole exome capture or by Long-PCR of the known USH genes. The main NGS sequencing platforms were used: SOLiD for whole exome sequencing, Illumina (Genome Analyzer II) and Roche 454 (GS FLX) for the Long-PCR sequencing. Long-PCR targeting was more efficient with up to 94% of USH gene regions displaying an overall coverage higher than 25×, whereas whole exome sequencing yielded a similar coverage for only 50% of those regions. Overall this integrated analysis led to the identification of 11 novel sequence variations in USH genes (2 homozygous and 9 heterozygous) out of 18 detected. However, at least two cases were not genetically solved. Our result highlights the current limitations in the diagnostic use of NGS for USH patients. The limit for whole exome sequencing is linked to the need of a strong coverage and to the correct interpretation of sequence variations with a non obvious, pathogenic role, whereas the targeted approach suffers from the high genetic heterogeneity of USH that may be also caused by the presence of additional causative genes yet to be identified.
Keywords: Child, Preschool; Exome; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Molecular Diagnostic Techniques; Pilot Projects; Sequence Analysis, DNA; Usher Syndromes

New insights in the sugarcane transcriptome responding to drought stress as revealed by superSAGE. - Kido, Éderson Akio; Ferreira Neto, José Ribamar Costa; Silva, Roberta Lane de Oliveira; Pandolfi, Valesca; Guimarães, Ana Carolina Ribeiro; Veiga, Daniela Truffi; Chabregas, Sabrina Moutinho; Crovella, Sergio; Benko-Iseppon, Ana Maria (ScientificWorldJournal, 2012)
In the scope of the present work, four SuperSAGE libraries have been generated, using bulked root tissues from four drought-tolerant accessions as compared with four bulked sensitive genotypes, aiming to generate a panel of differentially expressed stress-responsive genes. Both groups were submitted to 24 hours of water deficit stress. The SuperSAGE libraries produced 8,787,315 tags (26 bp) that, after exclusion of singlets, allowed the identification of 205,975 unitags. Most relevant BlastN matches comprised 567,420 tags, regarding 75,404 unitags with 164,860 different ESTs. To optimize the annotation efficiency, the Gene Ontology (GO) categorization was carried out for 186,191 ESTs (BlastN against Uniprot-SwissProt), permitting the categorization of 118,208 ESTs (63.5%). In an attempt to elect a group of the best tags to be validated by RTqPCR, the GO categorization of the tag-related ESTs allowed the in silico identification of 213 upregulated unitags responding basically to abiotic stresses, from which 145 presented no hits after BlastN analysis, probably concerning new genes still uncovered in previous studies. The present report analyzes the sugarcane transcriptome under drought stress, using a combination of high-throughput transcriptome profiling by SuperSAGE with the Solexa sequencing technology, allowing the identification of potential target genes during the stress response.
Keywords: Droughts; Gene Expression Profiling; Heat-Shock Response; Plant Proteins; Saccharum; Transcriptome

Nutlin-3 differentially modulates miRNA34a and miRNA181 versus miR26a and miR155 in p53 proficient and p53 deficient B chronic lymphocytic leukemia (B-CLL) samples. - di Iasio, Maria Grazia; Addobbati, Riccardo; Radillo, Oriano; Voltan, Rebecca (Invest New Drugs, 2012)
Keywords: Down-Regulation; Gene Expression Profiling; Gene Expression Regulation, Leukemic; Humans; Imidazoles; Leukemia, Lymphocytic, Chronic, B-Cell; MicroRNAs; Piperazines; Proto-Oncogene Proteins c-mdm2; Tumor Suppressor Protein p53

Pathergy as a cause of false-positive tuberculin skin test. - Pastore, Serena; Naviglio, Samuele; Ventura, Alessandro (Pediatr Infect Dis J, 2012)
Keywords: Adolescent; Behcet Syndrome; False Positive Reactions; Female; Humans; Hypersensitivity; Needles; Skin; Skin Tests; Tuberculin Test; Tuberculosis, Gastrointestinal

Peroxidase-like activity of ferruginous bodies isolated by exploiting their magnetic property. - Borelli, Violetta; Trevisan, Elisa; Vita, Francesca; Bottin, Cristina; Melato, Mauro; Rizzardi, Clara; Zabucchi, Giuliano (J Toxicol Environ Health A, 2012)
Ferruginous bodies (FB) are polymorphic structures whose formation is macrophage dependent, and are composed of a core, which may consist of an asbestos fiber coated with proteins, among which ferritin is the main component. Within ferritin, the ferric and ferrous ions are coordinated as ferrihydrite, which is the main iron (Fe) storage compound. However, when ferritin accumulates in some tissues following Fe overload it also contains magnetite along with ferrihydrite, which endows it with magnetic properties. Recently studies showed that magnetite exerts peroxidase-like activity, and since ferruginous bodies display magnetic properties, it was postulated that these particular structures may also contain magnetite within the ferritin coating, and thus may also exert peroxidase-like activity. Histochemical analysis for peroxidase of isolated FB smears demonstrated positive staining. Samples isolated from 4 different autopsy lung fragments were also able to oxidize 3,3',5,5'-tetramethyl-benzidine to a blue colored compound that absorbs at 655 nm. This activity was (1) azide and heat insensitive with optimal pH from 5 to 6, and (2) highly variable, changing more than 25-fold from one sample to another. These findings, together with evidence that the peroxidase-like activity of ferruginous bodies has a hydrogen peroxide and substrate requirement different from that of human myeloperoxidase, can exclude that this enzyme gives a significant contribution to the formation of FB. Standard Fe-rich asbestos fibers also express a peroxidase-like activity, but this appears negligible compared to that of ferruginous bodies. Strong acidification of standard Fe-containing asbestos fibers or magnetically isolated ferruginous bodies liberates a high amount of peroxidase-like activity, which is probably accounted for by the release of Fe ions. Further, FB also damage mesothelial cells in vitro. Data suggest that FB exert peroxidase-like activity and cytotoxic activity against mesothelial cells, and hence may be an important factor in pathogenesis of asbestos-related diseases.
Keywords: Air Pollutants, Occupational; Asbestos; Asbestosis; Benzidines; Catalysis; Cell Line; Chromogenic Compounds; Cytotoxins; Ferric Compounds; Ferritins; Ferrosoferric Oxide; Humans; Hydrogen-Ion Concentration; Lung; Magnetic Phenomena; Mesothelioma; Mineral Fibers; Oxidation-Reduction; Peroxidases; Respiratory Mucosa

Relation between maternal thrombophilia and stillbirth according to causes/associated conditions of death. - Monari, F; Alberico, S; Avagliano, L; Cetin, I; Cozzolino, S; Gargano, G; Marozio, L; Mecacci, F; Neri, I; Tranquilli, A L; Venturini, P; Facchinetti, F (Early Hum Dev, 2012)
OBJECTIVE: To investigate maternal thrombophilia in cases of Stillbirth (SB), also an uncertain topic because most case series were not characterised for cause/associated conditions of death. STUDY DESIGN: In a consecutive, prospective, multicentre design, maternal DNA was obtained in 171 cases of antenatal SB and 326 controls (uneventful pregnancy at term, 1:2 ratio). Diagnostic work-up of SB included obstetric history, neonatologist inspection, placenta histology, autopsy, microbiology/chromosome evaluations. Results audited in each centre were classified by two of us by using CoDAC. Cases were subdivided into explained SB where a cause of death was identified and although no defined cause was detected in the remnants, 64 cases found conditions associated with placenta-vascular disorders (including preeclampsia, growth restriction and placenta abruption - PVD). In the remnant 79 cases, no cause of death or associated condition was found. Antithrombin activity, Factor V Leiden, G20210A Prothrombin mutation (FII mutation) and acquired thrombophilia were analysed. RESULTS: Overall, the presence of a thrombophilic defect was significantly more prevalent in mothers with SBs compared to controls. In particular, SB mothers showed an increased risk of carrying Factor II mutation (OR=3.2, 95% CI: 1.3-8.3, p=0.01), namely in unexplained cases. Such mutation was significantly associated also with previous SB (OR=8.9, 95%CI 1.2-70.5). At multiple logistic regression, Factor II mutation was the only significantly associated variable with SB (adj OR=3.8, 95% CI: 1.3-13.5). CONCLUSION: These data suggest that Factor II mutation is the only condition specifically associated with unexplained SB and could represents a risk of recurrence. PVD-associated condition is unrelated to thrombophilia.
Keywords: Adult; Case-Control Studies; Cause of Death; Female; Fetal Diseases; Fetal Mortality; Humans; Infant, Newborn; Male; Placenta Diseases; Pre-Eclampsia; Pregnancy; Pregnancy Complications, Hematologic; Socioeconomic Factors; Stillbirth; Thrombophilia; Young Adult

Should cardiac involvement be included in the criteria for diagnosis of Churg Strauss syndrome? - Amaddeo, Alessandro; Ventura, Alessandro; Marchetti, Federico; Benettoni, Alessandra; Londero, Margherita (J Pediatr, 2012)
Keywords: Adolescent; Churg-Strauss Syndrome; Heart Diseases; Humans; Male

Slow growth: do not forget the thyroid. - Tornese, Gianluca; Tonini, Giorgio; Ventura, Alessandro (J Pediatr Gastroenterol Nutr, 2012)
Keywords: Constipation; Female; Humans; Hypothyroidism; Male; Thyroid Function Tests

The sorafenib plus nutlin-3 combination promotes synergistic cytotoxicity in acute myeloid leukemic cells irrespectively of FLT3 and p53 status. - Zauli, Giorgio; Celeghini, Claudio; Melloni, Elisabetta; Voltan, Rebecca; Ongari, Manuele; Tiribelli, Mario; di Iasio, Maria Grazia; Lanza, Francesco; Secchiero, Paola (Haematologica, 2012)
BACKGROUND: Both the multi-kinase inhibitor sorafenib and the small molecule inhibitor of the MDM2/p53 interaction, nutlin-3, used alone, have shown promising anti-leukemic activity in acute myeloid leukemia cells. Thus, in this study we investigated the effect of the combination of sorafenib plus nutlin-3 in acute myeloid leukemia. DESIGN AND METHODS: Primary acute myeloid leukemia blasts (n=13) and FLT3(wild-type)/p53(wild-type) (OCI-AML3), FLT3(mutated)/p53(wild-type) (MOLM), FLT3(mutated)/p53(mutated) (MV4-11), FLT3(wild-type)/p53(deleted) (HL60) or FLT3(wild-type)/p53(mutated) (NB4) acute myeloid cell lines were exposed to sorafenib, used alone or in association with nutlin-3 at a 1:1 ratio, in a range of clinically achievable concentrations (1-10 μM). Induction of apoptosis and autophagy was evaluated by transmission electron microscopy and by specific flow cytometry analyses. The levels of Mcl-1, p53 and Bak proteins were analyzed by western blotting. Knock-down of Bax and Bak gene expression was performed in transfection experiments with specific short interfering RNA. RESULTS: The sorafenib+nutlin-3 drug combination exhibits synergistic cytotoxicity in primary acute myeloid leukemia blasts and in acute myeloid leukemia cell lines with maximal cytotoxicity in FLT3(mutated) MV4-11 and MOLM, followed by the FLT3(wild-type) OCI-AML3, HL60 and NB4 cell lines. The cytotoxic activity of sorafenib+nutlin-3 was characterized by an increase of both apoptosis and autophagy. Moreover, Bax and Bak showed prominent roles in mediating the decrease of cell viability in response to the drug combination in p53(wild-type) OCI-AML3 and p53(deleted) HL-60 cells, respectively, as demonstrated in transfection experiments performed with specific short interfering RNA. CONCLUSIONS: Our data demonstrate that acute myeloid leukemia cells show a variable but overall good susceptibility to the innovative therapeutic combination of sorafenib+nutlin-3, which differentially involves the pro-apoptotic Bcl-2 family members Bax and Bak in p53(wild-type) and p53(deleted) cells.
Keywords: Antineoplastic Agents; Drug Synergism; Female; fms-Like Tyrosine Kinase 3; HL-60 Cells; Humans; Imidazoles; Leukemia, Myeloid, Acute; Male; Niacinamide; Phenylurea Compounds; Piperazines; Tumor Suppressor Protein p53

State of the art of the therapeutic perspective of sorafenib against hematological malignancies. - Zauli, G; Voltan, R; Tisato, V; Secchiero, P (Curr Med Chem, 2012)
The bi-aryl urea multi-kinase inhibitor Sorafenib (BAY 43-9006, Nexavar) was initially approved for the treatment of unresectable hepatocellular carcinoma and advanced renal cell carcinoma. Eleven years after its first description in PubMed, the therapeutic potential of Sorafenib has been evaluated in an increasing number of studies, mainly focused on solid tumors. More recently, the potential usefullness of Sorafenib has started to emerge also against hematological malignancies. At the molecular level, besides the RAF kinase pathway, which represents the first therapeutic target of Sorafenib, additional kinases, in particular the vascular endothelial growth factor receptor, have been identified as important targets of Sorafenib. A great interest for the potential use of Sorafenib against acute myeloid leukemia (AML) arose when it was demonstrated that a specific mutation of a kinase gene, called FMS-like tyrosin-kinase-3- internal tandem duplication (FLT-3-ITD) and occurring in more than 30% of AML, represents a molecular target of Sorafenib. However, recent phase I and II clinical studies showed that, in spite of its ability to suppress the activity of this mutated kinase, resistence to Sorafenib rapidly occurs in AML, suggesting that Sorafenib will be more effective in combined therapy than used as single drug. Another critical molecular target of Sorafenib is the anti-apoptotic protein Mcl-1. The ability of Sorafenib to rapidly shut-off Mcl-1 in virtually all the hematological malignancies investigated, including the B-chronic lymphocytic leukemia, represents a key element for its antileukemic activity as well as for therapeutic combinations based on Sorafenib. In this respect, it is of particular interest that many chemotherapeutic drugs or innovative anti-neoplastic compounds, such as recombinant TRAIL or inibitors of MDM2 protein, are either unable to down-regulate Mcl-1 or in some instances promote a paradoxical induction of Mcl-1. In this review, the growing evidences for the role of Mcl-1 in mediating the anti-leukemic activity of Sorafenib will be discussed in relationship with promising therapeutic perspectives.
Keywords: Apoptosis; Clinical Trials as Topic; fms-Like Tyrosine Kinase 3; Hematologic Neoplasms; Humans; Leukemia, Myeloid, Acute; Myeloid Cell Leukemia Sequence 1 Protein; Niacinamide; Phenylurea Compounds; Proto-Oncogene Proteins c-bcl-2; Proto-Oncogene Proteins c-mdm2; Receptors, Vascular Endothelial Growth Factor; TNF-Related Apoptosis-Inducing Ligand

The submerged dyslexia iceberg: how many school children are not diagnosed? Results from an Italian study. - Barbiero, Chiara; Lonciari, Isabella; Montico, Marcella; Monasta, Lorenzo; Penge, Roberta; Vio, Claudio; Tressoldi, Patrizio Emanuele; Ferluga, Valentina; Bigoni, Anna; Tullio, Alessia; Carrozzi, Marco; Ronfani, Luca (PLoS One, 2012)
BACKGROUND: Although dyslexia is one of the most common neurobehavioral disorders affecting children, prevalence is uncertain and available data are scanty and dated. The objective of this study is to evaluate the prevalence of dyslexia in an unselected school population using clearly defined and rigorous diagnostic criteria and methods. METHODS: Cross sectional study. We selected a random cluster sample of 94 fourth grade elementary school classes of Friuli Venezia Giulia, a Region of North Eastern Italy. We carried out three consecutive levels of screening: the first two at school and the last at the Neuropsychiatry Unit of a third level Mother and Child Hospital. The main outcome measure was the prevalence of dyslexia, defined as the number of children positive to the third level of screening divided by the total number of children enrolled. RESULTS: We recruited 1774 children aged 8-10 years, of which 1528 received parents' consent to participate. After applying exclusion criteria, 1357 pupils constituted the final working sample. The prevalence of dyslexia in the enrolled population ranged from 3.1% (95% CI 2.2-4.1%) to 3.2% (95% CI 2.4-4.3%) depending on different criteria adopted. In two out of three children with dyslexia the disorder had not been previously diagnosed. CONCLUSIONS: This study shows that dyslexia is largely underestimated in Italy and underlines the need for reliable information on prevalence, in order to better allocate resources both to Health Services and Schools.
Keywords: Area Under Curve; Child; Cross-Sectional Studies; Delayed Diagnosis; Dyslexia; Female; Humans; Italy; Male; Neuropsychological Tests; Prevalence; Questionnaires; ROC Curve

Successful induction of oral tolerance in Netherton syndrome. - Pastore, Serena; Gorlato, Gaia; Berti, Irene; Barbi, Egidio; Ventura, Alessandro (Allergol Immunopathol (Madr), 2012)
Keywords: Allergens; Alopecia; Child, Preschool; Desensitization, Immunologic; Disease-Free Survival; Eczema; Female; Food Hypersensitivity; Hair Follicle; Humans; Immune Tolerance; Immunoglobulin E; Infant, Newborn; Mouth; Netherton Syndrome; Treatment Outcome

Treatment with pamidronate for osteoporosis complicating long-term intestinal failure. - Pastore, S; Londero, M; Barbieri, F; Di Leo, G; Paparazzo, R; Ventura, A (J Pediatr Gastroenterol Nutr, 2012)
Long-term home parenteral nutrition (PN) is a potential risk for developing osteoporosis. Various attempts have been made to treat bone disease both by modifying the composition of PN and by administering hormones, such as calcitonin, parathyroid hormone, and sexual hormones. Bisphosphonates are recognized as a medication useful for the treatment of several bone disorders associated with excessive reabsorption. Nevertheless, there have been no paediatric studies on bisphosphonates use for intestinal failure-associated bone disease. Our study includes 6 paediatric patients receiving extremely long-term home PN (at least 3 years) who showed radiological and clinical signs of osteoporosis. Diagnosis of bone disease was made after a median period of 127.5 PN months. Treatment consisted in 2 cycles of intravenous pamidronate, 30 mg/m once per month for 6 months consecutively. They all showed a significant improvement in bone mineral density, evaluated after 6 and 12 months of pamidronate treatment. In our sample anthropometrical variables (weight, height, and body mass index) are not related with the z-score trend. Our patients had normal levels of calcium, phosphorus, and vitamin D, and proper nutrient intake. At the last follow-up, dual-energy x-ray absorptiometry scan showed that no patients had a z-score lower than -2.5; moreover, nobody developed bone fractures during the 108-month follow-up. The patients did not have any prominent adverse effect. Finally, in our experience, pamidronate is effective for improving bone mineral density and safe in patients with intestinal failure-associated bone disease.
Keywords: Absorptiometry, Photon; Adolescent; Bone Density; Bone Density Conservation Agents; Child; Child, Preschool; Diphosphonates; Female; Humans; Intestinal Diseases; Male; Osteoporosis; Parenteral Nutrition, Home

Upper gastrointestinal involvement in paediatric onset Crohn's disease: prevalence and clinical implications. - Crocco, S; Martelossi, S; Giurici, N; Villanacci, V; Ventura, A (J Crohns Colitis, 2012)
BACKGROUND AND AIMS: Our study evaluated the prevalence, the characteristics and implications of the upper gastrointestinal localisation (UGI+) in paediatric Crohn's Disease (CD) patients. METHODS: This prospective study evaluated 45 newly diagnosed CD patients at diagnosis and follow up with respect to CD localisation. RESULTS: All patients presented CD at the colon and/or ileum. In 24/45 patients (53.3%, 12 F and 12 M) an UGI+ involvement was also found. UGI+ patients had a younger age of onset (10.9 years versus 12.6 years; P<0.05). PCDAI at diagnosis was significantly higher in the UGI+ (41 vs. 25 P<0.01). UGI+ patients were overall more symptomatic. Pancolitis and extraintestinal manifestations were also more frequent (19/24 (80%) vs. 12/21 (57%) P<0.01). Growth was more impaired at diagnosis in UGI+ patients. By the end of the follow-up (mean 3 years, range 2 to 4) no significant difference was found in PCDAI (17 in UGI+ patients vs. 11 in UGI- P=NS), or the number of relapses. Weight and growth catch-up in UGI+ patients were comparable to UGI- ones. However, UGI+ patients required a more aggressive therapeutic approach. CONCLUSION: At least half of paediatric onset CD patients have an upper gastrointestinal localisation. UGI+ patients present an earlier onset and a more severe disease. The final outcome does not differ, but UGI+ patients require a more aggressive therapeutic approach.
Keywords: Adolescent; Age of Onset; Child; Crohn Disease; Female; Humans; Male; Prospective Studies; Upper Gastrointestinal Tract

Videogame playing as distraction technique in course of venipuncture. - Minute, M; Badina, L; Cont, G; Montico, M; Ronfani, L; Barbi, E; Ventura, A (Pediatr Med Chir, 2012)
BACKGROUND: Needle-related procedures (venipuncture, intravenous cannulation) are the most common source of pain and distress for children. Reducing needle related pain and anxiety could be important in order to prevent further distress, especially for children needing multiple hospital admissions. The aim of the present open randomized controlled trial was to investigate the efficacy of adding an active distraction strategy (videogame) to EMLA premedication in needle-related pain in children. METHODS: One-hundred and nine children (4 -10 years of age) were prospectively recruited to enter in the study. Ninety-seven were randomized in two groups: CC group (conventional care: EMLA only) as control group and AD group (active distraction: EMLA plus videogame) as intervention group. Outcome measures were: self-reported pain by mean of FPS-R scale (main study outcome), observer-reported pain by FLACC scale, number of attempts for successful procedure. RESULTS: In both groups FPS-R median rate was 0 (interquartile range: 0-2), with significant pain (FPS-R > 4) reported by 9% of subjects. FLACC median rate was 1 in both groups (interquartile range 0-3 in CC group; 0-2 in AD group). The percentage of children with major pain (FLACC > 4) was 18% in CC group and 9% in AD group (p = 0.2). The median of necessary attempts to succeed in the procedures was 1 (interquartile range 1-2) in both groups.. CONCLUSION: Active distraction doesn't improve EMLA analgesia for iv cannulation and venipuncture. Even though, it resulted in an easily applicable strategy appreciated by children. This technique could be usefully investigated in other painful procedures.
Keywords: Anesthetics, Local; Child; Child, Preschool; Female; Humans; Lidocaine; Male; Pain; Phlebotomy; Prilocaine; Prospective Studies; Video Games

Young girl with apical ballooning heart syndrome. - Berton, E; Vitali-Serdoz, L; Vallon, P; Maschio, M; Gortani, G; Benettoni, A (Int J Cardiol, 2012)
Keywords: Child; Diagnosis, Differential; Electrocardiography; Female; Humans; Takotsubo Cardiomyopathy

Ages of celiac disease: from changing environment to improved diagnostics. - Tommasini, Alberto; Not, Tarcisio; Ventura, Alessandro (World J Gastroenterol, 2011)
From the time of Gee's landmark writings, the recent history of celiac disease (CD) can be divided into many ages, each driven by a diagnostic advance and a deeper knowledge of disease pathogenesis. At the same time, these advances were paralleled by the identification of new clinical patterns associated with CD and by a continuous redefinition of the prevalence of the disease in population. In the beginning, CD was considered a chronic indigestion, even if the causative food was not known; later, the disease was proven to depend on an intolerance to wheat gliadin, leading to typical mucosal changes in the gut and to a malabsorption syndrome. This knowledge led to curing the disease with a gluten-free diet. After the identification of antibodies to gluten (AGA) in the serum of patients and the identification of gluten-specific lymphocytes in the mucosa, CD was described as an immune disorder, resembling a chronic "gluten infection". The use of serological testing for AGA allowed identification of the higher prevalence of this disorder, revealing atypical patterns of presentation. More recently, the characterization of autoantibodies to endomysium and to transglutaminase shifted the attention to a complex autoimmune pathogenesis and to the increased risk of developing autoimmune disorders in untreated CD. New diagnostic assays, based on molecular technologies, will introduce new changes, with the promise of better defining the spectrum of gluten reactivity and the real burden of gluten related-disorders in the population. Herein, we describe the different periods of CD experience, and further developments for the next celiac age will be proposed.
Keywords: Autoantibodies; Celiac Disease; Diet, Gluten-Free; Gliadin; Glutens; History, 19th Century; History, 20th Century; History, 21st Century; History, Ancient; History, Medieval; Humans; Transglutaminases

Association of tumor necrosis factor-related apoptosis-inducing ligand with total and cardiovascular mortality in older adults. - Volpato, Stefano; Ferrucci, Luigi; Secchiero, Paola; Corallini, Federica; Zuliani, Giovanni; Fellin, Renato; Guralnik, Jack M; Bandinelli, Stefania; Zauli, Giorgio (Atherosclerosis, 2011)
OBJECTIVE: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) exhibits biological activity on vascular cells in vitro. Rapid variation of circulating TRAIL levels occurs during acute coronary ischemia, suggesting that biological pathways involving TRAIL may be activated during ischemic heart disease. However, whether differential levels of soluble TRAIL in normal individuals are associated with adverse health outcomes has not been investigated. We tested the hypothesis that TRAIL levels predict mortality in a population based sample of community dwelling men and women. METHODS: Plasma TRAIL level was measured by ELISA at baseline in 1282 adults (mean age 68 years) enrolled in the InCHIANTI study. Vital status was ascertained over the six-year follow-up. RESULTS: In multivariable Cox regression analysis adjusted for potential confounders including prevalent cardiovascular diseases (CVD), ankle-brachial index, electrocardiogram abnormalities, and inflammatory markers, baseline TRAIL levels were inversely related to all-cause mortality (p=0.008). In stratified analyses, the prognostic effect of TRAIL level was strong and highly significant in participants with prevalent CVD (N=321), (lowest versus highest quartile: HR 3.1; 95% CI 1.5-6.5) while it was negligible in those free of CVD (p value for the interaction term between CVD status and TRAIL levels=0.038). Similar findings were obtained when CVD mortality was considered as the outcome of interest. CONCLUSIONS: In older patients with CVD, low levels of TRAIL were associated with increased risk of death over a period of 6 years. Lower concentration of circulating TRAIL may be related to the clinical evolution of older adults with CVD.
Keywords: Adult; Aged; Ankle Brachial Index; Cardiovascular Diseases; Female; Follow-Up Studies; Humans; Italy; Male; Middle Aged; TNF-Related Apoptosis-Inducing Ligand

Celiac disease and immigration in Northeastern Italy: the "drawn double nostalgia" of "cozonac" and "panettone" slices. - Parco, Sergio; Città, Angelo; Vascotto, Fulvia; Tamaro, Giorgio (Clin Exp Gastroenterol, 2011)
Many investigators consider children's drawings to be an important test in the evaluation of stress and anxiety, but few studies have examined the reliability and validity of indicators of emotional distress in children's projective drawings. In this report, we describe screening tests in children coming to the Friuli Venezia Giulia region in Northeastern Italy from non-European Union regions and suspected to have celiac disease, the problems involved in diagnosis of the disease, and the "drawn double nostalgia" of Romanian children for both Italian food and traditional Romanian foods. Of 3150 Western European cases, we found 712 with positive antibodies for IgA/IgG antitransglutaminase, 174 with a positive antiendomysium antibody confirmation test, and 20 with an IgA deficit. Of the children examined, 93% were children native to Western Europe, 4% were immigrants from Eastern Europe, and 1.6% originated from Africa. Among these, four Romanian children with celiac disease brought in their drawings, as requested in a hospital questionnaire. The prevalence of celiac disease is destined to increase among immigrants. Economic problems are common, and the twin nostalgia of immigrant children for foods and tastes that are "cozonac" (from the native country) and "panettone" (Italian cake flavor) represents a problem that will be difficult to resolve. Only some children's hospitals in Italy, ie, Burlo Garofolo and Gaslini, public and private foundations, or volunteer associations would be able to deal with this problem.

Clinical heterogeneity and diagnostic delay of autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy syndrome. - Mazza, Cinzia; Buzi, Fabio; Ortolani, Federica; Vitali, Alberto; Notarangelo, Lucia D; Weber, Giovanna; Bacchetta, Rosa; Soresina, Annarosa; Lougaris, Vassilios; Greggio, Nella A; Taddio, Andrea; Pasic, Srdjan; et al. (Clin Immunol, 2011)
Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) is a rare autosomal recessive organ-specific autoimmune disorder that is characterized by a variable combination of (i) chronic mucocutaneous candidiasis, (ii) polyendocrinopathy and/or hepatitis and (iii) dystrophy of the dental enamel and nails. We analyzed the AIRE (autoimmune regulator) gene in subjects who presented any symptom that has been associated with APECED, including candidiasis and autoimmune endocrinopathy. We observed that 83.3% of patients presented at least two of the three typical manifestations of APECED, while the remaining 16.7% of patients showed other signs of the disease. Analysis of the genetic diagnosis of these subjects revealed that a considerable delay occurs in the majority of patients between the appearance of symptoms and the diagnosis. Overall, the mean diagnostic delay in our patients was 10.2 years. These results suggest that molecular analysis of AIRE should be performed in patients with relapsing mucocutaneous candidiasis for early identification of APECED.
Keywords: Adolescent; Adult; Child; Child, Preschool; Heterozygote; Homozygote; Humans; Middle Aged; Mutation; Polyendocrinopathies, Autoimmune; Time Factors; Young Adult

Compliance with the gluten-free diet: the role of locus of control in celiac disease. - Bellini, Anna; Zanchi, Chiara; Martelossi, Stefano; Di Leo, Grazia; Not, Tarcisio; Ventura, Alessandro (J Pediatr, 2011)
OBJECTIVES: To verify whether subjects with celiac disease (CD) have a different locus of control (LoC) compared with healthy subjects, and to evaluate the relationship between LoC and compliance with a prescribed gluten-free diet (GFD) and quality of life (QoL). STUDY DESIGN: We studied 156 subjects on a GFD (mean age, 10 years) and 353 healthy controls (mean age, 12 years). All subjects completed tests on the Nowicki-Strickland Locus of Control Scale; the subjects with CD also completed a questionnaire to measure compliance with dietary treatment and the disease's impact on QoL. RESULTS: There was no difference in LoC values between patients with CD and controls. Subjects with CD with good dietary compliance had a more internal LoC compared with those who were not compliant (P = .01). Patients who reported a satisfactory QoL had a more internal LoC compared with those who reported negative affects on QoL due to CD (P = .01). CONCLUSIONS: Our study confirms the usefulness of the LoC concept for identifying those patients who might be at risk for dietary transgression. Given the enhanced, psychological, and social well being that can result from adherence to a GFD, educational and psychological support can help internalize the LoC in those patients at risk for dietary transgression.
Keywords: Adolescent; Age Factors; Case-Control Studies; Celiac Disease; Child; Diet, Gluten-Free; Female; Humans; Internal-External Control; Italy; Male; Patient Compliance; Quality of Life

Cryptic genetic gluten intolerance revealed by intestinal antitransglutaminase antibodies and response to gluten-free diet. - Not, Tarcisio; Ziberna, Fabiana; Vatta, Serena; Quaglia, Sara; Martelossi, Stefano; Villanacci, Vincenzo; Marzari, Roberto; Florian, Fiorella; Vecchiet, Monica; Sulic, Ana-Marija; Ferrara, Fortunato; Bradbury, Andrew; et al. (Gut, 2011)
BACKGROUND AND OBJECTIVE: Antitransglutaminase (anti-TG2) antibodies are synthesised in the intestine and their presence seems predictive of future coeliac disease (CD). This study investigates whether mucosal antibodies represent an early stage of gluten intolerance even in the absence of intestinal damage and serum anti-TG2 antibodies. METHODS: This study investigated 22 relatives of patients with CD genetically predisposed to gluten intolerance but negative for both serum anti-TG2 antibodies and intestinal abnormalities. Fifteen subjects were symptomatic and seven were asymptomatic. The presence of immunoglobulin A anti-TG2 antibodies in the intestine was studied by creating phage-antibody libraries against TG-2. The presence of intestinal anti-TG2 antibodies was compared with the serum concentration of the intestinal fatty acid-binding protein (I-FABP), a marker for early intestinal mucosal damage. The effects of a 12-month gluten-free diet on anti-TG2 antibody production and the subjects' clinical condition was monitored. Twelve subjects entered the study as controls. RESULTS: The intestinal mucosa appeared normal in 18/22; 4 had a slight increase in intraepithelial lymphocytes. Mucosal anti-TG2 antibodies were isolated in 15/22 subjects (68%); in particular symptomatic subjects were positive in 13/15 cases and asymptomatic subjects in 2/7 cases (p=0.01). No mucosal antibodies were selected from the controls' biopsies. There was significant correlation between the presence of intestinal anti-TG2 antibodies and positive concentrations of I-FABP (p=0.0008). After a gluten-free diet, 19/22 subjects underwent a second intestinal biopsy, which showed that anti-TG2 antibodies had disappeared in 12/15 (p=0.002), while I-FABP decreased significantly (p<0.0001). The diet resolved both extraintestinal and intestinal symptoms. CONCLUSIONS: A new form of genetic-dependent gluten intolerance has been described in which none of the usual diagnostic markers is present. Symptoms and intestinal anti-TG2 antibodies respond to a gluten free-diet. The detection of intestinal anti-TG2 antibodies by the phage-antibody libraries has an important diagnostic and therapeutic impact for the subjects with gluten-dependent intestinal or extraintestinal symptoms. Clinical trial number NCT00677495.
Keywords: Adolescent; Adult; Antibodies, Anti-Idiotypic; Asymptomatic Diseases; Celiac Disease; Child; Child, Preschool; Diet, Gluten-Free; Fatty Acid-Binding Proteins; Female; Genetic Predisposition to Disease; GTP-Binding Proteins; Health Status; Humans; Intestinal Mucosa; Male; Middle Aged; Peptide Library; Transglutaminases; Young Adult

Daily practice of mechanical ventilation in Italian pediatric intensive care units: a prospective survey. - Wolfler, Andrea; Calderoni, Edoardo; Ottonello, Giancarlo; Conti, Giorgio; Baroncini, Simonetta; Santuz, Pierantonio; Vitale, Pasquale; Salvo, Ida (Pediatr Crit Care Med, 2011)
OBJECTIVES: To assess how children requiring endotracheal intubation are mechanically ventilated in Italian pediatric intensive care units (PICUs). DESIGN: A prospective, national, observational, multicenter, 6-month study. SETTING: Eighteen medical-surgical PICUs. PATIENTS: A total of 1943 consecutive children, aged 0-16 yrs, admitted between November 1, 2006 and April 30, 2007. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Data on cause of respiratory failure, length of mechanical ventilation (MV), mode of ventilation, use of specific interventions were recorded for all children requiring endotracheal intubation for >24 hrs. Children were stratified for age, type of patient, and cause of respiratory failure. A total of 956 (49.2%) patients required MV via an endotracheal tube; 673 (34.6%) were ventilated for >24 hrs. The median length of MV was 4.5 days for all patients. If postoperative patients were excluded, the median time was 5 days. Bronchiolitis (6.7%), pneumonia (6.7%), and upper airway obstruction (5.3%) were the most frequent causes of acute respiratory failure, and altered mental status (9.2%) was the most frequent reason for MV. The overall mortality was 6.7% with highest rates for heart disease (nonoperative), sepsis, and acute respiratory distress syndrome (26.1%, 22.2%, and 16.7% respectively). Length of stay, associated chronic disease, severity score on admission, and PICU mortality were significantly higher in children who received MV (p < .05) than in children who did not. Controlled MV and pressure support ventilation + synchronized intermittent mandatory ventilation were the most frequently used modes of ventilatory assistance during PICU stay. CONCLUSIONS: Mechanical ventilation is frequently used in Italian PICUs with almost one child of two requiring endotracheal intubation. Children treated with MV represent a more severe category of patients than children who are breathing spontaneously. Describing the standard care and how MV is performed in children can be useful for future clinical studies.
Keywords: Adolescent; Child; Child, Preschool; Clinical Protocols; Female; Humans; Infant; Infant, Newborn; Intensive Care Units, Pediatric; Intubation, Intratracheal; Italy; Male; Prospective Studies; Respiration, Artificial; Respiratory Insufficiency

Dasatinib plus Nutlin-3 shows synergistic antileukemic activity in both p53 wild-type and p53 mutated B chronic lymphocytic leukemias by inhibiting the Akt pathway. - Zauli, Giorgio; Voltan, Rebecca; Bosco, Raffaella; Melloni, Elisabetta; Marmiroli, Sandra; Rigolin, Gian Matteo; Cuneo, Antonio; Secchiero, Paola (Clin Cancer Res, 2011)
PURPOSE: To analyze the effect of the combination of Dasatinib, a multikinase inhibitor, plus Nutlin-3, a nongenotoxic activator of the p53 pathway, in primary B chronic lymphocytic leukemia (B-CLL) patient samples and B leukemic cell line models. EXPERIMENTAL DESIGN: The induction of cytotoxicity was evaluated in both primary B-CLL cell samples (n = 20) and in p53(wild-type) (EHEB, JVM-2) and p53(deleted/mutated) (MEC-2, BJAB) B leukemic cell lines. The role of Akt in modulating leukemic cell survival/apoptosis in response to Dasatinib or Dasatinib + Nutlin-3 was documented by functional experiments carried out using specific pharmacological inhibitors and by overexpression of membrane-targeted constitutively active form of Akt. RESULTS: The combination of Dasatinib + Nutlin-3 exhibited a synergistic cytotoxicity in the majority (19 out of 20) of B-CLL samples, including patients carrying 17p- (n = 4), and in both p53(wild-type) and p53(deleted/mutated) B leukemic cell lines. At the molecular level, Dasatinib significantly counteracted the Nutlin-3-mediated induction of the p53 transcriptional targets MDM2 and p21 observed in p53(wild-type) leukemic cells. Conversely, Nutlin-3 did not interfere with the ability of Dasatinib to decrease the phosphorylation levels of ERK1/2, p38/MAPK, and Akt in both p53(wild-type) and p53(deleted/mutated) B leukemic cell lines. A critical role of Akt downregulation in mediating the antileukemic activity of Dasatinib and Dasatinib + Nutlin-3 was demonstrated in experiments carried out by specifically modulating the Akt pathway. CONCLUSIONS: These findings suggest that Dasatinib + Nutlin-3 might represent an innovative therapeutic combination for both p53(wild-type) and p53(deleted/mutated) B-CLL.
Keywords: Antineoplastic Agents; Apoptosis; Cell Line, Tumor; Cell Survival; Down-Regulation; Drug Synergism; Humans; Imidazoles; Leukemia, Lymphocytic, Chronic, B-Cell; Mutation; Piperazines; Protein Kinase Inhibitors; Protein Kinases; Proto-Oncogene Proteins c-akt; Pyrimidines; Thiazoles; Transcription, Genetic; Tumor Suppressor Protein p53

Differential action of 3-hydroxyanthranilic acid on viability and activation of stimulated lymphocytes. - Piscianz, Elisa; Cuzzoni, Eva; De Iudicibus, Sara; Valencic, Erica; Decorti, Giuliana; Tommasini, Alberto (Int Immunopharmacol, 2011)
Lymphocytes proliferation after antigen-driven activation leads to an increase in cell count, which could last some week, until apoptosis mechanisms allow the homeostatic control of the system. During the first days of this stimulation, activated lymphocytes display high resistance to apoptosis and to most immunosuppressive drugs. According to the literature, few compounds have been described to kill recently activated cells, by inhibiting metabolic processes fundamental to proliferation. The aim of our work was to evaluate comparatively these different compounds, in order to identify the best strategy to kill cells that have undergone proliferation, while sparing the repertoire of resting cells. After preliminary experiments, 3-HAA and bortezomib were selected as the most suitable compounds for our purposes. The possible synergic effect of 3-HAA with bortezomib or with manganese ions was also assessed. 3-HAA was confirmed to be the most reliable pharmacologic approach to inhibit proliferation with acceptable toxicity on resting cells. While in the case of PHA stimulation 3-HAA led to death of most lymphocytes, only a minor percentage of cells were killed after allo-stimulation, suggesting that the effect is proportional to the percentage of stimulated lymphocytes. Manganese ions further enhanced this effect, while results with bortezomib seemed to be less consistent. These results deserve further investigations to develop new procedures for targeting activated cells with pharmacological approaches.
Keywords: 3-Hydroxyanthranilic Acid; Boronic Acids; Cell Survival; Cells, Cultured; Humans; Lymphocyte Activation; Lymphocytes; Manganese; Pyrazines

ESPGHAN's 2008 recommendation for early introduction of complementary foods: how good is the evidence? - Cattaneo, Adriano; Williams, Carol; Pallás-Alonso, Carmen Rosa; Hernández-Aguilar, Maria Teresa; Lasarte-Velillas, Juan José; Landa-Rivera, Leonardo; Rouw, Elien; Pina, Mónica; Volta, Alessandro; Oudesluys-Murphy, Anne Marie (Matern Child Nutr, 2011)
Since 2002, the World Health Organization and many governments and professional associations have recommended exclusive breastfeeding for 6 months followed by complementary feeding (giving solid foods alongside breast milk) as optimal infant feeding practice. Several articles have been published challenging this recommendation. Arguably, the most influential has been the 2008 commentary of the European Society for Pediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) Committee on Nutrition, which recommended that complementary foods should be introduced to all infants between 17 and 26 weeks. We challenge the validity of ESPGHAN's position, questioning the adequacy of the literature search, the interpretation and evidence used to reach their conclusions and the balance of an approach that focuses on disease prevention, with scant consideration of growth and neuromotor development. We contend that ESPGHAN's position should be understood as an expert opinion that may be influenced by conflicts of interest. In our view, the ESPGHAN position paper is not evidence based and does not justify a change of the current public health recommendation for 6 months of exclusive breastfeeding. At an individual level, health professionals should understand that developmental readiness for starting solid foods has an age range like other developmental milestones; that fewer infants will probably be ready to start complementary feeding before, rather than after, 6 months; and that their role is to equip parents with the confidence and skills to recognise the signs of developmental readiness. This empowerment process for infants and parents should be preferred over the prescriptive ESPGHAN approach.
Keywords: Breast Feeding; Evidence-Based Practice; Humans; Infant; Infant Food; Infant Nutritional Physiological Phenomena; Milk, Human; Nutritional Status; Public Health; Reproducibility of Results; World Health Organization

Fine tuning of protein kinase C (PKC) isoforms in cancer: shortening the distance from the laboratory to the bedside. - Bosco, R; Melloni, E; Celeghini, C; Rimondi, E; Vaccarezza, M; Zauli, G (Mini Rev Med Chem, 2011)
The serine/threonine protein kinase C (PKC) family was first identified as intracellular receptor(s) for the tumor promoting agents phorbol esters. Thirty years after the discovery of PKC, the role of specific PKC isoforms has been described in relationship with an altered pattern of expression in different types of cancer and a good number of small molecule inhibitors (inhibitory peptides, antisense oligonucleotides or natural compounds) targeting PKC are now available. Despite all these achievements and a huge amount of basic research studies on the biochemical regulation of PKC, there has been a delay in clinical trials with drugs targeting PKC function. This delay is easily explained taking into account the extreme biological complexity of the PKC family of isoforms and the incomplete understanding of the specific role of each PKC isozyme in different types of cancers. Some of the difficulties in developing pharmacological compounds selectively tuning the different PKCs have started to be overcome. In this review, the growing evidences of the role of the PKC isoforms α, βII, δ, ε, ζ and ι is in promoting or counteracting tumor progression will be discussed in relationship with promising therapeutic perspectives.
Keywords: Antineoplastic Agents; Biological Products; Enzyme Inhibitors; Humans; Isoenzymes; Neoplasms; Oligonucleotides, Antisense; Peptides; Protein Kinase C

Foreign children with cancer in Italy. - Rondelli, Roberto; Dini, Giorgio; De Rosa, Marisa; Quarello, Paola; Bisogno, Gianni; Aricò, Maurizio; Vasconcelos, Carivaldo; Tamaro, Paolo; Casazza, Gabriella; Zecca, Marco; De Laurentis, Clementina; Porta, Fulvio; et al. (Ital J Pediatr, 2011)
BACKGROUND: There has been a noticeable annual increase in the number of children coming to Italy for medical treatment, just like it has happened in the rest of the European Union. In Italy, the assistance to children suffering from cancer is assured by the current network of 54 centres members of the Italian Association of Paediatric Haematology and Oncology (AIEOP), which has kept records of all demographic and clinical data in the database of Mod.1.01 Registry since 1989. METHODS: We used the information stored in the already mentioned database to assess the impact of immigration of foreign children with cancer on centres' activity, with the scope of drawing a map of the assistance to these cases. RESULTS: Out of 14,738 cases recorded by all centres in the period from 1999 to 2008, 92.2% were born and resident in Italy, 4.1% (608) were born abroad and living abroad and 3.7% (538) were born abroad and living in Italy. Foreign children cases have increased over the years from 2.5% in 1999 to. 8.1% in 2008.Most immigrant children came from Europe (65.7%), whereas patients who came from America, Asia and Oceania amounted to 13.2%, 10.1%, 0.2%, respectively. The immigrant survival rate was lower compared to that of children who were born in Italy. This is especially true for acute lymphoblastic leukaemia patients entered an AIEOP protocol, who showed a 10-years survival rate of 71.0% vs. 80.7% (p < 0.001) for immigrants and patients born in Italy, respectively. CONCLUSIONS: Children and adolescents are an increasingly important part of the immigration phenomenon, which occurs in many parts of the world. In Italy the vast majority of children affected by malignancies are treated in AIEOP centres. Since immigrant children are predominantly treated in northern Italy, these centres have developed a special expertise in treating immigrant patients, which is certainly very useful for the entire AIEOP network.
Keywords: Adolescent; Africa; Asia; Child; Child, Preschool; Databases, Factual; Emigrants and Immigrants; Ethnic Groups; Europe, Eastern; European Union; Female; Humans; Incidence; Infant; Infant, Newborn; Italy; Male; Neoplasms; North America; Oceania; Prevalence; Retrospective Studies; South America; Survival Rate

Forkhead box protein 3 (FOXP3) mutations lead to increased TH17 cell numbers and regulatory T-cell instability. - Passerini, Laura; Olek, Sven; Di Nunzio, Sara; Barzaghi, Federica; Hambleton, Sophie; Abinun, Mario; Tommasini, Alberto; Vignola, Silvia; Cipolli, Marco; Amendola, Mario; Naldini, Luigi; Guidi, Luisa; et al. (J Allergy Clin Immunol, 2011)
Keywords: Forkhead Transcription Factors; Gene Expression Regulation; Genetic Diseases, X-Linked; Humans; Immunologic Deficiency Syndromes; Intestinal Diseases; Male; Mutation; Polyendocrinopathies, Autoimmune

Functional type 1 regulatory T cells develop regardless of FOXP3 mutations in patients with IPEX syndrome. - Passerini, Laura; Di Nunzio, Sara; Gregori, Silvia; Gambineri, Eleonora; Cecconi, Massimiliano; Seidel, Markus G; Cazzola, Giantonio; Perroni, Lucia; Tommasini, Alberto; Vignola, Silvia; Guidi, Luisa; Roncarolo, Maria G; et al. (Eur J Immunol, 2011)
Mutations of forkhead box p3 (FOXP3), the master gene for naturally occurring regulatory T cells (nTregs), are responsible for the impaired function of nTregs, resulting in an autoimmune disease known as the immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome. The relevance of other peripheral tolerance mechanisms, such as the presence and function of type 1 regulatory T (Tr1) cells, the major adaptive IL-10-producing Treg subset, in patients with IPEX syndrome remains to be clarified. FOXP3(mutated) Tr1-polarized cells, differentiated in vitro from CD4(+) T cells of four IPEX patients, were enriched in IL-10(+) IL-4(-) IFN-γ(+) T cells, a cytokine production profile specific for Tr1 cells, and expressed low levels of FOXP3 and high levels of Granzyme-B. IPEX Tr1 cells were hypoproliferative and suppressive, thus indicating that FOXP3 mutations did not impair their function. Furthermore, we isolated Tr1 cell clones from the peripheral blood of one FOXP3(null) patient, demonstrating that Tr1 cells are present in vivo and they can be expanded in vitro in the absence of WT FOXP3. Overall, our results (i) show that functional Tr1 cells differentiate independently of FOXP3, (ii) confirm that human Tr1 and nTregs are distinct T-cell lineages, and (iii) suggest that under favorable conditions Tr1 cells could exert regulatory functions in IPEX patients.
Keywords: Cell Differentiation; Cell Lineage; Cells, Cultured; Enteritis; Forkhead Transcription Factors; Genetic Diseases, X-Linked; Humans; Immunity, Innate; Interleukin-2 Receptor alpha Subunit; Mutation; Polyendocrinopathies, Autoimmune; Syndrome; T-Lymphocytes, Regulatory

Gastroesophageal reflux disease at any cost: a dangerous paediatric attitude. - Taddio, Andrea; Bersanini, Chiara; Basile, Lucio; Fontana, Massimo; Ventura, Alessandro (Acta Paediatr, 2011)
Keywords: Diagnostic Errors; Gastroesophageal Reflux; Humans; Inappropriate Prescribing; Infant; Infant, Newborn; Male; Proton Pump Inhibitors; Spasms, Infantile

Gastrointestinal Foxp3 expression in normal, inflammatory and neoplastic conditions. - Villanacci, Vincenzo; Not, Tarcisio; Nascimbeni, Riccardo; Ferrara, Fortunato; Tommasini, Alberto; Manenti, Stefania; Antonelli, Elisabetta; Bassotti, Gabrio (Pathology, 2011)
BACKGROUND: Foxp3(+) regulatory T lymphocytes (T-regs) represent an important regulatory cell subset in inflammatory, preneoplastic and neoplastic conditions of the gastrointestinal tract. METHODS: Inflammatory, preneoplastic and neoplastic conditions of the gastrointestinal tract (189 cases) were studied with the evaluation of Foxp3 regulatory T cells based on immunohistochemistry. RESULTS: Few Foxp3(+) cells were found in controls and inflammatory conditions (oesophagitis, gastritis, coeliac disease, inflammatory bowel disease); in preneoplastic and neoplastic conditions the number of Foxp3(+) cells was significatively increased. CONCLUSIONS: In normal conditions the number of mucosal lymphocytes is very low throughout the gastro-intestinal tract; in active coeliac disease patients or on a gluten-free diet, only a slight increase in Foxp3(+) cells may be found. Gastrointestinal cancers are associated with higher Foxp3(+) cell proportion, compared with microscopically normal tissue and with precancerous conditions. However, it is uncertain whether the increase in these regulatory cells is a cause or a consequence of tumour progression.
Keywords: Adult; Aged; Celiac Disease; Cell Count; Disease Progression; Esophagitis; Female; Forkhead Transcription Factors; Gastric Mucosa; Gastritis; Humans; Inflammatory Bowel Diseases; Lymphocytes; Male; Middle Aged; Precancerous Conditions; Stomach Diseases; Stomach Neoplasms; Young Adult

Genetic predictors of glucocorticoid response in pediatric patients with inflammatory bowel diseases. - De Iudicibus, Sara; Stocco, Gabriele; Martelossi, Stefano; Londero, Margherita; Ebner, Egle; Pontillo, Alessandra; Lionetti, Paolo; Barabino, Arrigo; Bartoli, Fiora; Ventura, Alessandro; Decorti, Giuliana (J Clin Gastroenterol, 2011)
BACKGROUND: Glucocorticoids (GCs) are used in moderate-to-severe inflammatory bowel diseases (IBD) but their effect is often unpredictable. AIM: To determine the influence of 4 polymorphisms in the GC receptor [nuclear receptor subfamily 3, group C, member 1 (NR3C1)], interleukin-1β (IL-1β), and NACHT leucine-rich-repeat protein 1 (NALP1) genes, on the clinical response to steroids in pediatric patients with IBD. METHODS: One hundred fifty-four young IBD patients treated with GCs for at least 30 days and with a minimum follow-up of 1 year were genotyped. The polymorphisms considered are the BclI in the NR3C1 gene, C-511T in IL-1β gene, and Leu155His and rs2670660/C in NALP1 gene. Patients were grouped as responder, dependant, and resistant to GCs. The relation between GC response and the genetic polymorphisms considered was examined using univariate, multivariate, and Classification and Regression Tree (CART) analysis. RESULTS: Univariate analysis showed that BclI polymorphism was more frequent in responders compared with dependant patients (P=0.03) and with the combined dependant and resistant groups (P=0.02). Moreover, the NALP1 Leu155His polymorphism was less frequent in the GC responsive group compared with resistant (P=0.0059) and nonresponder (P=0.02) groups. Multivariate analysis comparing responders and nonresponders confirmed an association between BclI mutated genotype and steroid response (P=0.030), and between NALP1 Leu155His mutant variant and nonresponders (P=0.033). An association between steroid response and male sex was also observed (P=0.034). In addition, Leu155His mutated genotype was associated with steroid resistance (P=0.034). Two CART analyses supported these findings by showing that BclI and Leu155His polymorphisms had the greatest effect on steroid response (permutation P value=0.046). The second CART analysis also identified age of disease onset and male sex as important variables affecting response. CONCLUSIONS: These results confirm that genetic and demographic factors may affect the response to GCs in young patients with IBD and strengthen the importance of studying high-order interactions for predicting response.
Keywords: Adolescent; Child; Drug Resistance; Female; Follow-Up Studies; Genotype; Glucocorticoids; Humans; Inflammatory Bowel Diseases; Male; Multivariate Analysis; Polymorphism, Genetic; Receptors, Glucocorticoid; Regression Analysis; Retrospective Studies; Sex Factors; Treatment Outcome

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

Glutamine-enriched nutrition does not reduce mucosal morbidity or complications after stem-cell transplantation for childhood malignancies: a prospective randomized study. - Uderzo, Cornelio; Rebora, Paola; Marrocco, Emanuela; Varotto, Stefania; Cichello, Francesca; Bonetti, Maurizio; Maximova, Natalia; Zanon, Davide; Fagioli, Franca; Nesi, Francesca; Masetti, Riccardo; Masetti, Roberto; et al. (Transplantation, 2011)
BACKGROUND: Intravenous glutamine-enriched solution seems to be effective in posttransplant period in decreasing the severity and duration of mucositis. The aim of this randomized study was to determine the benefit of glutamine supplementation both on mucosal morbidity and in posttransplant associated complications. METHODS: Children undergoing allogeneic hematopoietic stem-cell transplantation (HSCT) for malignant hematological diseases were randomly assigned to standard total parenteral nutrition (S-TPN) or glutamine-enriched (GE)-TPN solution consisting of 0.4 g/kg/day of l-alanine-glutamine dipeptide. This treatment started on the day of HSCT and ended when the patients could orally cover more than 50% of their daily energy requirements. The severity and the rate of post-HSCT mucositis were based on World Health Organization criteria. All the analyses were conducted on intention-to-treat principle. RESULTS: One hundred twenty consecutive patients (83 men; median age, 8.1 years) were enrolled. The mean duration of treatment was 23.5 and 23 days in the two treatment arms. The mean calorie intake was 1538 kcal/d in the S-TPN group and 1512 kcal/d in GE-TPN group. All patients were well nourished before and after HSCT. Mucositis occurred in 91.4% and 91.7% of patients in S-TPN and GE-TPN arm, respectively (P=0.98). Odds ratio adjusted by type of HSCT was 0.98 (95% confidence interval, 0.26-2.63). Type and duration of analgesic treatment, clinical outcome (engraftment, graft versus host disease, early morbidity, and mortality, relapse rate up to 180 days post-HSCT) were not significantly different in the two treatment arms. CONCLUSION: GE-TPN solution does not affect mucositis and outcome in well-nourished HSCT allogeneic patients.
Keywords: Adolescent; Analgesia; Child; Child, Preschool; Double-Blind Method; Female; Glutamine; Hematopoietic Stem Cell Transplantation; Humans; Infant; Male; Mucositis; Mucous Membrane; Neoplasms; Odds Ratio; Parenteral Nutrition; Prospective Studies; Recurrence; Stem Cells; Treatment Outcome

High incidence of NLRP3 somatic mosaicism in patients with chronic infantile neurologic, cutaneous, articular syndrome: results of an International Multicenter Collaborative Study. - Tanaka, Naoko; Izawa, Kazushi; Saito, Megumu K; Sakuma, Mio; Oshima, Koichi; Ohara, Osamu; Nishikomori, Ryuta; Morimoto, Takeshi; Kambe, Naotomo; Goldbach-Mansky, Raphaela; Aksentijevich, Ivona; de Saint Basile, Geneviève; et al. (Arthritis Rheum, 2011)
OBJECTIVE: Chronic infantile neurologic, cutaneous, articular (CINCA) syndrome, also known as neonatal-onset multisystem inflammatory disease (NOMID), is a dominantly inherited systemic autoinflammatory disease. Although heterozygous germline gain-of-function NLRP3 mutations are a known cause of this disease, conventional genetic analyses fail to detect disease-causing mutations in ∼40% of patients. Since somatic NLRP3 mosaicism has been detected in several mutation-negative NOMID/CINCA syndrome patients, we undertook this study to determine the precise contribution of somatic NLRP3 mosaicism to the etiology of NOMID/CINCA syndrome. METHODS: An international case-control study was performed to detect somatic NLRP3 mosaicism in NOMID/CINCA syndrome patients who had shown no mutation during conventional sequencing. Subcloning and sequencing of NLRP3 was performed in these mutation-negative NOMID/CINCA syndrome patients and their healthy relatives. Clinical features were analyzed to identify potential genotype-phenotype associations. RESULTS: Somatic NLRP3 mosaicism was identified in 18 of the 26 patients (69.2%). Estimates of the level of mosaicism ranged from 4.2% to 35.8% (mean ± SD 12.1 ± 7.9%). Mosaicism was not detected in any of the 19 healthy relatives (18 of 26 patients versus 0 of 19 relatives; P < 0.0001). In vitro functional assays indicated that the detected somatic NLRP3 mutations had disease-causing functional effects. No differences in NLRP3 mosaicism were detected between different cell lineages. Among nondescript clinical features, a lower incidence of mental retardation was noted in patients with somatic mosaicism. Genotype-matched comparison confirmed that patients with somatic NLRP3 mosaicism presented with milder neurologic symptoms. CONCLUSION: Somatic NLRP3 mutations were identified in 69.2% of patients with mutation-negative NOMID/CINCA syndrome. This indicates that somatic NLRP3 mosaicism is a major cause of NOMID/CINCA syndrome.
Keywords: Adolescent; Adult; Carrier Proteins; Case-Control Studies; Child; Child, Preschool; Cryopyrin-Associated Periodic Syndromes; Female; Genetic Association Studies; Humans; Infant; Male; Mosaicism

HLA-G 14 bp deletion/insertion polymorphism in celiac disease. - Fabris, Annalisa; Segat, Ludovica; Catamo, Eulalia; Morgutti, Marcello; Vendramin, Anna; Crovella, Sergio (Am J Gastroenterol, 2011)
OBJECTIVES: Nonclassical major histocompatibility class I HLA-G antigen is a tolerogenic molecule that inhibits lytic activity of natural killer (NK) cells and cytotoxic T lymphocytes. Because of its immunomodulatory and tolerogenic properties, HLA-G molecules may have a role in celiac disease (CD). We analyzed the HLA-G 14 bp deletion/insertion polymorphism, known to have a functional effect on mRNA stability, in a group of 522 CD patients, stratified for the presence of HLA-DQ2 genotype, and 400 healthy individuals to evaluate the possible effect of the polymorphism on the risk to develop the disease. METHODS: HLA-G 14 bp deletion/insertion polymorphism (rs1704) was detected by polymerase chain reaction and double-checked by direct sequencing. RESULTS: The 14 bp inserted (I) allele and the homozygous I/I genotype were significantly more frequent in CD patients than in healthy controls. The presence of I allele was associated with an increased risk of CD (OR 1.35) and the effect of I allele was consistent with a recessive genetic model (P<0.001). CONCLUSIONS: Our results also indicate that the effect of the HLA-G D/I polymorphism is restricted for HLA-DQ2, and not simply due to the presence of linkage disequilibrium with the major known risk factor; moreover we found that the presence of the I allele confers an increased risk of CD in addition to the risk conferred by HLA-DQ2 alone and that subjects that carry both DQ2 and HLA-G I alleles have an increased risk of CD than subjects that carry DQ2 but not the I allele.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alleles; Case-Control Studies; Celiac Disease; Child; Child, Preschool; Confidence Intervals; Female; Genetic Predisposition to Disease; Genotype; Histocompatibility Antigens Class I; HLA Antigens; HLA-DQ Antigens; HLA-G Antigens; Humans; Male; Middle Aged; Mutagenesis, Insertional; Odds Ratio; Polymerase Chain Reaction; Polymorphism, Genetic; Reference Values; RNA Stability; Sequence Deletion; Young Adult

Interventions for the prevention of overweight and obesity in preschool children: a systematic review of randomized controlled trials. - Monasta, L; Batty, G D; Macaluso, A; Ronfani, L; Lutje, V; Bavcar, A; van Lenthe, F J; Brug, J; Cattaneo, A (Obes Rev, 2011)
The objective of this study was to analyse interventions for the prevention of overweight and obesity in children under 5 years of age. We carried out a systematic review focusing exclusively on randomized controlled trials (RCTs). Data sources include Medline, Cochrane Library, EMBASE, CINHAL, PsychInfo and Web of Science. Data were extracted from seventeen articles describing seven RCTs identified through electronic search, screening of references in systematic reviews, own files and contact with authors. RCTs were assessed with the Jadad scale. Four trials were carried out in preschool settings, one with an exclusive educational component, two with an exclusive physical activity component and one with both. Two trials were family-based, with education and counselling for parents and children. The remaining trial was carried out in maternity hospitals, with a training intervention on breastfeeding. None of the interventions had an effect in preventing overweight and obesity. The failure to show an effect may be due to the choice of outcomes, the quality of the RCTs, the suboptimal implementation of the interventions, the lack of focus on social and environmental determinants. More rigorous research is needed on interventions and on social and environmental factors that could impact on lifestyle.
Keywords: Child Nutrition Sciences; Child Nutritional Physiological Phenomena; Child, Preschool; Exercise; Female; Health Promotion; Humans; Life Style; Male; Obesity; Overweight; Randomized Controlled Trials as Topic

Letter to the editor: acute effects of intravenous administration of pamidronate in patients with osteoporosis. - Marcuzzi, Annalisa; Zanin, Valentina; Vuch, Josef; Pontillo, Alessandra; Crovella, Sergio (J Korean Med Sci, 2011)
Keywords: Anti-Inflammatory Agents; Cytokines; Diphosphonates; Humans; Injections, Intravenous; Osteoporosis

Marriage and parenthood among childhood cancer survivors: a report from the Italian AIEOP Off-Therapy Registry. - Pivetta, Emanuele; Maule, Milena M; Pisani, Paola; Zugna, Daniela; Haupt, Riccardo; Jankovic, Momcilo; Aricò, Maurizio; Casale, Fiorina; Clerico, Anna; Cordero di Montezemolo, Luca; Kiren, Valentina; Locatelli, Franco; et al. (Haematologica, 2011)
BACKGROUND: The aim of this study was to describe the patterns of marriage and parenthood in a cohort of childhood cancer survivors included in the Off-Therapy Registry maintained by the Italian Association of Pediatric Hematology and Oncology. DESIGN AND METHODS: We analyzed a cohort of 6,044 patients diagnosed with cancer between 1960 and 1998, while aged 0 to 14 years and who were 18 years old or older by December 2003. They were followed up through the regional vital statistics registers until death or the end of follow up (October 30, 2006), whichever occurred first, and their marital status and date of birth of their children were recorded. The cumulative probabilities of being married and having a first child were computed by gender and compared by tumor type within the cohort. Marriage and fertility rates (the latter defined as the number of live births per woman-year) were compared with those of the Italian population of the same age, gender, area of residence and calendar period by means of the observed to expected (O/E) ratios. RESULTS: During the follow-up period, 4,633 (77%) subjects had not married. The marriage O/E ratios were 0.56 (95% CI: 0.51-0.61) and 0.70 (95% CI: 0.65-0.76) among men and women, respectively. Overall, 263 men had 367 liveborn children, and 473 women had 697 liveborn children. The female fertility O/E ratio was 0.57 (95% CI: 0.53-0.62) overall, and 1.08 (95% CI: 0.99-1.17) when analyses were restricted to married/cohabiting women CONCLUSIONS: Childhood cancer survivors are less likely to marry and to have children than the general population, confirming the life-long impact of their previous disease on their social behavior and choices. The inclusion of counseling in the strategies of management and long-term surveillance of childhood cancer patients could be beneficial to survivors as they approach adulthood.
Keywords: Adult; Child; Child, Preschool; Cohort Studies; Female; Follow-Up Studies; Hematologic Neoplasms; Humans; Infant; Infant, Newborn; Italy; Male; Marriage; Middle Aged; Parents; Registries; Survivors

miR-34a induces the downregulation of both E2F1 and B-Myb oncogenes in leukemic cells. - Zauli, Giorgio; Voltan, Rebecca; di Iasio, Maria Grazia; Bosco, Raffaella; Melloni, Elisabetta; Sana, Maria Elena; Secchiero, Paola (Clin Cancer Res, 2011)
PURPOSE: To elucidate new molecular mechanisms able to downregulate the mRNA levels of key oncogenes, such as B-Myb and E2F1, in a therapeutic perspective. EXPERIMENTAL DESIGN: B-Myb and E2F1 mRNA levels were evaluated in primary B chronic lymphocytic leukemia (B-CLL, n = 10) and acute myeloid leukemia (AML, n = 5) patient cells, in a variety of p53(wild-type) and p53(mutated/deleted) leukemic cell lines, as well as in primary endothelial cells and fibroblasts. Knockdown experiments with siRNA for p53 and E2F1 and overexpression experiments with miR34a were conducted to elucidate the role of these pathways in promoting B-Myb downregulation. RESULTS: In vitro exposure to Nutlin-3, a nongenotoxic activator of p53, variably downregulated the expression of B-Myb in primary leukemic cells and in p53(wild-type) myeloid (OCI, MOLM) and lymphoblastoid (SKW6.4, EHEB) but not in p53(mutated) (NB4, BJAB, MAVER) or p53(deleted) (HL-60) leukemic cell lines. The transcriptional repression of B-Myb was also observed in primary normal endothelial cells and fibroblasts. B-Myb downregulation played a critical role in the cell-cycle block in G(1) phase induced by Nutlin-3, as shown by transfection experiments with specific siRNA. Moreover, we have provided experimental evidence suggesting that miR-34a is a central mediator in the repression of B-Myb both directly and through E2F1. CONCLUSIONS: Owing to the role of B-Myb and E2F1 transcription factors in controlling cell-cycle progression of leukemic cells, the downregulation of these oncogenes by miR-34a suggests the usefulness of therapeutic approaches aimed to modulate the levels of miR-34a.
Keywords: Base Sequence; Cell Cycle Proteins; Cell Line, Tumor; Cells, Cultured; Down-Regulation; E2F1 Transcription Factor; Gene Expression Regulation, Leukemic; HCT116 Cells; HL-60 Cells; Humans; Imidazoles; Leukemia; MicroRNAs; Models, Biological; Oncogenes; Piperazines; Sequence Homology, Nucleic Acid; Trans-Activators; Transfection

The missense variation Q705K in CIAS1/NALP3/NLRP3 gene and an NLRP1 haplotype are associated with celiac disease. - Pontillo, Alessandra; Vendramin, Anna; Catamo, Eulalia; Fabris, Annalisa; Crovella, Sergio (Am J Gastroenterol, 2011)
OBJECTIVES: Celiac disease (CD) is a multifactorial common disorder with several susceptibility loci. Variations in the NALP1/NLRP1 and NALP3/NLRP3 genes have been reported to confer risk for several autoimmune conditions. We hypothesized that polymorphisms in these genes, due to their role in innate immunity and inflammatory processes, may affect susceptibility to CD. METHODS: Two single-nucleotide polymorphisms (SNPs) in NLRP1 (rs12150220, rs2670660) and two SNPs (rs10754558, rs35829419) in NLRP3 genes were genotyped in 504 CD Italian patients and 256 healthy controls. RESULTS: The minor A allele of NLRP3 rs35829419 (Q705K) polymorphism appeared to exert a protective role against the development of CD (P=0.029; odds ratio (OR)=0.56). Moreover, a particular NLRP1 haplotype was associated with predisposition to CD (P=0.003; OR=1.38), even more when present in combination with the rs35829419 major C allele (P=0.002; OR=1.42). CONCLUSIONS: We hypothesized that the deregulation of CIAS1/NALP3/NLRP3 and NALP1/NLRP1 inflammasomes could have a role in CD pathogenesis.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Apoptosis Regulatory Proteins; Carrier Proteins; Celiac Disease; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Genotype; Glutamine; Haplotypes; Humans; Inflammasomes; Italy; Lysine; Male; Mutation, Missense; Polymorphism, Single Nucleotide

Molecular mechanism of glucocorticoid resistance in inflammatory bowel disease. - De Iudicibus, Sara; Franca, Raffaella; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana (World J Gastroenterol, 2011)
Natural and synthetic glucocorticoids (GCs) are widely employed in a number of inflammatory, autoimmune and neoplastic diseases, and, despite the introduction of novel therapies, remain the first-line treatment for inducing remission in moderate to severe active Crohn's disease and ulcerative colitis. Despite their extensive therapeutic use and the proven effectiveness, considerable clinical evidence of wide inter-individual differences in GC efficacy among patients has been reported, in particular when these agents are used in inflammatory diseases. In recent years, a detailed knowledge of the GC mechanism of action and of the genetic variants affecting GC activity at the molecular level has arisen from several studies. GCs interact with their cytoplasmic receptor, and are able to repress inflammatory gene expression through several distinct mechanisms. The glucocorticoid receptor (GR) is therefore crucial for the effects of these agents: mutations in the GR gene (NR3C1, nuclear receptor subfamily 3, group C, member 1) are the primary cause of a rare, inherited form of GC resistance; in addition, several polymorphisms of this gene have been described and associated with GC response and toxicity. However, the GR is not self-standing in the cell and the receptor-mediated functions are the result of a complex interplay of GR and many other cellular partners. The latter comprise several chaperonins of the large cooperative hetero-oligomeric complex that binds the hormone-free GR in the cytosol, and several factors involved in the transcriptional machinery and chromatin remodeling, that are critical for the hormonal control of target genes transcription in the nucleus. Furthermore, variants in the principal effectors of GCs (e.g. cytokines and their regulators) have also to be taken into account for a comprehensive evaluation of the variability in GC response. Polymorphisms in genes involved in the transport and/or metabolism of these hormones have also been suggested as other possible candidates of interest that could play a role in the observed inter-individual differences in efficacy and toxicity. The best-characterized example is the drug efflux pump P-glycoprotein, a membrane transporter that extrudes GCs from cells, thereby lowering their intracellular concentration. This protein is encoded by the ABCB1/MDR1 gene; this gene presents different known polymorphic sites that can influence its expression and function. This editorial reviews the current knowledge on this topic and underlines the role of genetics in predicting GC clinical response. The ambitious goal of pharmacogenomic studies is to adapt therapies to a patient's specific genetic background, thus improving on efficacy and safety rates.
Keywords: Drug Resistance; Glucocorticoids; Humans; Inflammatory Bowel Diseases; P-Glycoproteins; Polymorphism, Genetic; Receptors, Glucocorticoid; Signal Transduction; Transcription, Genetic

A multicenter, randomized, placebo-controlled trial of levetiracetam in children and adolescents with newly diagnosed absence epilepsy. - Fattore, Cinzia; Boniver, Clementina; Capovilla, Giuseppe; Cerminara, Caterina; Citterio, Antonietta; Coppola, Giangennaro; Costa, Paola; Darra, Francesca; Vecchi, Marilena; Perucca, Emilio (Epilepsia, 2011)
PURPOSE: To evaluate the potential efficacy of levetiracetam as an antiabsence agent in children and adolescents with newly diagnosed childhood or juvenile absence epilepsy. METHODS: Patients were randomized in a 2:1 ratio to receive de novo monotherapy with levetiracetam (up to 30 mg/kg/day) or placebo for 2 weeks under double-blind conditions. Responder status (primary end point) was defined as freedom from clinical seizures on days 13 and 14 and from electroencephalographic (EEG) seizures during a standard EEG recording with hyperventilation and intermittent photic stimulation on day 14. The double-blind phase was followed by an open-label follow-up. KEY FINDINGS: Nine of 38 patients (23.7%) were responders in the levetiracetam group, compared with one of 21 (4.8%) in the placebo group (p = 0.08). Seven of 38 patients (18.4%) were free from clinical and EEG seizures during the last 4 days of the trial (including 24-h EEG monitoring on day 14) compared with none of the patients treated with placebo (p = 0.04). Seventeen patients remained seizure-free on levetiracetam after 1 year follow-up. Of the 41 patients who discontinued levetiracetam due to lack of efficacy (n = 39) or adverse events (n = 2), 34 became seizure-free on other treatments. SIGNIFICANCE: Although superiority to placebo just failed to reach statistical significance for the primary end point, the overall findings are consistent with levetiracetam having modest efficacy against absence seizures. Further controlled trials exploring larger doses and an active comparator are required to determine the role of levetiracetam in the treatment of absence epilepsy.
Keywords: Adolescent; Age Factors; Anticonvulsants; Child; Child, Preschool; Double-Blind Method; Drug Resistance; Epilepsy, Absence; Female; Humans; Male; Outcome Assessment (Health Care); Piracetam

Multiple loci are associated with white blood cell phenotypes. - Nalls, Michael A; Couper, David J; Tanaka, Toshiko; van Rooij, Frank J A; Chen, Ming-Huei; Smith, Albert V; Toniolo, Daniela; Zakai, Neil A; Yang, Qiong; Greinacher, Andreas; Wood, Andrew R; Garcia, Melissa; et al. (PLoS Genet, 2011)
White blood cell (WBC) count is a common clinical measure from complete blood count assays, and it varies widely among healthy individuals. Total WBC count and its constituent subtypes have been shown to be moderately heritable, with the heritability estimates varying across cell types. We studied 19,509 subjects from seven cohorts in a discovery analysis, and 11,823 subjects from ten cohorts for replication analyses, to determine genetic factors influencing variability within the normal hematological range for total WBC count and five WBC subtype measures. Cohort specific data was supplied by the CHARGE, HeamGen, and INGI consortia, as well as independent collaborative studies. We identified and replicated ten associations with total WBC count and five WBC subtypes at seven different genomic loci (total WBC count-6p21 in the HLA region, 17q21 near ORMDL3, and CSF3; neutrophil count-17q21; basophil count- 3p21 near RPN1 and C3orf27; lymphocyte count-6p21, 19p13 at EPS15L1; monocyte count-2q31 at ITGA4, 3q21, 8q24 an intergenic region, 9q31 near EDG2), including three previously reported associations and seven novel associations. To investigate functional relationships among variants contributing to variability in the six WBC traits, we utilized gene expression- and pathways-based analyses. We implemented gene-clustering algorithms to evaluate functional connectivity among implicated loci and showed functional relationships across cell types. Gene expression data from whole blood was utilized to show that significant biological consequences can be extracted from our genome-wide analyses, with effect estimates for significant loci from the meta-analyses being highly corellated with the proximal gene expression. In addition, collaborative efforts between the groups contributing to this study and related studies conducted by the COGENT and RIKEN groups allowed for the examination of effect homogeneity for genome-wide significant associations across populations of diverse ancestral backgrounds.
Keywords: Genetic Loci; Genome-Wide Association Study; Humans; Leukocyte Count; Leukocytes; Molecular Epidemiology; Multigene Family; Phenotype; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Refractory iron-deficiency anaemia in a child with portal cavernoma. - Pastore, Serena; Londero, Margherita; Cont, Gabriele; Di Leo, Grazia; Ventura, Alessandro (Gut, 2011)
Keywords: Anemia, Iron-Deficiency; Antihypertensive Agents; Child; Hemangioma, Cavernous; Humans; Hypertension, Portal; Ileal Diseases; Male; Propranolol; Vascular Neoplasms

Safety and efficacy of high-dose acarbose treatment for dumping syndrome. - De Cunto, Angela; Barbi, Egidio; Minen, Federico; Ventura, Alessandro (J Pediatr Gastroenterol Nutr, 2011)
Dumping syndrome (DS) is a complication of Nissen fundoplication. Dietary strategies can ameliorate symptoms, but this approach is not always foolproof. Limited evidence reports the efficacy of acarbose for children who are unresponsive to feeding manipulations. We report 8 patients with DS aged between 7 and 24 months. In 4 of 8 nutritional strategies failed, and acarbose treatment was started. The initial dose was 25 mg for meals, and increased until postprandial glucose was stable. In 3 of 4 children the final dose was higher than previously reported, without adverse effects. Acarbose is useful to treat DS in cases of failure of dietary strategies.
Keywords: Acarbose; Child, Preschool; Dumping Syndrome; Female; Humans; Hyperglycemia; Hypoglycemic Agents; Infant; Male; Postprandial Period; Treatment Outcome

Serum anti-Müllerian hormone as a predictive marker of polycystic ovarian syndrome. - Parco, Sergio; Novelli, Caterina; Vascotto, Fulvia; Princi, Tanja (Int J Gen Med, 2011)
BACKGROUND: The anti-Müllerian hormone (AMH) is a dimeric protein secreted by the female ovaries and has two fundamental roles in follicle genesis. It delays the entrance of the primordial follicle into the pool of follicles in growth and diminishes the sensitivity of the ovarian follicle towards follicle-stimulating hormone (FSH). The purpose of this work was to study the AMH (nv 2.0-6.8 ng/mL) as a marker during assisted reproductive technology (ART), in order to identify cases of infertility due to polycystic ovarian syndrome (PCOS). This syndrome affects 10% of women with infertility problems, and a new biological marker could be useful to general practitioners of internal medicine to help generate the suspicion of PCOS so that they can refer the patient to the gynecologist for confirmation. METHODS: This study enrolled 236 patients aged 26-46 years undergoing assisted reproductive technology at the Institute for Maternal and Child Health, Trieste, Italy. On the third day of the ovarian cycle, the patients were given doses of AMH, FSH, and luteinizing hormone (LH, in cases of AMH < 2.0-6.8 ng/mL). A control pelvic ultrasound was also carried out. RESULTS: We identified 57 patients who were starting in vitro fertilization or embryo transfer with AMH values within the normal range (3.64 ± 1.51 ng/mL), 77 with values below normal (1.38 ± 0.32 ng/mL), and 96 cases with undetectable values of AMH. Six patients had very high AMH levels (10.0 ± 2.28 ng/mL) and, of these, five were found to have PCOS on pelvic ultrasound examination (P < 0.05). We also found inverse correlations between AMH levels and age (r = -0.52) and between AMH and FSH levels (r = -0.32). CONCLUSION: In clinical practice it is common to encounter patients who turn to medicine in search of a cure for female infertility. In our experience, AMH two or three times the normal amount (10 ± 2.28 ng/mL), is a good indication of PCOS and infertility.

A singular case of congenital self-healing histiocytosis with skin, liver and atypical eye involvement. - Parentin, Fulvio; Ventura, Giovanna; Pastore, Serena; Kiren, Valentina; Bibalo, Chiara; Pensiero, Stefano; Lepore, Loredana (Ocul Immunol Inflamm, 2011)
PURPOSE: To describe a rare case of congenital self-healing Langerhans cell histiocytosis (CSHLCH) presenting with atypical eye involvement. DESIGN: Case report. METHODS: A female newborn presented with purpuric lesions over the trunk, limbs, and face. Liver ultrasonography revealed hypoechogenic lesions with blurred borders. Biomicroscopy showed right posterior synechiae with fibrinoid deposits on the lens. At 7 months she presented with right acute glaucoma. RESULTS: Biomicroscopy showed the presence of inflammatory pseudo-membrane covering the anterior surface of the lens, iris, and iridocorneal angle. Ab externo trabeculotomy was performed; access to the anterior chamber with capsulorrhexis forceps permitted a peeling of the pseudo-membrane with normalization of the intraocular pressure. Histologic examination of the membrane revealed an inflammatory tissue with CD1a and S-100 positive histiocytic cells. CONCLUSIONS: This is the first case of CSHLCH describing acute glaucoma secondary to a pseudo-inflammatory membrane with typical histiocytic cells, occluding the iridocorneal angle.
Keywords: Antigens, CD1; Convalescence; Female; Glaucoma; Histiocytosis, Langerhans-Cell; Humans; Infant; Intraocular Pressure; Iridocorneal Endothelial Syndrome; Liver Diseases; S100 Proteins; Skin Diseases; Trabeculectomy

Somatic mosaic IDH1 and IDH2 mutations are associated with enchondroma and spindle cell hemangioma in Ollier disease and Maffucci syndrome. - Pansuriya, Twinkal C; van Eijk, Ronald; d'Adamo, Pio; van Ruler, Maayke A J H; Kuijjer, Marieke L; Oosting, Jan; Cleton-Jansen, Anne-Marie; van Oosterwijk, Jolieke G; Verbeke, Sofie L J; Meijer, Daniëlle; van Wezel, Tom; Nord, Karolin H; et al. (Nat Genet, 2011)
Ollier disease and Maffucci syndrome are non-hereditary skeletal disorders characterized by multiple enchondromas (Ollier disease) combined with spindle cell hemangiomas (Maffucci syndrome). We report somatic heterozygous mutations in IDH1 (c.394C>T encoding an R132C substitution and c.395G>A encoding an R132H substitution) or IDH2 (c.516G>C encoding R172S) in 87% of enchondromas (benign cartilage tumors) and in 70% of spindle cell hemangiomas (benign vascular lesions). In total, 35 of 43 (81%) subjects with Ollier disease and 10 of 13 (77%) with Maffucci syndrome carried IDH1 (98%) or IDH2 (2%) mutations in their tumors. Fourteen of 16 subjects had identical mutations in separate lesions. Immunohistochemistry to detect mutant IDH1 R132H protein suggested intraneoplastic and somatic mosaicism. IDH1 mutations in cartilage tumors were associated with hypermethylation and downregulated expression of several genes. Mutations were also found in 40% of solitary central cartilaginous tumors and in four chondrosarcoma cell lines, which will enable functional studies to assess the role of IDH1 and IDH2 mutations in tumor formation.
Keywords: Adult; Case-Control Studies; Cell Line, Tumor; DNA Methylation; Enchondromatosis; Female; Gene Expression Profiling; Gene Expression Regulation; Genome-Wide Association Study; Humans; Isocitrate Dehydrogenase; Male; Middle Aged; Mosaicism; Mutation, Missense; Sequence Analysis, DNA; Transcription, Genetic; Young Adult

Tag-single nucleotide polymorphism-based human leukocyte antigen genotyping in celiac disease patients from northeastern Italy. - Vatta, Serena; Fabris, Annalisa; Segat, Ludovica; Not, Tarcisio; Crovella, Sergio (Hum Immunol, 2011)
We genotyped celiac disease (CD)-associated haplotypes DQ2.5, DQ8, DQ2.2, and DQ7 in 1005 CD patients from North Eastern Italy using a Tag-single nucleotide polymorphism (SNPs) approach and real time PCR platform, checking the accuracy and reliability of the method and comparing it to traditional PCR-SSP. Only 14 of 2010 chromosomes analyzed (0.7%) showed discrepancies between the Tag-SNPs real-time polymerase chain reaction (PCR) method and the PCR-single-strand polymorphism (SSP) technique, indicating a high sensitivity and specificity (ranging from 0.987 to 1 and from 0.998 to 0.999, respectively) for tagging with respect to corresponding human leukocyte antigen (HLA) alleles identified by PCR-SSP. Moreover, the overall cost of the Tag-SNPs HLA typing method was low (3 to 4 €/sample instead of 35 to 70 €/sample with commercial kits), making it suitable for mass screenings. Hence, we believe that the Tag-SNPs HLA typing could be used to complement or replace classic HLA typing in at high-risk groups, for research purposes and eventually in population screening programs.
Keywords: Adolescent; Adult; Aged; Celiac Disease; Child; Child, Preschool; Female; Humans; Infant; Italy; Male; Mass Screening; Middle Aged; Polymerase Chain Reaction; Polymorphism, Single Nucleotide; Reproducibility of Results; Reverse Transcriptase Polymerase Chain Reaction; Sensitivity and Specificity

Thromboembolism in pediatric inflammatory bowel disease: systematic review. - Lazzerini, Marzia; Bramuzzo, Matteo; Maschio, Massimo; Martelossi, Stefano; Ventura, Alessandro (Inflamm Bowel Dis, 2011)
BACKGROUND: Several studies suggest an increased risk of venous and arterial thromboembolism (TE) in adults with inflammatory bowel disease (IBD) compared to the general population. We performed a systematic review of studies on incidence and characteristic of TE in children with IBD. METHODS: We searched Medline, LILACS, EMBASE, POPLINE, CINHAL, and reference lists of identified articles, without language restrictions, in August 2010. RESULTS: Population studies suggest that there is an increased risk of TE in children with IBD compared to controls. TE occurred in children with IBD in all age ranges, mostly (82.8%) during active disease, and more frequently in children with ulcerative colitis (odds ratio [OR] 3.7, 95% confidence interval [CI] 1.8-7.6). At least one specific risk factor for TE was recognized in 50% of cases; two risk factors were present in 24%. Out of 92 published cases of TE in children with IBD, 54.3% occurred in cerebral site, 26% in the limbs, 13% in the abdominal vessels, and the remaining in the retina and lungs. After a first episode of TE, an early recurrence was observed in 11.4% of children, a late recurrence in 10%. A number of different therapeutic schemes were used. Overall mortality was 5.7% and was mostly associated with cerebral TE. CONCLUSIONS: Population studies are needed to clarify the risk of TE in children with IBD, the relative weight of other risk factors, the characteristics of the events, and to define guidelines of therapy and prophylaxis.
Keywords: Adult; Child; Humans; Inflammatory Bowel Diseases; Risk Factors; Thromboembolism

Two lumens, one diagnosis. - Pastore, Serena; Gortani, Giulia; Maschio, Massimo; Di Leo, Grazia; Ventura, Alessandro (J Pediatr, 2011)
Keywords: Capsule Endoscopy; Child, Preschool; Gastrointestinal Hemorrhage; Humans; Male; Meckel Diverticulum; Recurrence

Usefulness of wireless capsule endoscopy for detecting inflammatory bowel disease in children presenting with arthropathy. - Taddio, Andrea; Simonini, Gabriele; Lionetti, Paolo; Lepore, Loredana; Martelossi, Stefano; Ventura, Alessandro; Cimaz, Rolando (Eur J Pediatr, 2011)
Inflammatory bowel disease (IBD) is a cause of chronic intestinal inflammation in children. In a subset of patients affected by IBD, arthropathy may be the leading presenting sign. In the past years, remarkable advances in gastrointestinal endoscopy techniques have been achieved; recently, the development of capsule endoscopy (CE) provided a non-invasive method for the complete endoscopic evaluation, including small bowel assessment. We report three children suffering from IBD but presenting with articular complaints in whom CE was a useful tool for detecting gut inflammation. Patients were investigated with the wireless CE: PillCam SB2 (Given Imaging, Yoqneam, Israel) capsule, the second-generation capsule, was used in our paediatric patients. Three patients were initially evaluated for arthropathy. Enteropathic arthritis was suspected for gastrointestinal symptoms and/or persistence of inflammatory markers elevation. In one of these children, conventional endoscopy was refused by parents, while in the other two children, CE was proposed as first-line diagnostic tool. In all patients, CE revealed to be safe and provided information that led to diagnosis. Paediatric rheumatologists should consider CE as a valid, non-invasive tool, eventually first level diagnostic approach in order to evaluate the presence of IBD in children presenting with chronic articular complaints.
Keywords: Adolescent; Arthritis, Juvenile; Capsule Endoscopy; Child; Colitis, Ulcerative; Colon; Crohn Disease; Diagnosis, Differential; Follow-Up Studies; Humans; Inflammatory Bowel Diseases; Intestine, Small; Male; Predictive Value of Tests; Sensitivity and Specificity; Severity of Illness Index; Treatment Outcome

X-ray fluorescence elemental mapping and microscopy to follow hepatic disposition of a Gd-based magnetic resonance imaging contrast agent. - Delfino, Riccarda; Altissimo, Matteo; Menk, Ralf Hendrik; Alberti, Roberto; Klatka, Tomasz; Frizzi, Tommaso; Longoni, Antonio; Salomè, Murielle; Tromba, Giuliana; Arfelli, Fulvia; Clai, Milan; Vaccari, Lisa; et al. (Clin Exp Pharmacol Physiol, 2011)
1. Spatially resolved X-ray fluorescence (XRF) spectroscopy with synchrotron radiation is a technique that allows imaging and quantification of chemical elements in biological specimens with high sensitivity. In the present study, we applied XRF techniques at a macro and micro level to carry out drug distribution studies on ex vivo models to confirm the hepatobiliary disposition of the Gd-based magnetic resonance imaging contrast agent B22956/1. 2. Gd presence was selectively quantified allowing the determination of the time dependent disappearance of the drug from blood and its hepatic accumulation in mice after administration. Elemental mapping highlighted the drug distribution differences between healthy and diseased livers. XRF microanalyses showed that in CCl(4) -induced hepatitis, B22956/1 has greatly reduced hepatic accumulation, shown as a 20-fold reduction of Gd presence. Furthermore, a significant increase of Fe presence was found in steatotic compared with healthy livers, in line with the disease features. 3. The present results show that XRF might be useful in preclinical pharmacological studies with drugs containing exogenous elements. Furthermore, quantitative and high-sensitivity elemental mapping allows simultaneous detection of chemical variation, showing pathological conditions. This approach was useful in suggesting reduced B22956/1 accumulation in steatotic livers, thus opening possible new diagnostic perspectives for this drug.
Keywords: Animals; Contrast Media; Fatty Liver; Female; Gadolinium; Hepatitis; Iron; Liver; Magnetic Resonance Imaging; Mice; Mice, Inbred CBA; Organometallic Compounds; Spectrometry, X-Ray Emission

Anti transglutaminase antibodies cause ataxia in mice. - Boscolo, Sabrina; Lorenzon, Andrea; Sblattero, Daniele; Florian, Fiorella; Stebel, Marco; Marzari, Roberto; Not, Tarcisio; Aeschlimann, Daniel; Ventura, Alessandro; Hadjivassiliou, Marios; Tongiorgi, Enrico (PLoS One, 2010)
BACKGROUND: Celiac disease (CD) is an autoimmune gastrointestinal disorder characterized by the presence of anti-transglutaminase 2 (TG2) and anti-gliadin antibodies. Amongst the neurological dysfunctions associated with CD, ataxia represents the most common one. METHODS: We analyzed by immunohistochemistry, the anti-neural reactivity of the serum from 20 CD patients. To determine the role of anti-TG2 antibodies in ataxia, two anti-TG2 single chain variable fragments (scFv), isolated from a phage-display IgA antibody library, were characterized by immunohistochemistry and ELISA, and injected in mice to study their effects on motor coordination. We found that 75% of the CD patient population without evidence of neurological involvement, has circulating anti-neural IgA and/or IgG antibodies. Two anti-TG2 scFvs, cloned from one CD patient, stained blood vessels but only one reacted with neurons. This anti-TG2 antibody showed cross reactivity with the transglutaminase isozymes TG3 and TG6. Intraventricular injection of the anti-TG2 or the anti-TG2/3/6 cross-reactive scFv provoked transient, equally intensive ataxia in mice. CONCLUSION: The serum from CD patients contains anti-TG2, TG3 and TG6 antibodies that may potentially cause ataxia.
Keywords: Adult; Animals; Antibodies; Ataxia; Autoimmune Diseases; Brain; Celiac Disease; Female; Gliadin; Humans; Isoenzymes; Male; Mice; Mice, Inbred C57BL; Middle Aged; Motor Skills; Rats; Rats, Sprague-Dawley; Transglutaminases

A child with pain after mild trauma. - Londero, Margherita; Pastore, Serena; Zanazzo, Giulio A; Bruno, Irene; Ventura, Alessandro (J Pediatr, 2010)
Keywords: Antigens, CD; Antigens, CD31; Antigens, CD34; Antigens, Differentiation, Myelomonocytic; Biopsy; Child; Factor VIII; Fingers; Hand Injuries; Hemangioendothelioma; Humans; Immunohistochemistry; Injury Severity Score; Male; Osteolysis; Pain; Pain Measurement; S100 Proteins; Vascular Neoplasms

Declining HCV seroprevalence in pregnant women with HIV. - Floridia, M; Tamburrini, E; Anzidei, G; Tibaldi, C; Muggiasca, M L; Guaraldi, G; Fiscon, M; Vimercati, A; Martinelli, P; Donisi, A; Dalzero, S; Ravizza, M (Epidemiol Infect, 2010)
We assessed recent trends in hepatitis C virus (HCV) prevalence in pregnant women with HIV using data from a large national study. Based on 1240 pregnancies, we observed a 3.4-fold decline in HCV seroprevalence in pregnant women with HIV between 2001 (29.3%) and 2008 (8.6%). This decline was the net result of two components: a progressively declining HCV seroprevalence in non-African women (from 35.7% in 2001 to 16.7% in 2008), sustained by a parallel reduction in history of injecting drug use (IDU) in this population, and a significantly growing presence (from 21.2% in 2001 to 48.6% in 2008) of women of African origin, at very low risk of being HCV-infected [average HCV prevalence 1%, adjusted odds ratio (aOR) for HCV 0.09, 95% CI 0.03-0.29]. Previous IDU was the stronger determinant of HCV co-infection in pregnant women with HIV (aOR 30.9, 95% CI 18.8-51.1). The observed trend is expected to translate into a reduced number of cases of vertical HCV transmission.
Keywords: Chi-Square Distribution; Female; Hepatitis C; HIV Infections; Humans; Italy; Logistic Models; Pregnancy; Risk Factors; Seroepidemiologic Studies

Decreased cholesterol levels reflect a consumption of anti-inflammatory isoprenoids associated with an impaired control of inflammation in a mouse model of mevalonate kinase deficiency. - Marcuzzi, Annalisa; Decorti, Giuliana; Pontillo, Alessandra; Ventura, Alessandro; Tommasini, Alberto (Inflamm Res, 2010)
OBJECTIVE: The aim of this study was to evaluate, in a mouse model of mevalonate kinase deficiency (MKD), the possible link between inflammatory symptoms and serum cholesterol levels. MATERIALS AND METHODS: Balb/c mice were treated with alendronate and bacterial muramyl dipeptide. Body temperature, interleukin-1 beta (IL-1 beta) secretion and serum cholesterol levels were measured. RESULTS: An increased production of the pro-inflammatory cytokine IL-1 beta (p < 0.05) and a rise in body temperature (p < 0.05) was observed, while, in parallel, serum cholesterol concentration significantly decreased (p < 0.05). These effects were completely reversed when animals were treated with exogenous isoprenoids. CONCLUSIONS: In the mouse model of MKD, the inflammatory response is associated with a reduction in cholesterol levels, and hence this parameter could be used as an indicator of isoprenoid consumption. In addition, plant derived isoprenoids could represent candidate treatments for this disease.
Keywords: Animals; Anti-Inflammatory Agents; Cholesterol; Disease Models, Animal; Inflammation; Interleukin-1beta; Male; Mevalonate Kinase Deficiency; Mice; Mice, Inbred BALB C; Random Allocation; Terpenes

Does infant gastro-oesophageal reflux really deserve medical attention? - Declich, V; Badina, L; Ventura, A (Arch Dis Child, 2010)
Keywords: Beds; Gastroesophageal Reflux; Humans; Infant; Infant Care; Posture; Prognosis

EULAR/PRINTO/PRES criteria for Henoch-Schönlein purpura, childhood polyarteritis nodosa, childhood Wegener granulomatosis and childhood Takayasu arteritis: Ankara 2008. Part I: Overall methodology and clinical characterisation. - Ruperto, Nicolino; Ozen, Seza; Pistorio, Angela; Dolezalova, Pavla; Brogan, Paul; Cabral, David A; Cuttica, Ruben; Khubchandani, Raju; Lovell, Daniel J; O'Neil, Kathleen M; Quartier, Pierre; Ravelli, Angelo; et al. (Ann Rheum Dis, 2010)
OBJECTIVES: To report methodology and overall clinical, laboratory and radiographic characteristics for Henoch-Schönlein purpura (HSP), childhood polyarteritis nodosa (c-PAN), c-Wegener granulomatosis (c-WG) and c-Takayasu arteritis (c-TA) classification criteria. METHODS: The preliminary Vienna 2005 consensus conference, which proposed preliminary criteria for paediatric vasculitides, was followed by a EULAR/PRINTO/PRES - supported validation project divided into three main steps. Step 1: retrospective/prospective web-data collection for HSP, c-PAN, c-WG and c-TA, with age at diagnosis <or=18 years. Step 2: blinded classification by consensus panel of a subgroup of 280 cases (128 difficult cases, 152 randomly selected) enabling expert diagnostic verification. Step 3: Ankara 2008 Consensus Conference and statistical evaluation (sensitivity, specificity, area under the curve, kappa-agreement) using as 'gold standard' the final consensus classification or original treating physician diagnosis. RESULTS: A total of 1183/1398 (85%) samples collected were available for analysis: 827 HSP, 150 c-PAN, 60 c-WG, 87 c-TA and 59 c-other. Prevalence, signs/symptoms, laboratory, biopsy and imaging reports were consistent with the clinical picture of the four c-vasculitides. A representative subgroup of 280 patients was blinded to the treating physician diagnosis and classified by a consensus panel, with a kappa-agreement of 0.96 for HSP (95% CI 0.84 to 1), 0.88 for c-WG (95% CI 0.76 to 0.99), 0.84 for c-TA (95% CI 0.73 to 0.96) and 0.73 for c-PAN (95% CI 0.62 to 0.84), with an overall kappa of 0.79 (95% CI 0.73 to 0.84). CONCLUSION: EULAR/PRINTO/PRES propose validated classification criteria for HSP, c-PAN, c-WG and c-TA, with substantial/almost perfect agreement with the final consensus classification or original treating physician diagnosis.
Keywords: Adolescent; Biopsy; Child; Delphi Technique; Granulomatosis with Polyangiitis; Humans; International Cooperation; Internet; Polyarteritis Nodosa; Purpura, Schoenlein-Henoch; Reproducibility of Results; Takayasu Arteritis

Exenatide in type 2 diabetes. - Verzegnassi, Federico; Chinello, Matteo (Lancet, 2010)
Keywords: Biological Markers; Diabetes Mellitus, Type 2; Energy Intake; Humans; Hypoglycemic Agents; Insulin; Insulin, Long-Acting; Peptides; Quality of Life; Venoms

Fasting increases tobramycin oral absorption in mice. - De Leo, Luigina; Di Toro, Nicola; Decorti, Giuliana; Malusà, Noelia; Ventura, Alessandro; Not, Tarcisio (Antimicrob Agents Chemother, 2010)
The pharmacokinetics of the aminoglycoside tobramycin was evaluated after oral administration to fed or fasting (15 h) mice. As expected, under normal feeding conditions, oral absorption was negligible; however, fasting induced a dramatic increase in tobramycin bioavailability. The dual-sugar test with lactulose and l-rhamnose confirmed increased small bowel permeability via the paracellular route in fasting animals. When experiments aimed at increasing the oral bioavailability of hydrophilic compounds are performed, timing of fasting should be extremely accurate.
Keywords: Administration, Oral; Animals; Anti-Bacterial Agents; Biological Availability; Fasting; Injections, Intramuscular; Injections, Intravenous; Intestinal Absorption; Lactulose; Male; Mice; Mice, Inbred BALB C; Rhamnose; Tobramycin

Follow-up and quality of life of patients with cryopyrin-associated periodic syndromes treated with Anakinra. - Lepore, Loredana; Paloni, Giulia; Caorsi, Roberta; Alessio, Maria; Rigante, Donato; Ruperto, Nicola; Cattalini, Marco; Tommasini, Alberto; Zulian, Francesco; Ventura, Alessando; Martini, Alberto; Gattorno, Marco (J Pediatr, 2010)
OBJECTIVE: To evaluate the quality of life and long-term follow-up of patients enrolled in the Italian registry of cryopyrin-associated periodic syndromes (CAPS). STUDY DESIGN: Since 2004, 20 patients with CAPS were enrolled in a common registry from different Italian Centers of Pediatric Rheumatology; 14 patients were treated with Anakinra in an open fashion. Both treated and untreated patients were routinely followed according to standard of care. The Child Health Questionnaire (CHQ-PF 50) was used to assess the health-related quality of life. RESULTS: The mean duration of follow-up was 37.5 months. In all treated patients, a complete and persistent control of the inflammatory manifestations was observed with no further progression of the disease. At enrollment in the registry, patients showed a poorer health-related quality of life than healthy children in both physical and the psychosocial summary scores. Treatment was associated with a dramatic and sustained amelioration of a variety of measures of poor quality of life, particularly in those concerning the global health perception, bodily pain-discomfort, and other physical domains. CONCLUSIONS: Long-term IL-1 blockade produces a significant and persistent improvement in the clinical manifestations associated with the disease and on the overall quality of life.
Keywords: Adolescent; Adult; Case-Control Studies; Child; Child, Preschool; Cryopyrin-Associated Periodic Syndromes; Female; Follow-Up Studies; Humans; Inflammation; Interleukin 1 Receptor Antagonist Protein; Interleukin-1; Male; Phenotype; Quality of Health Care; Quality of Life; Questionnaires; Syndrome; Treatment Outcome

A G to C transversion at the last nucleotide of exon 25 of the MYH9 gene results in a missense mutation rather than in a splicing defect. - Vettore, Silvia; De Rocco, Daniela; Gerber, Bernhard; Scandellari, Raffaella; Bianco, Anna Monica; Balduini, Carlo L; Pecci, Alessandro; Fabris, Fabrizio; Savoia, Anna (Eur J Med Genet, 2010)
MYH9-related disease (MYH9-RD) is a rare autosomal dominant disorder caused by mutations in MYH9, the gene encoding the heavy chain of non-muscle myosin IIA. Patients present with congenital macrothrombocytopenia and inclusion bodies in neutrophils and might develop sensorineural deafness, presenile cataract, and/or progressive nephropathy leading to end-stage renal failure. In two families with macrothrombocytopenia we identified a novel c.3485G > C mutation in the last nucleotide of exon 25. Bioinformatic tools for splice site prediction and minigene functional test predicted splicing anomalies of exon 25. However, analysis of RNA purified from patient's peripheral blood did not allowed us to detect any anomalies, suggesting that RNA processing is correct at least in this tissue. Therefore, we concluded that c.3485G > C leads to a novel missense mutation (p.Arg1162Thr) of myosin-9, which resulted to be slightly degraded in patient platelets. A precise definition of the effect of mutations is fundamental to improve our knowledge into the pathogenetic mechanisms responsible for the disease.
Keywords: Adolescent; Adult; Blood Platelets; Computational Biology; Exons; Female; Humans; Inclusion Bodies; Kidney Failure, Chronic; Molecular Motor Proteins; Mutation, Missense; Myosin Heavy Chains; Neutrophils; Nonmuscle Myosin Type IIA; Nucleotides; RNA Splicing; Thrombocytopenia

Hepatic glycogenosis in an adolescent with diabetes. - Bua, Jenny; Marchetti, Federico; Faleschini, Elena; Ventura, Alessandro; Bussani, Rossana (J Pediatr, 2010)
Keywords: Adolescent; Diabetes Mellitus, Type 1; Female; Glycogen Storage Disease; Humans; Liver Diseases

Methotrexate withdrawal at 6 vs 12 months in juvenile idiopathic arthritis in remission: a randomized clinical trial. - Foell, Dirk; Wulffraat, Nico; Wedderburn, Lucy R; Wittkowski, Helmut; Frosch, Michael; Gerss, Joachim; Stanevicha, Valda; Mihaylova, Dimitrina; Ferriani, Virginia; Tsakalidou, Florence Kanakoudi; Foeldvari, Ivan; Cuttica, Ruben; et al. (JAMA, 2010)
CONTEXT: Novel therapies have improved the remission rate in chronic inflammatory disorders including juvenile idiopathic arthritis (JIA). Therefore, strategies of tapering therapy and reliable parameters for detecting subclinical inflammation have now become challenging questions. OBJECTIVES: To analyze whether longer methotrexate treatment during remission of JIA prevents flares after withdrawal of medication and whether specific biomarkers identify patients at risk for flares. DESIGN, SETTING, AND PATIENTS: Prospective, open, multicenter, medication-withdrawal randomized clinical trial including 364 patients (median age, 11.0 years) with JIA recruited in 61 centers from 29 countries between February 2005 and June 2006. Patients were included at first confirmation of clinical remission while continuing medication. At the time of therapy withdrawal, levels of the phagocyte activation marker myeloid-related proteins 8 and 14 heterocomplex (MRP8/14) were determined. INTERVENTION: Patients were randomly assigned to continue with methotrexate therapy for either 6 months (group 1 [n = 183]) or 12 months (group 2 [n = 181]) after induction of disease remission. MAIN OUTCOME MEASURES: Primary outcome was relapse rate in the 2 treatment groups; secondary outcome was time to relapse. In a prespecified cohort analysis, the prognostic accuracy of MRP8/14 concentrations for the risk of flares was assessed. RESULTS: Intention-to-treat analysis of the primary outcome revealed relapse within 24 months after the inclusion into the study in 98 of 183 patients (relapse rate, 56.7%) in group 1 and 94 of 181 (55.6%) in group 2. The odds ratio for group 1 vs group 2 was 1.02 (95% CI, 0.82-1.27; P = .86). The median relapse-free interval after inclusion was 21.0 months in group 1 and 23.0 months in group 2. The hazard ratio for group 1 vs group 2 was 1.07 (95% CI, 0.82-1.41; P = .61). Median follow-up duration after inclusion was 34.2 and 34.3 months in groups 1 and 2, respectively. Levels of MRP8/14 during remission were significantly higher in patients who subsequently developed flares (median, 715 [IQR, 320-1 110] ng/mL) compared with patients maintaining stable remission (400 [IQR, 220-800] ng/mL; P = .003). Low MRP8/14 levels indicated a low risk of flares within the next 3 months following the biomarker test (area under the receiver operating characteristic curve, 0.76; 95% CI, 0.62-0.90). CONCLUSIONS: In patients with JIA in remission, a 12-month vs 6-month withdrawal of methotrexate did not reduce the relapse rate. Higher MRP8/14 concentrations were associated with risk of relapse after discontinuing methotrexate. TRIAL REGISTRATION: isrctn.org Identifier: ISRCTN18186313.
Keywords: Adolescent; Antirheumatic Agents; Arthritis, Juvenile; ATP-Binding Cassette Transporters; Calgranulin B; Child; Child, Preschool; Female; Humans; Infant; Male; Methotrexate; Predictive Value of Tests; Prospective Studies; Recurrence; Remission Induction

Predictors of poor response to methotrexate in polyarticular-course juvenile idiopathic arthritis: analysis of the PRINTO methotrexate trial. - Vilca, Iris; Munitis, Pablo Garcia; Pistorio, Angela; Ravelli, Angelo; Buoncompagni, Antonella; Bica, Blanca; Campos, Lucia; Häfner, Renate; Hofer, Michael; Ozen, Seza; Huemer, Christian; Bae, Sang Cheol; et al. (Ann Rheum Dis, 2010)
OBJECTIVES: To determine whether baseline demographic, clinical, articular and laboratory variables predict methotrexate (MTX) poor response in polyarticular-course juvenile idiopathic arthritis. METHODS: Patients newly treated for 6 months with MTX enrolled in the Paediatric Rheumatology International Trials Organization (PRINTO) MTX trial. Bivariate and logistic regression analyses were used to identify baseline predictors of poor response according to the American College of Rheumatology pediatric (ACR-ped) 30 and 70 criteria. RESULTS: In all, 405/563 (71.9%) of patients were women; median age at onset and disease duration were 4.3 and 1.4 years, respectively, with anti-nuclear antibody (ANA) detected in 259/537 (48.2%) patients. With multivariate logistic regression analysis, the most important determinants of ACR-ped 70 non-responders were: disease duration > 1.3 years (OR 1.93), ANA negativity (OR 1.77), Childhood Health Assessment Questionnaire (CHAQ) disability index > 1.125 (OR 1.65) and the presence of right and left wrist activity (OR 1.55). Predictors of ACR-ped 30 non-responders were: ANA negativity (OR 1.92), CHAQ disability index > 1.14 (OR 2.18) and a parent's evaluation of child's overall well-being < or = 4.69 (OR 2.2). CONCLUSION: The subgroup of patients with longer disease duration, ANA negativity, higher disability and presence of wrist activity were significantly associated with a poorer response to a 6-month MTX course.
Keywords: Adolescent; Antibodies, Antinuclear; Antirheumatic Agents; Arthritis, Juvenile; Child; Child, Preschool; Disability Evaluation; Female; Follow-Up Studies; Humans; Immunosuppressive Agents; Male; Methotrexate; Prognosis; Treatment Outcome

Therapeutic strategy in p47-phox deficient chronic granulomatous disease presenting as inflammatory bowel disease. - Freudenberg, Folke; Wintergerst, Uwe; Roesen-Wolff, Angela; Albert, Michael H; Prell, Christine; Strahm, Brigitte; Koletzko, Sibylle; Ehl, Stephan; Roos, Dirk; Tommasini, Alberto; Ventura, Alessandro; Belohradsky, Bernd H; et al. (J Allergy Clin Immunol, 2010)
Keywords: Age of Onset; Anti-Bacterial Agents; Antibodies, Monoclonal; Child; Drug Therapy, Combination; Gene Deletion; Granulomatous Disease, Chronic; Humans; Inflammatory Bowel Diseases; Male; NADPH Oxidase; Steroids; Treatment Outcome; Vidarabine

Thirty new loci for age at menarche identified by a meta-analysis of genome-wide association studies. - Elks, Cathy E; Perry, John R B; Sulem, Patrick; Chasman, Daniel I; Franceschini, Nora; He, Chunyan; Lunetta, Kathryn L; Visser, Jenny A; Byrne, Enda M; Cousminer, Diana L; Gudbjartsson, Daniel F; Esko, Tõnu; et al. (Nat Genet, 2010)
To identify loci for age at menarche, we performed a meta-analysis of 32 genome-wide association studies in 87,802 women of European descent, with replication in up to 14,731 women. In addition to the known loci at LIN28B (P = 5.4 × 10⁻⁶⁰) and 9q31.2 (P = 2.2 × 10⁻³³), we identified 30 new menarche loci (all P < 5 × 10⁻⁸) and found suggestive evidence for a further 10 loci (P < 1.9 × 10⁻⁶). The new loci included four previously associated with body mass index (in or near FTO, SEC16B, TRA2B and TMEM18), three in or near other genes implicated in energy homeostasis (BSX, CRTC1 and MCHR2) and three in or near genes implicated in hormonal regulation (INHBA, PCSK2 and RXRG). Ingenuity and gene-set enrichment pathway analyses identified coenzyme A and fatty acid biosynthesis as biological processes related to menarche timing.
Keywords: Adolescent; Aging; Body Height; Body Size; Child; DNA Copy Number Variations; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Inheritance Patterns; Menarche; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Time Factors

The universe of immune deficiencies in Crohn's disease: a new viewpoint for an old disease? - Tommasini, Alberto; Pirrone, Angela; Palla, Gabriella; Taddio, Andrea; Martelossi, Stefano; Crovella, Sergio; Ventura, Alessandro (Scand J Gastroenterol, 2010)
Crohn's disease (CD) is generally considered a multifactorial disorder, since different genetic and environmental factors are thought to play a role in its pathogenesis. Recently, genome wide linkage studies allowed to identify the association of several loci with the increased risk of CD, although it is still unclear how they interact with environmental factors in causing the disease. The fact that many CD-risk-related genes are involved in the function of phagocytes seems in agreement with the well known role of these cells in CD histopathology. Functional defects in cytokine production or in clearance of bacteria in CD patients have recently been reported. Growing evidence that CD could arise from primary phagocyte immunodeficiency is also coming from the study of cases with early onset in infancy. We review such evidences starting from selected cases and discuss the clinical implications of these findings.
Keywords: Biological Markers; Crohn Disease; Cytokines; Evidence-Based Medicine; Granulomatous Disease, Chronic; Hematopoietic Stem Cell Transplantation; Humans; Immunosuppressive Agents; Phagocytes; Treatment Outcome; Wiskott-Aldrich Syndrome

Usefulness of the measurement of azathioprine metabolites in the assessment of non-adherence. - Stocco, Gabriele; Londero, Margherita; Campanozzi, Angelo; Martelossi, Stefano; Marino, Sara; Malusà, Noelia; Bartoli, Fiora; Decorti, Giuliana; Ventura, Alessandro (J Crohns Colitis, 2010)
Azathioprine is a thiopurine immunosuppressive antimetabolite used to chronically treat inflammatory bowel disease and autoimmune hepatitis. Azathioprine treatment is a long-term therapy and therefore it is at risk for non-adherence, which is considered an important determinant of treatment inefficacy. Measurement of 6-thioguanine and 6-methylmercaptopurine nucleotides has been recently suggested as a screener for non-adherence detection. We describe four young patients in which non-adherence to azathioprine therapy was detected only through the measurement of drug metabolite concentrations, and the criterion for non-adherence was undetectable metabolite levels. After the identification of non-adherence, patients and their families were approached and the importance of a correct drug administration was thoroughly enlightened and discussed; this allowed obtaining a full remission in all subjects. Our observations support the use of undetectable metabolite levels as indicators of non-adherence to therapy in azathioprine treated patients. The additional level of medical supervision given by this assay allows getting a better adherence to medical treatment, which results in an improvement in the response to therapy; these benefits may justify the costs associated with the assay.
Keywords: 6-Mercaptopurine; Adolescent; Azathioprine; Child; Child, Preschool; Female; Guanine Nucleotides; Hepatitis, Autoimmune; Humans; Immunosuppressive Agents; Inflammatory Bowel Diseases; Male; Medication Adherence; Thionucleotides; Young Adult